Editorial: Special Edition on Banking, Competition & Corporate Law: Confronting Contemporary Challenges of Banking, Competition & Corporate Law to Enhance Consumer Protection - Chitimira, Howard (Potchefstroom Electronic Law Journal, 2024)
Although Zimbabwe has established several institutions to combat money laundering and related crimes, there is a perception that inadequate measures are taken to apprehend offenders responsible for financial crimes. Institutions such as the Financial Intelligence Unit (FIU), the Zimbabwe Anti-Corruption Commission (ZACC), the Zimbabwe Republic Police (ZRP), the National Prosecuting Authority (NPA) and the Reserve Bank of Zimbabwe (RBZ) have done little to prove that the government of Zimbabwe is resolute in combatting money laundering. On the contrary, it increasingly appears that these institutions are poorly equipped and lack the necessary capacity to enforce and uphold anti-money laundering (AML) measures in Zimbabwe. Further, there appears to be a selective application of the law, with one set of rules for individuals or institutions that are perceived as political adversaries of the incumbent establishment and a different set of rules for the political elite. Consequently, the selective application of the law projects Zimbabwe as a jurisdiction that is somehow tolerant to money laundering, corruption and related financial crimes, thereby lowering and tarnishing the standing of the country in the global economic community of nations. This paper provides a regulatory analysis of the AML role-players in Zimbabwe in order to assess their functions in combatting financial crimes. It also analyses whether these role-players are effective and substantively executing their responsibilities therein. The authors argue that while Zimbabwe is well able to effectively combat money laundering through the even application of the law to all persons regardless of their political or economic standing, it is imperative that its AML institutions operate without fear, favour or prejudice. This is crucial in combatting money laundering and instilling confidence in the general public's perception of AML institutions in Zimbabwe.
Keywords: Banking; Competition; Financial crimes; Financial markets; Securities

La stabilisation du mariage en droit sénégalais - Djigo, Yéro (Revue Africaine des Sciences Juridiques, Administratives et Politiques, 2024)
Modèle unique de conjugalité en droit sénégalais de la famille, le mariage constitue la base naturelle et morale de la communauté humaine en général et de la société sénégalaise en particulier et de ce fait placé sous la protection de l’Etat. Le législateur sénégalais se devait alors de lui assurer une stabilité certaine. Il s’est donc attelé à cette tâche à travers des règles de formation précises mais aussi en aménageant un dispositif juridique permettant au mariage de traverser les turbulences entre époux inhérentes aux contingences de la vie humaine. Néanmoins, il existe dans la société sénégalaise une pratique courante et bien ancrée qui réside dans la répudiation qui constitue un sérieux obstacle à la stabilité du mariage même si elle n’est pas érigée au rang de cause de divorce. Aussi, il convient de relever que l’incompatibilité d’humeur suscite une inquiétude certaine au regard de la plasticité de cette cause de divorce. A unique model of conjugality in Senegalese family law, marriage is the natural and moral foundation of the human community in general, and in Senegalese society in particular. It is therefore under the protection of the State. The Senegalese legislator, thus, had a duty to ensure its stability. So, it sets about this task not only by laying down precise rules for the formation of marriage, but also by creating a legal framework that would enable marriage to withstand the turbulence between spouses inherent in the contingencies of human life. Nevertheless, repudiation is a common and well-established practice in Senegalese society, and constitutes a serious obstacle to the stability of marriage, even if it is not elevated to the rank of cause for divorce. It should also be noted that incompatibility of temperament is a cause for concern, given the plasticity of this ground for divorce.
Keywords: Divorce; Fin de non-recevoir; Legal separation; Mariage; Marriage; Nullity; Nullité; Plea of inadmissibility; Repudiation; Répudiation; Stabilisation; Stabilization; Séparation de corps

Les droits politiques de l’associé en droit des affaires OHADA - Harouna, Mohamad Albachar; Diallo, Mahamoudou Bazzi (Revue Kurukan Fuga, 2024)
La qualité d’associés confère des obligations et des droits aux associés. Au nombre de ses droits figure les droits politiques, objet de la présente réflexion. Il nous semble opportun d’indiquer l’importance desdits droits dans la préservation des intérêts de l’associé au sein de l’institution sociale. La question se pose alors de savoir comment les droits politiques sont appréhendés par la législation en la matière et quelles sont leurs modalités de mise en œuvre ? L’objectif de l’analyse consiste à identifier ces droits politiques afin de connaitre leur portée vis-à-vis des autres droits. Pour ce faire, les méthodes empirique et théorique serviront d’aboutir à cet objet. Les résultats issus de cette analyse permettront aux futurs associés de pouvoir à une défense accrue de leurs droits dans la structure sociétaire dans la mesure où ces droits assurent la gendarme de tous les autres. Nous recommandons au législateur de permettre une mise en œuvre d'un tel droit même à l’associé détenant un pour cent du capital en vue de crédibiliser l’espace des affaires. Il serait logique d’examiner dans une première partie le droit politique attaché à l’information des associés et dans une seconde partie le droit politique tiré du droit de vote de l’associé.
Keywords: Associé; Droit politique; Information; Vote

La Cour Africaine des Droits de l’Homme : la liberté de circulation des étrangers et l’intégration africaine. Observations rétrospectives sur l’arrêt Ikili Rashidi contre République-Unie de Tanzanie du 28 mars 2019 - Moyen, Léandre SergeI (Revue Africaine des Sciences Juridiques, Administratives et Politiques, 2024)
La Cour africaine était sollicitée pour répondre à la question de savoir si les ressortissants des États africains peuvent avoir droit, au même titre que les nationaux d’un État, à une égale protection en ce qui concerne la liberté de circulation et de séjour, c’est-à-dire de choisir librement leur résidence sur le territoire d’un État membre de l’Union africaine et signataire de la Charte africaine des droits de l’homme, même quand la régularité de leur séjour n’est pas formellement établie. Cette question fait directement référence à la problématique de l’intégration africaine, et en s’inscrivant dans la perspective intégrationniste, il était possible d’y répondre par l’affirmative. Au regard de l’idéal politique panafricain de l’unité politique affirmé pas le traité constitutif de l’Union africaine, la Cour pouvait interpréter la Charte africaine des droits de l’homme ou la Déclaration universelle des droits de l’homme comme autorisant les ressortissants des États africains à établir leur résidence où ils le souhaitent sur n’importe quel territoire d’un État membre de l’Union. Mais l’absence d’une citoyenneté africaine a conduit la Cour à lire l’article 3 de la Charte africaine dans le sens opposé. Ce faisant, elle entérine le renforcement des législations nationales, qui se sont inspirées des législations européennes très restrictives à l’égard de l’entrée et du séjour des étrangers sur le territoire de l’Union européenne. Elle s’est abstenue de créer du droit substantiel, alors qu’elle avait toute latitude pour le faire, à l’instar de la Cour européenne qui limite volontiers le pouvoir souverain des États en matière de protection des droits fondamentaux des personnes. Cette attitude prudente s’est confirmée dans l’appréciation des règles du procès équitable, où la Cour fait un usage modéré des pouvoirs que lui confèrent les articles 56 alinéas 5 et 6 de la Charte africaine et 40 § 6 du Règlement de la Cour, bien que le cadre conventionnel soit plastique. En définitive, la Cour africaine n’a pas été conçue pour accompagner l’unité politique africaine ; elle n’est pas l’instrument de mise en œuvre de la politique d’intégration africaine, et la décision Ikili Rashidi montre à coup sûr les limites de l’office du juge panafricain dans la protection des droits et libertés des citoyens. Il est impératif que les États s’orientent vers l’institution du contrôle de constitutionnalité des lois à l’échelle fédérale, ce qui semble être la seule alternative permettant la mise en place d’une justice réellement souveraine au service de l’intégration.
Keywords: Cour africaine des droits de l’homme; Dignité humaine; Droits fondamentaux de la personne; Etranger; Expulsion; Intérêt supérieur de l’enfant; Justice (administration); Liberté de circulation; Procès équitable; Vie familiale; Vie privée

Les facteurs fragilisant la lutte contre la cybercriminalité au Mali - Sangaré, Sékou (Revue Africaine des Sciences Juridiques, Administratives et Politiques, 2024)
Le développement des technologies de l’information et de la communication constitue un tournant majeur de la civilisation humaine. Le réseau internet constitue aujourd’hui l’illustration parfaite des possibilités offertes par les technologies de l’information et de la communication qui, grâce aux services disponibles demeure un puissant vecteur de communication utilisée par des millions de personnes. Si ces nouvelles technologies participent de manière positive au développement de la vie économique, elles présentent aussi de nouveaux moyens de commettre des infractions, ce qui fait apparaître des dangers non négligeables, vue l’importance qu’elles ont désormais acquise.
Keywords: Cybercriminalité; Infractions; Mali; NTIC

Impact of the Revision of the OHADA Accounting System on the Decision to Grant Bank Credit to Cameroonian Companies: An Interview with Credit Analysts - Sekadjie, Dedy Christelle; Mbohwa, Charles (Journal of Accounting and Finance in Emerging Economies, 2024)
Purpose: The objective of this study is to evaluate the impact of accounting data produced after the revision of the OHADA accounting system on the decision to grant bank credit to Cameroonian companies. Methodology: qualitative approach was used in this study. We conducted semi-structured interviews with eight credit analysts in eight banks based in Cameroon. We used the Nvivo 10 software to carry out the content analysis. Findings: It emerges from the analysis of the content of the speeches collected that the most used ratios by credit analysts are: activity ratios, debt ratios, operating ratios, financial structure and autonomy ratios, debt ratios and net cash. In addition, the information provided by the new accounting system is increasingly fluid, detailed, and precise and facilitates decision-making. However, when it comes to the completeness and sincerity of the information provided, analysts remain wary because, companies always provide information subjectively based on their interests Implication: This study reveals that despite the revision of the accounting system, users still remain wary face of informations provided because of its subjective nature. It is therefore recommended that Member States promote unified information for all stakeholders.
Keywords: Accounting system; Bank credit; Decision-making; Revision

Du dessaisissement du juge étatique face à la convention d'arbitrage en droit de l'OHADA - Anciza Migani, Ryan; Mbazi, Grâce Beda; Murhula Bahati, Pacifique; Iragi Ntwali, Valéry (Studia Universitatis Babeș-Bolyai Studia Europaea, 2024)
The State Judge's Relinquishment of Jurisdiction over Arbitration Agreements under Ohada Law. The use of arbitration instead of state judges is increasingly popular in the business world. The parties to contracts thus prefer to choose a judge more quickly and less cumbersomely, with more confidentiality and less publicity. If the advantages of resorting to arbitration are undoubted, its effects leading to the total withdrawal of state jurisdictions attract the attention of many. The incompetence of the judge due to arbitration then tends to completely rule out the latter, which merits a better understanding of the powers and competence of the arbitrator and a good understanding of the place of the state judge in the arbitration procedure.
Keywords: Arbitration agreement; Convention d’arbitrage; Divestiture; Droit OHADA; Juge étatique; OHADA law; State judge

From Divergent Paths to the Same Trap: The Legitimacy Crisis of the Investor-State Dispute Settlement System - Sönmez, Esma Yağmur (Middle East Technical University, 2024)
This thesis critically examines a much-debated issue in international law: the legitimacy of the Investor-State Dispute Settlement system (ISDS). The system was initially conceived to provide an alternate dispute resolution mechanism for the protection and promotion of foreign investment. In time, this objective has incited a discussion on the legitimacy of the system as the developed world has started to experience the role of host states. Since then, they have taken the lead in the reform process to achieve a balance between host state's and foreign investors' rights. To this effect, both the European Union (EU) and the Third Way Approaches to International Law (TWAIL) are for centralization of the system arguing its current problems emanate from its ad hoc and decentralized nature. Although both are aimed at system centralization, the paths they take to achieve it clearly differ. The EU seeks a permanent investment court by which ad hoc arbitration would give way to a more centralized framework. However, TWAIL advocates for a return to the pre-ISDS era, where national courts resolve investment disputes between foreign investors and states. The effectiveness of these two reform ideas in addressing the purported legitimacy concerns of the ISDS is critically examined in this thesis using Martti Koskenniemi's legal approach. Ultimately, it asserts that neither proposal is adequate to resolve the legitimacy issue of the system, as legitimacy can only be achieved by strengthening the principle of justice, which is feasible alone through a more decentralized structure.
Keywords: ADR; Alternative dispute resolution; Foreign investment; Foreign investors; ISDS; Investment Dispute; Investments; Investor-State Dispute Settlement

La valorisation par le droit de la production des communs numériques - Bachelet, Vincent (Université Paris-Saclay, 2024)
Les communs sont des instruments de gestion des ressources très anciens - que l'on retrouve par exemple en France avec les communaux de la période féodale - qui, après avoir quasiment disparu du débat universitaire sont redevenus un sujet de premier plan grâce aux travaux d'Elinor Ostrom, avant d'être réinventés à l'aune des possibilités ouvertes par le numérique. En effet, on assiste actuellement à l'organisation et au développement de nombreux projets de communs numériques, Internet étant devenu le lieu de prédilection de la création collaborative, sans pour autant exclure de la démarche les rencontres physiques et organisations juridiques autour de ces projets. Par ailleurs, la multiplication de ces projets de communs numériques a conduit à un rapprochement avec le milieu du logiciel libre, du fait de leurs nombreux points communs. Ce rapprochement entre les communs numériques et les logiciels libres a mis en exergue la difficulté pour les projets numériques libres et open-source d'assurer leur pérennité économique sans altérer leur nature de communs.En effet, depuis l'origine, les logiciels libres - à l'instar de l'ensemble des œ œuvres libres - sont pensés comme la propriété collective des contributeurs, qui en fixent collectivement les règles de gouvernance, notamment par le recours à une licence libre. En cela, les logiciels libres sont pensés comme des communs numériques. Toutefois, ce n'est pas toujours le cas. Ainsi, si la gouvernance partagée et la propriété collective de la ressource constituent deux des trois caractéristiques des communs ; elles ne font pas partie des éléments de définition des logiciels libres. De fait, nombre de logiciels libres ne font pas l'objet d'une gouvernance partagée ou d'une propriété collective. Ainsi, ces différentes évolutions questionnent la viabilité dans le temps du modèle actuel du logiciel libre. De fait, si ces nouveaux instruments juridiques sont critiquables, et critiqués au sein de la communauté du libre et de l'open source, ils peuvent également être envisagés comme autant de raisons de s'interroger sur les outils juridiques à même de structurer un modèle économique permettant d'assurer la viabilité des logiciels libres tout en garantissant leur nature de communs numériques.
Keywords: Choses communes (droit); Communs numériques; Digital commons; Earmarked patrimony; Fiducie; Fiducie étrangère; Logiciels libres; Patrimoine d'affectation; Social economy; Économie sociale et solidaire

La numérisation des services publics et leur délégation à des entités privées - Catena, Joffrey (Université de Toulon, 2024)
La numérisation via le recours systématique aux technologies couvre désormais la majorité des secteurs de la société. Cette transformation impacte également les usages des administrés dans leur approche des services publics et de l’Etat. Or l’utilisation des services numériques implique un recours à des prestataires de services numériques qui sont par essence des entités privées. S’opère alors une délégation numérique des services publics qui, bien que restant sous le contrôle étatique, n’en demeure pas moins massivement externalisés du fait de leur mutation numérique. Ces prestataires de services numériques ne nous sont pas inconnus. Il s’agit majoritairement de géants numériques américains qui instille à travers les usages imprégnant leurs prestations de services connexe au numérique, la conception d’une mathématisation du droit. Ce concept vise à simplifier les macro-sciences dont fait partie la science humaine juridique afin de la rendre exploitable et calculable par des systèmes autonomes technologiques. Faire de la science humaine dite molle une science dite dure. Faire du droit une science mathématiquement calculable. Les services publics français dans leur transition numérique font ainsi office de cas d’étude venant mettre en exergue les menaces d’une casuistique juridique numérique généralisée, et les évolutions futures visant une délégation de ces services et par extension du droit à des technologies autonomes qui sont conçues afin de viser le statut d’entité. Digitization through the systematic use of technologies now covers most sectors of society. This transformation also impacts the uses of those administered in their approach to public services and the State. However, the use of digital services implies the use of digital service providers who are, in essence, private entities. There is then a digital delegation of public services which, although remaining under state control, nonetheless remain massively outsourced due to their digital transformation. These digital service providers are not unknown to us. These are mainly American digital giants who instill, through the uses permeating theirdigital-related services, the conception of a mathematization of law. This concept aims to simplify the macro-sciences of which legal human science is a part to make it exploitable and calculable by autonomous technological systems. Make so-called soft human science a so-called hard science. Make law a mathematically calculable science. French public services in their digital transition thus serve as a case study highlighting the threats of generalized digital legal casuistry, and future developments aimed at a delegation of these services and by extension the right to autonomous technologies which are designed to aim for entity status.
Keywords: Artificial intelligence; Casuistic; Casuistique juridique; Cybersecurity; Cybersécurité; Delegation; Délégation; Délégations de service public; Dématérialisation (informatique); Externalisation; France; Intelligence artificielle; MARD; New public management; Numérisation; Services publics; Smart contracts; Smart contrats

L'absorption d'une personne morale membre d'un conseil d'administration : étude comparée - Diomande, Yannick (Université de Bordeaux, 2024)
L’opération de fusion-absorption d’une personne morale est une question en soi difficilement appréhendée tant dans les effets qu’elles déploient que dans l’organisation d’une telle opération. Cette difficulté propre à la nature d’une telle opération prendra une allure tout autre lorsqu’une personne morale membre d’un conseil d’administration s’y trouve impliquer. Toutes les hypothèses pouvant être développées traduisent non seulement la diversité mais également la complexité d’un tel sujet. Si cette question telle qu’elle est évoquée, est révélatrice du caractère instrumental du droit des sociétés, force est de reconnaître que la résolution d’une telle problématique devrait se faire par la conciliation des caractéristiques propres au droit des fusions mais aussi en tenant compte des spécificités entourant la personne morale administrateur. La transmission universelle du patrimoine, la réorganisation des pouvoirs post-fusion, les droits des créanciers, le problème de la représentation de la personne morale dans la société absorbante, la gouvernance de la société administrée, l’intrusion d’une personne morale tierce, les questions de fusions internationales sont autant de questions soulevées par cette problématique. La solution de cette problématique commande une étude minutieuse des questions soulevées à l’aune du droit OHADA et du droit français.
Keywords: Absorbed legal person; Absorbing legal person; Commercial companies; Companies with board of directors; Conseil d'administration; Corporate law; Droit des sociétés; Droit des sociétés commerciales; France; Fusion-absorption; Merger; Pays de l'OHADA; Personne morale absorbante; Personne morale absorbée; Personnes morales; Restructuration; Restructuring; Études comparatives

L'intermédiation : contribution à une théorie générale en droit du travail - Mouhib, Yassine (Université de Bordeaux, 2024)
Le développement des plateformes numériques au milieu des années 2000 s’est accompagné d’un intense débat juridique cherchant à déterminer la nature de l’activité exercée par ces nouveaux acteurs économiques. Ces derniers prétendent n’être que des intermédiaires. Mais qu’est-ce que cela peut-il bien signifier du point de vue du droit du travail ? Cette étude cherche à répondre à cette interrogation en proposant une théorie qui se veut générale, à même de resituer l’activité des plateformes numériques parmi les autres formes traditionnelles d’intermédiation que connaît déjà le droit du travail. Face au développement croissant de nouvelles techniques d’intermédiation, du portage salarial au CDI intérimaire en passant par le prêt de main-d’oeuvre auprès d’une jeune, petite ou moyenne entreprise ou encore par les plateformes numériques, cette théorie cherche à révéler la cohérence sous-jacente de phénomènes qui peuvent se présenter au premier abord comme répondant à des logiques distinctes. En proposant une représentation d’ensemble, la construction d’une telle théorie est l’occasion d’identifier une propriété fondamentale de tout schéma d’intermédiation : la multipolarité. Cela signifie simplement que ces montages contractuels mobilisent une pluralité d’acteurs. La multipolarité des schémas d’intermédiation est cependant saisie de manière très diverse par le droit du travail. Le cadre d’application des règles juridiques à partir desquelles ces formes de travail sont encadrées peut être tantôt bilatéral, tantôt multilatéral. Dans ce dernier cas de figure, en s’émancipant de la figure traditionnelle de l’employeur, le droit du travail prend en compte une pluralité d’acteurs indépendants les uns des autres pour appliquer une règle juridique à une situation de travail. Ainsi, en proposant une représentation d’ensemble des différentes formes d’intermédiation, la présente étude a donc vocation à révéler la diversité des modes d’application du droit du travail.
Keywords: Droit du travail; Intermédiation; Labour law; Multilatéralité; Multipolarité; Médias numériques; Plateforme

La blockchain au service de la question sociétale : étude de ses fonctions en droit de la responsabilité sociétale des entreprises - Arrouas, David (Université de Strasbourg, 2024)
La blockchain à travers ses fonctions registres et smart contracts constitue un moteur de la confiance. Le registre blockchain, distribué sécurisé et sans autorité centrale, révolutionne la confiance. Le smart contract, adossé à une blockchain, auto-exécutant et inaltérable assure, lui, l'exécution automatique d'actions prédéfinies. Initialement conçus pour le secteur financier, le potentiel de cette technologie s’étend à la RSE en tant que support de la norme. Les smart social contracts seraient en mesure d’automatiser les processus liés à la RSE, tandis que le registre blockchain renforcerait la transparence et la traçabilité. Un cadre juridique clair reste cependant essentiel pour concilier innovation et protection des droits. Définir le rôle de la blockchain dans une démarche de RSE pourrait transformer les interactions des entreprises avec leurs parties prenantes, renforcer la confiance, la transparence, la réactivité et, plus largement, l’effectivité de norme sociétale.
Keywords: Blockchain; Blockchains; CSR; Confiance; Devoir de vigilance; Duty of vigilance; RSE; Responsabilité Sociétale de l'Entreprise; Smart contract; Smart social contract; Trust

L'articulation entre le droit commun et le droit spécial des contrats, à travers l'exemple des contrats de distribution - Cassagne, Alexandre (Université de Strasbourg, 2024)
La réforme du droit des contrats de 2016 a partiellement éludé la problématique de l’articulation entre les normes de droit commun et celles de droit spécial. Un article semble reprendre en substance l’adage specialia generalibus derogant. Mais cette nouvelle disposition énonce très peu ; et le peu qu’elle énonce ouvre sur des problèmes nouveaux. Le choix des contrats de distribution comme axe principal des recherches a été opéré afin de souligner les rapports nouveaux que le droit qui les régit entretient avec le droit commun, celui-ci reprenant désormais en considération la problématique des contrats structurellement déséquilibrés qui était autrefois propre aux droits spéciaux. L’étude chronologique de l’évolution de ces rapports permet de souligner les problèmes que soulève l’absence d’une règle détaillée d’articulation. Les juges se dirigent actuellement vers une relégation au second plan du droit commun ; au risque d’une marginalisation et d’un déficit dans la protection de la partie faible (le droit commun pouvant être devenu plus protecteur que le droit spécial). Il est proposé de confier au législateur le soin d’insérer une nouvelle règle d’articulation organisant les conflits entre le droit commun des contrats et le droit spécial des contrats de distribution. Inspirée du principe de faveur, cette nouvelle règle d’articulation serait insérée dans un livre dédié aux contrats de distribution au sein du Code de commerce.
Keywords: Articulation; Contractual balance; Contrats d'exclusivité; Contrats de distribution; Distribution contracts; Droit commun; Droit spécial; Favourability principle; General law; Pratiques restrictives; Principe de faveur; Restrictive practices; Special law; Subsidiarity; Subsidiarité; Équilibre contractuel

Droit positif et droit traditionnel : étude de leurs rapports au Sénégal - Diallo, Aliou (Université Paris Cité, 2024)
Depuis que le droit traditionnel est pris en compte par le droit positif au Sénégal, leurs rapports ont toujours été organisés en fonction de l'opposition juridique qui sous-tend cette reconnaissance officielle. L'opposition juridique dont il est question est celle des caractère et contenu respectifs du droit traditionnel et du droit moderne au Sénégal. L'organisation de leurs rapports par le droit positif a ainsi toujours eu pour objectif de déterminer les sujets et objets de droit ou les situations juridiques auxquels chacun se rapporte. Néanmoins, le droit positif au Sénégal étant essentiellement un droit moderne, c'est historiquement en défaveur du droit traditionnel que l'opposition juridique s'est officiellement manifestée : l'on observe ainsi au cours de l'histoire de leurs rapports une réduction tendancielle du champ de la prise en compte officielle du droit traditionnel. Pour autant, le déclin de cette reconnaissance officielle n'a pas eu pour effet de priver le droit traditionnel d'existence au Sénégal ; il trouve à y exister de manière informelle, c'est-à-dire en dehors du cadre strictement fixé par le droit positif. Cette existence informelle tient au fait que le droit traditionnel au Sénégal est essentiellement d'origine extraétatique et que, sur ce plan, il parvient à prospérer en raison des croyances et conceptions de la vie sociale qui le fondent et des autorités traditionnelles extraétatiques qui les portent. En tout état de cause, avec le déclin de la reconnaissance officielle du droit traditionnel au Sénégal, c'est le primat du droit moderne dans le droit positif qui y a été affirmé. Mais ce primat est en réalité précaire dans la mesure où l'existence informelle du droit traditionnel fait obstacle à la pleine effectivité du droit positif dans son application.
Keywords: Droit coutumier; Droit moderne; Droit positif; Droit traditionnel; Effectivité du droit; Existence informelle; Extraétatique; Reconnaissance officielle; Sénégal; Validité du droit

Le droit processuel appliqué au contentieux des brevets à l'aune de la Juridiction unifiée du brevet : quel rôle pour la Cour de justice de l’Union européenne ? - Lawrynowicz-Drewek, Anna (Université de Strasbourg, 2024)
La Juridiction unifiée du brevet (JUB), une nouvelle juridiction internationale spécialisée dans le contentieux des brevets européens, est soumise au respect du droit de l’Union européenne. Ce dernier, toutefois, demeure éparpillé et incomplet en matière de la procédure civile. La question du rôle effectif de la CJUE dans l’interprétation des règles procédurales de la JUB représente un intérêt majeur. Or, l’analyse approfondie des règles européennes et celles propres à la JUB conduisent au constat que ce rôle demeure à ce jour limité. L’absence de renforcement du rôle de la CJUE conduit à un risque de l’incohérence du droit de l’UE, de son application non uniforme ainsi que, de point de vue stratégique, à un forum shopping prononcé réduisant l’attractivité de la nouvelle juridiction spécialisée. Pour remédier à cette situation, la thèse suggère une série des propositions visant à renforcer le rôle de la CJUE en la matière, tantôt à travers des instruments horizontaux que spéciaux.
Keywords: Brevet européen; Brevet européen à effet unitaire; Brevets d'invention; Contentieux civil; Contentieux d'entreprise; Contentieux des brevets; Contrefaçon de brevet; Droit de procédure civile; Droit international privé; Droit processuel; Droits de l’Homme; Garanties procédurales; Juridiction internationale; Juridiction spécialisée; Juridiction unifiée du brevet; Union européenne (droit)

Vers un renouvellement de l'abus de position dominante face au défi de l'économie numérique ? Regards croisés entre droit antitrust américain et droit européen et interne de la concurrence - Nielson, Nathalie (Université Côte d'Azur, 2024)
L’économie numérique a posé des défis inédits en droit de la concurrence,la combinaison de phénomènes économiques ayant conduit à une tendance deconcentration des marchés, réduisant leur contestabilité. En tant que contrôleurd’accès, certaines plateformes d’intermédiation incontournables ont été en mesured’adopter des stratégies de verrouillage et des comportements prédateurs, élevantdes barrières à l’entrée quasi infranchissables. L’approche économique de l’Écolede Chicago, prédominante depuis les années 1980 en droit américain et ayantprogressivement imprégné le droit européen et interne de la concurrence, a ainsimontré des limites, questionnant l’effectivité du droit de la concurrence etspécifiquement de la prohibition des pratiques anticoncurrentielles unilatérales –monopolisation ou abus de position dominante. Entre autres, la gratuité de certainsproduits ou services, la forte connexité des marchés, ou encore la difficile mesurede la substituabilité a complexifié l’évaluation du marché pertinent et du pouvoir demarché.Face à cette défaillance des marchés numériques, une réaction régulatoires’observe, avec l’adoption du Digital Markets Act en droit européen et l’introductionde propositions législatives aux Etats-Unis suivant le même modèle. Nonobstant, ladiversité des modèles économiques des plateformes d’intermédiation rend malaiséeune régulation sectorielle et pose des obligations parfois trop lourdes pour certains,ou non pertinentes.Ainsi, pratique décisionnelle et jurisprudence européenne et interne ont su s’adapterà ces problématiques, initiant une modernisation de la notion d’abus pour saisir lespratiques commerciales déloyales de ces plateformes sous le prisme d’un regaind’intérêt pour l’abus d’exploitation et de nouvelles théories de l’abus d’éviction. Acontrario, le droit américain ne vient que très récemment de s’en emparer avecl’introduction de multiples poursuites civiles à l’encontre des GAFAM depuis octobre2020. Un renouvellement de la prohibition s’avère donc nécessaire afin deconsolider cette orientation et pour que le droit de la concurrence puisse de nouveauefficacement contrôler les pouvoirs privés économiques et maintenir uneconcurrence libre et loyale tout en préservant l’innovation
Keywords: Abus de position dominante; Antitrust; Competencia; Competition law; Concurrence; Digital Economy; Digital platforms; Droit comparé; Droit économique; Economic law; Monopolization; Plateforme numérique; Économie Numérique; Économie numérique

La transversalité en droit de la propriété intellectuelle - Armand-Toureuh, Rebecca (Université Paris-Saclay, 2024)
Le droit de la propriété intellectuelle, derrière l'apparence unitaire que livre le singulier de cette qualification, est, en réalité, un droit constitué d'une pluralité de régimes juridiques, tels que le droit d'auteur et ses droits voisins, le droit des dessins et modèles, le droit des signes distinctifs, ou encore le droit des brevets. À première vue, cette pluralité de droits ne répond à aucune cohérence d'ensemble.Des raisons historiques peuvent expliquer la disparité actuelle : chaque droit de propriété intellectuelle étant apparu de manière isolée, chacun d'entre eux a développé sa propre logique. Bien que le Code de la propriété intellectuelle rassemble ces différentes protections sous une qualification unitaire et les présente de manière organisée, il ne contient pas de dispositions communes. Au demeurant, l'adoption progressive de différentes protections, telles que le droit sui generis sur les bases de données, le droit d'auteur sur les logiciels, ou encore les droits voisins des éditeurs de presse, réinterrogent sans cesse les frontières de la matière.Pour tenter d'en rétablir la cohérence, la transversalité, qui s'entend d'une approche transversale, peut être mobilisée afin de se demander si, à la lumière des éléments de transversalité identifiés, ceux-ci sont susceptibles de contribuer à l'élaboration d'une théorie générale de la propriété intellectuelle.Ces éléments communs aux différents droits de propriété intellectuelle sont recherchés sous l'angle, d'abord, de l'objet du droit, puis du régime juridique pour, enfin, appréhender leur influence sur la nature juridique du droit de la propriété intellectuelle. En ce qui concerne l'objet du droit, si l'approche transversale permet de révéler certains critères de définition transversaux, elle ne permet pas de dégager une qualification unitaire de l'objet de propriété intellectuelle. S'agissant du régime juridique, l'approche transversale permet, là encore, la mise en exergue d'éléments transversaux qui sont prompts à définir un régime commun de la propriété intellectuelle, mais ces éléments se limitent au volet patrimonial du droit et à sa sanction. L'ensemble de ces éléments de transversalité, susceptibles de constituer le « noyau dur » de la propriété intellectuelle peuvent, enfin, permettre de porter un autre regard sur la nature juridique du droit de la propriété intellectuelle, en interrogeant de manière systémique sa qualification propriétaire. Behind the unitary appearance of this singular term, intellectual property law is actually made up of a plurality of legal regimes, such as copyright and related rights, design rights, trademark law and patent law. At first glance, this plurality of rights does not reflect any overall coherence.Historical reasons may explain the current disparity: each intellectual property right having emerged in isolation, each has developed its own logic. Although the French Intellectual Property Code groups these different types of protection under a single title and presents them in an organized manner, it does not contain any common provisions. In fact, the gradual adoption of different forms of protection, such as sui generis rights for databases, copyright for software, or related rights for press publishers, is constantly reexamining the boundaries of this field.In an attempt to re-establish coherence, transversality, which is understood as a transversal approach, can be mobilized to ask whether, in the light of the elements of transversality identified, these are likely to contribute to the development of a general theory of intellectual property.These elements, which are common to the various intellectual property rights, are examined first from the point of view of the object of the right, then from the point of view of the legal regime and, finally, from the point of view of their influence on the legal nature of intellectual property law. With regard to the object of the right, while the transversal approach reveals certain transversal definition criteria, it does not allow us to identify a unitary qualification of the object of intellectual property. With regard to the legal regime, the transversal approach once again brings to light transversal elements that are likely to define a common intellectual property system, but these elements are limited to the patrimonial aspect of the right and its sanction. All these transversal elements, which are likely to constitute the “hard core” of intellectual property, may finally enable us to take another look at the legal nature of intellectual property law, by systemically questioning its proprietary qualification.
Keywords: Intellectual property; Interdisciplinarité; Propriedade intelectual; Propriété intellectuelle; Transversality; Transversalité; Unity; Unité

Les mutations du droit de la filiation - Damy, Marion (Université de Bordeaux, 2024)
Avant même la loi de ratification de 2009, réformant l’ordonnance relative à la filiation en 2005, la matière semblait déjà devoir affronter de nouveaux défis. L’évolution des progrès techniques et scientifiques ainsi que la diffusion des droits fondamentaux perturbent, en effet, les équilibres entre les enjeux collectifs et individuels inhérents à l’encadrement des relations familiales. Davantage tournées vers l’individu, ces influences conjuguées densifient la subjectivisation décrite par le doyen Carbonnier. Partant du constat que ce phénomène a franchi une nouvelle étape depuis la libéralisation du mariage en 2013, cette étude a vocation à étudier les mutations à l’œuvre en droit de la filiation qui en découlent. Il en ressort que la nouvelle étape du phénomène consiste à considérer davantage les singularités tant en amont qu’en aval de la loi. Au stade de l’élaboration, le contenu de la loi est négocié quand, au stade de l’application, la solution est établie concrètement. La limite opposée à la volonté individuelle doit désormais être plus concrète et justifiée. En conséquence, le contrôle du domaine se déplace principalement en faveur du juge, au plus près des situations d’espèce.
Keywords: Best interest of the child; Droits fondamentaux; Engendrement; Famille; Family; Filiation; Fundamental rights; Intérêt de l'enfant; Reproduction; Social transformations; Transformations sociales

L'équilibre contractuel : étude de droit commun des contrats - Pocard, Justine (Université de Lorraine, 2024)
L’équilibre contractuel a pu susciter des débats en doctrine tant son appréhension paraissait intuitive, et souvent interchangeable avec d’autres notions, telles que l’équivalence. Pourtant incontournable en droit des contrats, invoquée par la doctrine, le législateur, et parfois même par la jurisprudence, cette notion n’a, paradoxalement, fait l’objet d’aucune étude de portée générale, c’est-à-dire indépendamment des différents modèles contractuels dans lesquels il se manifeste, laissant régner une certaine confusion autour de la notion. La thèse se propose d’apporter une clarification notionnelle en appréhendant l’équilibre au regard de la notion de contrat, indépendamment de ses espèces. L’équilibre contractuel peut ainsi s’analyser comme une finalité, tenant à la satisfaction des intérêts contractuels. Cette définition favorise l’appréhension de l’équilibre contractuel en droit positif, ainsi que l’identification des phénomènes du droit positif subsumés sous la notion d’équilibre contractuel. Pour favoriser cet idéal, cela suppose l’identification de certains critères, non absolus, induisant une prévention et un traitement rationnel de l’équilibre contractuel, permettant, notamment, la conservation de l’intérêt de l’outil contractuel
Keywords: Balance; Behavior of contractors; Comportement des contractants; Contract; Contrat; Equilibre; France; Interest; Intérêt; Liberté contractuelle; Équilibre contractuel

La mise en œuvre des règles de la responsabilité civile en matière de contrat de travail - Wysocki, Dorine (Université de Lille, 2024)
La relation de travail entre le salarié et l’employeur se matérialise par un contrat de travail. Ce dernier présente un caractère déséquilibré. En réaction à cette situation, les règles de la responsabilité civile sont mobilisables et mobilisées. Cette imbrication entre le droit du travail et le droit de la responsabilité civile s’opère notamment grâce à une intégration et à une adaptation de ces règles. Elles permettent d’apporter une protection au salarié. Cette protection a un double caractère. D’une part, dans la mesure où le déséquilibre a souvent lieu en défaveur du salarié, une protection légitime mérite de lui être accordée. D’autre part, les règles de la responsabilité civile regorgent d’outils conduisant à une protection dynamique de la partie défavorisée. Au travers de cette double protection, c’est une recherche constante de rééquilibrage qui émerge. La mise en œuvre des règles de la responsabilité civile offre ainsi des solutions pour rééquilibrer le contrat de travail.
Keywords: Contrat de travail; Déséquilibre; Employment contract; Faute; Faute (droit); Imbalance; Mistake; Obligation; Obligations (droit); Prejudice; Protection; Préjudice; Responsabilité civile; Responsabilité contractuelle; Responsabilité délictuelle; Équilibre contractuel

La compliance en droit bancaire et financier, une fonction juridique et managériale - Amoussou, Henry (Université de Reims Champagne-Ardenne, 2024)
La compliance s’est traduite par une floraison des obligations, des techniques et des procédures, portées par des règles de ''droit dur'' et de ''droit souple''. Leurs mises en œuvre ont été confiées à de nouveaux acteurs. Dans le domaine bancaire et financier, loin de dénaturer la conformité et la régulation, la compliance les renforce en étendant les obligations de cartographie des risques et de vigilance aux risques de corruption et environnementaux. Cependant, le blanchiment de capitaux et le financement du terrorisme restent les risques dominants. Ils sont au cœur de la compliance, notamment au regard de l'activité de sanctions de l’Autorité de contrôle prudentiel et de résolution (ACPR). La prévention de ce risque impose la mise en application des dispositifs normatifs que sont les principes de cartographie des risques et de vigilance. Au-delà de la conformité aux principes normatifs (juridique), la compliance mobilise toutes les fonctions de l’entreprise au niveau opérationnel (management). Ces fonctions opérationnelles sont relatives aux procédures d’alerte, de signalements, de contrôles, de sanctions et constituent des dispositifs procéduraux. Pouvant être qualifiée en ce sens, de « fonction juridique et managériale », la compliance pousse à envisager autrement les régimes de responsabilités en milieu bancaire et financier, fondés sur des défaillances ''obligationnelles'', tant juridiques que managériales. Cela renvoie à l’épineuse obligation de connaissances en management requises pour les juristes et les autorités d’une part, et d'autre part, au caractère inextricable des fonctions juridiques et managériales (d’où les formations en droit des affaires et management).
Keywords: Compliance; Conformité; Droit bancaire; Droit financier

Criminalité économique transfrontalière : stratégies pour une sortie de crise - ERSUMA - OHADA (2024)

L'économie collaborative et le droit de la concurrence - Maillard, Marine (Université du Littoral et de la Côte d'Opale, 2024)
Par les règles existantes à adapter et par de nouveaux outils, le droit de la concurrence joue un rôle déterminant pour encadre mais aussi favoriser l'économie collaborative. L'économie collaborative est une économie nouvelle qui procède d'un modèle disruptif permettant au particulier de devenir acteur de l'économie. Ces derniers peuvent ainsi préférer une consommation plus raisonnable des produits déjà existants. Pour ce faire, ils vont vendre des biens et des services sous-exploités et leur donner une valeur nouvelle sous forme de prix et donc en dégager un revenu tout en évitant la consommation et la production de produits neufs. Cette économie s'est rapidement développée à partir de 2008 et de la création d'Airbnb. Par leur mode de fonctionnement unique, reposant sur les utilisateurs, ces plateformes ont pu échapper, en partie, à la réglementation. Le phénomène prenant de l'ampleur, avec l'arrivée de nouveaux acteurs, il était urgent de réglementer l'économie collaborative. Mais la disparité des acteurs, plateformes et utilisateurs, appel à la prudence. Là où le droit de la concurrence peut s'appliquer aux plateformes car elles sont des entreprises, il ne peut, en principe, agir pour les utilisateurs car ils sont de simples particuliers. L'économie collaborative apportant des bénéfices certains, il faut alors veiller à sa viabilité et à son développement, notamment par la protection, par le droit de la concurrence, des outils de plateformes.
Keywords: Airbnb; Collaborative; Competencia; Competition law; Concurrence; Economy; Loyalty; Loyauté; Vinted; Économie; Économie collaborative

New Public Management Reforms and the Performance of Public Enterprises: An Assessment of Privatization in Nigeria's Telecommunications Sector - Adejuwon, David; Amodu, Akeem; Majekodunmi, Aderonke (African Journal of Politics and Administrative Studies, 2024)
The implementation of New Public Management (NPM) reforms, particularly privatization, has been a significant strategy adopted by governments worldwide to enhance the performance of public enterprises. This article focuses on the telecommunications sector in Nigeria, where privatization was introduced as part of broader economic reforms in the early 2000s. The objective is to assess the influence of privatization on the performance of public enterprises within this sector. The article is anchored on public choice theory. It is qualitative in nature, relying on secondary sources of data, such as, journals, textbooks, official publications and internet materials. It observes that privatization of public enterprises in the telecommunication sector in Nigeria has led to improvements in operational efficiency, increased investment inflows, and expanded service coverage. However, challenges such as regulatory effectiveness, equity in service provision, and the socio-economic impact on marginalized populations remain significant concerns. It contributes to the broader discourse on NPM reforms by providing empirical insights into the complexities and outcomes of privatization within Nigeria's telecommunications sector. It concludes with policy recommendations aimed at optimizing the benefits of privatization while addressing its associated challenges to ensure sustainable and inclusive growth in the sector.
Keywords: New Public Management; Operational Efficiency; Privatisation; Public Enterprises; Public Sector Performance; Service Delivery

The Challenges of Adoption of Eco Single Currency among ECOWAS Member-States - Anele, Livinus; Anuga, Joseph (African Journal of Politics and Administrative Studies, 2024)
The Economic Community of West African States, ECOWAS, had an agreement to adopt the Eco as its single currency for the fifteen member-states of the West African Sub-regional organization. This major objective has failed to materialize after a long period of time. This paper, therefore seeks to highlight the major challenges confronting the Eco currency project. Data were collected from secondary sources, using content analysis. The paper of discusses the challenges facing the proposed Eco single currency in West Africa, discusses the theoretical framework of monetary integration using Mundell’s factors of Mobility Theory and Mundell’s Optimum Currency Area Theory applied. Based on the findings, Some of the challenges facing the proposed Eco currency in ECOWAS include lack of political will, influence of France on its former territories in West Africa, membership of multiple regional blocs by member states of ECOWAS and fear of domination of the smaller states in the bigger ones. Other challenges include; security and political challenges, inadequate legal instruments to enforce treaty obligations, inadequate modern infrastructure among others. To make this proposed Eco currency a success, the paper suggests that West Africa Monetary Zone member states must take concrete action by showing political will towards the creation of Eco currency area in West Africa. There should be clearly spelt out benefits and costs accruing to each member state in the proposed Eco community currency area. All member states of ECOWAS must be treated as equal partners.
Keywords: Adoption; Anglophone-Francophone; Development; ECOWAS; Eco single currency

Nigeria-United States Economic Relations and the Development of the Oil Sector - Okorie, Ikechukwu; Iwuozor, Obialor; Itumo, Anthony (African Journal of Politics and Administrative Studies, 2024)
This study examines Nigeria – United States economic relations from 1999-2018. It was noted that since the Nigeria’s economic relation with United States, the development stride which Nigeria state so desired in the oil sector did not yield any tangible result within the period under study viz opening of new refineries and effective turn around maintenance of the refineries. The specific objectives of this study are: 1. To examine whether Nigeria-United States economic relations has led to opening of new indigenous refineries in Nigeria 2.To determine whether Nigeria–United States economic relations improved the maintenance of refineries in Nigeria within the periods under study 3.To ascertain if Nigeria and United States economic relations had advanced technological transfer in the oil sector industry in Nigeria. The data employed for the study were collected from documentary sources while content analysis was implored for data analysis. The theoretical framework that anchored this study is the Rentier State Theory (RST). After a critical analysis, the following findings were made: 1. it was discovered that Nigeria United States economic relations did not lead to opening of new indigenous refinery 2. The crude oil export to the United States did not improve the maintenance of oil refinery in Nigeria 3. The Nigeria-United States economic relations had not advanced technological transfer in the oil sector industry in Nigeria. In line with the findings the researcher made the following recommendations: 1.That Nigeria government should make a policy that will bring a paradigm shift from net import to net export 2. Nigerian government should make it policy easier as to accommodate and encourage private sector participation in the refining of petroleum products 3. Nigeria government should partner with other countries of the world outside United States that are willing to develop her indigenous technological skills.
Keywords: Crude oil; Development; Economic Relations; Oil sector; Petroleum

Corporate social responsibility performance of property-development firms in Nigerian south-western urban cities - Oyesomo, Oyewole; Oyedeji, Oyewale; Saheed, Omobolaji; Anifowose, Titilayo (Acta Structilia, 2024)
Previous studies on corporate social responsibility (CSR) in the construction and property-development domain have mainly focused on countries in the Global North with very few studies in the Global South. These prior studies have defined the pyramid elements (economic, legal, ethical, and philanthropic) that make up overall CSR, but none of them have assessed how well corporations performed in relation to each pyramid element, particularly in the property-development industry. Consequently, reflecting on the limited CSR studies in the Global South, this study examines the performance of property-development companies regarding the CSR pyramid elements. The study also assesses the barriers and strategic drivers of CSR among property-development companies. The study employed a descriptive survey research, and questionnaires were administered to 43 property-development companies. Descriptive data analysis was done to rank the relative importance of items from the questionnaire. Results showed that, although companies performed ‘well’ in their legal CSR, and ‘average’ in their economic and ethical CSR, companies performed ‘poorly’ in the area of philanthropic CSR. Lack of support by top management, corruption/lack of transparency, lack of knowledge and awareness by professionals, and lack of regulatory framework were identified as significant barriers to CSR implementation among property-development companies. Vision of founders/support by top management, regulatory framework, stakeholder activism, and good relationship-building are potential key strategic drivers of CSR implementation programmes among property-development companies. Given the findings, it is recommended that property-development companies should integrate CSR principles into their vision and mission statement and consider it to be a business function. This can be done by mitigating the barriers identified through the adoption of strategic drivers as postulated by this study.
Keywords: CSR; RSE

SME contractors’ management practices to achieve sustainable business performance in the Eastern Cape province, South Africa - Sogaxa, Athenkosi (Acta Structilia, 2024)
The construction industry in the Eastern Cape province of South Africa plays a crucial role in the region’s economy, yet small and medium enterprise (SME) construction companies face significant challenges in achieving long-term business sustainability. This article aims to provide practical guidelines for SMEs, by investigating the most critical construction management practices adopted by SME contractors. Utilising a quantitative approach, data were collected from 59 purposefully selected participants, including directors, construction managers, quantity surveyors, site agents, and technicians, all registered under the Construction Industry Development Board (CIDB) Grades 1-4 in General Building (GB). The management practices of SME contractors were analysed using the relative importance index (RII) and factor analysis to rank these practices according to their significance. Findings indicate that SME contractors prioritise health and safety strategies, effective resource utilisation, integrated project management systems, competent recruitment, strong leadership skills, and robust health and safety management as essential practices. The principal component analysis identified six key management factors to enhance competitiveness while contributing to the region’s sustainable development goals. These factors include shared knowledge among management, effective project scope planning, comprehensive health and safety management, ownership of construction business knowledge, scope control on projects, and clearly defined goals for management teams. This study is original in its focus on the specific management practices that can strengthen the sustainability of SME contractors within a developing region, providing a valuable framework for enhancing their operational effectiveness.

Le droit applicable aux contrats conclus entre les organisations internationales et les personnes privées - Gnoto, Hadeba (CY Cergy Paris Université, 2024)
Dans le cadre de leurs missions, les organisations internationales sont appelées à contracter avec les personnes privées. Cette relation contractuelle est destinée à remplir certains besoins quotidiens auxquels font face les organisations internationales. (Fourniture de service, constructions de locaux etc.) Ces contrats d'apparence ordinaire ont tout de même une nature particulière, résultant de la différence de régime juridique auquel sont soumises les deux parties. Pour la personne privée, contracter avec une association d'État qui est régie par son traité constitutif et qui dispose d'organes propres est une opération délicate car elle est en relation avec une entité dont le statut juridique relève d'une convention internationale. Quant aux organisations internationales, il s'agit de subvenir à leurs besoins tout en ne compromettant pas les missions dont elles sont investies. La question du droit applicable à ce type de contrat est donc au carrefour des deux intérêts divergents. Il en ressort que les contrats d'organisation sont caractérisés par une adaptabilité et les parties en présence sont amenées à effectuer des combinaisons juridiques afin d'appliquer un droit qui serait capable de couvrir leurs attentes : d'une part il s'agit d'une nécessité de protection de la personne privée. D'autre part, les organisations internationales aspirent, par les contrats qu'elles concluent, à sauvegarder leurs intérêts et leur indépendance et assurer le respect des objectifs pour lesquels elles ont été créées.
Keywords: Contracts; Contrats; Contrats d'organisation; International organizations; Organisations internationales; Personnes privées; Private individuals

La notion d’apport en nature dans les sociétés de capitaux - Ellaji, Abderrazak (Le CNAM, 2024)
La notion d’apport en nature revêt des enjeux d’une grande complexité, tant sur le plan juridique que pratique. Elle soulève de nombreuses difficultés d’interprétation et de mise en œuvre. Celles-ci sont exacerbées par l’essor de la diversité des biens et droits susceptibles d’être apportés en société, ainsi que par la multiplicité des modes de rémunération des associés. Cependant, cette évolution n’a pas été suffisamment suivie par le législateur et la contribution d’une partie importante de la jurisprudence et de la doctrine antérieures est devenue quasi obsolète. Face à cette problématique émergente, un renouvellement du contour juridique de la notion d’apport en nature dans toutes ses dimensions est devenu une nécessité impérieuse.Cette thèse propose une approche globale de la notion d’apport en nature. Cet apport peut être effectué à titre particulier, permettant ainsi la réintégration d’un ou plusieurs actifs ou activités utiles au développement de la société. En outre, le délestage d’un actif non nécessaire à l’exploitation, par voie d’apport, est également possible. Toutefois, le régime juridique de droit commun auquel est soumis cet apport peut s’avérer inapplicable en raison de restrictions de nature légale ou contractuelle. Dans ce contexte, l’apport à titre universel constitue une solution pertinente pour surmonter cette contrainte. Cet apport concerne notamment les opérations de fusion, de scission et d’apport partiel d’actifs et se concrétise toujours par une transmission universelle de patrimoine, dont les enjeux et conséquences sont examinés en profondeur dans la présente étude.Ce travail aborde également le paradoxe lié à l’évaluation de l’apport en nature et aux modes de rémunération et tente de mettre en évidence une synthèse des insuffisances du cadre législatif et doctrinal entourant le sujet. Il propose ainsi des alternatives envisageables pour surmonter les contraintes inhérentes à la réalisation de certaines opérations d’apport. Restent d’autres situations, dans lesquelles l’intervention du législateur apparaît nécessaire pour contourner les contraintes mises en évidence dans l’étude.
Keywords: Apport en capital; Apport en nature; Apports (droit commercial); Contribution in kind; Contribution to a capital company; Entreprises (réorganisation); Fusion d'entreprises; Fusion des sociétés; Merger of companies; Restructuration des sociétés; Restructuring of companies

Le commerçant et le domaine public - Nabe, Baba (Université Grenoble Alpes, 2024)
Pendant très longtemps, le statut de commerçant sur le domaine public n’avait pas profondément évolué. La raison principale est qu’il y avait une antinomie entre le régime de la domanialité publique et les règles protectrices qui fondent le statut de commerçant en droit commercial. Par conséquent, ce régime faisait obstacle à toutes les évolutions. De par son effet, le commerçant ne pouvait par exemple pas exploiter son fonds de commerce sur le domaine public, ni non plus bénéficier de la législation sur les baux commerciaux. Aussi, en cas de faillite, les règles dérogatoires issues des procédures collectives dont bénéficient le commerçant sont altérées par ledit régime. De surcroît, le principe de la liberté du commerce et de l’industrie qui garantie l’activité commerciale est mise à mal par les restrictions du commerce non-sédentaire sur le domaine public.Constatant que cette situation constitue une insécurité juridique pour le commerçant sur le domaine public, le législateur a réagit par la loi n°2014-626 du 18 juin 2014, dite Loi Pinel, en autorisant le fonds de commerce sur le domaine public. Si cette évolution législative permet a priori de sécuriser les droits du commerçant sur le domaine public, il faudra en même temps retenir qu’elle est insuffisante, au regard des difficultés rencontrées par le commerçant sur le domaine public. L’ambition de cette thèse, est de contribuer à l’aboutissement des évolutions déjà amorcées par le législateur, en proposant l’extension des droits du commerçant en vue de parfaire le processus de valorisation économique du domaine public.
Keywords: Bail commercial; Baux commerciaux; Collective procedure; Commercial lease; Commercial property; Commerçant; Domaine public; Fonds de commerce; Procédure collective; Public domain; Trader

La participation de la cible au financement de l'acquisition avec effet de levier - Abdou, Camilla (Université Paris-Saclay, 2024)
L'aptitude d'une société à participer à l'acquisition de contrôle avec effet de levier de ses titres sociaux, constitue un sujet aux incidences juridiques et financières pluridimensionnelles. Cette participation suppose un aménagement préalable. Le processus allant de la sélection à l'acquisition de la cible conduit les parties à l'exécution du contrat d'acquisition. Le levier juridico-financier suppose de respecter la dissociation entre le pouvoir de direction et la détention capitalistique de la cible. L'objectif pour les acquéreurs financiers est d'organiser la participation de la cible post-acquisition au service de la dette d'acquisition de sa nouvelle société mère, la holding de reprise. Une appréciation duale de la cible s'opère, sur ses capacités financières et sur son appartenance au groupe de sociétés constitué à l'effet de son acquisition.Bien que ces méthodes de participation post-acquisition comportent des risques inhérents, celles-ci sont l'objet d'une pratique prisée et sophistiquée par les acquéreurs financiers. En somme, l'accomplissement de la stratégie de participation de la cible au financement de l'acquisition avec effet de levier repose sur un exercice délicat de conciliation entre l'optimisation du montage et la préservation de l'intérêt social de la société acquise, ainsi que du groupe auquel elle s'intègre.
Keywords: Acquisition avec effet de levier; Actionnariat; Contrat d'acquisition; Contrats; Conventions intragroupe; Corporate law; Droit des sociétés; Financement; Financing; Garanties et sûretés; Intercompany agreements; Leveraged buy-Out; Purchase agreement; Shareholding; Warranties and securities

Étude des régimes matrimoniaux : Approche comparative entre le droit français et le droit béninois - Fakeye, Edmond Moboladji Akambi (Université de Toulon, 2024)
Les régimes matrimoniaux constituent une partie importante du droit de la famille. Ils règlent l’ensemble des rapports patrimoniaux des époux à travers la répartition de leurs biens, l’attribution des pouvoirs et la liquidation de leurs intérêts. L’étude comparative des droits français et béninois au sujet des régimes matrimoniaux révèle une grande similitude entre les règles établies par les deux systèmes. En effet, comme pour la plupart des pays francophones de l’Afrique occidentale, le droit béninois se révèle dans plusieurs de ses aspects être un héritage du droit colonial. Ainsi, le Code des personnes et de la famille (CPF) adopté en août 2004, reprend en grande partie les principes du Code civil français relatifs aux relations familiales. L’organisation et la gestion du patrimoine des époux ont donc été élaborées sur la base du modèle français. La principale divergence entre les deux systèmes juridiques se situe au niveau du régime légal. En effet, la différence des réalités sociologiques entre les deux pays ont conduit les législateurs français et béninois à opter l’un pour un régime de communautéet l’autre pour un régime de séparation. Or, de nos jours, en France comme au Bénin, ces réalités sociologiques ont évolué en raison des mutations successives de la société, favorisant ainsi une émergence de nouveaux modes de conjugalité. La conception de la famille par la société a donc évolué avec la naissance de nouveaux cadres pour sa réalisation. Par conséquent, le droit des régimes matrimoniaux qui jusqu’ici est limité aux seuls couples mariés doit s’étendre à ces nouvelles formes de conjugalité. Par ailleurs, cette étude permet de faire des propositions dans la perspective d’une réforme des droits des régimes matrimoniaux français et béninois en vue d’une adaptation du droit contemporain aux réalités sociologiques des deux pays. Matrimonial regimes constitute an important part of family law. They regulate all of the property relations of the spouses through the distribution of their property, the attribution of powers and the liquidation of their interests. The comparative study of French and Beninese laws regarding matrimonial regimes reveals a great similarity between the rules established by the two systems. Indeed, as in most French-speaking countries in West Africa, Beninese law reveals itself in several of its aspects to be a legacy of colonial law. Thus, the Personal and Family Code (CPF) adopted in August 2004 largely incorporates the principles of the French Civil Code relating to family relations. The organization and management of the spouses' assets were therefore developed based on the French model. The main divergence between the two legal systems lies at the level of the legal regime. Indeed, the difference in sociological realities between the two countries led French and Beninese legislators to opt for a community regime and the other for a separation regime. However, today, in France as in Benin, these sociological realities have evolved due to successive changes in society, thus favoring the emergence of new modes of conjugality. Society's conception of the family has therefore evolved with the birth of new frameworks for its realization. Consequently, the law of matrimonial regimes which until now is limited only to married couples must extend to these new forms of conjugality. Furthermore, this study makes it possible to make proposals with a view to reforming the rights of French and Beninese matrimonial regimes with a view to adapting contemporary law to the sociological realities of the two countries.
Keywords: Benin; Bénin; Communauté réduite aux acquêts; Communauté universelle; Community reduced to acquisitions; Droit comparé; France; Mariage; Marriage; Matrimonial regimes; Participation aux acquêts; Participation in acquisitions; Régimes matrimoniaux; Separation of property; Séparation des biens; Universal community

Confidentialité, secret, protection des données et intelligence artificielle dans la procédure arbitrale - Zengue, Laurent-Fabrice (Modes Alternatifs de Règlement des Différends (MARD), Justice amiable, 2024)
L’arbitrage étant l’un des modes alternatifs de règlement des différends, sa particularité est qu’il est confidentiel, secret, rapide, conventionnel et juridictionnel. En ce qui concerne spécifiquement l’obligation de confidentialité et de secret, son étendue est double. D’abord, il y a l’étendue matérielle, qui porte sur la procédure arbitrale, la composition du tribunal arbitral, la nature du litige, les ordonnances du tribunal arbitral, les documents soumis par les parties litigantes, les délibérations et la sentence. En second lieu, il y a l’étendue personnelle, qui concerne les témoins, les parties, les arbitres, le comité d’arbitrage, l’institution ou le centre d’arbitrage, le secrétaire du tribunal arbitral, les experts et tous les autres intervenants de la procédure arbitrale. La problématique centrale est d’analyser comment la confidentialité, le secret, la protection des données personnelles, y compris dans l’hypothèse du recours à l’intelligence artificielle peut être adressée et solutionnée dans le cadre d’une procédure arbitrale.
Keywords: Arbitrage; Arbitration; Confidentialité des données; Intelligence artificielle; Protection des données

Analyse des risques juridiques à l’épreuve de la jurisprudence bancaire : cas des contentieux des voies d’exécution - Luaba Nkuna, Dieudonné (Revue de l'UKA, 2024)
Le domaine bancaire garantit le développement socio-économique des Etats à travers le financement des activités. Bien que les procédures demeurent complexes, elles sont soumises à une autorité de régulation tenant compte des risques et des responsabilités qui en découlent en vue de sécuriser les acteurs intervenants publics comme privés. The banking sector ensures socio-economic development of States, through the financing of activities although the procedures are complex, they are subject to regulatory authority that takes into account the associated risks and responsabilities, aiming to secure the interests of both public and private stakeholders.
Keywords: Banking operations; Banking risks; Bien meuble corporel; Bien meuble incorporel; Contentieux; Enforcement litigation; Execution; Intangible property; Opération bancaire; Precautionary seizure; Risque bancaire; Saisie; Saisie conservatoire; Tangible property; Voie d’exécution

Analyse de la solidité financière du secteur bancaire congolais de 2016 à 2021 - Mutombo Muimbayi, Florent (Revue de l'UKA, 2024)
La solidité bancaire traduit une situation dans laquelle le fonctionnement des différentes composantes du système bancaire et surtout leurs relations réciproques, sont assurées de manière saine et sans perturbations majeures. Cet article se propose d’analyser la solidité financière des banques commerciales en RDC. Les banques commerciales retenues dans le cadre de notre travail ont un ratio de liquidité conforme aux exigences de la BCC. La principale ressource des banques est constituée des dépôts à court terme.
Keywords: Liquidité; Rentabilité; Solidité bancaire; Solvabilité

Intra-Africa trade and the need to rethink the neo-liberal approach - Ngwu, Franklin; Ojah, Kalu (Transnational Corporations Review, 2024)
Notwithstanding past trade reforms, trade in Africa and particularly intra-Africa trade, remain dismal. Africa has even created economic communities, fitted with monetary, fiscal, and socio-political anchors, by way of various Regional Economic Communities (RECs) – now reflected by the African Continental Free Trade Area (AfCFTA). Whilst these have yielded marginal benefits, the persistence of low intra-Africa trade calls into question their suitability. Focused on the realities of institutions targeted by these reforms and Africa's context – i.e., weak linkages between institutions, high informality, and low social capital – we posit that reforms have not elicited the hoped-for high intra-Africa trade because of their near total reliance on the neo-liberal approach, which neglects Africa's context. Drawing on Africa's sociology and new institutional economics, we use a conceptual institutional analysis to evolve a political economy based framework that suggests potential solutions: Linking the formal sector that currently underpins economic/trade policies to the informal institutions that are reflective of Africa's norms, values, cultures and expectations (the informal sector), and scaling up production; via the cooperatives production model, strategic procurement mandates, and effectuation of continental transportation infrastructure network, are our recommended pathways to reversing the current dismal intra-continental trade.
Keywords: Africa; Africa's sociology; Growth and trade policies; Institutional economics; Intra-Africa trade

La réparation des conséquences des pratiques anticoncurrentielles en matière internationale - Adai, Yao B. Vincent de Paul (Université de Perpignan Via Domitia, 2024)
La mondialisation des échanges économiques a accentué les défis liés à la réparation des pratiques anticoncurrentielles, telles que les abus de position dominante et les ententes illicites. À l’échelle internationale, la diversité des systèmes juridiques et la multiplicité des juridictions rendent la réparation des préjudices complexe et incertaine. Cette thèse analyse en profondeur ces enjeux et explore des solutions pour améliorer les mécanismes de réparation en matière internationale. En mettant l’accent sur le private enforcement, la coopération internationale, ainsi que les innovations législatives et règlementaires, cette recherche propose des pistes pour une application plus efficace des recours privés à l’échelle mondiale. The globalization of economic exchanges has heightened the challenges related to the redress of anticompetitive practices, such as abuses of dominant position and illicit agreements. At the international level, the diversity of legal systems and the multiplicity of jurisdictions make damage compensation complex and uncertain. This thesis offers an in-depth analysis of these issues and explores solutions to improve redress mechanisms in the international arena. By focusing on private enforcement, international cooperation, and legislative and regulatory innovations, this research proposes pathways for a more effective implementation of private remedies on a global scale.
Issue: 2024PERP0050
Keywords: Action en reparation; Anti-Competitive practices; Competition law; Concurrence (droit); Contentieux de la concurrence; Droit de la concurrence; Globalization; Mondialisation; Pratiques anticoncurrentielles; Private enforcement; Restrictions à la concurrence; Réparation (droit international)

Les entreprises multinationales et les normes internationales de responsabilité sociale des entreprises - Aerts, Lisa (Université Paris 1, 2024)
Qu’elles soient considérées comme des alliées ou des concurrentes des États, employeurs des citoyens ou sources d’incidences négatives sur leur environnement, le rôle des entreprises multinationales dans l’ordre juridique international est indéniable. La sphère internationale s’est, bien que difficilement, progressivement munie de normes enjoignant aux entreprises multinationales de respecter un certain nombre de droits, parmi lesquels les Principes directeurs de l’OCDE, les Principes directeurs de l’ONU, le Pacte mondial, la Déclaration tripartite de l’OIT, et l’ISO 26 000. Cependant, le statut et la nature de ces entités transnationales, couplés à une économie libérale encline à ne pas freiner l’activité économique, ne permettent pas d’imposer ces standards et relèvent de prime abord de la soft law. Il a donc fallu faire appel au sujet de ces normes pour qu’elles soient diffusées tout au long de leurs chaînes de production. Ainsi, par stratégie, par philosophie gestionnaire ou, comme le clament certaines, par humanisme, les entreprises multinationales se sont graduellement dotées de codes de conduite d’entreprises ou à l’intention de leurs fournisseurs, et ont négocié des accords-cadres mondiaux s’appuyant sur les normes internationales. Cette étude porte sur la réalité de l’influence du droit international sur le contenu de ces instruments privés. Ces derniers, bien que volontairement élaborés, peuvent être des pistes et des atouts pour une responsabilité sociale des entreprises plus pertinente, cohérente et effective. S’appuyant sur un corpus de 138 codes de conduite et accords-cadres, ainsi que l’ensemble des Accords du Rana Plaza, cette recherche tend à identifier les textes internationaux dont se saisissent les entreprises et ceux qu’elles évitent, les droits et devoirs qu’elles s’engagent à respecter et ceux qu’elles semblent vouloir ignorer, ainsi que les conséquences de ces arbitrages. Les normes internationales encouragent également les entreprises à mettre en place des processus dans l’élaboration, l’application et la vérification de leurs engagements tels que la due diligence, ou la transparence ainsi que la prise en compte des parties prenantes. Là encore, les entités économiques opèrent de différentes manières plus ou moins proches des attendus internationaux. L’analyse de ces instruments privés de RSE, le rôle des multiples acteurs internationaux dans leur déploiement — dont l’État —, et leur respect ou non du droit international, soulignent des pistes de contrainte et de possible durcissement du droit international pour aboutir à une responsabilité sociale des entreprises multinationales réellement transnationale et aux résultats plus probants. Whether they are considered allies or competitors of States, employers of citizens or sources of negative environmental impact, the role of multinational companies in the international legal order is undeniable. The international sphere has, with some difficulties, gradually equipped itself with standards requiring multinational companies to respect a number of rights, including the OECD Guidelines, the UN Guiding Principles, the Global Compact, the ILO Tripartite Declaration and ISO 26000. However, the status and nature of these transnational entities, coupled with a liberal economy inclined not to curb economic activity, do not allow these standards to be imposed, and are at first sight a matter of soft law. It was therefore necessary to appeal to the subject of these standards for them to be applied throughout their supply chains. Thus, as a matter of strategy, management philosophy or, as some claim, humanism, multinational companies have gradually adopted corporate codes of conduct or codes of conduct for their suppliers, and negotiated global framework agreements based on international standards. This study examines the influence of international law on the content of these private instruments. The latter, though deliberately elaborate, can be a path to more relevant, coherent and effective corporate social responsibility. Based on a corpus of 138 codes of conduct and framework agreements, as well as the Rana Plaza Accords, this research aims to identify the international texts that companies take up and those they avoid, the rights and duties they undertake to respect and those they appear to ignore, and the consequences of those choices. International standards also encourage companies to set up processes for drawing up, applying and verifying their commitments, such as due diligence process, transparency and stakeholder involvement. Here again, economic entities operate in a variety of ways, more or less in line with international expectations. An analysis of these private instruments, the role of the many international players involved in their deployment - including the States - and whether or not they comply with international law, highlights possible avenues of constraint and possible tightening of international law to achieve more effective transnational corporate social responsibility.
Issue: 2024PA01D060
Keywords: Accords-cadres mondiaux; Codes de conduite; Codes of conduct; Entreprises multinationales; Global Compact; Global framework agreemen; ILO; Multinational companies; OCDE; OECD; OIT; ONU; Pacte mondial; Rana Plaza; UN

Le choix de l’épuisement international des droits de propriété industrielle en droit de l’Organisation Africaine de la Propriété Intellectuelle (OAPI) - Alla Koffi, Etienne (Revue africaine de droit des affaires, 2024)
Les réflexions sur la propriété intellectuelle au service de la créativité, de l’innovation et du développement durable des États et des entreprises sont d’une actualité prégnante. À l’opposé du système de PI empreint d’exclusivité, d’autres tentatives vont dans le sens de la mise en place de marchés communs par la propriété intellectuelle, et donc d’un système d’ouverture. Prenant l’exemple de l’épuisement de droits, pour lequel l’Organisation Africaine de la Propriété Intellectuelle (OAPI) a fait le choix de l’épuisement international avec la révision de l’Accord de Bangui, Acte de Bamako de 2015, au détriment de l’épuisement régional qui existait jusque-là, cette analyse s’interroge sur la pertinence de ce choix. Elle démontre alors que ce choix se justifie au moins doublement, d’une part, par sa conformité juridique avec les instruments juridiques internationaux supérieurs et, d’autre part, parce que s’inscrivant dans une logique d’ouverture (ou de construction du marché commun de la PI) dans l’espace de l’OAPI et dans le cadre de la ZLECAf. Choix justifié certes, mais il reste discuté – pour ne pas dire discutable. La discutabilité de ce choix est mise en relief à travers notamment deux interrogations : pour ou contre l’épuisement international ? Pour une approche globale ou différenciée du principe d’épuisement du droit ?
Keywords: Intellectual property; Propriedade intelectual; Propriété industrielle; Propriété intellectuelle

Les entreprises de tendance - Delyfer, Anne-Marie (Université Paris 10, 2024)
Contrairement aux entreprises dites "classiques", qui ont pour objectif principal la production de biens ou de services dans un cadre lucratif, l'entreprise de tendance est une catégorie juridique et sociale à part. Sa spécificité ne réside pas dans la recherche de profits, mais dans la promotion et la défense de convictions, qu'elles soient religieuses, politiques, ou philosophiques. Cette dimension convictionnelle distingue ces entreprises des autres et impose de définir avec précision leurs contours, car toutes ne peuvent pas revendiquer ce statut. L'entreprise de tendance n’est donc pas un modèle d'entreprise ordinaire. Au cœur de son fonctionnement se trouvent des valeurs et des croyances qui façonnent non seulement son activité mais aussi son identité. Ce type d’entreprise devient un instrument au service d'une idéologie ou d'une foi, portant un message à la société et jouant un rôle crucial dans le maintien du pluralisme idéologique dans une démocratie. Cependant, la reconnaissance juridique des entreprises de tendance varie largement d’un pays à l’autre, en fonction de l’histoire, des sensibilités sociétales et du cadre législatif.La manière dont les États reconnaissent et encadrent les entreprises de tendance reflète leur conception de la place des convictions religieuses ou politiques dans l'espace public. En fonction de cette reconnaissance sociale et légale, ces entreprises peuvent bénéficier de régimes juridiques particuliers, tant dans leurs relations avec les salariés qu’en matière de financement. Cette reconnaissance variable, ainsi que les privilèges qui peuvent en découler, doivent être analysés, notamment à l'aune des décisions des Cours européennes.
Issue: 2024PA100133
Keywords: Convictions; Employees; Employer; Employeur; Employé; Entreprise de tendance; Ideological; Ideological organization; Idéologie; Idéologique; Relationships; Salariés

L'influence du droit français sur le droit des contrats des États-Unis. - Derzhavets, Diana (Université Paris Cité, 2024)
Cette étude est consacrée à l'influence du droit français sur le droit des contrats des États-Unis à partir du XIXe siècle et jusqu'à nos jours. La présente recherche vise à montrer que, bien que les États-Unis soient les héritiers de la tradition juridique de la common law anglaise, les droits continentaux, notamment, le droit français, ont apporté une grande contribution dans le développement du droit moderne des contrats aux États-Unis. Le sujet est abordé dans le temps passé et présent. D'une part, nous examinons le rôle du droit français des contrats au XIXe siècle et surtout à partir de 1860, autrement dit, pendant la période marquée par la codification du droit civil dans les différents États américains. D'autre part, nous nous attarderons sur la situation récente et contemporaine afin de confirmer la persistance des emprunts américains au droit français et leur actualité, mais aussi afin d'étudier l'influence des approches et des méthodes du droit français dans la codification américaine au niveau fédéral. Notre étude s'inscrit dans le processus d'analyse de l'ensemble du droit continental qui a rayonné significativement sur le sol américain dans le passé, mais peu observable aujourd'hui. Parmi les autres droits continentaux, le droit français connu le plus grand succès à cause de sa fidélité au droit romain et à son expérience réussie de codification. La réalisation de notre projet nous permettra d'identifier les emprunts faits au droit français, de suivre leur évolution au sein du droit américain des contrats, et de retracer les liens juridiques entre les États-Unis et la France. This study is devoted to the influence of French law on the United States contract law from the 19th century to the present day. This research aims to show that, although the United States is the heir to the legal tradition of English common law, the continental law (in particular, French law) made a noticeable contribution to the development of the modern contract law of this country.The subject is approached in the past and present times. On one hand, we examine the role of French contract law in the 19th century, and especially from 1860, in other words, during the period marked by the codification of civil law in various American states. On the other hand, we focus on the recent and contemporary situation not only to confirm the persistence of American borrowings from French law and their relevance, but also to study the influence of these approaches and methods of French law on American codification at the federal level. Our study is part of the analysis of the whole continental law which had a significative impact on American soil in the past, but which is hardly observable today. Among the other continental laws, French law had the greatest success because of its fidelity to Roman law and its successful codification experience. The realization of our project will allow us to identify the law influences derived from French law, to follow their evolution within American contract law, and to trace the legal connections between the United States and France.
Issue: 2024UNIP7252
Keywords: Code Napoléon; Codification; Common Law; Continental Law; Contract Law; Droit continental; Droit des contrats; Droit français; French Law; Influence; Napoleon Code; United States; États-Unis

Diaspora as a Generator of Foreign Direct Investment - Dizdarević, Emina (IUS LAW Journal, 2024)
Focusing on Bosnia and Herzegovina, this study examines how diasporas contribute to the creation of foreign direct investment (FDI) in developing countries. It defines FDI as the acquirement over assets in a foreign nation and highlights how diaspora populations support investment flows. It also examines diaspora investment strategies, such as diaspora portfolio investment (DPI) and diaspora direct investment (DDI), and offers a historical overview of diaspora FDI patterns and how Bosnia and Herzegovina's policies are changing to engage its diaspora more.One case study illustrates the impact of diaspora-led FDI by highlighting the success of Senad Šantić, a Bosnian entrepreneur who returned to his home country to start a tech company. While these investments support development and economic growth, there are still issues, like the possibility of putting one's own interests ahead of the interests of the economy as a whole. Particularly in Bosnia and Herzegovina, where diaspora participation has historically been low, the implementation of effective policies and procedures is crucial, especially from a regulation perspective.The study also looks at the future of FDI, emphasizing the part that digital technology and new investment patterns will play. Opportunities for developing nations can be found in digital FDI, especially in industries like fintech and e-commerce, yet obstacles still exist in luring these investments. According to all the findings, developing nations can improve their chances for economic success by creating an atmosphere that encourages diaspora investment which will shift those nations into the global investment scene. Ultimately, FDI regulations and government programs are needed in order to fully utilize diaspora-led FDI for sustained growth.
Keywords: Bosnia and Herzegovina; Diaspora Engagement; Diaspora Investment; Economic Development; FDI; Foreign direct investment

Essai sur les critères d'arbitrabilité des litiges en Droit OHADA et en Droit Français - Dizo, Kevin (Nantes Université, 2024)
Le sujet de thèse explore comment définir les critères d’arbitrabilité des litiges acceptés par la justice arbitrale et étatique en France et dans l’espace OHADA. Les recherches ont montré que chaque système juridique a déjà des critères établis par les législateurs et la doctrine. L’arbitrage, étant à la fois juridictionnel et conventionnel, implique une interaction entre les justices arbitrales et étatiques, nécessitant des critères d’arbitrabilité efficaces. Ces critères doivent distinguer clairement les litiges arbitrables des inarbitrables et repartir soigneusement les compétences entre les juridictions. Alors, notre thèse questionne l’efficacité de ces critères et propose des améliorations pour remédier à leurs limites. The thesis topic explores how to define the arbitrability criteria of disputes accepted by arbitration and state justice in France and in the OHADA space. Research has shown that every legal system already has criteria set by legislators and doctrine. Arbitration, being both jurisdictional and conventional, involves an interaction between the arbitral and state courts, requiring effective arbitrability criteria. These criteria must clearly distinguish between arbitrable and non-arbitrable disputes and carefully allocate jurisdiction between the courts. So, our thesis questions the effectiveness of these criteria and proposes improvements to remedy their limitations.
Issue: 2024NANU3022
Keywords: Arbitrability; Arbitrabilité; Arbitrage (droit); Arbitration; Criteria; Critères; Droit prospectif; Effectiveness; Efficacité; Pays de l'OHADA; Prospective law

Le remboursement des apports en société - Elzahar, Nada Morsy (Université Paris 1, 2024)
Le remboursement des apports en société est l’une des notions utilisées fréquemment juridiquement, mais qui n’est pas définie ni par la loi ni par la jurisprudence ; il n’existe pas un régime juridique, indépendant et délimité, qui l’encadre. De plus, un nombre limité d’auteurs ont fourni des définitions pour le remboursement des apports qui ne sont pas même unifiées. Ils ont aussi fait référence à la restitution des apports souvent dans le même contexte, sans établir une distinction entre les deux termes « remboursement » et « restitution ». Avec l’absence d’une définition précise de remboursement des apports, les questions se posent : si d’après le régime juridique applicable dans le cadre des sociétés, il existe une obligation de restitution des apports qui va se varier selon le type de l’apport en cause ; ou le remboursement de l’apport constitue le paiement d’une obligation, autre que celle d’une restitution. Notamment, à la lumière de la relation entre l’apport et le capital social en vertu de laquelle les titres sociaux sont eux qui représentent les différents droits de l’associé et le montant du capital social est celui qui représente la dette de la société et l’ensemble des créances des associés. L’étude fournit ainsi une identification des éléments caractéristiques de remboursement des apports en société. Elle fournit également une identification de ses éléments perturbateurs, en abordant la question d’éventuelle manifestation de remboursement des apports au cours de la vie sociale, et en analysant le statut original de l’apporteur en industrie dont l’apport ne fait pas juridiquement l’objet de remboursement. The reimbursement of the contributions to a company is one of the notions frequently used in legal contexts, but it has not been defined either by law or by jurisprudence. There is no independent and defined legal regime governing it. Moreover, only a limited number of authors have provided definitions of the reimbursement of contributions that are not even unified. They have referred to the restitution of contributions, always in the same context, without making the distinction between the two terms "reimbursement" and "restitution". With the absence of a precise definition of the reimbursement of contributions, questions arise: according to the applicable legal regime for companies, does an obligation of restitution of contributions, varying according to the type of contribution, exist, or is the reimbursement of contributions the payment of an obligation other than restitution? These questions are especially relevant in light of the relationship between contributions and capital, under which shares represent the different rights of the partners and the amount of the capital represents the debt of the company. Thus, the study provides an identification of the characteristic elements of the reimbursement of contributions to a company. It also identifies its disruptive elements by addressing the eventual manifestation of the reimbursement of the contributions during the life of the company, and by analyzing the distinct status of a partner who has made a contribution in industry, which is not legally subject to reimbursement.
Issue: 2024PA01D033
Keywords: Apport; Capital; Capital social; Contribution; Dissolution de la société; Dissolution of the company; Droit des sociétés commerciales; Monetary obligation; Obligation de somme d'argent; Paiement; Payment; Rachat des titres par la société; Repurchase of shares by the compan; Restitution; Shares; Titres sociaux

The Blockchain Data Gatekeepers Limited Liability for Violations of the GDPR - Jusić, Asim (IUS LAW Journal, 2024)
Data gatekeepers (data controllers and processors) that use blockchain for data transfer effectively enjoy limited liability for violations of the GDPR. This is due to the fact that applying the GDPR’s data gatekeeper system of liability to a decentralized technology such as blockchain is difficult for three reasons. Firstly, identifying data gatekeepers on the blockchain can only be done by either assigning data gatekeeper roles to actors on the blockchain, or structuring the blockchain as private or permissioned one, so as to fit with GDPR requirements. Neither of these approaches provides a universally applicable and satisfactory method for privacy protection. Secondly, because of their knowledge and investment in infrastructure, large data gatekeepers such as IBM, Amazon and Microsoft have an informational advantage over data protection authorities (DPAs) and an additional protective layer against liability, as their blockchain infrastructure is used by other businesses and corporations that are primarily liable for data processing. Finally, administrative fines and reputational damages for non-compliance with the GDPR are insufficient deterrents for large data gatekeepers, whereas damages awarded to individual data subjects for data gatekeepers’ violations of GDPR are extremely low and too costly to obtain.
Keywords: Blockchain; Compliance; Data gatekeepers; GDPR; Liability

La régulation du couple par le droit pénal congolais - Kasereka Muyisa, Jean Chrysostome; Vuanazobe Mukakala, Magdala (International Multilingual Journal of Science and Technology, 2024)

La protection du cessionnaire de droits sociaux - Koumba, Euloge Mesmin (Revue africaine de droit des affaires, 2024)
La loi ne permet toujours pas de mieux protéger le cessionnaire de droits sociaux. Elle lui offre une protection qui ne tient pas souvent compte des sacrifices financiers consentis par ce dernier. Face à cette insécurité juridique, la pratique a mis en place certaines clauses contractuelles ayant une fonction protectrice. Celles-ci varient selon qu’il s’agit d’une clause contractuelle ou d’une clause d’assurance contre la défaillance du cédant. Pour protéger son investissement, le cessionnaire devrait se mettre à l’abri du comportement malveillant du cédant ou du vendeur en insérant obligatoirement dans le contrat certaines clauses contractuelles sur mesure, à savoir : la clause de garanties de passif et la clause d’assurance.

La liberté d'établissement intracommunautaire des sociétés commerciales dans les espaces de la CEDEAO et de l'Union Européenne - Kpatindé, Métogbé (Université de Perpignan Via Domitia, 2024)
Les sociétés commerciales dans un espace communautaire sont amenées à développer ou délocaliser leurs activités dans d'autres pays membres que celui dans lequel où elles sont originairement installées. La liberté d'établissement régit le droit pour une société de s'installer dans un autre État membre et d'y exercer une activité de façon durable. C'est notamment le cas lors des délocalisations, des opérations de fusions-acquisitions, de création de filiales, ou de représentation à l'étranger. C'est le cas aussi dans le transfert de siège social. Chaque société commerciale agit selon les règles juridiques de l'État où elle est établie. Dès lors qu'elle étend, déplace ses activités ou effectue des opérations dans plusieurs États, elle engendre automatiquement des éléments d'extranéité et se trouve confrontée à des questions spécifiques telles que celles de sa reconnaissance dans un État étranger, de la loi qui lui est applicable ou de sa nationalité. Cette mobilité entraîne aussi le changement de son environnement juridique. Désormais c'est dans un autre droit des sociétés qu'elle se meut. Toutes les matières du droit des sociétés se trouvent affectées : les droits fiscaux, sociaux, environnementaux, le droit du travail, le droit comptable, etc. Dans leurs textes fondateurs, les deux espaces communautaires que sont la Communauté Économique des États de l'Afrique de l'Ouest (CEDEAO) et l'Union Européenne (EU) consacrent ce principe de la liberté d'établissement au profit des sociétés. Bien que le but recherché par les législateurs africains et européens soit l'intégration économique, ce principe soulève néanmoins certaines questions et difficultés relatives à la mise en œuvre des normes communautaires. Contrairement aux pays membres de la CEDEAO qui ont pour socle technique d'uniformisation de leur droit interne l'OHADA (Organisation pour l'Harmonisation en Afrique du Droit des affaires) les pays de l'Union Européenne, eux, ne disposent pas de cadre juridique intégré, ce qui multiplie les difficultés pour la mobilité des sociétés au sein de l'espace communautaire européen. Commercial companies in a community space are often required to develop or relocate their activities to other Member States than the one in which they are originally established. Freedom of establishment is the right for a company to establish itself in another Member State and to carry on business there in a sustainable manner. This is particularly the case for relocations, mergers and acquisitions or the setting up of subsidiaries. It is also the case when the head office is transferred. Commercial companies operate according to the legal rules of the State where they have been settled. Every company considering expansion into another Member State is likely to generate foreign elements and to face specific issues such as its recognition in the foreign State, the law applicable to it or its nationality. The entire legal environment might change and all branches of corporate law can be affected: tax, social, environmental, labour, accounting and other laws. In their founding texts, the two Community spaces, the Economic Community of West African States (ECOWAS) and the European Union (EU), enshrine this principle of freedom of establishment within their Member States. Even though the goal pursued by African and European legislators is economic integration, this principle nevertheless raises a number of issues and serious questions relating to the implementation of Community standards. Unlike the ECOWAS member States, which have OHADA (Organization for the harmonization of business Law in Africa) as an existing basis for the unification of their domestic business law, members States of the European Union do not have a unified legal framework, which increases the issues a company must face in its mobility processes within the European Community space
Issue: 2024PERP0051
Keywords: Business mobility; CEDEAO; Commercial companies; Corporate law; Droit des sociétés; ECOWAS; European union; Freedom of establishment; Liberté d'établissement; Mobilité des sociétés; OHADA; Pays de l'OHADA; Pays de l'Union européenne; Sociétés commerciales; Union europeenne

Quelques interrogations sur le droit OHADA révisé du recouvrement de créance et des voies d’exécution de 2023 - Moneboulou Minkada, Hervé Magloire (Revue africaine de droit des affaires, 2024)
L’AUPSRVE a été adopté le 1ᵉʳ juillet 1998 et révisé le 17 octobre 2023. Cette révision a permis à la présente analyse d’effectuer quelques interrogations sous forme de morceaux choisis. La démarche a consisté à visiter le droit objectif et les droits subjectifs pour poser des questions et apporter des réponses. En évitant la prétention à l’exhaustivité, il importe de préciser le domaine de ces interrogations. En prenant en compte le droit objectif, le droit matériel et jurisprudentiel sont visés. Et concernant les droits subjectifs, la personne morale de droit public et l’entreprise publique sont les sujets de droit intéressés.

Le prélèvement de l’impôt à l’épreuve de la digitalisation de l’économie - Moudjongue, Régine Laure (Revue des Réflexions Constitutionnelles : Revue mensuelle de publication en droit constitutionnelle, 2024)
L’on convient au fait que le numérique produit des effets indésirés. Ce sentiment s’affirme au vu des difficultés auxquelles fait face le fisc, s’agissant de sa mission originelle de collecte de l’impôt. Ceci est la résultante d’un cadre juridique n’ayant pas tardé à devenir un espoir très vite déçu, à la faveur des transmutations subies, s’agissant de la détermination de l’établissement stable en fiscalité internationale. La conséquence en est que, toute tentative de saisie aux fins d’imposition par un Etat, se bute contre la difficulté de la localisation. De cette manière, ces multinationales et entreprises du numérique pourraient même à tort bénéficier d’une « double non-imposition ». De cette manière, la précarisation du prélèvement par le digital, est confortée par la pérennisation des risques subséquents à la digitalisation.
Keywords: Economie (digitalisation); Etat; Impôt; Territorialité

La constitution des sociétés de capitaux à l’aune de la dématérialisation des titres - N'Tchatat Tounya, Fabrice Léonel (Revue africaine de droit des affaires, 2024)
Avant la réforme de l’acte uniforme relatif au droit des sociétés commerciales et du groupement d’intérêt économique (AUDSCGIE) en 2014, les sociétés par actions simplifiées (SAS) n’existaient pas dans l’espace OHADA et la naissance des sociétés anonymes (SA) nécessitait la rédaction d’un contrat de société et l’émission de titres physiques. La réforme a eu pour effet, entre plusieurs innovations, d’introduire, d’une part, les SAS pour simplifier la création d’entreprises, notamment PME, et, d’autre part, la dématérialisation des valeurs mobilières par le truchement de l’article 744-1. Ainsi, la démarche de constitution de ces sociétés s’est vue profondément modifiée. Désormais, les statuts doivent être ajustés pour supprimer la numérotation des titres et spécifier les modalités de gestion des titres dématérialisés. De plus, la dématérialisation a entraîné des changements dans les modalités d’émission et de transmission des titres, remplaçant les émissions de titres physiques par des titres dématérialisés et la transmission physique par des virements de compte à compte. Face à ces évolutions normatives, les notaires éprouvent des difficultés à assimiler ces nouveaux processus, nécessitant ainsi une sensibilisation. En outre, le rôle des dépositaires centraux dans la gestion des titres dématérialisés des SA et SAS s’avère crucial dans ce nouveau contexte.

La Protection juridique des dossiers passagers - Nawaf Shathil, Shathil (Université Paris 1, 2024)
Les attentats du 11 septembre 2001 ont profondément bouleversé les sociétés occidentales. Le transport aérien international mais également plusieurs branches du droit, dont le droit pénal et le droit des libertés publiques, ont été affectés. Le droit américain a imposé aux compagnies aériennes la transmission des données personnelles des passagers aériens, appelées Passenger Name Record (PNR). Alors que les États-Unis exigent cette transmission pour des raisons de sécurité nationale, le droit européen privilégie la protection de la vie privée et des données personnelles. Bien que l'accord euro-américain et d'autres accords similaires, ainsi que la directive européenne sur les PNR, visent à encadrer les échanges de données, ils sont susceptibles de porter atteinte aux droits fondamentaux des passagers. Cet équilibre entre sécurité et droits individuels se heurte à une réalité juridique : une limitation des libertés au nom de la sécurité collective. Tandis que le Conseil et la Commission européenne prônent des mesures sécuritaires, le Parlement européen et la Cour de justice de l'Union européenne cherchent à préserver les libertés individuelles. De nouvelles menaces pèsent sur la protection juridique des dossiers passagers telles que la collecte massive de données et le profilage aux frontières. L'intervention croissante des acteurs privés, notamment dans les aéroports, affaiblit cette protection et la déterritorialisation des données accentue cette vulnérabilité. Les crises internationales, comme la pandémie du coronavirus, ont encore renforcé l'usage de ces données, compliquant leur encadrement juridique. The terrorist attacks of September 11, 2001, significantly disrupted Western societies. International transport law, along with areas of law such as criminal law and public freedoms, were profoundly affected. U.S. legislation imposed an obligation on airlines to transmit the personal data of air passengers, referred to as Passenger Name Record (PNR). While the U.S. requires this transmission for purposes of national security, European law prioritizes data protection. Despite the aim of the Euro-American agreement, other bilateral accords, and the European PNR Directive to regulate data exchanges, they pose a risk of infringing upon passengers' fundamental rights. This legal balance between security and individual rights reveals a tension: the restriction of civil liberties in the name of collective security. While the European Council and Commission endorse security-focused measures, the European Parliament and the Court of Justice of the European Union (CJEU) seek to uphold individual liberties. Emerging threats to the legal protection of passenger data include mass data collection and profiling at borders, which are at odds with privacy rights. The growing involvement of private actors, particularly in airports, further undermines this protection, while the de-territorialization of data exacerbates its vulnerability. Additionally, international crises such as the COVID-19 pandemic have led to an expanded use of passenger data, complicating its legal regulation and oversight.
Issue: 2024PA01D034
Keywords: Airport; Aéroport; Données des dossiers passagers; Droits fondamentaux; Etats-Unis; European Union; Individual rights; PNR; Protection; Protection de l'information (informatique); Sécurity; Sécurité collective; Terrorisme; Transport; Union européenne; United States

L’indisponibilité du corps humain à l’épreuve de la commercialité juridique - Nkoa, François Nestor Patrice (Afrilex : Revue d’étude et de recherche sur le droit et l’administration dans les pays d’Afrique, 2024)
La commercialité grandissante des éléments et produits du corps humain et, en plus, de tout ce qui se rattache à la personne est un germe d’inquiétudes légitimes. Tout peut-il se vendre ? Le don n’est pas toujours exempt de risques. La conception traditionnelle de l’extra-commercialité se révèle contraire à l’état du droit positif actuel. Elle mérite d’être rejetée dès lors que son application incite au surplus à des pratiques contraires à la morale. La catégorie des choses hors du commerce existe-t-elle encore dans notre droit positif ? On serait tenté de répondre par la négative en observant la réalité de la situation juridique actuelle des produits et éléments du corps humain.
Keywords: Commerce juridique; Corps humain; Indisponibilité; Non patrimonialité

L'autonomie de la clause compromissoire en droit de l'arbitrage Marocain et Québécois: entre consécration et limites - Rafai, Khawla (Université de Montréal, 2024)
Le principe de l’autonomie de la clause compromissoire est au cœur du mécanisme de l’arbitrage, tout en demeurant complexe et polyvalent. Cette étude met en lumière les différentes dimensions de ce principe, tout en identifiant ses limites face aux exigences fondamentales de justice et d’ordre public. L’autonomie de la clause compromissoire signifie d’abord que cette clause, bien qu’intégrée dans un contrat principal, existe et survit de manière indépendante. Concrètement, cela veut dire qu’une contestation ou une invalidité du contrat principal n’affecte pas automatiquement la clause compromissoire. Cette indépendance permet aux parties de préserver leur engagement à soumettre les litiges à un tribunal arbitral, offrant ainsi une sécurité juridique et une continuité au processus de résolution des conflits. L’arbitrage repose ici sur un engagement volontaire et anticipé, qui ne saurait être remis en cause par des circonstances affectant le contrat lui-même. Au-delà de cette indépendance, l’évolution du principe d’autonomie a permis d’introduire une autre dimension : la liberté de choix dans les règles qui régissent la clause compromissoire. Cela signifie que les parties ne sont pas nécessairement liées aux règles du contrat principal. Cette forme d’autonomie favorise la flexibilité, permettant aux parties de concevoir une procédure arbitrale adaptée à leurs besoins spécifiques. Cependant, cette liberté rencontre certaines limites, notamment en matière d’ordre public, qui agit comme un rempart pour protéger les valeurs fondamentales de justice et d’équité. Un autre aspect fondamental de ce principe est son interaction avec le concept de compétence-compétence, selon lequel le tribunal arbitral est habilité à statuer sur sa propre compétence. Cette relation étroite entre les deux principes peut créer une certaine confusion, car si l’autonomie de la clause concerne sa validité et son indépendance, la compétence-compétence relève plutôt du pouvoir décisionnel des arbitres. Toutefois, ces deux notions, bien que distinctes, contribuent ensemble à garantir l’efficacité de l’arbitrage en permettant de résoudre rapidement les questions liées à la compétence et à la validité de la clause. L’étude aborde également la transmissibilité de la clause compromissoire, qui pose un défi théorique à l’idée d’autonomie. En cas de cession ou de transfert du contrat principal, la clause compromissoire accompagne généralement le contrat, ce qui semble paradoxal par rapport à son indépendance. Cette apparente contradiction s’explique toutefois par la nécessité pratique d’assurer la continuité des mécanismes d’arbitrage, en particulier dans des situations complexes comme les contrats multipartites ou les groupes d’entreprises. Enfin, le principe d’autonomie, malgré sa robustesse et son importance dans l’arbitrage, demeure encadré. La protection des intérêts fondamentaux des parties les plus vulnérables et des principes essentiels de justice impose des limites nécessaires. L’ordre public joue ici un rôle clé en veillant à ce que la liberté contractuelle ne se traduise pas par une atteinte aux droits fondamentaux ou aux valeurs essentielles de la société. En conclusion, l’autonomie de la clause compromissoire est un instrument essentiel qui garantit la stabilité et l’efficacité de l’arbitrage. Elle repose sur une double dynamique : une indépendance par rapport au contrat principal et une flexibilité permettant aux parties d’organiser librement la procédure arbitrale. Toutefois, cette autonomie doit coexister avec des limites claires pour concilier la liberté contractuelle avec les exigences de justice, assurant ainsi un équilibre nécessaire entre efficacité et protection des principes fondamentaux. The principle of the autonomy of the arbitration clause is central to the arbitration mechanism, while remaining both complex and multifaceted. This study sheds light on the various dimensions of this principle and identifies its limits in the face of fundamental justice and public policy requirements. The autonomy of the arbitration clause primarily signifies that the clause, although incorporated into a principal contract, exists and survives independently. In practical terms, this means that a dispute regarding or the invalidity of the principal contract does not automatically affect the arbitration clause. This independence enables the parties to uphold their agreement to submit disputes to arbitration, thereby ensuring legal certainty and continuity in conflict resolution processes. Arbitration thus rests on a voluntary and preemptive commitment that cannot be undermined by circumstances affecting the main contract. In addition to this independence, the development of the principle of autonomy has introduced another significant aspect: the freedom of the parties to determine the rules governing the arbitration clause. This autonomy allows the parties to deviate from the rules of the principal contract, fostering flexibility and enabling the design of arbitration procedures that meet their specific needs. However, this freedom is not without limits, particularly where public policy intervenes as a safeguard to preserve fundamental principles of justice and fairness. A crucial component of this principle is its interaction with the kompetenz-kompetenz doctrine, which empowers the arbitral tribunal to rule on its own jurisdiction. This close relationship between the two concepts may cause confusion: the autonomy of the arbitration clause concerns its validity and independence, whereas kompetenz-kompetenz pertains to the decision-making authority of arbitrators. Despite their distinctions, both principles collectively enhance the effectiveness of arbitration by facilitating the prompt resolution of jurisdictional and validity-related challenges. This study also explores the issue of the arbitration clause’s transmissibility, which presents a theoretical challenge to the notion of autonomy. In cases where the principal contract is assigned or transferred, the arbitration clause typically follows the contract, creating a seemingly paradoxical situation regarding its independence. This apparent contradiction can, however, be justified by the practical need to maintain the continuity of arbitration mechanisms, particularly in complex contexts such as multiparty contracts or corporate groups. Ultimately, despite its essential role and resilience, the autonomy of the arbitration clause is subject to necessary constraints. The protection of vulnerable parties and the preservation of fundamental principles of justice impose clear limitations. Public policy serves as a crucial safeguard to ensure that contractual freedom does not infringe upon fundamental rights or societal values. In conclusion, the autonomy of the arbitration clause is a cornerstone of arbitration’s stability and effectiveness. It is characterized by independence from the principal contract and the flexibility afforded to the parties in shaping their arbitration proceedings. However, this autonomy must be balanced against clear limits to harmonize contractual freedom with justice requirements, ensuring an essential equilibrium between efficiency and the protection of core principles.
Keywords: Arbitrability; Arbitrabilité; Arbitration; Arbitration clause; Autonomie; Autonomy; Clause compromissoire; Extension; Ordre public; Public policy; Transmissibility; Transmission

Business Environment and its Impact on Attracting Foreign Direct Investment - Tanrıverdi, Elif Tanrıverdi (IUS LAW Journal, 2024)
This study provides an in-depth look at the complex relationship between business environments and foreign direct investment. The study examines this critical issue by focusing on emerging economies, such as Kosovo. In this research, analytical and empirical research methods have used to highlight the importance of FDI in promoting economic growth. FDI not only increases production capacity but also supports economic growth by increasing purchasing power and creating employment opportunities, especially in countries in transition. This analysis distinguishes between endogenous and exogenous variables to classify the various elements of the business environment. It is important to emphasize how a supportive business environment plays a vital role in attracting investment. The main factors affecting FDI include infrastructure quality, political stability, workforce skills, market potential and tax incentives. These initiatives are critical to creating a more favorable investment climate.As a result of the variables the study concludes by emphasizing the need for continuous reforms to strengthen the business environment. Such strategic efforts are crucial to optimize FDI flows and advance sustainable economic development. By strengthening regulatory frameworks and improving infrastructure, developing countries can be in better position itself to attract foreign investors. Furthermore, creating a strong business environment can also support the development of local entrepreneurs, increasing economic diversification. As a result, it not only facilitates the flow of capital, but also contributes to the long-term stability and growth of the national economy. Therefore, policymakers and governments need to prioritize these initiatives and develop comprehensive and sustainable strategies to improve the business environment.
Keywords: Business Environment; Economic growth; Foreign direct investment; Investment Incentives; Investments; Political Stability

L’organisation du capital dans la société anonyme patrimoniale - Toe, Souleymane (Revue africaine de droit des affaires, 2024)

The role and mandate of the motor industry ombudsman of South Africa : addressing prospects and challenges to enhance consumer protection - Tshabalala, Thapelo; Magau, Phemelo (PER / PELJ, 2024)
The Motor Industry Ombudsman of South Africa (MIOSA) is an industry ombud recognised under the Consumer Protection Act 68 of 2008 (CPA). The MIOSA regulates the interaction and provides for alternative dispute resolution in the automotive and related industries in South Africa. Moreover, the MIOSA is an impartial organisation that focusses on the resolution of disputes where a deadlock has been reached between the automotive and related industries and their customers, as well as relationships among participants in the automotive and related industries to the benefit of the parties. The role of the MIOSA is to make recommendations in cases referred to it where parties cannot reach common ground and are unable to arrive at mutually acceptable agreements following a dispute. This analysis explores and proffers possible solutions to address the challenges that impede the MIOSA from discharging its role and mandate under the CPA effectively in resolving consumer disputes in the South African automotive industry.
Keywords: Automotive industry; Consumer protection; Dispute resolution; MIOSA; Ombuds

La place de l’aéronef et du navire en droit des biens et en droit des sûretés - Wagué, Hamadi Gatta; Mfini, Mon-espoir (Revue africaine de droit des affaires, 2024)
L’aéronef et le navire sont deux biens hybrides ; ils sont à la fois meubles et immeubles. Le droit des biens a tenu compte de la nature spéciale de ces biens. En conséquence, ces biens d’une importante valeur ne se confondent pas avec tous les autres biens, dont la nature juridique est aisée à déterminer. Appartenant au sous-continent du droit maritime et aérien, le navire et l’aéronef ont une particularité par rapport aux biens classiques. Aussi, lorsqu’il faut les envisager comme éléments de garanties du crédit, les questions sont nombreuses. En effet, si le navire et l’aéronef peuvent être mobilisés pour garantir une dette, ceux-ci ne peuvent obéir au régime de toutes les sûretés réelles. C’est dire que certaines sûretés réelles ne leur sont pas applicables. Cette assertion est vraie aussi bien pour le droit français que pour le droit de l’OHADA. Toutes ces considérations sont mises en lumière dans cette étude. L’analyse de la nature juridique de l’aéronef et du navire précède l’étude de ces biens au regard du droit des sûretés.

Legal Certainty in the Resolution Process of Business Disputes due to Default on Payment with Bank Guarantee through Arbitration - Wijaya, Didit Wijayanto (International Journal of Science and Research, 2024)
Corporations have been established and recognized in Indonesia as entities engaged in business activities since 1602. In these business activities, disputes can occur regarding the non-disbursement of Bank Guarantees through the Indonesian National Arbitration Board (BANI). Therefore, this research uses the Normative Juridical method through a literature review. The research questions considered are (1) What is the guarantee of legal certainty in the process of resolving business disputes regarding Bank Guarantee payments through the Arbitration Board? (20) What can the Supreme Court Decision provide legal certainty for resolving business disputes through arbitration in Indonesia? The process of resolving business disputes in default on Bank Guarantee payments through the Arbitration Court has fulfilled the legal certainty principle. The results showed that the rules were available through different Arbitration and Alternative Dispute Resolution Laws, as well as other laws applied consistently in the BANI Surabaya Decision Number 59/ARB/BANI-SBY/XI/2021. The Supreme Court Decision Number 918 B/Pdt.Sus-Arbt/2023 tried the appeal case and rejected the application for annulment of the arbitration decision from the Applicant. In addition, legal certainty is created for corporate legal efforts to take the arbitration route.
Keywords: Arbitrage; Arbitragem; Arbitration; Business Disputes; Default; Legal Certainty

Les contrats de fourniture de main-d’œuvre - Langaney, Cécile (Université Paris 10, 2024)
La fourniture de main-d’œuvre est une forme de mise au travail qui procède d’un éclatement. Elle conduit à ce que les différentes fonctions appelées à jouer un rôle dans le processus d’exploitation d’un travailleur soient distribuées entre plusieurs personnes. Plus exactement, celui qui bénéficie du travail réalisé, voire qui exerce le pouvoir de direction, est ici un autre que celui qui protège le travailleur contre le risque économique.Les opérations de ce type sont servies par un schéma contractuel en deux temps, dont l’un demeure encore largement méconnu. Les contrats que concluent le bénéficiaire du travail et le protecteur du travailleur, ou « contrats de fourniture de main-d’œuvre » n’ont jamais fait l’objet d’une étude dédiée. À leur sujet, les zones d’ombre sont encore nombreuses, et l’incertain règne.La présente thèse a l’ambition de combler cette lacune.L’étude des contrats de fourniture de main-d’œuvre implique d’abord une analyse de ces contrats per se. En se fondant sur la considération du but économique poursuivi par leurs parties, l’on en vient à pouvoir identifier les véhicules contractuels dans lesquels se coulent les accords portant sur la fourniture de main-d’œuvre. Les contrats de fourniture de main-d’œuvre s’ancrent ainsi dans un contenant. Un contenant qui, lui-même, permet ensuite l’identification de l’obligation principale autour de laquelle s’organisent ces conventions. Les contrats de fourniture de main-d’œuvre révèlent ainsi leur contenu.Après avoir procédé à l’analyse des contrats de fourniture de main-d’œuvre per se, l’étude propose leur analyse in situ, c’est-à-dire en les rapportant à la place qu’ils occupent au sein des opérations du même nom. Les contrats de fourniture de main-d’œuvre n’existent en effet qu’au sein d’opérations de fourniture de main-d’œuvre, environnement dans lequel ils ont à s’articuler avec un contrat de travail. Il s’agit alors de faire le jour sur la nature de cette articulation, en empruntant tantôt les outils que propose le droit des contrats, tantôt ceux qu’offre le régime général de l’obligation. Les contrats de fourniture se font alors, ici, les rouages d’ensembles sous-contractuels, et là, les composantes de stipulations pour autrui ou de cessions de l’émolument de la créance.
Keywords: Contracts; Contrats; Contrats de travail; Fourniture de main d'oeuvre; Hiring-Out of workers; Labor Supply; Mise à disposition de salarié; Prestation de services; Provision of Services; Prêt de main d'oeuvre; Services – Travail; Temporary work; Travail temporaire

Digital Vulnerability and the Formulation of Harmonised Rules for Algorithmic Contracts: A Two-Sided Interplay - Rodriguez, Teresa de Las Heras Ballell (The New Shapes of Digital Vulnerability in European Private Law, 2024)
This book provides an analysis on whether and how the current European legal framework adequately deals with personal conditions in which digital...

L'influence de la réforme du droit des contrats en droit du travail - Schoepfer, Vincent (Université de Strasbourg, 2024)
Au regard de l’ordonnance du 10 février 2016 et de la loi du 20 avril 2018, cette thèse cherche à déterminer 1’influence que produit la réforme du droit des contrats en droit du travail. Il s’avère qu’à notre sens, le degré de cette influence est supérieur à ce que les auteurs ont pu imaginer ; il serait non négligeable.L’existence de cette influence résulte d’abord de la lettre du nouvel article 1105 du Code civil, qui est vecteur de deux principes distincts : le comblement des lacunes travaillistes par le recours au droit commun et la cohabitation des règles spéciales et générales. De surcroît, il apparaît que certaines nouvelles règles civilistes, comme le contrat d’adhésion et son régime, le vice de violence pour abus de l'état de dépendance ou le devoir précontractuel d'information présentent un attrait indéniable pour certains acteurs des relations de travail, qui se traduit par la production d’une influence au degré variable en droit du travail.L’exacte étendue de cette influence ne peut toutefois résulter de la seule analyse de la réforme du droit des contrats ; la chambre sociale de la Cour de cassation possède en effet un double rôle difficilement conciliable. Tout d’abord, lorsque la mise en œuvre de la règle civiliste présente un risque pour les acteurs travaillistes, le juge peut en faire une application déformée — ce qui peut nuire à son influence voire décider de l’évincer du litige qui lui est soumis. Ensuite, il est d’autres hypothèses où, par le recours délibéré au nouveau droit des contrats, le juge social pourrait être l’acteur premier de l’amplification de 1’influence de la réforme en droit du travail.
Keywords: Benefits; Collective labour relations; Contract law; Contrats (réforme); Droit des contrats; Droit du travail (réforme); Individual labour relations; Influence; Labour law; Reform; Relations collectives de travail; Relations individuelles de travail; Réforme; Utilité

Le renforcement du caractère contradictoire de la procédure dans la phase préparatoire du procès pénal - Traoré, Namongo (Université de Toulon, 2024)
La procédure pénale est le résultat de la combinaison de deux systèmes de référence. Il s’agit des systèmes inquisitoire et accusatoire. Le législateur avait historiquement opté pour une phase de jugement accusatoire et la phase préparatoire du procès était plutôt inquisitoire. Toutefois avec d’une part le triomphe des droits de la défense et d’autre part, l’importance des éléments de preuve recueillis dans cette phase préparatoire et leurs influences sur l’issue du procès, le législateur s’est vu dans l’obligation de se lancer dans un grand processus d’aménagement de cette phase préparatoire pour y introduire des éléments caractéristiques du système accusatoire jugé plus favorable aux droits de la défense. Cet exercice auquel le législateur s’est livré est non seulement le fait de sa volonté mais et surtout le fait du droit européen. La rencontre entre ces deux mouvements a considérablement fait évoluer la phase préparatoire et y a donné un nouveau souffle aux droits de la défense en général et au principe du contradictoire en particulier. Cette transformation constante de la phase préparatoire qui constitue l’essentiel des règles étudiées dans le cadre de ce travail est apparue tellement poussée que l’on s’est interrogé tout au long de cet exercice s’il est encore possible de continuer cette mutation sans pour autant nuire à la qualité des procédures en termes d’efficacité. C’est donc en se proposant de répondre à cette interrogation que l’étude du renforcement du caractère contradictoire de la procéduredans la phase préparatoire du procès pénal a permis de mettre en évidence les manifestations de cette transformation tant dans la phase de l’enquête que dans celle de l’instruction préparatoire.
Keywords: Accusatoire; Accusatory; Avocat; Contestation; Contradictoire; Contradictory; Droit pénal; Droits de la défense; Défense (procédure pénale); Enquête; Information; Instruction; Lawyer; Police investigation; Preparatory instruction; Principe du contradictoire; Rights of the defense

Perspectives of post-commencement financiers regarding their voting rights on a business rescue plan - Van Niekerk, Larisa (University of Pretoria, 2024)
Post-commencement financiers provide a lifeline to companies under business rescue and these financiers have their best interest in the survival of these companies. Should it be that the business rescue plan is unsuccessful, the chances are that the post commencement financiers will be the largest creditors. In Wescoal Mining (Pty) Ltd v Mkhombo NO, a dispute arose regarding the appropriate adoption of a business rescue plan during the meeting. One critical legal issue was whether the Companies Act bestows voting rights exclusively to the company's creditors who existed at the initiation of business rescue, or if creditors accruing after the commencement may also partake in voting on the plan. Following an assessment by Judge Wilson, it was established that only creditors with claims predating the commencement were eligible to participate in the voting process. Subsequently, Judge Wilson believed that section 135 of the Companies Act places post-commencement financiers as creditors in a different class and provides for their protection and interests in a different way. Against this background, the dissertation evaluates the position of post-commencement creditors when it comes to voting on a business rescue plan.
Keywords: Business rescue; Company law; Creditors; Insolvency; Insolvency law; Life-line; Post-commencement creditors; Post-commencement finance

L’institution d’une "assurance vie environnementale" (AVE) comme levier de sauvetage des entreprises en difficulté - Tsevi, Koffi (Université Bourgogne Franche-Comté, 2024)
Le droit de l’environnement et le droit des entreprises en difficulté sont deux disciplines aux intérêts antagonistes. L’exploitation d’une ICPE impose à l’entreprise une obligation de remise en état des sites et sols pollués à la cessation d’activité. L’ouverture d’une procédure de liquidation judiciaire vouée à une clôture pour insuffisance d’actif est une menace sérieuse à la prise en charge des créances environnementales par l’entreprise en difficulté. Le mécanisme des garanties financières paraît plus adapté au principe pollueur-payeur qui fonde l’obligation de remise en état mais reste inefficace tandis que les systèmes mutualistes et la « séniorisation » d’une partie des créances environnementales dans l’apurement du passif par la loi portant industrie verte contrastent avec la philosophie du principe pollueur-payeur. Cette étude se propose de concilier les intérêts du droit de l’environnement et ceux du droit des entreprises en difficulté par le concept d’une « assurance-vie environnementale » comme outil juridique et financier au service de l’intérêt général
Keywords: Assurance-Vie environnementale; Companies in difficulty; Créances environnementales; Dividende latent; Entreprises en difficulté; Entreprises en difficulté (droit); Environmental claims; Environmental life insurance; ICPE; Installations classées; Latent dividend; Pollueur-Payeur; Polluter pays

Réflexions autour de l'utilisation des sciences dans la preuve pénale - Coste, Angéline (Université Jean Moulin Lyon 3, 2024)
Alors que la preuve pénale doit être guidée par un principe de liberté, l’utilisation des sciences semble devenue indispensable à l’exercice du droit de punir. La réalisation d’actes scientifiques d’investigation imprègne la recherche de la vérité. En effet, en plus d’être employées pour établir la participation à l’infraction, les sciences peuvent servir à adapter la réponse pénale à la personnalité de l’auteur des faits. L’apport d’éléments scientifiques de preuve légitime la vérité judiciaire, qui se rapproche de la vérité matérielle traditionnellement convoitée. L’utilisation des sciences participe à l’érosion du système probatoire actuel et apparaît peu compatible avec la fondamentalisation de la procédure pénale, dont elle cristallise les insuffisances. Cette utilisation ne permet pas d’évincer tout risque d’erreur : les disciplines et les méthodes employées progressent, mais l’irréductible faillibilité de l’homme impose de renoncer à toute quête de certitude. S’il peut prêter le flanc à la critique, le déséquilibre affectant la relation qui s’est nouée entre les sciences et la preuve pénale gagnerait à être corrigé. Ainsi, après avoir analysé les incidences de l’utilisation des sciences sur l’opération probatoire, la présente étude tentera de formuler des propositions destinées à rééquilibrer cette relation, tant pour le présent à travers la réglementation accrue de l’utilisation des sciences, que pour l’avenir à travers l’encadrement des nouveaux actes scientifiques d’investigation.
Keywords: France; Preuve; Preuve (droit pénal); Procédure pénale; Sciences

الأوراق التجارية الإلكترونية - منزول, يمينة (Ibn Khaldun University of Tiaret, 2024)
يعد موضوع الأوراق التجارية الإلكترونية من المواضيع القديمة الحديثة بتطورها من حيث آليات معالجتها وإنشائها والوفاء بها إلكترونيا، لذلك لا يمكن ا عتبارها من ضمن وسائل الوفاء الحديثة في المجال التجاري والمصرفي، وإنما طورت بتطور تقنيات الكتابة والتوقيع، وطورت كذلك إستجابة لمحاكاة الرقمنة مختلف القطاعات التجارية والمصرفية. لذا تهدف دراسة موضوع الأوراق التجارية الإلكترونية إلى الوقوف عن مدى استجابة التشريعات الدولية والوطنية لمتطلبات الرقمنة، ووضع تنظيم قانوني تبرز من خلاله الخصوصية الإلكترونية في الأوراق التجارية من جهة، دون المساس بالوظائف الأساسية أو المبادئ التي يرتكز عليها قانون الصرف وإمكانية توافق أحكام قانون الصرف التقليدية مع رقمنة الأوراق التجارية وقابليتها للتطبيق عليها من جهة أخرى مع إلزامية البحث عن الأطر الحمائية التشريعية المنتهجة للأوراق التجارية الإلكترونية، دوليا ووطنيا مدنيا وفنيا وجنائيا بما يكفل التعامل ا لآمن بها The subject of electronic commercial papers is considered one of the old and modern topics in terms of its development in terms of mechanisms for processing creating, and fulfilling it electronically. Therefore, it cannot be considered among the modern means of fulfillment in the banking field. Rather, it was developed with the development of writing and signing techniques, and it was also developed in response to the simulation of digitization in various commercial and banking sectors. Therefore, the study of the issue of electronic commercial papers aims to determine the extent to which international and national legislation responds to the requirements of digitization, and to develop a legal regulation through which electronic privacy in commercial papers is highlighted on the one hand, without prejudice to the basic functions or principles on which the exchange law is based and the possibility of compatibility of the provisions of the traditional exchange law with The digitization of commercial papers and their applicability to them, on the other hand, along with the obligation to search for the legislative protective policy adopted for electronic commercial papers, internationally and nationally civilly, technically, and criminally, in a way that ensures safe dealing with them.

An Exploration of Selected Anti-Money Laundering Role-Players in Zimbabwe - Chitimira, Howard; Torerai, Elfas; Jana, Vimbai (Potchefstroom Electronic Law Journal, 2024)
Although Zimbabwe has established several institutions to combat money laundering and related crimes, there is a perception that inadequate measures are taken to apprehend offenders responsible for financial crimes. Institutions such as the Financial Intelligence Unit (FIU), the Zimbabwe Anti-Corruption Commission (ZACC), the Zimbabwe Republic Police (ZRP), the National Prosecuting Authority (NPA) and the Reserve Bank of Zimbabwe (RBZ) have done little to prove that the government of Zimbabwe is resolute in combatting money laundering. On the contrary, it increasingly appears that these institutions are poorly equipped and lack the necessary capacity to enforce and uphold anti-money laundering (AML) measures in Zimbabwe. Further, there appears to be a selective application of the law, with one set of rules for individuals or institutions that are perceived as political adversaries of the incumbent establishment and a different set of rules for the political elite. Consequently, the selective application of the law projects Zimbabwe as a jurisdiction that is somehow tolerant to money laundering, corruption and related financial crimes, thereby lowering and tarnishing the standing of the country in the global economic community of nations. This paper provides a regulatory analysis of the AML role-players in Zimbabwe in order to assess their functions in combatting financial crimes. It also analyses whether these role-players are effective and substantively executing their responsibilities therein. The authors argue that while Zimbabwe is well able to effectively combat money laundering through the even application of the law to all persons regardless of their political or economic standing, it is imperative that its AML institutions operate without fear, favour or prejudice. This is crucial in combatting money laundering and instilling confidence in the general public's perception of AML institutions in Zimbabwe.
Keywords: Anti-money laundering; Corruption; Financial crimes; Money laundering; Role-players

La politique pénale de l'administration fiscale - Cohen, Liora (Université Paris-Saclay, 2024)
Le ministre de la Justice conduit la politique pénale déterminée par le Gouvernement. Celle-ci s'est progressivement imposée comme une stratégie de poursuite. En matière de délits de fraude fiscale, l'administration fiscale endosse un rôle clé dans la détermination de la politique pénale. En effet, depuis la création du délit de fraude fiscale en 1920, un mécanisme procédural emblématique appelé le « verrou de Bercy » a permis à l'administration de sélectionner les affaires susceptibles de donner lieu à l'engagement de poursuites correctionnelles. Le législateur a ainsi confié à l'administration un monopole de l'initiative des poursuites, lui permettant de disposer d'un rôle prééminent en matière de fraude fiscale.Toutefois, à la suite de la crise financière mondiale déclenchée en juillet 2007 aux États-Unis, les pouvoirs publics ont pris conscience de l'ampleur de la fraude, de plus en plus internationale et complexe, et ont souhaité renforcer le rôle de l'autorité judiciaire dans le cadre de la lutte contre la fraude fiscale.À cet effet, l'une des principales mesures adoptées par le législateur a porté sur la modification du mécanisme du verrou de Bercy. Le monopole de l'initiative des poursuites a alors été transféré au parquet, uniquement pour les cas de fraude les plus graves.Ces dernières évolutions législatives conduisent à réinterroger le rôle de l'administration fiscale et sa politique pénale en matière de fraude fiscale.La présente étude tend à démontrer que l'administration est indissociable de la politique pénale en matière de fraude fiscale dans la mesure où son rôle est toujours prépondérant sur celui de l'autorité judiciaire et que l'action administrative demeure prépondérante sur l'action pénale.
Keywords: Contrôle fiscal; Coopération administrative internationale; Coopération internationale; Cumul des poursuites; Cumulative prosecution; Détection de la fraude fiscale; Fraude fiscale; Impôt; International administrative cooperation; Opportunité des poursuites; Plaintes (procédure pénale); Poursuites judiciaires; Tax audit; Tax fraud; Tax fraud detection; Verrou de Bercy

Essays on Corporate Finance and Corporate Governance - Ding, Zijun (McMaster University, 2024)
This thesis includes three essays that examine the effects of firm policies on labor costs, corporate culture, and stock markets. The first essay studies the impact of major customers on supplier firms’ performance, and I find that supplier firms are willing to collaborate with their major customers while keeping low financial leverages. The cooperation with major customers results in higher productivity and strategic alliance, which could explain the reduction in the labor share of supplier firms. In my study, labor share is defined as the ratio of labor costs to total revenue. Compared to firms without major customers, supplier firms with at least one major customer would reduce labor shares on average by 33% in absolute terms. The findings contribute to the growing literature on the global trend of labor share reduction. The second essay examines the effect of market competition on corporate openness, which is a particular aspect of corporate culture. Corporate openness reflects how open firms are when facing new ideas and experiences, and measures firms’ willingness to innovate and cooperate. I conclude that market competition improves firms’ corporate openness through good corporate governance. Furthermore, corporate social responsibility activities are seen as a positive social outcome of corporate openness. As to economic consequences, less open firms would experience stock return reductions when the market competition is high. The third essay studies the firms listed on Chinese stock exchanges that established an internal whistleblowing mechanism. The results show that the employee whistleblowing system prevents firms from misconducting and leads to reduced stock price crash risk. Furthermore, a cooperative corporate culture helps the internal whistleblowing system decrease crash risk, while an unfair organizational climate exerts the opposite influence. Overall, this study contributes to the emerging literature on the governance role of whistleblowing.

Le projet d'un brevet africain à effet unitaire - El Ghassem, El Ghassem (Université de Montréal, 2024)
Le brevet est un titre de propriété industrielle, qui confère à son titulaire une exclusivité d’exploitation de l’invention. À l’heure actuelle, il n’existe pas de véritable brevet africain, il existe seulement une procédure d’enregistrement unique auprès de l’organisation africaine de propriété intellectuelle (OAPI). Le brevet africain unitaire est un projet de recherche, inspiré du brevet européen à effet unitaire. Ce brevet permettra l’obtention d’une protection dans tous les pays africains, membres de l’OHADA et l’OAPI, par le biais du dépôt d'une seule demande auprès du nouvel office du brevet africain unitaire (OBAU). L’idée d’instaurer un brevet africain unitaire (BAU) émerge comme une entreprise d’une magnitude cruciale au sein du contexte évolutif de l’essor économique du continent africain. Dans le monde, présentement, il existe plusieurs systèmes de brevets unitaires, notamment celui du CGG, Eurasie, et le brevet européen à effet unitaire qui servira d’ailleurs de modèle pour le brevet africain unitaire. Le BAU est un nouveau titre de propriété intellectuelle, qui consiste à produire un effet juridique attribué à un nouveau titre : le brevet africain unitaire. C’est un nouvel instrument de protection et un droit de propriété intellectuelle, dans la mesure où il nécessite une procédure spécifique de délivrance. De plus, l’effet unitaire ne possède pas une durée déterminée, il naît et disparaît par application des règles particulières. L’une de ses caractéristiques principales est la faculté de fournir une protection uniforme et de produire les mêmes effets dans tous les États membres participants. Il s’agit donc d’une protection unitaire et dont son obtention est soumise à des conditions qui doivent être scrupuleusement respectées pour pouvoir bénéficier des prérogatives octroyées par le BAU. Enfin, son annulation ou sa révocation résulte du droit de l’OHADA et OAPI sur le nouveau brevet africain unitaire. Le développement économique de l’Afrique se trouve indéniablement lié à sa capacité à encourager l’innovation, à protéger les droits de propriété intellectuelle et à exploiter les ressources créatives de ses citoyens. À une période où la préservation des inventions et des innovations se révèle impérative afin de catalyser la croissance économique, l’établissement d’un mécanisme de brevetage harmonisé propose des perspectives considérables. Ce mémoire vise à mettre en lumière l’importance capitale de l’implantation d’un brevet africain unitaire en fournissant une étude approfondie de la problématique. Dans un premier temps, nous étudierons l’état des lieux d’un brevet unifié sur le plan européen et africain puis nous envisagerons dans un second temps la création d’un brevet africain à effet unitaire.
Keywords: African Patent office; African judicial institutions; Brevet à effet unitaire; Droit de la propriété intellectuelle; European Patent Office; Industrial property and patents; Institutions judiciaires africaines; Intellectual property; Juridiction unifiée du brevet à effet unitaire; OAPI; OHADA; Office du brevet africain unitaire; Office du brevet européen; Propriété industrielle et brevet d’invention; Qualitative research; Unified Patent; Unified Patent Court with unitary effect; Étude qualitative

Ne faudrait-il pas consacrer l’infraction d’escroquerie sentimentale en droit positif camerounais ? - Kanchop, Thierry Noël (Afrilex : Revue d’étude et de recherche sur le droit et l’administration dans les pays d’Afrique, 2024)
En réformant, il y a quelques années, son arsenal juridique répressif à travers la loi no 2016/007 du 12 juillet 2016 portant Code pénal, le législateur camerounais entendait actualiser sa loi pénale en prenant en charge les nouvelles formes de criminalité. Malgré l’exaltation dont ce texte a fait l’objet en raison de ses multiples innovations, les comportements repréhensibles des hommes ont continué d’évoluer, entraînant des mutations constantes du phénomène criminel qui invitent le législateur à une veille permanente, et par conséquent à une activité législative régulière. La recrudescence dans la société camerounaise des pratiques d’escroquerie sentimentale, qui portent de graves atteintes à la sécurité des personnes et de leurs biens, invitent dès lors à se demander s’il ne faudrait pas consacrer l’infraction d’escroquerie sentimentale en droit pénal camerounais. Un tel questionnement, qui se situe au confluent de la politique criminelle, de la philosophie, du droit, de la légistique et de la sociologie, est porteur d’un conflit idéologique entre les thèses qui pourraient justifier une opposition ou une adhésion à l’idée de pénaliser ce phénomène nouveau. Garant de l’ordre public, de l’efficacité et de l’actualité de la loi pénale, le législateur camerounais se doit de répondre de manière satisfaisante à cette interrogation. L’hésitation à y répondre par l’affirmative, justifiable à plusieurs titres, doit pouvoir tout de même être surmontée par la nécessité actuelle d’incriminer ledit phénomène. When Cameroon’s legislature reformed its repressive legal system a few years ago with Law 2016/007 of 12 July 2016 on the Criminal Code, it intended to update its criminal law by taking into account the new forms of crime. Though this text has been much appreciated for its many innovations, reprehensible human behaviour has continued to change, leading to regular modifications in the criminal phenomenon that require the legislator to keep a constant look and, therefore a steady legislative activity. The resurgence in Cameroonian society of emotional swindling practices, which seriously undermine the security of individuals and their property, raises the question of whether the offence of sentimental swindling should be enshrined in Cameroonian criminal law. Such questioning, which lies at the confluence of criminal policy, philosophy, law, legal theory and sociology, gives rise to an ideological conflict between the theses that could justify opposition to or support for the idea of penalising this new phenomenon. The Cameroonian legislator, as the guardian of public order, effectiveness and timeliness of the criminal law, has a duty to provide a satisfactory answer to this question. Although the hesitation to reply positively is justifiable on several grounds, it must be overcome by the current need to criminalise the phenomenon in question.
Keywords: Escroquerie sentimentale; Penalization; Principe de nécessité; Principle of necessity; Pénalisation; Sentimental swindling

La solidarité en droit de la protection sociale : analyse d'un rapport de droit redistributif - Lacroix, Gauthier (Université Jean Moulin Lyon 3, 2024)
Souvent a-t-on pu trouver des lectures passionnantes traitant des liens entre solidarité et protection sociale d’un point de vue historique, sociologique, ou encore économique. Rarement, en revanche, la solidarité a fait l’objet d’une étude générale en droit de la protection sociale. Afin de mesurer les évolutions qui parcourent le droit de la protection sociale et leurs répercussions sur la solidarité, il faut d’abord contribuer à l’identification juridique de cette notion. Force est de constater que la solidarité dispose d’une traduction spécifique en droit de la protection sociale à travers la création d’un rapport de droit singulier entre les individus et une normativité tout aussi singulière. Or, l’inflation des réformes du droit de la protection sociale ces dernières font naître des contraintes sur la solidarité qui se trouve alors tiraillée entre l’assistance publique et l’assurance marchande. L’étude de ce processus, largement impulsé par le droit de l’Union européenne, ne devra toutefois pas empêcher une hypothèse contraire : celle de la permanence de la solidarité dans le droit de la protection sociale. Pour la défendre, encore faut-il identifier en droit positif des mécanismes susceptibles de l’étayer. Parmi ceux-ci, une attention particulière peut être portée sur les mécanismes de protection sociale complémentaire. Le transfert de charge de protection sociale sur de nouvelles collectivités doit pouvoir s’analyser, non plus comme un simple désengagement de l’État ou une privatisation de la sécurité sociale, mais comme une opportunité unique de consolider la protection sociale au service de la solidarité. Plus largement, et en dehors du seul champ de la protection sociale complémentaire, il semble nécessaire de s’intéresser dans cette même optique à l’accès aux droits des individus. Cet objectif d’accès aux droits suppose tout à la fois une redéfinition du rôle des acteurs de la protection sociale ainsi que de la place accordée aux bénéficiaires au sein du système de protection sociale afin de dépasser la figure de l’individu consommateur, sujet passif du droit à la protection sociale, à l’individu-acteur, sujet actif du droit de la protection sociale. Often, one can find captivating readings addressing the links between solidarity and social protection from a historical, sociological, or even economic perspective. Rarely, however, has solidarity been the subject of a general study in social protection law. To assess the changes taking place in social protection law and their impact on solidarity, we must first contribute to the legal identification of this concept. Solidarity has a specific translation in social protection law through the creation of a unique legal relationship between individuals and an equally unique normativity. However, the inflation of social protection law reforms in recent years has created constraints on solidarity, which is now caught between public assistance and commercial insurance. The study of this process, largely driven by European Union law, should not, however, preclude an opposing hypothesis: the permanence of solidarity in social protection law. To defend this, it is necessary to identify in positive law mechanisms capable of supporting it. Among these, particular attention can be given to complementary social protection mechanisms. The shift of social protection responsibilities to new entities should no longer be viewed simply as a disengagement of the state or a privatization of social security, but as a unique opportunity to strengthen social protection in the service of solidarity. More broadly, and beyond the field of complementary social protection, it seems necessary to also focus on individuals' access to rights with this same perspective. This goal of access to rights implies both a redefinition of the role of social protection actors and the place granted to beneficiaries within the social protection system, to move beyond the figure of the individual as a consumer, a passive subject of social protection law, towards that of the individual-actor, an active subject of social protection law.
Issue: 2024LYO30052
Keywords: ACCESS TO RIGHTS; Accès aux droits; Droit; Finances sociales; Gouvernance; Governance; Law; Marché; Market; Protection sociale; Social finances; Social security; Solidarity; Solidarité

Climate change and international investment law : lessons from Africa's investment treaty practice - Mogashoa, Lebogang Paul (University of Pretoria, 2024)
This dissertation critically analyses new generation continental, regional and bilateral investment treaties in Africa with the aim to explore enhancements that could be made thereto in order to enable African citizens to hold investors accountable for investment-related climate change issues in Africa. The main research question answered in the dissertation is: to what extent does African investment treaty practice incorporate climate change-related provisions and investor accountability for climate change. The dissertation analysed traditional investment treaties, particularly noting their silence on climate change and investor accountability, and their partiality to investor protection. Using the AfCFTA Investment Protocol as an anchor alongside other new generation continental, regional and bilateral investment treaties in Africa, it discusses a fundamental contemporary shift in African investment treaty practice towards ensuring sustainable investments and greater investor accountability for sustainability in Africa. It also explores the various limitations in these new generation investment treaties that still make investor accountability. In the end it proposes reforms to the Investor-State Dispute Settlement provisions of these investment treaties to recognise citizen-led arbitral claims against investors, utilising the Hague Rules on Business and Human Rights as the procedural infrastructure for handling arbitration of such claims.
Keywords: AfCFTA; African Continental Free Trade Area; Climate change; ISDS; Investment treaties; Investments; Investor-State Dispute Settlement

The relationship between the business rescue practitioner and the directors of the company - Mokoka, Neo (University of Pretoria, 2024)
This dissertation on the relationship between the business rescue practitioner and the directors of the company under business rescue. In essence, this dissertation investigates whether a conflict arises between the duties, roles and powers of the business rescue practitioner and those of directors of the financially distressed company. The aim of this dissertation is to study what are the limitation on duties, roles and powers of directors of the company as a result of the appointment of the business rescue practitioner and the extent thereof. In achieving the above objective, this dissertation commences with setting out the background of business rescue proceedings in South Africa by analysing provisions of Chapter 6 of the Companies Act 71 of 2008 which has introduced “a new corporate rescue procedure” in South Africa, being business rescue. The focus is on provisions dealing with duties, roles and powers of directors in the ordinary course as set out in section 66, 75 to 77 of the Act. The focus then shifts to the provisions dealing with the commencement of business rescue proceedings, the appointment of the business rescue practitioner and his duties, roles and powers. In order to establish whether a conflict truly exists between the duties, roles and powers, various sources dealing with this issue are considered. In order to assess whether there are solutions in dealing with the conflict and/or limitation that arises, this dissertation includes a comparative study on selected foreign jurisdictions dealing with the interaction between the board of directors and business rescue practitioner are considered. In particular, this dissertation considers corporate rescue mechanisms in the Commonwealth of Australia, the United Kingdom and the United States of America. The purpose of the comparative study is to determine which lessons can be learned from the practices in the aforementioned jurisdictions. The overall objective of this study is to determine how the South African legal framework pertaining to the interaction between directors and business rescue practitioners can be enhanced.
Keywords: Business rescue; Business rescue practitioner; Companies Act 71 of 2008; Comparative study; Duties of directors; Limitations on powers; Powers of directors; Roles of directors; US bankruptcy code

La transaction fiscale au Cameroun - Nanan Lekogmo, Hermann (Revue des Réflexions Constitutionnelles : Revue mensuelle de publication en droit constitutionnelle, 2024)
La transaction existe en droit fiscal camerounais. Depuis une dizaine d’années, elle a connu des aménagements en vue de pacifier les relations entre les contribuables et l’administration fiscale et de réduire les restes à recouvrer (RAR). Il s’agit pour les pouvoirs publics d’encourager le recours à la transaction en matière fiscale. Ils ont permis, contrairement à ce qui a généralement cours dans d’autres matières et législations, que la transaction fiscale, au Cameroun, vise, plus qu’une modération des pénalités, une modération des impositions. Or les juridictions sont confrontées à un volume de dossiers à traiter supérieur à leur capacité. Malheureusement, le nombre de transactions reste encore limité. Et cela est dommage ! La transaction fait partie de la justice alternative et est plutôt utilisée en matière fiscale et contractuelle afin d’amener l’administration fiscale et le contribuable à trouver une solution rapide et moins onéreuse qu’un procès. Quelle appréciation peut être faite de la transaction fiscale en droit camerounais ? Il semble que sa nature et les caractères de son identification soient sources de problèmes. Peut-être aussi que la culture de la common law dont elle est sujette semble ne pas trouver un terreau fertile au Cameroun. Si l’instauration de la technique transactionnelle est aisée, son application demeure malaisée. Tax transaction exists in Cameroonian tax law. For about ten years, it has undergone adjustments with a view to pacifying relations between taxpayers and the tax administration and reducing outstanding amounts. The aim of the public authorities is to encourage the use of tax transactions. They have allowed, contrary to what is generally the case in other matters and legislation, that tax transactions in Cameroon aim, more than a moderation of penalties, a moderation of taxes. However, the courts are faced with a volume of cases to process that exceeds their capacity. Unfortunately, the number of transactions is still limited. And that is a shame! La transaction fait partie de la justice alternative et est plutôt utilisée en matière fiscale et contractuelle afin d’amener l’administration fiscale et le contribuable à trouver une solution rapide et moins onéreuse qu’un procès. Quelle appréciation peut être faite de la transaction fiscale en droit camerounais ? It seems that its nature and the characteristics of its identification are sources of problems. Perhaps also that the culture of common law to which it is subject does not seem to find fertile ground in Cameroon. If the establishment of the transactional technique is easy, its application remains difficult.
Keywords: Administration fiscale; Alternative justice; Alternative procedure; Contribuable; Justice alternative; Procédure alternative; Tax administration; Tax transaction; Taxpayer; Transaction fiscale

Theories on the nature and purpose of the company and their implications for corporate governance - Ramalho, Anna Francina (University of Pretoria, 2024)
Despite the emergence of corporate governance as a formal discipline more than thirty years ago, the proliferation internationally of scholarly work on the topic and its formal regulation over this period, the scope, definition and direction of corporate governance remain contested. Company theories could potentially assist in this regard but have been inconsistent in their explanations of the both the means and ends of corporate governance. This has led to scepticism about the efficacy of theories to illuminate the phenomena associated with companies and company law. Notwithstanding, theory is critical as it makes explicit what is implicit in policymaking by regulators, as well as in the behaviour and decision-making by corporate actors, so that regulation and decisions are transparent for analysis and evaluation. The study, therefore, set out to provide a synthesis and doctrinal analysis of the main theories on the nature and general purpose of corporations in historical context. It was found that objections can be raised against all of these theories to a greater or lesser extent for inaccurate portrayal of the law, limited explanatory power and detachment from the real word. This study shows that corporate theories are a product of the settings in which they have developed and consequently none of these theories represents a universal or absolute truth, nor are they an inevitability due to widespread adoption and use. This leaves room for new formulations of the corporate form and its purpose fit for today’s context with its political, social and environmental challenges. This dissertation also includes further directions for theoretical exploration.
Keywords: Contractarianism; Corporate governance; Entity theories; Shareholder primacy; Stakeholder theories

Le droit pénal à l'épreuve de l'IA : De l'infraction à la répression numérique - Rousseau, Théo (Université Savoie Mont Blanc, 2024)
Le droit pénal est confronté, comme toutes les matières juridiques, à la numérisation de la société. La matière pénale est soumise à des changements multiples induits par le recours aux outils numériques : les auteurs d'infractions utilisent le numérique, les enquêteurs y ont recours, la procédure pénale et la Justice se numérisent. De plus, le support de l'infraction se transforme. D'objet inerte, il devient logiciel, dit "intelligent" ou "autonome", capable en tout cas d'agir sans qu'un humain le contrôle directement. Tout cela influence la définition de l'infraction et les limites de la responsabilité pénale. En parallèle, le recours aux outils numériques connaît une généralisation et une banalisation sans précédent. Tout doit être numérisé, de l'Etat et ses fonctions régaliennes aux rapports sociaux entre les individus. Le champ infractionnel numérique est étendu proportionnellement aux moyens dont disposent ceux qui font un usage nocif, hostile, des technologies disponibles. En réaction, le législateur semble voir dans la numérisation à la fois une menace et un outil de salut. Une menace, car tout peut être atteint par une connexion internet ou équivalent, ce qui parait imposer de surveiller, contrôler et donc réprimer au maximum tout comportement considéré comme "dangereux" et non plus seulement illicite, du moment qu'il peut s'exprimer par l'outil numérique. Un salut, car le recours à ces mêmes technologies est la solution présentée comme incontournable pour protéger les populations civiles. La surveillance se généralise et se développe, la répression s'automatise et doit s'accélérer, le tout en ayant recours à l'"IA", aux logiciels capables, mieux que l'humain, traiter de la dangerosité et des comportements répréhensibles. Pourtant, cette foi en l'outil numérique comme un absolu et un incontournable, l'"IA" étant appelée à incarner et s'incarner pour supplanter l'intelligence humaine, n'est pas exempt de vices et de dangers pour ceux qui subiront ou subissent déjà ses décisions. Notre étude se doit de mettre en lumière les biais de raisonnement, les menaces pour les droits collectifs et individuels ainsi que les enjeux, à long terme, de cette recherche d'anticipation et de décision contraignante, par le numérique et contre l'humain. Like all legal fields, criminal law is confronted with the digitization of society.Criminal law is undergoing multiple changes brought about by the use of digital tools: offenders are using digital technology, investigators are using it, and criminal procedure and the justice system are going digital.What's more, the medium in which offences are committed is changing. From being an inert object, it is becoming software, so-called “intelligent” or “autonomous”, capable in any case of acting without direct human control. All this influences the definition of the offence and the limits of criminal liability.At the same time, the use of digital tools is becoming increasingly widespread and commonplace. Everything must be digitized, from the State and its regalian functions to social relations between individuals.The scope of digital crime is expanding in proportion to the means available to those who make harmful, hostile use of the technologies available.In response, legislators seem to see digitization as both a threat and a means of salvation.A threat, because anything can be reached via an Internet connection or equivalent, which would seem to make it necessary to monitor, control and therefore repress to the utmost any behavior considered “dangerous” and no longer merely illicit, as long as it can be expressed using digital tools.A salvation, because the use of these same technologies is the solution presented as inescapable to protect civilian populations. Surveillance is becoming more widespread, repression automated and accelerated, all through the use of “AI”, software capable of handling dangerousness and reprehensible behavior better than humans.However, this faith in the digital tool as an absolute and inescapable, with “AI” destined to embody and become embodied to supplant human intelligence, is not without its vices and dangers for those who will undergo or are already undergoing its decisions.Our study must highlight the biases in reasoning, the threats to collective and individual rights, and the long-term stakes involved in this quest for anticipation and binding decisions, through digital technology and against human beings.
Issue: 2024CHAMA044
Keywords: AI; Artificial Intelligence; Crime; Droit pénal; Infraction; Infrigement; Intelligence artificielle; Numérique; Offence; Répression numérique

The Middle Eastern and African Arbitration Review 2024 : CRCICA and new CRCICA Arbitration Rules - Selim, Ismail; Hafez, Mohamed (The Cairo Regional Centre for International Commercial Arbitration, 2024)

Selected problem areas pertaining to the removal of directors from office - Shange, Thandokuhle Wandile (University of Pretoria, 2024)
This paper constitutes a composite analysis of the legal framework and procedures for removing directors and the key challenges presented by the framework. It achieves this by looking at four legal questions: Firstly, it looks into what is the legal framework for director removal in South Africa, secondly, it delves into the challenges and/or uncertainties presented by this process, and further explores if there are any possible learnings South Africa can learn from foreign jurisdiction.
Keywords: Companies Act 2008; Comparative company law; Director removal; Director’s right; Judicial review; Section 71

Proposed legal reforms to protect South Africa's informal social security - Zeelie, Robin Erin (University of Pretoria, 2024)
Informal social security is a non-governmental form of social security between kin and/or community members and is a prevalent practice in South Africa. The question this dissertation analyses is whether the South African government fails in its constitutional duty to protect and advance informal social security. The dissertation limits itself to analysing cash transfers through social grants, and social insurance in the Unemployment Insurance Act and the Compensation for Occupational Injuries and Diseases Act. This dissertation delineates its definition of informal social security, historically contextualises its practice, and explains the contemporary formal social security framework. This dissertation finds five prominent shortcomings in the formal framework, and that these shortcomings have a profoundly negative, weakening effect on informal social security, as the more people who rely on informal mechanisms, the less it can respond to needs arising from life contingencies, shocks, and risks. The dissertation concludes by analysing three legal reform proposals the state can implement: extending existing social insurance frameworks to those in the informal sector, promoting cooperatives as a formal platform for the informal, and the basic income grant.
Keywords: Basic income grant; Cooperatives; Duty; History; Informal social security; Republic of South Africa; Social assistance; Social security

Attachment Proceedings for Goods Onboard an Aircraft: A Closer Look at the OHADA Law on Simplified Recovery Procedures and Measures of Execution - Atemlefac, Atemnkeng Micheal (Scholars International Journal of Law Crime and Justice, 2024)
The practical application of international conventions like the Montreal Convention of 1999 and the OHADA Uniform Act of 2023 in the context of attaching goods onboard aircraft presents significant challenges. These frameworks do not explicitly address the attachment of such goods, focusing instead on liability and recovery procedures. The OHADA Uniform Act aims to simplify recovery processes but may struggle with conflicting national regulations and regional legal practices. The absence of specific legislation for attaching goods in-flight creates a critical gap, leading to uncertainty and inefficiency in enforcement. Addressing this gap in this paper requires developing targeted legal solutions that align with international standards while addressing the unique demand of air transport.
OpenAlex: https://openalex.org/W4403880779
Keywords: Aircraft; Goods; Measures of Execution; Simplified Recovery Procedures

Extinção dos contratos de colaboração empresarial: uma abordagem pela teoria dos contratos relacionais - Barros, Simone Rodrigues Alves Rocha de (Universidade de São Paulo, 2024)
The work proposes to investigate the extension of collaboration contracts through traditional tools that rely on the classic contractual model based on exchange and whether these solutions are more suitable for this type of contract. The theory of contracts is to assist in the task of understanding the specifics and the environment of business collaboration contracts and the prospect of terminating the relationship due to the lack of collaboration, based either on default or on the impossibility of the performance itself in the interest of the creditor. In collaboration contracts, collaboration is, by the very definition of these contracts, the main obligation, integral to the core of the contractual object. It is collaboration that is one of the other obligations, allowing the configuration of the common project as a contract. In this type of relationship, the binomial provision and consideration is multifaceted, as are the positions of creditor and debtor. In this context, the study of these collaboration contracts requires a more comprehensive and complex view of the institutes that, originally, were formulated for a tight exchange relationship and for well-defined contractual positions. What we intend to confirm in this research is that the lack of collaboration, in this type of contract, can lead to positive violation or absolute default, which must be determined according to the interest of the creditor which, in corporate contracts, has to do with the economic function, with its own contractual program. Given the difficulty of characterizing a positive breach of the contract or, even more so, absolute default, the investigation also encompasses a broadening of the perspectives of the default itself, to conclude that the performance ultimately serves the interest of the creditor (understood in an amplified position) and can only be read from the economic function of the business. When collaboration between the parties is no longer possible, the specific execution of obligations appears useless and involving.

L'effectivité de la protection de la mer Méditerranée par le statut juridique de l'écosystème marin - Lelong, Emma (Université de Bretagne Occidentale, 2024)
La mer Méditerranée, qui est l’une des plus polluées du monde, fait l’objet de mesures de protection juridiques issues du droit international, du droit de l’Union européenne, de législations nationales des États ou encore de systèmes de protection des mers régionales. Pourtant, l’effectivité de ces diverses mesures de protection est discutable : mauvaise surveillance, mauvaise mise en oeuvre, mécanismes de contrôle juridictionnel et extra-juridictionnel parfois insuffisants, manque de financement, d’acceptabilité sociale ou encore inadaptation à l’endémisme de la biodiversité méditerranéenne sont des facteurs d’échec. Face à ce constat, cette thèse a vocation à questionner les apports et limites à l’effectivité d’une approche par le statut juridique de l’écosystème marin de la mer Méditerranée. Elle explore donc les catégories de sujet de droit, de personnalité juridique, d’objet, de chose, de patrimoine à des fins d’amélioration du niveau de protection et à la lumière de la théorie des communs. Pour ce faire, la thèse explore la faisabilité d’une gouvernance commune de la mer Méditerranée sur la base d’une relation qui lierait la mer aux acteurs qui l’entourent et utilise une approche comparative avec les autres initiatives de reconnaissance de statuts juridiques à la nature dans le monde. Elle interroge ensuite les apports et limites de cette approche par les différentes typologies de statuts juridiques identifiés par rapport au niveau de protection existant.
Keywords: Common heritage; Droits de la nature; Effectiveness; Effectivité; Effectivité et validité du droit; Legal status; Mediterranean; Méditerranée; Méditerranée (mer); Patrimoine commun; Protection; Rights of nature; Statut juridique; Écologie marine

Les enjeux de la transition écologique dans le transport maritime : analyse et perspectives d'évolution du cadre juridique - Querel, Morgane (Nantes Université, 2024)
Le transport maritime est une activité essentielle pour le fonctionnement des sociétés modernes. Il a des fonctions économique et sociale incontestables. Elles ne s’arrêtent pas au navire, objet principal du transport maritime. De nombreux acteurs terrestres, nécessaires à sa construction, sa vie opérationnelle puis à son démantèlement, vivent aussi pour et grâce à cette activité. Tous ces éléments en font une activité d’importance mondiale. Dans un contexte de prise de conscience de l’impact des activités humaines sur l’environnement, le transport maritime peut être « pointé du doigt » pour la pollution marine et atmosphérique qu’il génère. C’est pourquoi, il est aujourd’hui indispensable de travailler sur une transition de cette activité pour la rendre plus respectueuse de l’environnement. Toutefois, cette transition comporte plusieurs enjeux. En effet, de nombreux obstacles techniques et économiques, en plus de l’importance de préserver le marché mondial du transport maritime, vont compliquer le travail pour réduire la pollution provenant des navires. C’est dans ce cadre que le droit maritime va intervenir. Il est adopté principalement, mais pas uniquement, au niveau international. Ce droit va inciter, ou obliger, selon les sujets, les acteurs du secteur à réduire leur empreinte environnementale. Il est produit principalement par l'Organisation Maritime Internationale (OMI) et porte majoritairement sur le navire. Dans son élaboration, il doit prendre en compte tous les enjeux liés à cette activité. Toutefois, en analysant certaines réglementations qui existent aujourd’hui, des lacunes apparaissent pour permettre la transition écologique du transport maritime. À l’inverse, d’autres réglementations ont fait leurs preuves dans la lutte contre un type de pollution. L’analyse de tous ces textes, mise en lumière avec des retours d’expériences régionales ou nationales, fait ressortir les éléments nécessaires pour construire un droit effectif et efficace, et ouvre des voies d’amélioration du droit maritime international.
Keywords: Bruit sous-marin; Droit maritime; Eaux de ballast; Ecological transition; Environment; Environnement; International Maritime Organization (IMO); Marée noire; Mer; Organisation Maritime Internationale (OMI); Pollution; Pollution atmosphérique; Pollution marine; Recyclage des navires; Transition écologique; Transports maritimes

L’impact de l'adoption des IFRS sur la reconnaissance des pertes en temps opportun : Étude des sociétés cotées à la Bourse de Casablanca - El Idrissi Rioui, Samia; Touicher, Ouardia (Revue du contrôle, de la comptabilité et de l’audit, 2024)
Les Normes Internationales d’Information Financière (IFRS), émises par l'International Accounting Standards Board (IASB), deviennent de plus en plus le régime comptable privilégié parmi les entreprises des pays africains. La recherche sur l’effet de l’adoption des IFRS sur la qualité de l’information comptable dans les économies émergentes est encore rare. Par conséquent, cet article examine l’effet de l’adoption des IFRS sur la reconnaissance rapide des pertes, un indicateur de la qualité de l’information comptable. Les données financières de 34 entreprises cotées à la Bourse de Casablanca, couvrant la période de 2009 à 2019, sont analysées en utilisant une régression logistique dans le cadre d'une méthodologie économétrique quantitative. Deux panels équilibrés ont été constitués : l'un regroupant 14 entreprises ayant adopté les normes IFRS, et l'autre constitué de 20 entreprises suivant les normes comptables marocaines. Les résultats indiquent que la qualité des bénéfices (mesurée par la reconnaissance rapide des pertes) ne s’est pas améliorée après l’adoption des IFRS. Cette constatation implique que les régulateurs comptables et les organismes comptables des pays africains devraient encourager une application rigoureuse des IFRS en formant continuellement les comptables et auditeurs des entreprises cotées sur la mise en œuvre pratique de ces normes. Ces formations devraient être obligatoires et accessibles.
Keywords: Normes IFRS; Normes comptables marocaines; Reconnaissances rapide des pertes; Régression logistique

La preuve en droit des systèmes d'intelligence artificielle - Pons, Ronan (Université Toulouse Capitole, 2024)
En 2021, la Commission européenne proposait d'encadrer spécifiquement les systèmes d'IA au sein du marché européen. Adopté et publié en 2024, le règlement européen sur l'IA a pour objectif de protéger la santé, la sécurité et les droits fondamentaux des individus face aux risques de l'IA. Pour cela, le texte énonce plusieurs obligations relatives à la conception de certains systèmes d'IA. Toutefois, l'application d'exigences juridiques vagues à des outils quantitatifs et précis comme les systèmes d'IA représente un défi de taille. Comment s'assurer que les futurs systèmes d'IA respecteront fidèlement les exigences prévues par le droit ? Au cœur de cet enjeu d'application se trouve la preuve juridique. Ainsi, nous nous intéresserons à la preuve afin de comprendre le(s) rôle(s) qu'elle joue au sein du futur droit des systèmes d'IA. Par le prisme de la preuve, nous proposons une perspective nouvelle sur le nouveau droit des systèmes et ses conséquences sur notre système juridique.
Keywords: AI Act; AI Systems; Certification; Intelligence artificielle; Legal evidence; Preuve (droit); Preuves; Règlement sur l'IA; Régularisation (droit); Systèmes d'IA

Lawyers and Non-Lawyers in International Arbitration: Discovering Diminishing Diversity - Nottage, Luke; Teramura, Nobumichi; Tanna, James (Loyola of Los Angeles International and Comparative Law Review, 2024)

La capacité de la personne représentée - Taffin, Gwendoline (Université de Bordeaux, 2024)
Les études concernant les personnes représentées que sont le mineur ou le majeur protégé (majeur placé sous un régime de représentation) se focalisent souvent sur l’incapacité de ces derniers, celle-ci ayant pour objet de les protéger. En effet, l’incapacité du majeur protégé et du mineur a une finalité protectrice cependant, il ne faut pas négliger que ces incapacités viennent également réduire l’exercice de certains droits. Il convient alors de constater qu’il est possible de protéger la personne représentée, protection nécessaire au regard de sa particulière vulnérabilité, tout en soutenant qu’elle dispose d’une certaine forme de capacité. La capacité des personnes représentées a beaucoup évolué à travers l'influence des différentes réformes récentes en droit des personnes ou encore en droit des obligations. Le droit français tend alors à évoluer vers une meilleure reconnaissance de l’autonomie des personnes soumises à un régime d'incapacité, qu'elles soient mineures ou majeures protégées bénéficiant d'une mesure de représentation.
Keywords: Capacity; Capacité; Incapacité (droit); Majeurs protégés; Majorité (droit civil); Mineurs; Mineurs (droit); Minors; Protected adults; Vulnérabilité (droit)

Termination of the Mandate of an Agent: An Examination under OHADA Uniform Act on General Commercial Law - Ndekwena Noh, Alison (Scholars International Journal of Law Crime and Justice, 2024)
When an agency relationship is created, it confers on the parties obligations which must be fulfilled by the parties. These obligations do not remain forever as they can come to an end. This can be done under normal circumstances by the act of the parties or by operation of the law and when the conduct of the agent is in contradiction to the mandate agreement as may be the case if the agent is liable for serious misconduct as provided by the OHADA Uniform Act on General Commercial Law. The provisions of the act regarding termination on grounds of serious misconduct is worrisome, as the act talks about termination in such manner only for commercial agents and is silent about the other two types of agents: the broker and the commission agent. The act also, does not tell us what this serious misconduct it mentions by the commercial agent is, nor gives us insights on what constitutes such conduct to warrant termination of the mandate of the agent by the principal. When termination of the agency is done under conditions as such, it has grave consequences on the agent who might not be entitled to certain benefits associated with termination of the contract such as loss of the right to compensatory allowance or indemnity and more importantly may give room to arbitrary or wrongful termination of the mandate of the agent. Through analytical and comparative studies, this paper focuses on termination of the mandate of an agent under the OHADA Uniform Act on General Commercial Law, wherein, the different modes of termination of the mandate of an agent have been discussed, and more specifically makes an attempt in looking at what serious misconduct is and what could amount to such conduct so as to avoid arbitrary or wrongful termination. It is therefore suggested that, statutory guidelines found in other statutes in relation to the subject matter can serve as a lamp light in our context.
OpenAlex: https://openalex.org/W4403198358
Keywords: Mandate

Editorial on Doing business in Africa: Navigating opportunities and challenges in Africa's emerging markets - Adomako, Samuel; Shenkar, Oded; Liu, Xiaohui; Amankwah-Amoah, Joseph; Ahsan, Mujtaba (Journal of International Management, 2024)
This editorial delves into the evolving context of doing business in Africa, tracing its journey from being dubbed the “hopeless continent” to becoming a beacon of hope and opportunity. Drawing on a wealth of scholarly research, it highlights Africa's increasing attractiveness for global investments, underscored by rising FDI inflows and the emergence of a vibrant middle class. Despite these promising trends, the editorial also sheds light on the persistent challenges, including institutional fragility and political instability, coupled with limited representation in the existing international business discourse. We advance a more nuanced understanding of Africa's business environment, emphasizing the need for responsible growth, improved governance, and sustainable development. Thus, the Special Issue offers insights into the complexities and challenges of doing business in Africa, as well as the paradoxes and potential for fostering competitiveness and inclusive growth on the global stage.
Keywords: Africa; Doing business; International business; MNEs

'Banking' on artificial intelligence to enhance bank risk management - Chiba, Mayuree (University of Pretoria, 2024)
This dissertation investigates the impact of digital transformation on risk management within the banking sector, emphasizing the integration of artificial intelligence (AI) in enhancing operational risk management. It examines key research questions about how digitisation reshapes risk management practices, the extent to which South African banks align with international standards, and the role of AI in advancing these frameworks. The study finds that AI holds substantial potential to improve risk management, particularly in managing operational risks, while underscoring the indispensable role of human oversight. Ultimately, this shift toward a more AI-driven, adaptive approach marks a pivotal evolution in the financial sector, suggesting that the future of risk management can indeed rely on AI's transformative capabilities.
Keywords: Artificial Intelligence; Bank; Inteligência artificial; Intelligence Artificielle; Operational risk; Risk management

Product liability in an age of development risks : should South Africa reconsider adopting a development risk defence? - Tennant, Sarah-lynn; Van Heerden, C. M. (Corlia) (Journal of African Law, 2024)
To provide protection against harm caused by defective, unsafe products and to promote product safety, the law of product liability has developed as a specialized area of the law of delict (tort). The vexing question is, who should bear such liability? This contribution interrogates the notorious EU development risk defence, which exonerates manufacturers that meet certain stringent requirements for undiscoverable development risks in products that consequently inflict harm on consumers. In particular, it considers the election by South Africa, which recently adopted a “strict” product liability regime with the introduction of the Consumer Protection Act 2008, not to adopt such a defence. The purpose of this contribution is to consider the nature and scope of the development risk defence as contained in article 7(e) of the European Union (EU) Product Liability Directive and to determine whether it was prudent for South Africa to steer clear of incorporating a similar defence in its new statutory product liability regime.
Keywords: Defective product; Developmental risk; Hybrid regime; Product liability; Strict liability

Violations de données personnelles : vers une intégration profonde entre les risques de sécurité de l'information et les risques de non-conformité au RGPD - Enríquez Álvarez, Luis Fernando (Université de Lille, 2024)
La sécurité de l'information est étroitement liée au droit de protection des données, car une mise en œuvre inefficace de la sécurité peut entraîner des violations de données à caractère personnel. Le RGPD repose sur la gestion de risques pour la protection des droits et libertés des personnes concernées, ce qui signifie que la gestion de risques est le mécanisme de protection des droits fondamentaux. Cependant, l'état de l'art en matière de gestion des risques liés à la sécurité de l'information et de gestion des risques juridiques sont encore immatures. Malheureusement, l'état actuel de l'art n'évalue pas la multidimensionnalité des risques liés à la protection des données, et il n'a pas tenu compte de l'objectif principal d'une approche basée sur les risques, à savoir mesurer les risques pour prendre des décisions éclairées. Le monde juridique doit comprendre que la gestion des risques ne fonctionne pas par défaut et plusieurs fois nécessite des méthodes scientifiques appliquées d'analyse des risques. Cette thèse propose un changement d'état d'esprit sur la gestion des risques liés à la protection des données, avec une approche holistique qui fusionne les risques opérationnels, financiers et juridiques. Le concept de valeur à risque des données personnelles est présenté comme le résultat de plusieurs stratégies quantitatives basées sur la modélisation des risques, la jurimétrie, et l'analyse de la protection des données à la lumière de l'apprentissage automatique. Les idées présentées ici contribueront également à la mise en conformité avec les prochaines réglementations basées sur le risque qui reposent sur la protection des données, telles que l'intelligence artificielle. La transformation au risque peut sembler difficile, mais elle est obligatoire pour l'évolution de la protection des données.
Keywords: Analyse quantitative des risques; Apprentissage automatique; Droit à la vie privée; Gestion des risques; Gestion du risque; Jurimétrie; Protection de l'information (informatique) – Droit; Protection des données; Recherche quantitative; Vie privée; Violation des données; Évaluation du risque

Problématique de l’entrepreneuriat féminin dans le secteur de la logistique et des transports au Mali - Lassina, Togola; Bayogo, Yapégué (African Scientific Journal, 2024)
A l’instar des autres secteurs d’activités, l’entrepreneuriat féminin est buté à de multiples problèmes dans le secteur de la logistique et des transports au Mali. Ces problèmes sont d’ordre organisationnel et sont dus à la complexité de la planification du matériel de transport ainsi que la gestion du personnel tant bien administratif que celui de la conduite. Ces multiples problèmes font que les entreprises de transport et en particulier celles du secteur de la logistique et des transports naissent et disparaissent en un laps de temps. Selon le droit OHADA, la durée de vie d’une entreprise est de 99 ans. Cette durée est largement supérieure à la durée moyenne de vie de nos entreprises du secteur de la logistique et des transports qui varie entre 10 ans et 20 ans. L’objectif de  l’étude est d’établir un lien entre l’entrepreneuriat féminin dans son ensemble et le cas spécifique de la logistique et des transports au Mali. La méthodologie utilisée consiste à faire d’abord une recherche documentaire permettant d’analyser l’évolution des entreprises du secteur de la logistique et des transports, leur durée de vie moyenne puis une étude qualitative a été faite à l’aide d’un guide d’entretien adressé à des personnes cibles. Le guide d’entretien a été adressé aux personnes suivantes : 3 entrepreneurs du secteur de la logistique et des transports, 2 agents de la Direction Générale des Transports, 2 agents de la Direction générale du commerce et de la concurrence, 2 agents du conseil malien des chargeurs, 2 agents de l’Agence pour la promotion des investissements. Les résultats de l’étude montrent la fragilité du dit secteur qui défavorise l’entrepreneuriat féminin et entraine souvent le déclin rapide des entreprises de la logistique et des transports. De même, l’étude montre que le taux de rentabilité interne des entreprises dudit secteur est faible. Like other sectors of activity, women's entrepreneurship faces multiple problems in the logistics and transport sector in Mali. These problems are of an organizational nature and are due to the complexity of the planning of transport equipment as well as the management of both administrative and operational personnel. These multiple problems mean that transport companies, and in particular those in the logistics and transport sector, are born and disappear in a short period of time. According to OHADA law, the lifespan of a company is 99 years. This is much longer than the average lifespan of our companies in the logistics and transport sector, which varies between 10 and 20 years. The objective of the study is to establish a link between women's entrepreneurship as a whole and the specific case of logistics and transport in Mali. The methodology used consists of first conducting documentary research to analyse the evolution of companies in the logistics and transport sector, their average lifespan, and then a qualitative study was carried out using an interview guide addressed to target people. The interview guide was sent to the following people: 3 entrepreneurs in the logistics and transport sector, 2 agents of the Directorate General of Transport, 2 agents of the Directorate General of Trade and Competition, 2 agents of the Malian Shippers' Council, 2 agents of the Agency for the Promotion of Investments. The results of the study show the fragility of the said sector, which disadvantages female entrepreneurship and often leads to the rapid decline of logistics and transport companies. Similarly, the study shows that the internal profitability rate of companies in this sector is low.
Keywords: Entrepreneuriat féminin; Fragility; Fragilité; Logistics; Logistique; Mali; Transport; Women's entrepreneurship

Le régime de l’obligation in solidum à la dette douanière - Pulby, Baptiste (Université de Rouen Normandie, 2024)
Cette thèse propose une étude du régime de l’obligation à la dette douanière lorsqu’elle implique plusieurs débiteurs, en se basant sur la notion d’obligation in solidum. Cette obligation a été retracée depuis ses origines pénales jusqu’à sa dégradation en un simple dérivé de l’obligation solidaire au XXe siècle. L’analyse des sources romaines met en lumière ses caractéristiques fondamentales de l’obligation in solidum, qui la singularisent de l’obligation solidaire. Sur le plan structurel, l’obligation in solidum se distingue par une structure reposant sur la pluralité d’objets individuels pour chaque codébiteur et une cause indivisible. L’étude avance une qualification contractuelle des actes douaniers particuliers, incluant des autorisations et des déclarations de placement, les définissant respectivement comme contrat-cadre et contrats d’application. Ces analyses révèlent une logique de bonne foi et introduisent le concept de « dol douanier communautaire » pour expliquer l’annulation des contrats entachés de mauvaise foi. Sur le plan de la dette douanière elle-même, les faits générateurs de l’obligation révèlent sa nature indivisible et les caractéristiques propres à une obligation in solidum. Chaque débiteur est personnellement responsable de l'intégralité de la dette, en raison de cette cause indivisible, tout en conservant des objets indépendants de la dette, structure qui rend le régime solidaire inapplicable. La distinction entre obligation solidaire et obligation in solidum se manifeste dans l’absence de bénéfices de discussion et de division, confirmant la nature in solidum de l’obligation douanière. La seconde partie explore les effets secondaires du régime in solidum de la dette douanière, comme la prescription, la remise de dette et la transaction. En matière de prescription, la pluralité des faits générateurs affecte les délais de prescription ainsi que la portée des effets relatifs des actes interruptifs ou suspensifs, illustrant le caractère indépendant des objets de l’obligation douanière. Quant à la remise de dette, l’analyse conclut que le créancier peut accorder une remise partielle sans affecter les autres débiteurs, en cohérence avec les principes de l’obligation in solidum. L’étude des causes d’extinction montre que la dette douanière, dotée de finalités indemnitaire et répressive, peut subsister malgré la disparition de sa cause indemnitaire si le débiteur a encouru des poursuites. Derrière ce régime européen d’apparence confuse et semblant dépourvu de logique se trouvait en réalité un régime d’obligation à pluralité de sujets, dont les propriétés fondamentales et structurelles constituaient des clés de compréhension, rendant perceptible l’essence logique qui en animait le fonctionnement. C’est à l’aune de cette découverte que nous sommes parvenus à valider l’hypothèse selon laquelle l’obligation à la dette douanière obéissait au régime de l’obligation in solidum, en ce qu’elle était pourvue des mêmes caractéristiques fondamentales et structurelles, que son fonctionnement obéissait à une logique semblable et enfin qu’elle produisait des effets principaux et secondaires identiques à cette institution romaine préjustinienne
Keywords: Customs debt; Customs law; Dette douanière; Douanes; Droit douanier; In solidum; Joint and several liability; Joint and several obligation; Obligations (droit); RGO; Solidarité; Solidarité (droit)

Le développement de l'électricité au Niger : Aspects juridiques - Chaibou Oumarou, Ali (Université Côte d'Azur, 2024)
L’énergie électrique évoque la légende grecque du roi Midas qui transformait en « or » tout ce qu’il touchait. Depuis sa création artificielle, l’électricité change en « or » les conditions d’existence de l’humanité en favorisant le progrès, par l’amélioration du confort des populations ou sa promotion et, par la stimulation des activités productives. Dans cette perspective, elle donne accès à la jouissance effective des droits fondamentaux en raison de son incidence sur l’alimentation, l’éducation, la santé, l’eau potable et l’assainissement, au travail, etc. Cette importance justifie le fondement juridique, notamment constitutionnel, que la République du Niger a attribué à son développement. Pour atteindre les objectifs de souveraineté énergétique et d’accès universel à l’énergie, une volonté politique ferme des pouvoirs publics, ainsi que le soutien des partenaires techniques et financiers, sont nécessaires. Cependant, elle requiert autant, sinon davantage, l’expansion de l’électricité, comme forme d’énergie unique. Ce besoin d’expansion concentre la réflexion sur les conditions et moyens ; il éprouve l’exercice des pouvoirs et des droits. Cette thèse africaine pour les africains repose sur une démarche du droit vivant, celle qui réintègre le droit dans son environnement, en mêlant de nombreuses disciplines juridiques (voire non juridiques comme la science économique ou politique). L’auteur soutient que le cadre juridique de l’expansion de l’électricité en tant que condition du développement économique et social est riche, mais néanmoins perfectible. Il souligne deux aspects complémentaires. Il observe d’abord que les responsabilités de souveraineté de l’État sont préservées dans la détermination des options énergétiques et le contrôle du sous-secteur de l’électricité. Il montre ensuite que la République du Niger a fait le choix de promouvoir l’initiative privée qui s’inscrit dans les cadres du service public et de l’autonomie individuelle.
Keywords: Action (Public-Private); Action (publique-Privée); Autonomie (énergétique); Distribution; Développement durable; ENERGIE (ACCES); Niger; Politique énergétique; Populations; Populations (access to essential service for); Réseaux électriques (énergie); Self-Sufficiency (energy); Service essentiel (accès); Souveraineté energétique; Sustainable development; Électricité

Limites e desafios do plano de recuperação judicial alternativo de credores - Garcia, Carlos Alberto Junqueira de Andrade (Universidade de São Paulo, 2024)
Esta dissertação tem como objetivo analisar, de forma aprofundada, os principais limites e desafios do plano de recuperação judicial alternativo, cuja legitimidade de apresentação é dos credores e subsidiária à do devedor, instrumento que foi introduzido nas recuperações judiciais apenas recentemente, por meio das alterações promovidas pela Lei no 14.112/2020 na Lei no 11.101/2005 (legislação de insolvência empresarial brasileira). Inicialmente, será explorado o contexto e os motivos que levaram o legislador pátrio a substituir o Decreto-Lei no 7.661/1945, regramento de insolvência que vigeu no Brasil por quase 60 (sessenta anos), por um novo modelo de reestruturação empresarial com natureza e objetivos completamente distintos. Serão feitas, então, breves considerações sobre os processos que sucederam a concordata, a recuperação extrajudicial e a recuperação judicial, destacando o fato de que foi por meio desta última que se recuperou a primazia da negociação, e os credores passaram a ser os principais responsáveis por decidir o destino da empresa em crise. Será feita, então, a análise do plano de recuperação judicial, principal documento e objetivo primário do processo, sua natureza jurídica, conteúdo obrigatório, liberdade de meios de reestruturação, procedimento para a sua aprovação e os limites que devem ser observados. Traçados os seus contornos principais, adentrar-se-á no estudo da sua modalidade alternativa, que pode ser apresentada pelos credores apenas de forma subsidiária e em determinada situações, que serão enfrentadas. Feito isso, serão investigados os limites do plano alternativo de credores que, além dos próprios limites que já incidem sobre o plano do devedor (uma vez que se altera apenas a legitimidade para a sua apresentação), outros específicos que devem igualmente ser observados quando de sua apresentação. Além disso, será demonstrado que, além dos limites legais, existem, ainda, diversos outros desafios de ordem prática que limitam a aplicação dos planos alternativos, especialmente diante das lacunas legais existentes, fazendo com que a sua aplicação prática permaneça ainda restrita, e muito aquém do que foi idealizado pelo legislador. Por fim, considerando que os planos alternativos são um importante instrumento que pode viabilizar a apresentação de propostas melhores pelos devedores (sob pena de ser-lhes imposto um plano de cuja elaboração não participou e cujo conteúdo muito provavelmente não concordará) e tornar mais céleres os processos de recuperação judicial, melhorias na legislação são imprescindíveis, e são feitas sugestões que podem servir como esboço para tanto. This dissertation aims to analyze, in depth, the main limits and challenges to the alternative judicial plan of reorganization, whose presentation legitimacy belongs to the creditors and is subsidiary to the debtor\'s, an instrument that was introduced in judicial reorganizations only recently, through the amendments promoted by Law No. 14,112/2020 in Law No. 11,101/2005 (Brazilian corporate insolvency legislation). Initially, it will be explored the context and reasons that led the Brazilian legislator to replace Decree-Law No. 7,661/1945, an insolvency rule that was in force in Brazil for almost 60 (sixty years), with a new model of business restructuring with a completely different nature and objectives. Brief considerations will then be made on the processes that succeed concordata, extrajudicial reorganization and judicial reorganization, pointing out the fact that it was through the latter that the primacy of negotiation was regained, and creditors became the main responsible for deciding the fate of the company in crisis. An analysis will then be made of the judicial reorganization plan, the main document and primary objective of the reorganization process, its legal nature, mandatory content, freedom of restructuring means, procedure for its approval and the limits that must be observed. With its main contours pointed out, its alternative modality will then be studied, which can be presented by creditors only in a subsidiary way and in certain situations, which will be analyzed. Once this is done, other specific limits to the creditors alternative plan of reorganization will be investigated, in addition to the limits that already affect the debtor\'s plan (since only the legitimacy for its presentation changes). Furthermore, it will be demonstrated that, in addition to legal limits, there are also several other practical challenges to the alternative plans of reorganization that restrict their application, especially given the existing legal gaps, which is yet far lower than what was idealized by legislator. Finally, considering that alternative plans are an important instrument that can force debtors to present better proposals (under penalty of being imposed a plan that they did not elaborate and whose content they most likely will not agree with) and optimize the judicial reorganization processes, improvements in legislation are essential, and suggestions that can serve as an outline for this are made.
Keywords: Alternative plan; Challenges; Creditors plan; Desafios; Judicial reorganization; Judicial reorganization plan; Limites; Limits; Plano alternativo; Plano de credores; Plano de recuperação judicial; Recuperação judicial

Protection des œuvres littéraires et artistiques dans l'environnement numérique dans l'espace OAPI - Ouedraogo, Peingdeweindé Jean (Université Lumière Lyon 2, 2024)
Les technologies de l’information interrogent la propriété littéraire et artistique de façon permanente. Chaque changement technologique entraine d’importantes répercussions dans la manière de protéger les œuvres culturelles. C’est ainsi qu’avec le développement du numérique des années 2000, plusieurs législations ont été mises à jour en commençant par le droit international. L’accord de Marrakech adopté par l’OMC le 15 décembre 1994 et les deux traités de l’OMPI de 1996 à savoir le traité de l’OMPI sur le droit d’auteur et le traité de l’OMPI sur les interprétations et exécutions et les phonogrammes sont les fruits de ces mutations. Au niveau régional et national, on pourrait également citer le Digital Millénium Copyright Act de 1998 pour l’Amérique et la Directive européenne sur la société de l’information de 2001 pour ce qui est de l’Union Européenne. Tenant compte de ces changements au niveau international et dans les ordres juridiques voisins, le législateur africain a opéré une révision de l’Accord communautaire le 15 décembre 2015. Cette révision prend cependant insuffisamment en compte les préoccupations suscitées par la technologie numérique. L’exemple le plus emblématique est l’occultation des influences de l’Intelligence artificielle sur la propriété littéraire et artistique. Cette thèse vise donc à proposer des solutions pour parachever l’adaptation du droit OAPI de sorte qu’il soit à jour des standards internationaux et tienne compte des développements du droit régional dont la construction est initié par l’Union Africaine avec la mise en place de l’Organisation Panafricaine de la Propriété Intellectuelle. (OAPI). Cette étude touchant à la fois le droit matériel et le système institutionnel de l’OAPI a eu pour objectif de renforcer davantage la sécurité des intérêts des titulaires de droits et ceux des utilisateurs de leurs œuvres de sorte à rendre le cadre communautaire africain plus équilibré et sécurisé.
Keywords: AI; Acte de Bamako; Adaptation; African Regional Intellectual Property Organization; Afrique; Artificial Intelligence; Bamako Act; Copyright; CyberSpace; Cyberspace; Droit d’auteur; Inteligência artificial; Intellectual property; Intelligence Artificielle; Internet; Organisation Panafricaine de la Propriété intellectuelle; Organisation africaine de la propriété intellectuelle; Pan-African Intellectual Property Organization; Propriété intellectuelle (droit international)

Les monnaies numériques dans le marché de la finance africaine - ERSUMA - OHADA (Ecole régionale supérieure de la Magistrature, 2024)

Les frontières de l'espace européen de sécurité en matière de données à caractère personnel : droit international et données personnelles - Gondolo, Jòan (Université Paris 1, 2024)
La présente thèse se situe à la croisée du droit international et du droit des données à caractère personnel. Elle se concentre sur le déploiement, dans l’espace, du droit européen des données à caractère personnel depuis les lois de première génération, jusqu’au RGPD. C’est en premier lieu la définition du champ d’application des textes relatifs aux données à caractère personnel qui interroge. Les critères de rattachement employés sont de moins en moins techniques et se concentrent désormais plutôt sur le responsable du traitement et la personne concernée. Les méthodes localisatrices traditionnelles du droit international qui sont remises en question. Plutôt, c’est à travers une approche fondamentale du droit des données à caractère personnel, que le droit international est mobilisé pour servir l’objectif substantiel d’assurer une protection effective de la personne concernée. La définition du champ d’application des textes se fait alors de manière large, unilatérale et extraterritoriale : elle démontre toute l’ambition de créer un espace européen de sécurité en matière de données à caractère personnel. L’ambition européenne interroge néanmoins quant à la capacité qu’ont l’Union et ses États membres à réaliser effectivement cet espace de sécurité. L’étude porte alors, en second lieu, sur la réalisation de l’espace de sécurité. Le droit international privé joue un rôle central par le recours direct de la personne concernée contre le responsable du traitement ou son sous-traitant. Ce recours soulève alors des questions relatives à la compétence des juridictions judiciaires et au droit national applicable. Si le RGPD traite de la première question, la seconde est passée sous silence. Plus largement, l’ambition européenne appelle des développements quant à la recherche d’efficacité des décisions européennes en contexte international. Nous analysons ainsi la manière dont le droit européen limite le recours à l’exécution des décisions administratives et judiciaires en dehors de l’Union mais aussi les mécanismes qu’il emploie quand une exécution hors du territoire de l’Union est nécessaire. Enfin, la relation complexe qu’entretiennent l’Union européenne et les États-Unis fait l’objet de développements spécifiques alors que les différents accords transatlantiques ont connu des échecs retentissants.
Keywords: Données personnelles; Données à caractère personnel; Droit européen; Droit international; Droit international privé; Extraterritorialité; Protection de l'information (informatique); RGPD

Product Liability in a More Circular Economy : A Study of Liability for Alternative Methods of Distributing and Producing Consumer Goods - Van Gool, Elias (Université de Lille, 2024)
Specific, more strict theories of product liability, which have now largely been maximally harmonised in the EU, have developed on the basis of a linear economic model. By using doctrinal and economic legal research, this thesis examines the state of EU product liability law and how it is tested by alternative, circular economic methods of distributing and producing consumer goods, like product reuse, repurposing, resales and other retransfers, repairs, refurbishments and remanufacturing. Besides direct relevance to circular economy in the consumer goods sector, this study of so-far overlooked questions offers new theoretical insights about product liability with broader academic and practical relevance. After a general introduction to the domains of product liability and circular economy, a normative framework is developed that blends distributive justice in terms of economic efficiency with corrective justice. Subsequently, it is argued that also in a more circular economic setting a more strict product liability rule like the EU harmonisation is preferable in light of this normative framework, while the added value of product liability increases compared to its main regulatory alternatives. The thesis then studies the application to the aforementioned circular strategies of current EU product liability law based on the 1985 Directive and its almost finally adopted 2024 successor. Overall, EU product liability law turns out to be quite versatile and its relevance in a more circular consumption sector is improved by several of the new proposed rules. Nevertheless, some limitations remain and also some interpretative issues are identified in the proposed new Directive, for which amendments are proposed. Les théories spécifiques et plus strictes de la responsabilité du fait des produits, qui ont maintenant été largement harmonisées au maximum dans l'UE, se sont développées sur la base d'un modèle économique linéaire. En utilisant la recherche doctrinale et économique en droit, cette thèse examine l'état du droit européen en matière de responsabilité du fait des produits et comment il est mis à l'épreuve par des méthodes économiques alternatives et circulaires de distribution et de production de biens de consommation, comme la réutilisation des produits, le réemploi, la revente et autres retransferts, les réparations, les reconditionnements et la refabrication. Outre une pertinence directe pour l'économie circulaire dans le secteur des biens de consommation, cette étude des questions jusqu'à présent négligées offre de nouvelles perspectives théoriques sur la responsabilité du fait des produits avec une pertinence académique et pratique plus large. Après une introduction générale aux domaines de la responsabilité du fait des produits et de l'économie circulaire, un cadre normatif est développé qui mélange la justice distributive en termes d'efficacité économique avec la justice corrective. Ensuite, il est soutenu que, même dans un cadre économique plus circulaire, une règle de responsabilité du fait des produits plus stricte comme l'harmonisation de l'UE est préférable à la lumière de ce cadre normatif, tandis que la valeur ajoutée de la responsabilité du fait des produits augmente par rapport à ses principales alternatives réglementaires. La thèse étudie ensuite l'application aux stratégies circulaires susmentionnées du droit actuel de l'UE en matière de responsabilité du fait des produits basé sur la Directive de 1985 et son successeur de 2024 presque adopté. Dans l'ensemble, le droit européen en matière de responsabilité du fait des produits se révèle assez polyvalent et sa pertinence dans un secteur de consommation plus circulaire est améliorée par plusieurs des nouvelles règles proposées. Néanmoins, certaines limitations subsistent et des questions d'interprétation sont également identifiées dans la nouvelle directive proposée, pour lesquelles des amendements sont proposés.
Keywords: Accidents; Accidents de biens de consommation; Biens d'occasion; Biens de consommation; Circular economy; Commerce d'occasion; Consommateur (protection); Consumer product accidents; Product liability; Produits d'occasion; Repair; Responsabilité (droit); Responsabilité du fait des produits; Responsabilité du fait des produits (droit européen); Responsabilité du fait des services; Reuse; Réparation; Réutilisation; Second-Hand; Économie circulaire

Limites à atuação do acionista controlador no regime de recuperação judicial - Dias, Laís Dumitrescu (Universidade de São Paulo, 2024)
Esta Dissertação examina a figura do acionista controlador à luz do contexto da recuperação judicial, com ênfase na legislação brasileira, especialmente a Lei no 11.101/2005, que regula a recuperação de empresas no Brasil. A recuperação judicial é um instrumento jurídico que visa viabilizar a superação de uma crise econômico-financeira da empresa devedora, garantindo a sua continuidade e preservação da função social. Ao mesmo tempo em que o acionista controlador mantém a sua posição de direito após o ajuizamento da recuperação judicial, essa nova situação em que a companhia se encontra poderá alterar de maneira substancial a forma e contornos do exercício do seu poder de controle, seja por força de disposições legais ou pelo surgimento de agentes externos que passarão a ter maior influência nos negócios da companhia, como a coletividade de credores. A fim de analisar as raízes por trás dessas interferências, a Dissertação parte inicialmente de uma investigação da evolução histórica do tratamento legal do acionista controlador no Brasil, tanto do prisma do direito societário quanto do direito falimentar. Em um segundo momento, o trabalho se debruça sobre os impactos específicos da recuperação judicial na atividade do acionista controlador, sempre em comparação entre o que se espera e se observa do comportamento do acionista controlador em situações normal da atividade da companhia. Por fim, serão apresentadas as conclusões extraídas do estudo. This work examines the figure of the controlling shareholder in the context of judicial reorganization, with an emphasis on Brazilian legislation, especially the Brazilian Bankruptcy Act n. 11,101/2005, which regulates the reorganization of companies in Brazil. Judicial reorganization is a legal instrument that aims to make it possible to overcome an economic and financial crisis of the debtor company, guaranteeing its continuity and preserving its social function. While the controlling shareholder retains its position after the filing of the judicial reorganization, this new situation in which the company finds itself can substantially alter the form and contours of the exercise of its power of control, either by virtue of legal provisions or by the emergence of external agents who will have greater influence on the company's business, such as the collectivity of creditors. In order to analyze the roots behind these interferences, the work begins by investigating the historical evolution of the legal treatment of the controlling shareholder in Brazil, both from the perspective of Corporate Law and Bankruptcy Law. Secondly, the work focuses on the specific impacts of judicial reorganization on the activity of the controlling shareholder, always comparing with what is expected and observed of the controlling shareholder's behavior in the company's normal activity. Finally, the conclusions drawn from the study will be presented.
Keywords: Acionista controlador; Controle externo; Controlling shareholder; Creditors; Credores; External control; Joint-stock company; Judicial reorganization; Poder de controle; Power of control; Recuperação judicial; Sociedade anônima

Optimisation du management stratégique et opérationnel de ligne maritime congolaise SA, entreprise publique commerciale en république démocratique du Congo (2019-2023) - Mupier Muka, Naomie (Université de Liège, 2024)
Les entreprises publiques congolaises ont fait l'objet de réformes en juillet 2008, car elles n'atteignaient pas les objectifs qui leur avaient été assignés en termes de contribution à l'économie nationale et de réponse aux problèmes sociaux de la communauté. Certaines ont été transformées en établissements publics ou en sociétés commerciales, tandis que d'autres ont été dissoutes et liquidées. Cependant, la question de l'orientation stratégique des sociétés commerciales publiques congolaises au regard de ces objectifs reste posée. Ces entreprises mettent-elles en place les outils de management stratégique nécessaires pour les atteindre ? Cette étude visait donc à analyser l'effectivité et la performance du management stratégique dans ce secteur, ainsi que son mécanisme opérationnel, en prenant le cas de l'entreprise LMC SA. Plusieurs outils techniques ont été utilisés, notamment l'analyse documentaire et des entretiens semi-directifs. Les résultats montrent un certain déficit dans la planification stratégique de ces entreprises, notamment au niveau de la gestion des ressources humaines, matérielles et financières. Sur la base de ces constats, l'étude formule quelques recommandations managériales : • Restructuration des prérogatives de l'organe de gouvernance ; • Réévaluation du capital humain et réduction des postes en trop ; • Allocation objective des ressources financières grâce à une démarche de benchmark.
Keywords: Entreprise publique commerciale; Management stratégique; République Démocratique du Congo

Beyond free trade in raw materials: Reconciling international trade rules with planetary boundaries - Kuppuswamy, Chamundeeswari; Boklan, Daria (The Extractive Industries and Society, 2024)
International trade rules enshrined in agreements like the General Agreement on Tariffs and Trade (GATT) promote free trade, with exceptions for environmental protection. This paper explores the tension between these rules and Earth Systems Science's concept of planetary boundaries, which define environmental tipping points beyond which humanity faces irreversible harm. We analyse GATT's provisions, particularly Article XI's prohibition on trade restrictions and Article XX's exceptions, through the lens of planetary boundaries. Our analysis argues that current interpretations of these articles are inadequate to address the environmental impact of raw material trade. We further examine the concept of permanent sovereignty over natural resources, which grants states autonomy over resource exploitation and trade. We posit that planetary boundaries are not a restriction on sovereignty but a call for modifying state trading behaviour and consequently how international trade rules is structured and interpreted. This analysis demonstrates the complexity of transforming the legal landscape necessary for a global just energy transition, a response to climate change that requires aligning international trade with environmental sustainability.
Keywords: Climate change; GATT Art. XX; No-harm principle; PSNR; Planetary boundaries; WTO trade rules

L'application extraterritoriale des sanctions économiques dans le commerce international - Abada-Fasquelle, Marjolaine (Université Paris 1, 2024)
La problématique des sanctions économiques extraterritoriales a pris une ampleur particulière depuis l’amende transactionnelle record versée par BNP Paribas pour violation des programmes de sanctions américains. En effet, avec cette affaire, l’extraterritorialité des sanctions économiques est devenue non seulement un sujet encore plus prégnant de la doctrine juridique, en particulier internationaliste, mais aussi un véritable enjeu économique et politique. Or de nombreuses incertitudes entourent le régime juridique des sanctions économiques extraterritoriales, que ce soit dans l’ordre international ou dans l’ordre interne. Cette étude a pour ambition d’apporter des réponses aux différentes questions soulevées par les sanctions économiques extraterritoriales, en mêlant droit positif et prospectif afin de préciser l’état de l’art, mais aussi d’ouvrir certaines pistes de réflexion. À travers une approche à la fois comparative et pluridisciplinaire, le sujet sera abordé sous deux angles : d’un côté, la licéité de l’application extraterritoriale des sanctions économiques et, de l’autre, l’impact de ces dernières sur le commerce international. Plus concrètement, l’étude repose sur une progression dans l’analyse qui consiste, après avoir défini les concepts, à étudier la licéité des sanctions économiques extraterritoriales, puis à mettre en lumière l’impact d’une telle pratique sur les opérateurs économiques et, enfin, à détailler les différentes solutions qui ont pu être proposées pour contrecarrer cette pratique et les effets qui lui sont associés. Cela étant, l’agression de l’Ukraine par la Russie a considérablement influé sur la teneur des débats. Ainsi, bien que l’UE n’ait pas officiellement changé de position vis-à-vis des sanctions extraterritoriales des États-Unis – qu’elle considère traditionnellement comme illicites au regard du droit international public –, elle a commencé elle-même à recourir à des mesures dont la portée pourrait être apparentée, mutatis mutandis, à de l’extraterritorialité. Dans ce contexte, cette étude entend donc finalement faire la jonction entre la perception des sanctions extraterritoriales ayant prévalu pendant plusieurs décennies et le changement de paradigme qui est en train de s’opérer. The issue of extraterritorial economic sanctions has become a matter of particular importance in the wake of the record settlement fine imposed upon BNP Paribas for violating US sanctions programs. This case has thus highlighted the necessity for further discussion and analysis within international legal doctrine, as the extraterritoriality of economic sanctions has also grown in significance as an economic and political issue. The legal framework of extraterritorial economic sanctions is replete with uncertainty, whether in international or domestic law. This study aims to address the multitude of questions surrounding extraterritorial economic sanctions by combining positive and prospective legal approaches. Hence, it ambitions to clarify the current state of the art while also opening paths of thought. The subject will be addressed through a comparative and multidisciplinary approach, examining two perspectives: firstly, the legality of the extraterritorial application of economic sanctions; secondly, the impact of the latter on international trade. The study is based on a progression in the analysis, which begins with the definition of the relevant concepts. It then examines the legality of extraterritorial economic sanctions, before highlighting the impact of such a practice on economic operators. Finally, it outlines the various solutions that have been submitted to counter this practice and the effects associated with it. However, the Russian aggression against Ukraine has had a considerable influence on the content of the debates. Indeed, although the EU has not formally revised its stance on US extraterritorial sanctions – which it traditionally deems unlawful under public international law – it has itself adopted measures whose scope could be seen as extraterritorial. In this context, this study will establish a connection between the perception of extraterritorial sanctions that prevailed over several decades and the paradigm shift that is currently underway.
Issue: 2024PA01D015
Keywords: Anti-circumvention mechanism; Anti-coercion instrument; Blocking statutes; Droit international public; Economic sanctions; Extraterritoriality; Extraterritorialité; Instrument anti-coercition; International public law; Lois de blocage; Mesures restrictives; Mécanisme anti-contournement; Restricitve measures; Sanctions économiques

La zone de libre-échange continentale africaine (ZLECAf) : une institution d’intégration éprouvée - Bipelé Kemfouedio, Jacques (Afrilex : Revue d’étude et de recherche sur le droit et l’administration dans les pays d’Afrique, 2024)
Inscrite depuis 2018 dans la galaxie des organisations d’intégration économique, la ZLECAf, qu’on pensait porteuse de tous les espoirs dans la construction du marché commun, reste éprouvée. A quelles épreuves cette institution est-elle confrontée ? La présente étude a conduit au résultat suivant lequel la ZLECAf, structure d’intégration continentale, reste confrontée à des épreuves de double nature. Ainsi, aux épreuves endogènes caractérisées par le déficit d’un développement harmonieux et la récurrence des atteintes à la paix ainsi qu’à la sécurité, s’ajoutent les épreuves exogènes marquées par l’influence inhibitrice des pouvoirs économiques transnationaux et la perpétuation perverse des rapports de domination entre les institutions internationales et les Etats membres de la ZLECAf. Ces différentes limites ont pour implication le caractère dérisoire et fantomatique des stratégies d’intégration continentale. L’étude débouche sur de nouvelles pistes susceptibles de contribuer à la consolidation du processus d’intégration économique continentale. Part of the galaxy of economic integration organisations since 2018, the AfCFTA, which was thought to be the bearer of all hopes for the construction of a common market, is still being tested. What are the difficulties facing this institution? This study has led to the conclusion that the AfCFTA, a continental integration structure, continues to face two types of difficulties. In addition to endogenous difficulties, characterised by the lack of harmonious development and the recurrence of breaches of peace and security, there are exogenous difficulties marked by the inhibiting influence of transnational economic powers and the perverse perpetuation of relations of domination between international institutions and the member States of the AfCFTA. The implication of these various limitations is that continental integration strategies are derisory and ghostly. The study suggests new avenues that could help consolidate the process of continental economic integration.
Keywords: AfCFTA; Common market; Continental economic integration; Endogenous difficulties; Epreuves endogènes; Epreuves exogènes; Exogenous difficulties; Intégration économique continentale; Marché commun; ZLECAf

Intégration de la RSE en droit OHADA au travers des codes de gouvernement d’entreprise : pour un changement de paradigme - Byaombe Malumalu, Christian; Nzohabonayo, Anaclet (Revue africaine de droit des affaires, 2024)
La RSE peut s'immiscer en droit des sociétés OHADA au travers des codes de gouvernement, pourvu qu'ils adoptent un changement de paradigme ou de la vision dominante limitée à l'organisation des relations entre les actionnaires et les dirigeants sociaux. Or, pour intégrer les enjeux de la RSE, ces codes doivent élargir leur champ aux différentes parties prenantes à la vie de l'entreprise, notamment des salariés, clients, fournisseurs, créanciers, populations locales et l'État. Un tel changement de paradigme peut se fonder sur la conception mixte de l'intérêt social et la récente consécration du reporting extrafinancier dans l'espace OHADA. Ceci implique par ailleurs que les organisations représentatives des entreprises fassent participer les parties prenantes, en amont, au processus d'adoption et en aval, au contrôle d'application de codes de gouvernement d'entreprise à travers, par exemple, un comité RSE ou ESG.
Keywords: CSR; Gouvernement d'entreprise; RSE

Le devoir de vigilance de l’entreprise sociétaire - Cisse, Issiaka (Revue africaine de droit des affaires, 2024)
L’environnement de l’entreprise sociétaire connaît de nouvelles mutations juridiques. Celles-ci sont le témoin de la juridicité des actions moralisatrices des sociétés commerciales. De toute évidence, la nécessité d’élaborer un plan de vigilance se révèle comme un moyen de protection contre les atteintes éventuelles de l’activité sociétaire. Un tel élan juridique connait au passage tout un processus avant de révéler toute sa portée en droit africain OHADA.

La propriété privée en droit foncier malien - Diabaté, Alhousseini (Afrilex : Revue d’étude et de recherche sur le droit et l’administration dans les pays d’Afrique, 2024)
Le législateur malien a construit un régime de la propriété privée, à partir des principes hérités du modèle australien et du Code civil français. Cependant, tout en charriant cet héritage, il a tracé son propre chemin pour parvenir à un régime de la propriété foncière prenant en compte ses propres réalités et surtout ses impératifs de développement économique. Le titre foncier, dérivé du système australien, est la clé de voûte de la protection de la propriété privée en droit foncier malien. Lorsqu’il est régulièrement établi, il confère un droit de propriété avec les attributs de l’article 544 du Code civil français. Mais dans ce régime, la mise en valeur économique de la terre est à la fois la condition d’accès et du maintien du droit de propriété. La propriété privée est ainsi redéfinie à partir d’un critère économique : « le droit de jouir et de disposer des choses de la manière la plus absolue, pourvu qu’on n’en fasse pas un usage prohibé par la loi, ou par les règlements, et sous réserve d’une mise en valeur conforme aux objectifs de développement économique ». Malian lawmakers have built a private property regime based on principles inherited from the Australian model and the French Civil Code. However, while carrying this heritage with it, it has charted its own course to achieve a system of land ownership that takes account of its own realities and, above all, its economic development imperatives. The land title, derived from the Australian system, is the cornerstone of the protection of private property in Malian land law. When properly established, it confers a right of ownership with the attributes of article 544 of the French Civil Code. However, under this system, the economic development of the land is both a condition of access and a condition for maintaining ownership rights. Private property is thus redefined on the basis of an economic criterion: «the right to enjoy and dispose of things in the most absolute manner, provided that no use is made of them that is prohibited by law or by regulations, and provided that they are developed in accordance with economic development objectives».
Keywords: Droit foncier; Développement économique; Economic development; Land law; Mali; Private property; Propriété privée

La souscription ou rachat d’actions par la société (achat de ses propres actions) - Dolo, Anidjou; Coulibaly, Alou; Diallo, Hamadi; Dakouo, Jacques Mawé (Revue des Réflexions Constitutionnelles : Revue mensuelle de publication en droit constitutionnelle, 2024)
Le problème du rachat par les sociétés de leurs propres actions est une question classique du droit des sociétés qui fait l’objet d’un regain d’actualité. En effet, une société peut-elle devenir son propre actionnaire ? Il s’agit là d’une question paradoxale. C’est pourtant celle que pose l’achat par une société de ses propres actions. L’opération est en effet curieuse, puisque l’établissement émetteur ou la société émettrice se comporte à l’égard de ses propres titres comme un tiers. Indiscutablement, l’opération est dangereuse. Elle l’est, tout d’abord, pour la société elle-même. Elle l’est également pour les créanciers, lorsqu’une partie du capital a servi à financer l’opération qui s’analyse alors comme une diminution de fait du capital, non assortie de garanties au profit des tiers. Elle l’est, enfin, pour les associés. The problem of companies repurchasing their own shares is a classic question of corporate law which is the subject of renewed relevance. Indeed, can a company become its own shareholder? This is a paradoxical question. However, itis the problem posed by the purchase by a company of its ownshares. The operation is indeed curious, since the issuing institution or the issuing company behaves with regard to its own securities like a third party. Unquestionably, the operation is dangerous. It is, first of all, for society itself. It is also for creditors, when part of the capital was used to finance the operation which is then analyzed as a de facto reduction in capital, not accompanied by guarantees for the benefit of third parties. It is, finally, for the partners.
Keywords: Capital (diminution); Capital (reduction); Ownshares; Propres actions; Rachat; Repurchase; Transaction dangereuse

Product Liability in a More Circular Economy : A Study of Liability for Alternative Methods of Distributing and Producing Consumer Goods - Gool, Elias van (Université de Lille ; Katholieke Universiteit Leuven, 2024)
Specific, more strict theories of product liability, which have now largely been maximally harmonised in the EU, have developed on the basis of a linear economic model. By using doctrinal and economic legal research, this thesis examines the state of EU product liability law and how it is tested by alternative, circular economic methods of distributing and producing consumer goods, like product reuse, repurposing, resales and other retransfers, repairs, refurbishments and remanufacturing. Besides direct relevance to circular economy in the consumer goods sector, this study of so-far overlooked questions offers new theoretical insights about product liability with broader academic and practical relevance. After a general introduction to the domains of product liability and circular economy, a normative framework is developed that blends distributive justice in terms of economic efficiency with corrective justice. Subsequently, it is argued that also in a more circular economic setting a more strict product liability rule like the EU harmonisation is preferable in light of this normative framework, while the added value of product liability increases compared to its main regulatory alternatives. The thesis then studies the application to the aforementioned circular strategies of current EU product liability law based on the 1985 Directive and its almost finally adopted 2024 successor. Overall, EU product liability law turns out to be quite versatile and its relevance in a more circular consumption sector is improved by several of the new proposed rules. Nevertheless, some limitations remain and also some interpretative issues are identified in the proposed new Directive, for which amendments are proposed. Les théories spécifiques et plus strictes de la responsabilité du fait des produits, qui ont maintenant été largement harmonisées au maximum dans l'UE, se sont développées sur la base d'un modèle économique linéaire. En utilisant la recherche doctrinale et économique en droit, cette thèse examine l'état du droit européen en matière de responsabilité du fait des produits et comment il est mis à l'épreuve par des méthodes économiques alternatives et circulaires de distribution et de production de biens de consommation, comme la réutilisation des produits, le réemploi, la revente et autres retransferts, les réparations, les reconditionnements et la refabrication. Outre une pertinence directe pour l'économie circulaire dans le secteur des biens de consommation, cette étude des questions jusqu'à présent négligées offre de nouvelles perspectives théoriques sur la responsabilité du fait des produits avec une pertinence académique et pratique plus large. Après une introduction générale aux domaines de la responsabilité du fait des produits et de l'économie circulaire, un cadre normatif est développé qui mélange la justice distributive en termes d'efficacité économique avec la justice corrective. Ensuite, il est soutenu que, même dans un cadre économique plus circulaire, une règle de responsabilité du fait des produits plus stricte comme l'harmonisation de l'UE est préférable à la lumière de ce cadre normatif, tandis que la valeur ajoutée de la responsabilité du fait des produits augmente par rapport à ses principales alternatives réglementaires. La thèse étudie ensuite l'application aux stratégies circulaires susmentionnées du droit actuel de l'UE en matière de responsabilité du fait des produits basé sur la Directive de 1985 et son successeur de 2024 presque adopté. Dans l'ensemble, le droit européen en matière de responsabilité du fait des produits se révèle assez polyvalent et sa pertinence dans un secteur de consommation plus circulaire est améliorée par plusieurs des nouvelles règles proposées. Néanmoins, certaines limitations subsistent et des questions d'interprétation sont également identifiées dans la nouvelle directive proposée, pour lesquelles des amendements sont proposés.
Issue: 2024ULILD015
Keywords: Accidents de biens de consommation; Biens d'occasion; Circular economy; Consumer product accidents; Product liability; Repair; Responsabilité du fait des produits et du fait des services; Reuse; Réparation; Réutilisation; Second-Hand; Économie circulaire

La préservation de l’éthique dans la titularité des droits sur les créations intellectuelles des salariés en droit OAPI - Kanchop, Thierry Noël (Revue africaine de droit des affaires, 2024)
La titularité des droits sur les créations intellectuelles des salariés est un terreau fertile pour les pratiques contraires aux valeurs éthiques ; et pour cause, le droit du travail et le droit de la propriété intellectuelle ne poursuivent pas en principe les mêmes objectifs. D’ailleurs, une question fondamentale a de tout temps jalonné la rencontre du droit du travail et de la propriété intellectuelle : celle de savoir qui sera titulaire des droits qui découleraient des créations intellectuelles réalisées par un salarié. La logique économique voudrait que la réponse soit en faveur de l’employeur, le salarié étant rémunéré dans le cadre de son contrat de travail. Cependant, cette logique économique est loin de correspondre à la réalité du régime juridique de la titularité des droits sur ces créations de salariés. De plus, il existe au sein du droit de la propriété intellectuelle deux régimes bien distincts qui ne concilient pas les mêmes intérêts : celui du droit d’auteur qui, par la prépondérance de sa nature personnaliste, a tendance à favoriser l’auteur ; et le régime de la propriété industrielle qui a plutôt pour but d’inciter les entreprises à investir dans la recherche. En optant pour une optimisation de la conciliation entre les divers intérêts en présence, le législateur OAPI entend préserver l’éthique dans la titularité des créations intellectuelles des salariés. À la question de savoir quels sont les mécanismes mis en œuvre par le législateur OAPI pour préserver cette éthique, il faut retenir que le législateur OAPI garantit cette éthique en procédant à une régulation tant légale que conventionnelle de l’influence du lien de subordination sur la titularité de telles créations.

La loyauté en droit bancaire français - Ketcheuzeu Nana, Soline (Revue africaine de droit des affaires, 2024)
L’éthique des affaires est au cœur des préoccupations contemporaines. Elle varie selon les disciplines et selon les époques, mais certaines de ses valeurs telles l’intégrité, la loyauté sont considérées comme universelles. Dans le domaine commercial, l’éthique met l’accent sur la transparence, l’intégrité et la priorité donnée aux intérêts du client. L’éthique a progressivement imprégné le droit bancaire à travers l’une de ses déclinaisons, qu’est la loyauté. Cette dernière se manifeste à travers les obligations d’information, de conseil et de mise en garde adaptées à chaque situation. La loyauté s’exprime aussi à travers le secret professionnel. Elle vise donc la protection des clients. Cependant, la banque mérite de voir sa liberté contractuelle préservée tout en garantissant la sécurité des contrats bancaires. C’est cet équilibre difficile à trouver qui rend complexe l’application de la loyauté en droit bancaire. Ainsi, est-il important pour les banques de repenser des techniques permettant de rendre aisée, la pratique de la loyauté et d’améliorer la traçabilité du respect de l’obligation de loyauté.

L’intérêt social à l’épreuve des normes éthiques en droit OHADA des sociétés commerciales - Ligan, Cyrille Sèmako (Revue africaine de droit des affaires, 2024)
En droit des affaires OHADA, le droit des sociétés ne semble pas être la discipline la plus friande des valeurs éthiques. L’objectif avoué, égoïste et trivial, de la société commerciale est de permettre à ses associés de partager les profits issus d’entreprises communes. L’intérêt social aurait ainsi pour fil conducteur une recherche forcenée et effrénée du profit qui ne considère pas l’éthique ou s’en méfie. Le constat à dresser devrait donc être très sombre, puisqu’on aurait affaire à un droit anéthique. Mais la réalité se révèle différemment, et le tableau s’éclaire lorsqu’on aborde certaines dispositions de l’Acte uniforme relatif au droit des sociétés commerciales et des groupements d’intérêt économique ainsi que leurs applications jurisprudentielles. En clair, la trivialité manifeste dans la poursuite de l’intérêt social doit être nuancée, car elle s’accommode parfaitement de normes éthiques. Cet accommodement semble toutefois limité et invite à une révision de la définition de l’« intérêt social » en droit OHADA des sociétés commerciales afin d’y intégrer les enjeux humanitaires et environnementaux, vecteurs de normes éthiques.

TIC et éthique en droit des sociétés commerciales OHADA - Looha Bongue Sosso, Stéphane (Revue africaine de droit des affaires, 2024)
L’éthique est en perpétuelle quête de repères. Elle a révolutionné le management des entreprises et amélioré leur efficacité. Le législateur OHADA l’a mise au cœur de la gestion des sociétés commerciales, en instituant des mécanismes d’amélioration continue. Cette approche durable s’est accentuée dans un contexte interconnecté et ultra-concurrentiel où une crise de légitimation des règles éthiques, combinée à un usage tous azimuts des TIC, impacte la gouvernance d’entreprise. En effet, plus l’outil technologique augmente son impact sur la société, plus les problèmes éthiques s’accroissent davantage du fait de nouvelles opportunités d’actions. Pour y remédier, l’usage légal et rationnel des TIC peut désormais servir à améliorer les formes d’expression de l’éthique, tandis qu’un usage éthique des TIC est requis.

L’éthique des affaires et l’actionnaire des sociétés OHADA - Ngodobo, Denis (Revue africaine de droit des affaires, 2024)
Existe-t-il un Acte uniforme relatif à l’éthique des affaires en droit de l’organisation pour l’harmonisation en Afrique du droit des affaires ? L’éthique des affaires mériterait un encadrement normatif en droit OHADA pour un développement a priori de l’entreprise du marché et a postériori de la sécurité juridique des investissements. Cet encadrement juridique visera à prescrire des devoirs qui assainiront les comportements des acteurs, et en particulier l’actionnaire des sociétés OHADA. En droit positif OHADA, les règles éthiques visant l’actionnaire sont éparses et d’application restrictive, d’où l’impasse. La nécessité d’explorer le droit des contrats et le droit des sociétés pour l’extraction d’un contenu normatif s’impose. Cet exercice heuristique vise à aider le législateur, seulement pour ce qui concerne l’actionnaire des sociétés, à l’élaboration d’une normativité de l’éthique des affaires.

Libre propos sur l’éthique dans la gouvernance de l'entreprise coopérative OHADA - Okomen Tsague, Renaud Etiennis (Revue africaine de droit des affaires, 2024)
Plus d’une décennie après adoption de l’acte uniforme marquant le point de départ du nouveau droit coopératif OHADA, il apparaît opportun de questionner la dimension éthique inhérente à la gouvernance des sociétés coopératives ; à l’effet d’en mesurer la prise en compte dans l’espace OHADA. D’où la question de savoir : quelle appréciation peut-on faire de la prise en compte de l’éthique dans la gouvernance de l’entreprise coopérative dans l’espace juridique OHADA ? Répondant à cette question, au demeurant très intéressante pour envisager l’avenir ou le devenir de l’entreprise coopérative à l’ère de la globalisation économique et de la révolution technologique, cette réflexion suggère loin de toute réaction euphorique, une attitude circonspecte dans l’appréciation de la prise en compte de la dimension éthique dans la gouvernance de la société coopérative. En effet, l’occasion donnée de prendre la mesure de la mise en œuvre de l’éthique dans la gouvernance de la coopérative OHADA laisse entrevoir un ancrage indéniable de l’éthique dans la gouvernance de la coopérative OHADA. Mais au-delà de ces considérations textuelles, les contraintes contextuelles permettent d’envisager de possibles relâchements des exigences éthiques sur le sentier de la recherche du juste équilibre entre efficacité économique et observance des valeurs et principes coopératifs.

The role and liability of internet service providers in South Africa : a critical and comparative appraisal - Nameka, Celeste Zara (University of South Africa, 2024)
This research uses a comparative approach to explore the role and liability of internet service providers in South Africa. The research aims to analyse and compare the role and liability of internet service providers for crimes and civil infractions committed by content providers and/or internet users. Against this aim, the researcher argues that internet service providers, as intermediaries, are ideally placed to monitor and control illicit content provision and/or internet use by the end user. The research focuses on South Africa, China, Ireland, and Nigeria. The research interrogated legislative control and queried the fitness for purpose of these mechanisms for internet service providers and the lacunae created by a rapidly expanding digital world comparatively. The research points out recurrent controversial and problematic concerns that affect both the internet service provider and the consumer. The researcher further explores challenges in applying legal imperatives to internet service providers that affect their end users. The comparative analysis assists in indicating how internet service providers operate in practice and their control (or lack thereof) by various legal frameworks. The researcher makes recommendations and offers solutions to assist with the future role and development of internet service providers and their impact on the end-user and criminal justice system.

Anticipation of ratings during crises and investor behaviour: The case of MENA countries - Mahouachi, Noura; Henchiri, Jamel Eddine (African Journal of Economic and Business Research, 2024)
The study explores the reaction of stock markets to anticipated or unexpected rating announcements by the market in a crisis context by conducting an empirical study on the MENA (Middle East and North Africa) stock market over the period from December 2010 to August 2022. The results show that the crisis context support the anticipation of bad ratings and neutral ratings as opposed to good ratings. These results validate the asymmetry in investor reaction to announcements of anticipated rating downgrades compared with announcements of upgrades in times of crisis. This reaction highlights the irrational behave of investors in times of crisis. In fact, when investors detect a risk concerning the financial situation of a stock, they anticipate a downgrade and react quickly, even before the official announcement of the downgrade, by selling their shares on masse. This action will cause the share price to fall. Similarly, the market’s weak reaction to early good announcements is explained by the fact that this type of announcement does not provide them with any unknown information to guide their financial decisions.
Keywords: Abnormal returns; Anticipation; Event study; Expected rating; Stock markets; Unexpected rating

The Impact of Financial Technology (Fin Tech) on Economic Growth: Evidence from Tanzania - Ngeze, Raphael Michael; Seif, Muba (African Journal of Economic and Business Research, 2024)
This research is driven by the rapid spread of fintech, and its contributions to Tanzania’s economic growth. This study uses quantitative quarterly time series data from Tanzania from 2008 to 2022. The Augmented Dicky Fuler (ADF) is used for the stationarity test, Johansen Cointegrations for the hypothesis and Cointegrations test, VAR and VECM for testing both short-run and long-run causality relationships, and Granger Causality for testing variable causality. The Ordinary Least Squares (OLS) regression model is used for parameter estimation, modelling and significance testing. The results show that the model is statistically significant and the independent variables in the regression accounted for around 89% of the overall variation in GDP. Fintech variable subscriptions have a positive impact on Tanzania’s economic growth. Thus, unemployment in Tanzania may be alleviated by the growing sector of financial technology. Fintech has involved many people from all over the world, including Tanzania, and has had a positive impact on both the national economy and per capita growth. Since TTCL and ZANTEL have witnessed a sharp decline in subscriptions, the government, as a fixed-wired broadband service provider, must take the necessary steps to increase the subscriptions.
Keywords: Economic growth; Financial Technology; M-Pesa; OLS; VAR; VECM

Effect of Taxpayer’s Attitudes on Tax Evasion among SMEs in Tanzania: A Case of Singida Tax Region - Chindengwike, James (African Journal of Economic and Business Research, 2024)
Paying taxes is essential to attaining sustainable economic growth and national economic independence, hence tax evasion is a concern for the economies of both wealthy and developing countries. This study examined how tax payer attitudes, particularly in the Singida Tax Region, affect tax evasion in Tanzanian Small and Medium-Sized Enterprises (SMEs). This study employed a survey method in which data collection comprised both qualitative and quantitative research approaches. A multiple regression model was employed in combination with a descriptive study approach to ascertain the outcomes. 145 SMEs taxpayers made up the study's as a sample size. The findings demonstrate that, among SMEs in the Singida Region, peer influence, tax awareness, tax morale, and tax evasion have statistically significant relationships with the taxpayer's attitude. This association is supported by statistics. Consequently, the United Republic of Tanzanian government needs to consider how taxpayer attitudes including peer pressure, tax knowledge, and morale affect tax evasion. This will contribute to the goal of reducing tax avoidance by all taxpayers, including SMEs Taxpayers.
Keywords: SMEs Taxpayers; Tanzania; Tax evasion; Taxpayer’s Attitudes

Facilitating Trade through Rules of Origin: A Consideration of the African Continental Free Trade Area - Okoroma, Blessing Ijeoma (University of Calgary, 2024)
Rules of origin play a pivotal role in free trade agreements. Apart from serving as a tool to distinguish goods by determining the nationality of a product, rules of origin have the capacity to increase trade relations or deter it. Of course, it is the hope of any viable state to increase profitable trading relations, and if rules of origin can help with that, it becomes expedient to fully understand how these rules of origin operate. In Africa, we see rules of origin being implemented amongst the Regional Economic Communities (RECs), but this has come with many struggles. In fact, low intra-African trade can be narrowed down to complex rules of origin regimes deployed in regional agreements in Africa. As of date, the major RECs have each implemented different rules of origin, leading to the co-existence of conflicting rules of origin across Africa. This non-uniformity in the rules of origin regimes in Africa has resulted in low continental trade in Africa. As such, these RECs have not yielded the expected increase in intra-African trade. With the creation of the African Continental Free Trade Area (AfCFTA), which currently doubles as the latest and largest FTA in Africa, it is expected that better rules of origin will be deployed to mitigate the existing intra-African trade deficits. This thesis thus deploys a doctrinal approach in determining whether AfCFTA’s rules of origin are positioned to achieve greater intra-African trade. Consequently, this thesis uncovers some lapses in AfCFTA’s rules of origin and calls for harmonization of all the rules of origin in Africa and recommends a possible amendment to Article 19 of the Agreement establishing AfCFTA to accommodate the intended harmonization.
Keywords: African Continental Free Trade Area; Free Trade Area; Rules of Origin

Selected legal aspects of money-laundering control in trade-finance instruments - Makuyana, Tsanangurai (University of South Africa, 2024)
The traditional perception that trade-finance instruments are less susceptible to the risk of money laundering has changed due to the increasing threat of trade-based money laundering (TBML). In the process of facilitating trade-finance transactions, financial institutions may be entrapped in the dangers of TBML and be abused for criminal gains. In this regard, the institutions play a significant role in ensuring that only legitimate trade is facilitated through trade finance without being tainted by TBML. Despite that, vulnerabilities for the vice have been discovered in the trade-finance sector. This study employs a macro-comparative approach in examining how selected jurisdictions respond to the problem of TBML in trade-finance instruments. It analyses the vulnerabilities of documentary credits, documentary collections, demand guarantees and standby letters of credit to the potential risk of TBML. The thesis compares the response of the South African AML regime with that of the English, the US and Singapore AML regimes to the threat of TBML in the selected trade-finance instruments. The study reveals, inter alia, that there is not much difference between the South African AML regime and the AML regimes of the comparative jurisdictions in terms of the legislative response to the challenge of TBML in trade-finance transactions. However, the difference is apparent when it comes to the varied institutional responses to the problem within the jurisdictions considered in this thesis. While South African AML authorities have not made any official pronouncement against TBML in trade finance, those from other comparative jurisdictions have done so. The latter have also gone a step further to produce best practice reports on TBML for banks and other financial institutions involved in trade-finance transactions to enable the institutions to prepare for the challenge. However, similar to the South African position, there has not been any legislative change in the comparative jurisdictions to provide for TBML in specific terms. This means that these jurisdictions also deal with TBML using current AML legislation, which was designed originally for cash-based money-laundering operations. Therefore, the institutions and laws under the South African AML regime are relevant in the combatting of TBML. However, they may require some modifications to appropriately counter the challenge. The study makes various policy and best practice recommendations to strengthen the South African AML regime against TBML in trade-finance transactions.
Keywords: AML Regime; Bankers Association for Finance and Trade; Black Market Peso Exchange; Customer Due Diligence; Demand Guarantees; Documentary Collections; Documentary Credits; English AML Regime; FinCEN; Financial Action Task Force; Financial Intelligence Centre Act 38 of 2001; Financial Intelligence Unit; International Best Practices; International Chamber of Commerce; International Trade; Money Laundering; Money-Laundering Control; Prevention of Organised Crime Act 121 of 1998; RBA; Red-Flag Indicators; SAMLIT; Singapore AML Regime; South African AML Regime; Standby-Letters of Credits; TBML; Trade Finance; Trade-Based Money Laundering; Trade-Finance Instruments; Trade-Finance Principles; Trade-Finance Transactions; US AML Regime; World Customs Organisation; the Wolfsberg Group

African Continental Free Trade Area and Regional Trade in ICT and Digital Technologies - Adams, Kweku; Attah-Boakye, Rexford; Yu, Honglan; Chu, Irene; Mali, Dafydd (Journal of International Management, 2024)
This study examines the impact of the African Continental Free Trade Area (AfCFTA) on regional trade in the Information and Communication Technology (ICT) and Digital Technologies (DT) sector across 43 African countries from 2014 to 2021. Employing the augmented gravity model and confidence-level estimations, it highlights AfCFTA's mediating role in enabling ICT&DT trade on the continent. Using hierarchical regression analysis of a panel dataset comprising 5,160 observations, the findings imply that trade openness and productive capacities not only facilitate trade in the ICT&DT sector but also result in positive spillover effects across various economic sectors. This study contributes to the international business literature by refining the application of the gravity model to capture the need for sector-specific analyses to unpack institutional dynamics and dis-enablers of trade. It identifies AfCFTA as a pivotal yet underexplored element in the global trade landscape, highlighting its potential as Africa seeks a more prominent role on the global stage. The research stresses the significance of digital empowerment and policy reforms to maximise the benefits of regional integration under AfCFTA.
Keywords: AfCFTA; ICT and digital technologies; Regional trade; Trade enablers; Trading bloc

Joint and several liability at the interface of national and international law and the FIDIC conditions of contract - Mahasneh, Nisreen (Uniform Law Review, 2024)
The international terms of the 2017 FIDIC Red Book (reprinted and amended in 2022) state that, when the contractor is a joint venture (JV), all members are jointly and severally liable to the employer. These terms also establish certain procedural rules—the most important ones being the submission to the employer of the JV undertaking and the appointment of a leader. However, these international terms do not provide for substantive rules pertaining to the plurality of the JV members. These require reference to the applicable law that governs the construction contract. The applicable law can be domestic law, such as Qatari law, or an international soft law, such as the Unidroit Principles. Comparing these two possibly applicable laws, it becomes evident that there are no significant differences between the two regarding the substantive rules concerning a plurality of obligors. Furthermore, it is argued that the majority of these substantive legal rules, whether national or international, are inoperative in a construction contract incorporating the international terms of the FIDIC Red Book.

From red tape to red carpet: the Unidroit Cape Town Convention and MAC Protocol’s Adventure in Africa - Otabor-Olubor, Iyare (Uniform Law Review, 2024)
This article examines the implementation of the Mining, Agricultural and Construction (MAC) Equipment Protocol under the Cape Town Convention in Africa, focusing on enhancing economic growth and sustainable development through improved access to financing for high-value mobile equipment. Africa’s economic development is significantly hindered by inadequate infrastructure, which escalates transaction costs and limits access to international markets. Investment in modern infrastructure, particularly in the mining, agricultural, and construction sectors, is typically expensive for many businesses in the African region. The MAC Protocol aims to address these challenges by providing a uniform legal framework that supports the financing of MAC equipment. The Convention and the MAC Protocol facilitate access to affordable capital and reduce risks for financiers who take international interests in MAC equipment, promoting economic activities in Africa. The article highlights the legal protections offered by the MAC Protocol, ensuring rights against third-party claims and enhancing the enforceability of international interests. The adoption of the MAC Protocol by African States could significantly impact their ability to meet the United Nations Sustainable Development Goals by making modern, cost-efficient equipment more accessible, thus boosting productivity and economic diversification. The article advocates for adopting the MAC Protocol, emphasizing its potential to enhance foreign investment in the mining, agriculture, and construction sectors, stimulating economic development in Africa. This strategic move will propel African countries towards greater economic resilience and integration into the global economy. The article also critically analyses and illustrates the several declaration mechanisms available to countries adopting the MAC Protocol, accompanied by a guidance note to sensitize lawmakers when signing and/or ratifying or acceding to the Cape Town Convention and the MAC Protocol.

Les attributs de la procédure du contentieux fiscal en droit camerounais - Aba’A Andje, Gullit Jordy (Revue des Réflexions Constitutionnelles : Revue mensuelle de publication en droit constitutionnelle, 2024)
Keywords: Cameroun; Contentieux fiscal; Droit camerounais; Droit fiscal

L'équité et les droits des États sans littoral dans le droit international de la mer : perspectives africaines - EL Abboubi, Bouchta (Revue Internationale du Chercheur, 2024)

Compliance with decent work standards by multinational enterprises - Maluleke, Tirhani Foster (University of Pretoria, 2024)
In contemporary times, the issue of human and labour rights violations has gained significant momentum, rendering it imperative for international organisations, states, and businesses to address this critical concern. It is widely acknowledged that while multinational enterprises can aid in achieving economic growth by investing directly overseas and raising the standard of living for the residents of host nations, their business operations may also result in abuse of human and labour rights. The United Nations (UN) Charter was drafted to set forth obligations for individual states, yet businesses do not bear international legal obligations. The Universal Declaration on Human Rights was adopted to implement the substantive contents of human rights referred to in the UN Charter in the general way. The preamble of the Universal Declaration refers to all organs of society, but, at the time of its adoption, businesses were not considered among such organs. It was inconceivable that business organisations would become so economically powerful within a few decades that they would pose a significant risk to human and labour rights, which would not be easily regulated under the national law of their host nations. It is the hypothesis of this study that numerous multinational enterprises (MNEs) violate core human and core labour rights, and that the existing regulatory framework does not adequately regulate them. To prove this hypothesis, this thesis will adopt a two phased approach. Firstly, a careful case law and literature review will reveal the inadequate regulation of MNEs. Evidence suggests that MNEs are guilty of flagrant labour standards and human rights violations. As a result of globalisation, MNEs have gained stronger international influence, and they are able to move their businesses to countries with low cost of labour and less regulations. This phenomenon weakens the governments of host nations as they are keen to promote foreign direct investment in order to reduce unemployment and to ensure economic growth. As a result, the host nations are encouraged to set laws that will attract MNEs at the expense of human and core labour rights. As result, MNEs are not held accountable in respect of their violation of human and labour rights. Secondly, this thesis will assess the efficacy of the regulatory instruments developed by the international community in response to the mentioned problem. This aspect is covered in Chapter 3 to 7 of this thesis. The strategies include the public and private hard law and soft law mechanisms developed at international level as well as campaigns by Non-Governmental Organisations (NGOs). Based on evidence, this thesis will conclude that a soft law approach is not fully effective. As such, Chapter 8 of this thesis proposes the introduction of some hard law measures to improve the existing soft law instruments to augment the existing legislative frameworks of the host countries. In particular, the thesis recommends regulatory reforms, which will empower the International Labour Organisation to intervene to prevent the labour rights violations by MNEs and where such violations occur, to at least provide effective remedies to vulnerable employees. This thesis constitutes a theoretical study, which attempts to provide suggestions regarding the implementation of realistic measures, which if implemented, may contribute to the attainment of decent work for all men and women who are engaged in work for MNEs.
Keywords: Codes of conduct; Decent work; Hard law; Human rights; Human rights due diligence; ILO MNE declaration; International Labour Organisation; International framework agreements; Labour rights; Multinational enterprises; OECD guidelines; Regional free trade agreements; Soft law

Mise en exergue de l’importance des enjeux de durabilité et de transparence dans l’arbitrage du CIRDI - Sanchez, Matthias Jean Cyril (Université de Montréal, 2024)
Il est un fait peu contestable que le développement durable, en tant que sujet d’actualité mondiale, prend une place de plus en plus centrale des discussions ayant cours dans un monde de plus en plus industrialisé et globalisé. Dans cette nouvelle ère où les défis environnementaux, économiques, sociaux, culturels ou encore climatiques se multiplient et se complexifient, il devient de plus en plus primordial d’axer les réflexions internationales vers un meilleur équilibre des croissances de chacun, le tout, en tenant compte des enjeux de durabilité. C’est dans ce contexte que s’inscrit le présent mémoire, axé sur la mise en lumière de l’importance des enjeux environnementaux et de transparence à travers les procédures et les jurisprudences de l’arbitrage du Centre international pour le règlement des différends relatifs aux investissements (CIRDI). Le présent argumentaire visera donc à apporter un éclairage nouveau sur les défis auxquels le CIRDI est confronté dans l’intégration des principes de développement durable et de transparence, notamment, dans ses décisions, à travers les implications des normes internationales sur le comportement des États et des investisseurs. Ce mémoire s'adresse ainsi principalement à ceux qui s'intéressent aux développements du droit international des investissements et de la durabilité des conséquences que ce dernier permet. Il vise aussi à contribuer au débat en proposant des recommandations concrètes permettant un alignement optimal des pratiques du CIRDI avec celles d’autres organes d’arbitrage nationaux et internationaux et avec les exigences de transparence et de durabilité.
Keywords: Arbitrage international; Bilateral Investment Treaties (BITs); Business law; Centre international pour le règlement des différends relatifs aux investissements (CIRDI); Droit des affaires; Droit international; Droits humains; Durabilité; Développement durable; Human rights; International Centre for Settlement of Investment Disputes (ICSID); International arbitration; International investment; International law; Investissement international; Sustainability; Sustainable development; Traité bilatéral d’investissement (TBI); Transparence; Transparency

Le juge et la science : une étude rationaliste des biais conscients et inconscients dans l’appréciation de la preuve forensique en matière criminelle - Sénéchal, Carole (Université de Montréal, 2024)
Tant par l’ampleur que le caractère pérenne de leurs conséquences sur la vie des différentes parties prenantes, les erreurs judiciaires suscitent l’indignation autant des régulateurs que des journalistes et de l’opinion publique. Assurer une prise de décision correcte dans le contexte judiciaire nécessite des balises institutionnelles visant, d’une part, à permettre une présentation complète de toute la preuve pertinente devant le juge des faits et, d’autre part, à limiter les erreurs d’appréciation de cette preuve. Notre thèse s’intéresse aux sources d’erreurs d’origine humaine qui limitent une correcte appréciation de la preuve dans le contexte judiciaire qui sont les moins susceptibles d’être mis en évidence par voie de contrôle juridictionnel (d’appel) et qui peuvent justifier la mise en place de balises institutionnelles additionnelles à celles existantes. Tout d’abord, une revue de littérature critique en criminologie et en sciences sociales sur les sources d’erreurs qui entachent généralement la rationalité des jugements (chapitre 1) indique que les décisions rendues dans le contexte judiciaire sont vulnérables à la fois aux biais et « bruits » à toutes les étapes d’un procès. Ensuite, nous nous intéresserons en particulier aux problèmes de compréhension et d’interprétation propres aux preuves scientifiques, comprenant les expertises ainsi que celles obtenues par des outils statistiques, actuariels et technologiques (chapitre 2). En effet, la science apparaît à première vue comme un « auxiliaire de justice » précieux par l’introduction de l’expertise dans les procès. Or, la production en justice d’une preuve forensique doit passer par un travail d’exégèse et de traduction de l’expert forensique au juge ou aux jurés. Tout au long de ce processus, la myopie métacognitive des experts forensiques, le mécanisme du procès contradictoire, l’aménagement des salles d’audience et la manière dont l’information est présentée, ainsi que les difficultés de compréhension de la preuve forensique par les décideurs, pourraient constituer autant d’aléas et de risques de dérive ébranlant la rationalité supposée de ce travail collectif qu’est la tenue d’un procès afin de faire émerger la vérité… judiciaire. Considérant que le contrôle juridictionnel des erreurs de faits par les juges d’instance s’avère assez limité au Canada (chapitre 3), nous proposons en dernier lieu (chapitre 4) quelques pistes de réforme afin de mieux rationaliser l’appréciation de la preuve par les décideurs de faits. Tout d’abord, il y a lieu d’ajouter quelques garanties d’ordre procédural et certaines inférences spécifiquement interdites pour limiter l’occurrence de biais cognitifs en général. Nous nous sommes inspirés ensuite de la formule bayésienne ainsi que la Déclaration de Sydney relative à la science forensique, pour proposer une démarche permettant de « rationaliser » le processus d’appréciation de la preuve afin de limiter les erreurs de compréhension sur la portée et les limites de la preuve d’expert. La formule bayésienne souligne en effet la nécessité de distinguer la probabilité des effets (qui relève des experts), de la probabilité des causes (du ressort exclusif du juge au procès). L’évaluation de ces deux probabilités ne se chevauche pas et fait appel à des considérations distinctes. Dans cette évaluation, la prise en compte du contexte et d’éléments circonstanciels s’avère à double tranchant en ce qu’elle peut à la fois être pertinente pour orienter l’investigation (aider à la génération de nouvelles pistes, hypothèses ou explications alternatives) que constitutive de biais. Le potentiel de biais s’accentue dans les cas de figure plus ambigus ou dont la preuve reste essentiellement circonstancielle. Nous suggérons finalement l’institution du rôle de « critique d’experts » qui peut agir en véritable auxiliaire de justice devant la cour ou en amont, comme auditeur indépendant, pour mieux contrôler l’intégrité du processus forensique et la manière dont la preuve scientifique est présentée devant les tribunaux.
Keywords: Appréciation de la preuve; Biais; Bias; Evidence assessment; Forensics; Forensique; Juge; Justice; Preuve; Science criminelle

Le juge africain face au droit international humanitaire - Tapsoba, Armel Ghislain (Afrilex : Revue d’étude et de recherche sur le droit et l’administration dans les pays d’Afrique, 2024)
Le juge est le maillon fort de la chaine judiciaire qui a reçu le pouvoir d’appliquer la règle de droit. En tant qu’érudit du droit, le juge connait diverses situations juridiques litigieuses qui font appel à l’interprétation d’un matériau assez vaste. Dans ce matériau, l’application du droit international demeure un enjeu majeur pour l’office du juge. Ceci est d’autant plus vrai en ce qui concerne le droit international humanitaire, qui est très spécifique. Au regard des circonstances politiques, économiques et des conditions professionnelles qui encadre l’office du juge africain, l’intérêt transparait à travers cette formule : quelles sont les postures du juge africain dans l’application du droit international humanitaire ? Une telle interrogation évoque la question de la réception des règles internationales dans les ordres juridiques internes, mais aussi leur appropriation par les acteurs chargés de leur mise en œuvre. Cette interrogation permet de relever les efforts au regard de la présence des facteurs inhibiteurs en Afrique surtout. Ces efforts, quoique toujours insuffisants, s’inscrivent indéniablement dans une dynamique de promotion et de consolidation du droit international humanitaire. Juge promoteur, juge consolidateur sont les postures observées en Afrique dans les affaires relatives à l’application du droit international humanitaire, mais toujours dans une camisole d’insuffisance. The judge is the strong link in the judicial chain, empowered to apply the rule of law. As a legal scholar, the judge is familiar with a variety of contentious legal situations that call for the interpretation of a vast body of rules. Within this legal corpus, the application of international law remains a major challenge for the judge’s office. This is all the more true in the case of international humanitarian law, which is highly specific. In view of the political and economic circumstances and the professional conditions that govern the office of the African judge, the question arises: what are the African judge’s attitudes to the application of international humanitarian law? Such a question raises the issue of how international rules are received by domestic legal systems, and how they are appropriated by the actors responsible for implementing them. This question helps to highlight the efforts being made in view of the presence of inhibiting factors, especially in Africa. These efforts, though still insufficient, are undeniably part of a dynamic to promote and consolidate international humanitarian law. Judge-promoter, judge-consolidator are the postures observed in Africa in cases relating to the application of international humanitarian law, but always in a straitjacket of inadequacy.
Keywords: Africa; Afrique; Droit international humanitaire; International humanitarian law; Judge; Juge

Biopsie de la cohabitation entre la cour commune de justice et d'arbitrage et la Cour de justice de la communauté d'Afrique de l'Est - Mbazi, Grâce Beda; Iragi Ntwali, Valéry; Cirhuza, Guillain (HAL - UPEC, 2024)
La reconnaissance simultanée des compétences judiciaires à la Cour commune de justice et d’arbitrage et à la cour de la Communauté de l’Afrique de l’Est agit comme obstacle à la réussite de l’intégration économique des pays appartenant simultanément à ces deux communautés, qui constitue pourtant un préalable fondamental en vue de leur développement. Suite à cette situation, les investisseurs pourraient se trouver dans une situation telle que des litiges tombent sous le champ d’application tant du droit de l’OHADA que de celui de la Communauté de l’Afrique de l’Est et appeler ainsi à la compétence tant de la CCJA que de la cour de justice de la CAE. Ce télescopage peut véritablement être à l'origine d'une insécurité juridique. Toutefois, pour vider les problèmes de cohabitation, la mise en œuvre d’une juridiction régionale compétente pour les affaires découlant de la mise en œuvre des Traités d’intégration régionale en Afrique serait importante. La CCJA présente dans ce sens des mérites qui peuvent être capitalisés.

Le travailleur domestique en République Démocratique du Congo : un des oubliés de la législation du travail? - Ayikaba, Jules Masuku (Recht in Afrika, 2024)
The glaring lack of employment opportunities in the Democratic Republic of Congo (DRC) has led to the conclusion of special employment contracts, includin…

Le droit au partage équitable des biens des époux : relecture du droit congolais de la famille à la lumière du Protocole de Maputo - Bayongi, Eric Katusele (Recht in Afrika, 2024)
The African Commission on Human and Peoples' Rights recently published a general comment interpreting article 7(d) of the so-called Maputo Protocol.…

La gouvernance des sociétés coopératives dans l’espace OHADA ERS2024-C3 - ERSUMA - OHADA (2024)

Cross-border banking and bank stability: evidence from Sub-Saharan Africa - Gondwe, Sopani; Gwatidzo, Tendai; Mahonye, Nyasha (Journal of Banking Regulation, 2024)
Based on bank-level data from 29 Sub-Saharan African countries between 2005 and 2019, we apply panel fixed effects (FE) and two-step system GMM estimators to investigate whether increased cross-border banking affects domestic banking sector stability. We find significant evidence that the stability of banks in host countries declines with an increased presence of foreign banks—and the impact is more pronounced on banks that are small and less efficient. The stability impact of foreign banks is also found to depend on the quality of governance institutional factors in the host country. The findings shed some important insights on the downside of financial liberalisation policy in developing countries and the need for increased cross-border collaboration between home and host supervisory authorities in the SSA region—especially in jurisdictions where the foreign bank affiliates are systemically important. The domestic supervisory authorities thus need to effectively manage the inherent trade-off between reaping the benefits from international financial integration while effectively safeguarding domestic banking systems against cross-border contagion and fragility.
Keywords: Bank stability; Consolidated supervision; Cross-border banks; Home-host countries; Systemically important

A Proposal for Reforming the Calculation of Damages in Investment Treaty Arbitration = Proposition pour le calcul des dommages-intérêts dans l’arbitrage au titre des traités d’investissement = Propuesta para Reformar el Cálculo de Daños en el Arbitraje de Los Tratados de Inversión - Jarrett, Martin (Investment Treaty News, 2024)

Mutation Comptable PCGC/OHADA et qualité de l’information financière dans les entreprises publiques en RD Congo - Mposhi, François NGONGO; Chanhoun, Maxime José (Revue du contrôle, de la comptabilité et de l’audit, 2024)
L’Objectif de cette recherche est de comprendre la portée de la mutation comptable sur la production d’une information financière de qualité. Pour ce faire, nous avons opté pour une posture épistémologique interpretativiste adossée sur une démarche qualitative inductive. A l’aide d’un guide d’entretien, nous avons réalisé les entretiens semi-directifs auprès de dix (10) gestionnaires financiers des entreprises publiques en RD Congo. Les données collectées, ont fait l’objet d’une analyse de contenu et automatisée à l’aide du logiciel Nvivo 10. Il ressort de ces analyses que la mutation comptable PCGC/OHADA contribuerait à l’amélioration de la qualité de l’information financière dans les entreprises publiques en RD Congo. Ce qui interpelle les gestionnaires des entreprises publiques d’une part et le conseil permanent de la comptabilité au Congo d’autre part de veiller véritablement à l’applicabilité stricte du SYSCOHADA pour une information financière de qualité. Car la mutation comptable PCGC/OHADA s’implémente avec beaucoup des difficultés dans les entreprises publiques en RD Congo surtout lors des travaux d’inventaires.
Number: 2
Keywords: Entreprises Publiques; Mutation comptable; Qualité d’états financiers; SYSCOHADA

Les vicissitudes de l’entreprise et la stabilité de l’emploi en droit camerounais - Azangue Ngouajio, Josiane (Revue des Réflexions Constitutionnelles : Revue mensuelle de publication en droit constitutionnelle, 2024)
Si la sécurité de l'emploi reste forte, la stabilité de l'emploi, elle, continue à être un sujet de préoccupation. Il n'y a qu'une faible relation entre l'indicateur objectif de la sécurité de l'emploi qu'est la durabilité et la perception qu'en ont les gens à travers les pays. Ainsi, « il existe une relation positive entre le travail décent et la sécurité de l'emploi ». La sécurité de l'emploi peut être générée par son caractère stable, mais quand se profile une récession ou que s'accélèrent les changements structurels, la stabilité de l'emploi risque d'être mise en péril. Dans ces situations, les salariés ont besoin de compter sur leurs systèmes de protection sociale. Mais c’est de toute évidence dans l’optique de sécuriser l’emploi que le législateur prévoit des techniques conciliantes entre l’employeur et les employés afin de stabiliser l’emploi. De ce fait, on observe une redynamisation des conditions de travail par la modification des dispositions contractuelles. En outre, même en cas de changement dans la situation juridique de l’employeur le principe reste celui de la subsistance du contrat en cours. If job security remain strong, job stability continues to be a subject of concern. There is only a weak relationship between the objective indicator of job security and this is sustainability and the perception of it by people accross the country. Thus, « there is a positive relationship between decent work and job security ». Job security can be generated by its stable nature, but when a recession looms or structural changes accelerate, job stability risks being jeopardized. In these situations, employees have need to rely on their social protection systems. But, it is obviously with a view to securing employment that the legislator provides conciliatory techniques between the employer and employees in order to stabilize employment. As a result, we are considering a revitalization of working conditions by modifying contractual provisions. Furthermore, even in the event of a change in the legal situation of the employer, the principle remains that of the continuation of the current contract.
Keywords: Decent work; Job stability; Protection sociale; Social protection; Stabilité de l’emploi; Travail décent; Vicissitudes

La fréquentation de plaisance dans les aires marines protégées : des solutions juridiques au regard des enjeux socio-économiques - Bruck de Moraes Ponna Schiavetti, Mariana (Université de Bretagne Occidentale, 2024)
The increasing nautical frequentation within marine protected areas (MPA) presents significant challenges for managers. Amidst growing anthropogenic pressures, recreational nautical activities offer economic benefits and cultural significance, yet they also pose a threat to marine ecosystems. In response, managers of MPA are seeking solutions, particularly on a legal level, to regulate both individual activities and overall visitation. This doctoral research aims to contribute to this effort by firmly anchoring its investigation within the realm of law while adopting an interdisciplinary approach to grasp the complexity of the issues at hand and provide concrete responses to managers and local stakeholders. Through the analysis of two case studies, the Iroise Marine Natural Park and the Port-Cros National Park, it explores the legal constraints and opportunities and formulates contextually appropriate recommendations. Moreover, the analysis underscores the importance of appropriate governance to regulate recreational and nautical activities within MPA. Having identified shortcomings in both legal and non-legal instruments utilized within environmental law to manage thoses activities within MPA, this research delves into several strategies to mitigate these deficiencies. These strategies encompass a spectrum of approaches, from embracing negotiated governance structures to advocating for the innovative concept of behavioral adjustment. These approaches foster close collaboration among stakeholders and heighten environmental awareness, thereby facilitating effective regulation of nautical frequentation within MPA. L'augmentation de la fréquentation de plaisance dans les aires marines protégées (AMP) pose des défis majeurs aux gestionnaires. Dans le cadre d'une anthropisation croissante, les activités liées à la plaisance sont économiquement bénéfiques et culturellement significatives, mais elles représentent également une menace pour les écosystèmes marins. Face à cette problématique, les gestionnaires des AMP recherchent des solutions, notamment sur le plan juridique, afin de réguler à la fois les activités pratiquées individuellement et la fréquentation elle-même dans son ensemble. La présente recherche doctorale propose de contribuer à ce travail en ancrant résolument sa réflexion dans le champ du droit, tout en adoptant une posture interdisciplinaire pour saisir la complexité des enjeux en présence et apporter des réponses concrètes aux gestionnaires et aux acteurs locaux. À travers l'analyse de deux études de cas, le Parc naturel marin d'Iroise et le Parc national de Port-Cros, elle explore les limites et les leviers d'action juridiques et formule des recommandations adaptées aux contextes. Ainsi, l'analyse met en évidence l'importance d'une gouvernance adaptée pour réguler la plaisance dans les AMP. Après avoir vérifié les lacunes de certains outils juridiques et non juridiques mobilisés en droit de l’environnement pour réguler les activités de plaisance au sein des AMP, cette recherche explore les différentes voies pour pallier ces lacunes depuis l'adoption du concept de gouvernance négociée, au choix raisonné en faveur d'un outil innovant : le terme d'ajustement de conduite. Ces approches favorisent une collaboration étroite entre les parties prenantes et renforcent la conscientisation environnementale, ouvrant ainsi la voie à une régulation plus efficace de la fréquentation de plaisance dans les AMP.
Issue: 2024BRES0041
Keywords: Behavioral adjustment commitment; Droit de l'environnement; Effets de l'homme; Environmental law; Gouvernance; Governance; Nature; Parcs marins; Regulation; Réglementation; Terme d'ajustement de conduite

Ghana: Business perspectives - Invisible barriers to trade - International Trade Centre (ITC) (International Trade Centre (ITC), 2024)
This report examines the experiences of Ghanaian exporters and importers with trade regulations and related procedural obstacles – highlighting their concerns and the challenges they face. A survey of 960 traders on non-tariff measures found that almost half of exporters in Ghana encounter obstacles. This finding underscores the importance of the solutions proposed in the country’s National Export Development Strategy. The report finds that tackling foreign and domestic trade obstacles such as conformity assessment requirements, export inspections and customs clearance procedures could help Ghana boost its annual exports by up to $4.3 billion by 2025.

Characterization (and Registration) of a “BRI Dispute” - Kirkwood, Jamieson (Asian Journal of International Law, 2024)
This article explores the terms “BRI dispute” and “BRI jurisprudence”. It undertakes a practical and theoretical analysis that considers whether “BRI disputes” have distinct and visible characteristics and are capable of being identified in a legal sense. This is important since practitioners – arbitration centres and law firms – use the term broadly and without specific criteria. By exploring the customary usage and the approach of legal scholars to the term, presenting examples of “BRI disputes” and examining their unique features, and constructing a theoretical approach (utilizing the concepts of ratione materiae, ratione loci, ratione temporis, and ratione personae; and considering the jurisprudence of the ICSID), this article moves from a broad to a narrow analysis to develop both a definition and a system of registration of “BRI disputes” for use by academics, practitioners, and policymakers.
Keywords: BRI; Belt and Road; China; Dispute Settlement; ICSID

An overview of the extent of the powers of South African competition authorities in the regulation of price discrimination under the Competition Act 89 of 1998 in the context of digital transformation - Magau, Phemelo (PER / PELJ, 2024)
The purpose of the Competition Act 89 of 1998 as amended (the Competition Act) is, among others, to promote the efficiency, adaptability and development of the economy as well as to provide consumers with competitive prices and product choices. In line with this purpose, the Competition Act provides that a dominant firm is prohibited from engaging in price discrimination if such conduct will likely substantially prevent or lessen competition, which would be to the detriment of consumers. Notably, the Competition Act has established various bodies to regulate competition and act against any conduct prohibited by this Act in South Africa. These bodies include the Competition Commission, the Competition Tribunal, and the Competition Appeal Court. Notwithstanding the prohibition of price discrimination, the Competition Act does not expressly provide adequate enforcement tools for competition authorities to combat uncompetitive practices in the digital era. Moreover, the Competition Act does not expressly grant these statutory bodies clear roles and mandates on providing consumers with adequate and suitable redress when they have been victims of algorithmic price discrimination. With recent technological developments, electronic commerce (e-commerce), and digital transformation, consumers have become vulnerable to various challenges such as excessive pricing, data breaches and algorithmic pricing. The online and digital markets are characterised by complex transactions, innovative technologies and business practices which expose all consumers, including vulnerable consumers, to different risks. As such, the role of the competition authorities needs to be recalibrated to enhance consumer protection on the pricing of goods and services. To this end this paper seeks to investigate the role and ambit of the powers of these competition authorities in the regulation of price discrimination in the context of digital transformation and the digital economy. This is done to assess whether the competition authorities have the necessary tools of enforcement to ensure that markets are competitive and to combat uncompetitive conduct in the digital economy and online markets.
Keywords: Algorithmic pricing; Competition authorities; Consumer protection; Digital transformation; Price discrimination

Corporate Social Responsibility Practices in the Nigerian Public Sector - Mohammed, Abbas (University of Plymouth, 2024)
This study examines Corporate Social Responsibility (CSR) practices in Nigerian public sector organisations using a comprehensive mixed-methods approach. The data collection process involved analysing 185 organisation-year observations from annual reports spanning 2011–2020, as well as questionnaires distributed to key stakeholders and interviews with senior executives from various organisations.The analysis utilised a multi-pronged strategy, including quantitative techniques such as regression analysis to explore the relationship between CSR practices and corporate governance mechanisms and qualitative methods such as narrative analysis and thematic coding to gain insights from survey responses and interviews.The findings indicate that CSR practices in the Nigerian public sector are moving in a positive direction. Organisations demonstrated commitment to CSR activities, including community development, education, environmental conservation, and philanthropy. Survey results showed that 83% of organisations engaged in CSR, driven by community acceptance and moral obligation. Additionally, 84% of organisations complied with regulatory frameworks, and 79% aligned their CSR policies with national or international standards. The analysis also found a significant positive relationship between CSR practices and factors such as larger board sizes, greater board independence, the presence of women on the board, and CEOs with longer tenures, higher educational qualifications, and international exposure.By triangulating these findings, it is clear that organisations have a strong commitment to giving back through various CSR initiatives, such as humanitarian assistance, youth empowerment, and educational programmes. Despite challenges such as budgetary constraints and weak accountability frameworks, organisations recognise the perceived benefits of CSR, including increased public confidence, improved stakeholder perceptions, enhanced organisational reputation, trust-building, community engagement, and empowering marginalised communities through education.The insights gained from this study conducted in an emerging economy namely, Nigeria, provide a new understanding of CSR practices in public-sector organisations. They also highlight the proactive approach of public sector organisations towards responsible practices. Consequently, the implications of this research extend beyond national boundaries, encouraging diverse and dedicated leadership to enhance CSR efforts and create lasting social impact. Future studies could explore comparative analysis between the public and private sectors or different countries, as well as sector-specific impact assessments.
Keywords: CSR; Corporate Social Responsibility; ESG; Sustainability

La protection juridique du patient en France et en Côte d'Ivoire - N'Da, Anna (Université de La Rochelle, 2024)
L’étude comparative de la protection juridique du patient en France et en Côte d’Ivoire, fait apparaître l’existence d’une reconnaissance commune d’un droit du patient à être protégé qui se traduit par un véritable statut juridique de celui-ci en tant que tel. Si dans les deux systèmes, le patient bénéficie d’une protection juridique fondée sur sa double qualité de personne humaine et de bénéficiaire de soins, au contenu évolutif face aux progrès scientifiques et aux lois bioéthiques, le contexte socio-culturel de chaque État conduit toutefois à une similitude qui n’est pas absolue. En France, les droits toujours plus nombreux reconnus au patient font de lui un véritable acteur de sa santé tant à l’égard du consentement qu’il doit exprimer que de l’information dont il est bénéficiaire. En Côte d’Ivoire, le paternalisme médical encore latent révèle que le patient est beaucoup plus passif à l’égard du professionnel de santé et de sa prise en charge. C’est ce même contexte socio-culturel qui permet de constater que l’efficacité de la protection juridique du patient n’est pas identique en France et en Côte d’Ivoire, ce qui rend sa protection différemment perfectible. Il existe en France un système de conciliation tout à fait original entre les règles de la responsabilité médicale et celles de l’indemnisation fondées sur la solidarité nationale, tandis que la responsabilité fondée sur la faute reste la seule voie offerte au patient en droit ivoirien. En outre, l’accès aux soins notamment avec le système d’assurance maladie n’a pas atteint ici et là le même degré de maturité. Par ailleurs, la juridicisation et la judiciarisation de la protection qui se développent en France ne se retrouvent pas de façon semblable en Côte d’Ivoire où le patient est beaucoup plus frileux à actionner le système judiciaire. Entre une protection toujours plus poussée sur le territoire français et une protection encore lacunaire en Côte d’Ivoire, l’idéal se trouverait sans doute dans un juste milieu. A comparative study of the legal protection of patients in France and Ivory Coast reveals the existence of a common recognition of a patient's right to protection, which translates into a genuine legal status for patients as such. While in both systems, patients benefit from legal protection based on their dual status as human beings and recipients of care, the content of which evolves in the light of scientific progress and bioethics laws, the socio-cultural context of each country nevertheless leads to a similarity that is not absolute. In France, the ever-increasing number of rights granted to patients makes them real players in their own health, both in terms of the consent they must give and the information they receive. In Ivory Coast, the still latent medical paternalism reveals that patients are much more passive towards the health professional and his care. It is this same socio-cultural context which allows to note that the effectiveness of legal protection for patients is not identical in France and Ivory Coast, which makes his protection differently perfectible. In France, there is a highly original system of reconciliation between the rules of medical liability and those of compensation based on national solidarity, whereas liability based on fault remains the only option available to patients under Ivorian law. In addition, access to healthcare, particularly through the health insurance system, has not reached the same degree of maturity everywhere. Furthermore, the legalization and judicialization of protection that are developing in France are not found in a similar way in Ivory Coast, where patients are much more reluctant to turn to the judicial system. Between the ever-increasing protection afforded in France and the gaps in protection in Ivory Coast, the ideal situation would undoubtedly be found in a happy medium.
Issue: 2024LAROD001
Keywords: Compensation; Doctor; Indemnisation; Médecin; Patient; Protection; Responsability; Responsabilité; Vulnerability; Vulnérabilité

Le droit de retrait du salaire - Vanié, Bi Djè Aristide (Afrilex : Revue d’étude et de recherche sur le droit et l’administration dans les pays d’Afrique, 2024)
Aux termes de l’article 41.4 alinéa 2 du code du travail ivoirien, tout salarié ou groupe de salariés en présence d’une situation de travail dont il a un motif raisonnable de penser qu’elle représente un danger grave et imminent pour sa vie ou sa santé, ou celles d’autrui, doit, après s’en être retiré, en informer le comité de santé et de sécurité au travail. Tel est le sens de la disposition majeure qui consacre, dans cet ordre juridique, le droit de retrait du salarié. L’objectif de cette étude est de démontrer, qu’en dépit de sa nouveauté, le droit de retrait du salarié est un droit mal dimensionné. Se pose alors le problème de son caractère absolu ou non. Aux arguments qui poussent à croire à un droit de retrait absolu en droit du travail ivoirien, l’on peut objecter qu’il s’agit en réalité d’une prérogative mitigée. Under the terms of article 41.4 paragraph 2 of the Ivorian labor code, any employee or group of employees in the presence of a work situation which he has reasonable grounds to believe represents a serious and imminent danger for his life or his health, or those of others, must, after withdrawing, inform the workplace health and safety committee. This is the meaning of the major provision which establishes in this legal order the employee’s right of withdrawal. The objective of this study is to demonstrate that, despite its novelty, the employee’s right of withdrawal is a poorly dimensioned right. The problem then arises of its absolute character or not. To the arguments which lead one to believe in an absolute right of withdrawal in Ivorian labor law, one can object that it is in reality a mixed prerogative.
Keywords: Danger; Droit du travail; Labour law; Retrait; Safety; Sécurité; Withdrawal; Word

The use of blockchain for collecting value-added tax on online cross-border trade in digital goods - Kabwe, Ruddy Kapasula (University of Pretoria, 2024)
The collection of value-added tax from the cross-border supply of digital goods remains a challenge for tax authorities around the world. South Africa is no different. The traditional methods of collecting VAT from the supply of digital goods relies on the honesty of the consumer and on the supplier to account for and remit VAT to the tax authorities in the jurisdiction where the goods are consumed. The traditional collection models are often unreliable, inefficient, burdensome, and expensive for the consumers and the suppliers. The adoption of blockchain technology as a model to collect VAT on the cross-border supply of digital goods has the potential to alleviate the compliance burden on consumers and suppliers of digital goods, improve the efficiency of tax administration, and reduce VAT fraud. Importantly, blockchain technology can create trust between tax authorities, suppliers of digital goods, and consumers. This thesis critically discusses the advantages and disadvantages of implementing blockchain technology for the collection of VAT on the cross-border supply of digital goods in South Africa. This thesis unpacks the consideration factors for policymakers in the implementation of blockchain technology for the collection of VAT on cross-border trade in digital goods. The thesis makes recommendations for the South African VAT Act to be amended to make provision for the collection of VAT by utilising blockchain technology.
URI: https://repository.up.ac.za/handle/2263/97005
Keywords: Anonymisation; Blockchain technology; Decentralisation; Digital goods; Private blockchain; Smart contracts; Taxpayer privacy; Value-added tax

Patentes de invenção, tecnologia e desenvolvimento : exploração local como requisito constitucional e legal das patentes - Vera, Maria Carolina Rezende (Universidade de São Paulo, 2024)
A transferência de tecnologia e a capacitação tecnológica no Brasil são temas relevantes para o debate jurídico nacional, considerando a condição brasileira como país em desenvolvimento. Nesse contexto, a exploração do objeto do direito de patente de invenção em território brasileiro, prevista no art. 68, § 1o, inc. I, da Lei no 9.279/1996, ganha importância. Ao configurar-se como um dos requisitos para o licenciamento compulsório, esse instituto contribui para o alcance das finalidades dos direitos de propriedade intelectual estabelecidas no art. 5o, inc. XXIX, da Constituição Federal de 1988, quais sejam: o interesse social e o desenvolvimento econômico e tecnológico. A partir da matriz constitucional dos Direitos de Propriedade Intelectual, é possível identificar o trígono de finalidades traçadas pelo constituinte originário para esses direitos. Ademais, tais propósitos encontram-se ainda refletidos na Ordem Social brasileira, nos arts. 218 e 219 da Constituição Federal; pois são tarefas do Estado a promoção da inovação e da autonomia tecnológica. A Lei no 9.279/1996 guia-se pelos preceitos estatuídos na Carta Magna, concedendo proteção e privilégio temporário às invenções dotadas de novidade, atividade inventiva e aplicação industrial, nos termos do seu art. 8o. Destaca-se que a exclusividade só é justificada se estiver presente o contributo mínimo. Como é possível extrair dos textos legais, o Estado retira do mercado uma parcela de liberdade de atuação dos agentes econômicos, delegando a gestão privada dos bens a um só deles, com o objetivo de atingir a inovação. Por tais motivos, a legislação prevê uma ameaça aos titulares da patente que não explorem seus direitos dentro do país. A exploração no território brasileiro torna-se uma ferramenta à disposição dos países que não são desenvolvidos para o alcance da inovação. Assim, a presente dissertação propõe-se a relacionar o mecanismo da exploração local aos fins constitucionais e legais das patentes. Por meio de pesquisa qualitativa, aplicada, exploratória e bibliográfica e utilizando os métodos dedutivo e hipotético-dedutivo, este trabalho busca construir uma interpretação sobre a tensão entre acesso de agentes econômicos às tecnologias, exploração das patentes e garantia de exclusividade. O estudo observa que a exploração local é um recurso à disposição dos países em desenvolvimento para que se alcance a inovação e o desenvolvimento econômico e tecnológico. A atuação do Estado no domínio econômico, especialmente no campo dos direitos de propriedade intelectual, foi um recurso utilizado por países atualmente desenvolvidos para alcançar o atual estágio tecnológico em que se encontram. Por tal motivo, é possível que as nações em desenvolvimento utilizem o requisito da exploração obrigatória de patentes em território nacional para difundir avanços sociais, tecnológicos e econômicos. The transfer of technology and technological training within Brazil are relevant topics for the national legal debate, considering the Brazilian condition as a developing country. In this context, the local patent working requirement in Brazilian territory, provided for in art. 68, § 1, inc. I, of Law No. 9,279/1996, gains importance. By being one of the legal requirements for compulsory licensing, this institute contributes to the achievement of the purposes of intellectual property rights established in art. 5th, Inc. XXIX, of the Federal Constitution of 1988, namely: social interest and economic and technological development. From the constitutional matrix of Intellectual Property Rights, it is possible to identify the trigon of purposes traced by the original constituent for these rights. Furthermore, such purposes are still reflected in the Brazilian Social Order, in arts. 218 and 219 of the Federal Constitution; because it is the State\'s task to promote innovation and technological autonomy. Law no 9.279/1996 is guided by the precepts established in the Magna Carta, granting protection and temporary privilege to inventions endowed with novelty, inventive step and industrial application, under the terms of its art. 8th. It should be noted that exclusivity is only justified if the minimum contribution is present. As it is possible to extract from the legal texts, the State withdraws from the market a portion of the freedom of action of economic agents, delegating the private management of assets to one of them, with the objective of achieving innovation. For these reasons, the legislation poses a threat to patent holders who do not exploit their rights within the country. Exploration in Brazilian territory becomes a tool available to countries that are not developed to reach innovation. Thus, the present dissertation proposes to relate the mechanism of local working to the constitutional and legal purposes of patents. Through qualitative, applied, exploratory and bibliographic research and using deductive and hypothetico-deductive methods, this work seeks to build an interpretation of the tension between access of economic agents to technologies, patent local working and guarantee of exclusivity. The study notes that local exploration is a resource available to developing countries to achieve innovation and economic and technological development. The States action in the economic domain, especially in the field of intellectual property rights, was a tool used by currently developed countries to reach the current technological stage in which they find themselves. For this reason, it is possible for developing nations to use the requirement of mandatory exploitation of patents in national territory to disseminate social, technological and economic advances.
Keywords: Compulsory licensing; Desenvolvimento de tecnologia; Desenvolvimento econômico; Economic development; Exploração local; Innovation; Inovação; Licença compulsória; Local working; Patent; Patente de invenção; Technological development

Favoriser la culture du règlement amiable des différends : étude du droit béninois à la lumière du droit français - Ligan, Cyrille Sèmako (Université de Limoges, 2024)
Cette réflexion se propose de contribuer au développement des modes amiables de règlement des différends dans la culture juridique béninoise afin de permettre aux justiciables, majoritairement analphabètes, d'avoir des alternatives opportunes aux voies judiciaires classiques. Tandis que la justice fait face à de nombreux défis, aussi bien en France qu'au Bénin, le développement et la promotion remarqués des modes amiables de règlement des différends connaissent un certain succès en la matière en France. Au Bénin, le législateur encourage, incite mais ne propose aucun régime particulier pour le recours effectif au règlement amiable des différends. Cette recherche tente ainsi d'examiner de façon approfondie et d'interroger les différends mécanismes législatifs existants, tant les enjeux en termes d'accès à la justice sont considérables. Les principaux enjeux de cette thèse sont donc liées aux perspectives du développement des mode amiables et à leur encadrement pour remédier aux insuffisances et contre-performances de la justice étatique béninoise.
Cette thèse est sous embargo jusqu’au 27/06/2029.
Keywords: Amicable settlement; Bénin / OHADA; Civil Procedure; Culture; France; Justice; MARD; Mediación; Mediation; Mediação; Médiation; Procédure civile; Règlement amiable

La libre circulation des personnes dans l'espace CEDEAO-UEMOA - Zouho, Bagnon César (Université de Strasbourg, 2024)
Intervenant sur le même espace régional, les deux principales organisations de l’Afrique de l’ouest à savoir la Communauté Economique Des Etats d’Afrique de l’Ouest (CEDEAO) et l’Union Economique et Monétaire Ouest Africaine (UEMOA) partagent l’objectif de parvenir à la libre circulation des personnes. Pourtant, il est constamment relevé que les droits qui devraient faciliter cette mobilité sont loin d’être mis en œuvre et qu’un contraste subsiste entre l’objectif de parvenir à la réalisation effective du principe de la libre circulation des personnes et les pratiques qui traduisent un exercice limite de cette liberté. La présente étude a trait aux problématiques en lien avec la question migratoire en Afrique de l’ouest, rend compte de l’adéquation apparente du régime adopte par la CEDEAO et l’UEMOA a l’effet de doter le principe de la libre circulation des personnes d’une véritable assise juridique. Il apparait ainsi que la qualité de cet ensemble de normes découle aussi bien de la diversification des bénéficiaires que de la cohérence de son contenu. Toutefois, l’analyse des modalités de réalisation du régime mis en place révèle des imperfections tenant aussi bien à la construction incomplète, qu’à l’application ineffective du droit de la libre circulation des personnes dans l’espace CEDEAO -UEMOA. Au demeurant la présence de facteurs extra-juridiques découlant des divergences et incohérences observées dans les positions des acteurs notamment les Etats, les organisations régionales et les peuples ouest-africains, laisse entrevoir la persistance d’obstacles d’ordre pratique qui compromettent l’atteinte des objectifs. Il s’ensuit que la libre circulation des personnes dans l’espace CEDEAO -UEMOA doit être considéré comme un processus dynamique dont l’évolution dépend de la capacite de l’ensemble des acteurs à réinventer des réponses adaptées a la spécificité des problématiques et contexte ouest-africains.
Keywords: Afrique occidentale; Borders; CEDEAO; Communauté économique des États de l'Afrique de l'Ouest; ECOWAS; Etats; Free movement of people; Frontières; Intégration régionale; Libre circulation des personnes; Regional integration; States; Travailleur; UEMOA; Union économique et monétaire Ouest africaine; Visa; Worker

المسؤولية الجزائية لمصفي الشركات التجارية - مرجي, نفيسة (Université Abd El Hamid Ibn Badis Mostaganem, 2024)
مــلخص مذكرة الماستر تحتل الشركات التجارية في العصر الراهن أهمية بالغة في بناء وتنمية اقتصاد الدول، بحيث أصبحت تشكل دعامة لاستقرارها الاقتصادي، ولقد حظيت باهتمام المشرع الجزائري فنظم حياة الشركة في مختلف مراحلها بداية من تأسيسها وتسييرها إلى غاية انقضائها . إن الشركة باعتبارها شخصا معنويا تتأسس وتباشر نشاطها لتحقيق الغرض الذي أنشئت من أجله، فإنها معرضة لانقضائها ولحلها لأي سبب من أسباب الانقضاء، فتنتهي الرابطة القانونية التي تجمع بين الشركاء وتدخل في مرحل التصفية

Recuperação extrajudicial : alienação de estabelecimento e inocorrência de sucessão - Filho, Oliveira; De, Paulo Furtado (Universidade de São Paulo, 2024)
Este trabalho tem por objetivo a análise da disciplina da alienação do estabelecimento empresarial na recuperação extrajudicial, especialmente quanto à ocorrência ou não da sucessão do adquirente nas obrigações do alienante. As normas que ensejam a sucessão do adquirente, durante o período de normalidade econômica, buscam proteger os credores, mas contêm desincentivos à celebração do negócio, que tendem a ser ainda maiores num cenário de crise do alienante, diante da perspectiva de que não lhe sobrarão bens bastantes para honrar suas obrigações. Diante disso, a disciplina da alienação do estabelecimento empresarial, na recuperação judicial e na falência, expressamente eliminou a sucessão do adquirente, atraindo maior número de interessados, com a maximização do valor dos ativos e a perspectiva de continuação da atividade, em benefício dos interesses sociais e econômicos que gravitam em torno da empresa, em especial dos empregados, fornecedores, consumidores e o Fisco. Mesmo após o advento da reforma operada pela Lei no 14.112/2020, contudo, não há, na disciplina da recuperação extrajudicial, uma norma clara afirmando a inocorrência de sucessão na alienação de estabelecimento empresarial. Isso explica a preferência pela recuperação judicial em detrimento da extrajudicial, uma solução mais simples, célere e barata para superação da crise do devedor, em benefício dele próprio, dos credores, stakeholders e do funcionamento da máquina judiciária. Daí porque o estudo da disciplina da sucessão na alienação do estabelecimento empresarial ganha especial importância. A depender de como ela for compreendida, o trespasse tanto poderá constituir instrumento de superação da crise e preservação da empresa (ainda que sob outra titularidade), ou ser completamente inviabilizado, em prejuízo dos interesses econômicos e sociais que poderiam ser por ele atendidos. This work focuses on the analysis of the Brazilian legal framework regarding the sale of business in out-of-court restructuring proceedings (known as extrajudicial restructuring), specifically concerning the occurrence or non-occurrence of debt succession from the debtor- seller to the purchaser (successor liability). The rules establishing successor liability for purchasers were drawn up to protect creditors during periods of economic normalcy. However, those rules contain disincentives to the business sale, which tend to be even greater during scenarios of crisis, given the debtors prospects of not having enough assets left to fulfil their obligations. In light of this, Brazilian regulation regarding business sale in judicial restructuring and bankruptcy proceedings explicitly exclude successor liability, attracting a greater number of interested parties, and maximizing asset value and the prospects of continuity for the business activity. All of this in benefit of the social and economic interests that gravitate around the company, especially employees, suppliers, consumers, and the Tax Authority. Nevertheless, even after the reform by Law No. 14,112/2020, there is no clear rule over extrajudicial restructuring stating the non-occurrence of successor liability in a business sale. This explains a preference for judicial over extrajudicial reorganisation, a simpler, faster, and less costly solution for overcoming the debtor\'s crisis, benefiting the debtor himself, the creditors, the stakeholders, and the Judiciarys functioning. Hence, the study of the regulation applied to successor liability in sales of business gains special importance. Depending on how this regulation is understood, the sale can either be a tool for overcoming crisis and preserving the company (even if under different ownership) or it can be made utterly unviable, damaging economic and social interests that could be protected by it.
Keywords: Alienação de estabelecimento; Alienação de unidade produtiva isolada (UPI); Business sale; Extrajudicial restructuring (Out-of-court reorganisation); Recuperação extrajudicial; Successor liability; Sucessão; UPI (Isolated Productive Unit) Sale

Guide de légistique - Union Economique et Monétaire Ouest Africaine (UEMOA, 2024)
L’article 4 du Traité modifié de l’UEMOA assigne, entre autres, comme objectifs à l’Union, « le renforcement de la compétitivité des activités économiques dans le cadre d’un environnement juridique rationalisé et harmonisé » et «l’harmonisation des législations des États membres». Dès lors, l’atteinte de ces objectifs implique la prise au niveau communautaire de textes juridiques à destination des citoyens et des administrations des États membres. La Commission de l’UEMOA, en sa qualité d’Organe exécutif de l’Union, dispose du pouvoir d’initiative des actes prévus par le Traité modifié de l’Union. Aussi, dans sa volonté de mise en place d’une bonne gouvernance normative et d’amélioration de la qualité rédactionnelle des actes communautaires, la Commission a jugé utile d’élaborer un guide de légistique visant à renforcer les capacités de ses cadres, en matière de techniques d’élaboration des actes. Ce document de référence a vocation à encadrer tout processus d’élaboration d’un texte communautaire, de sa phase de conception à celle de son adoption. Ainsi, le présent guide de légistique de la Commission, qui décline les fondamentaux et directives de bonne pratique de l’activité normative, s’articule autour de quatre (4) parties, à savoir (i) les acteurs de l’activité normative, (ii) la phase exploratoire de l’activité normative, (iii) le choix de l’instrument normatif et (iv) les techniques générales de rédaction des textes communautaires. La première partie du guide de légistique renseigne sur les différents acteurs du processus normatif. Les services des départements de la Commission initient des projets de textes communautaires, qui sont soumis pour avis, validation, approbation ou adoption à diverses entités communautaires et étatiques, en fonction du domaine dans lequel intervient le projet d’acte. À cet effet, le guide de légistique insiste sur le fait que l’activité normative est participative et itérative. La consultation de ces acteurs peut être systématique, comme c’est le cas pour les experts étatiques et la Direction des Affaires Juridiques, ou facultative, c’est le cas notamment des Institutions spécialisées autonomes ou des Organes consultatifs de l’Union. Les procédures d’approbation et d’adoption spécifiques à chaque acte communautaire sont explicitées à travers la présentation des instances de décision habilitées et des Organes impliqués. Le guide de légistique aborde, dans sa deuxième partie, la phase exploratoire de l’activité normative qui constitue une étape décisive. Cette phase permet d’évaluer s’il est nécessaire de procéder à l’adoption d’un texte pour résoudre un problème ou combler un besoin d’organisation juridique spécifique. Au cours de cette phase, l’initiateur du projet d’acte s’interroge notamment sur l’identification du problème à résoudre et la détermination de la nécessité de l’adoption d’un texte normatif. À l’issue de ces interrogations, le guide de légistique recommande particulièrement l’élaboration d’une feuille de route visant à répertorier les étapes clés de l’activité normative, comme le recours à une mission de consultance, la réalisation éventuelle d’une étude d’impact, l’organisation d’une mission circulaire dans les États membres, la consultation des acteurs concernés par le projet d’acte, la date probable de la saisine de l’autorité normative aux fins d’adoption de l’acte normatif. Le guide suggère de diligenter une étude d’impact, en vue d’évaluer les incidences économiques, financières, sociales et environnementales du projet de texte. Établie au début du processus, cette étude devrait apporter des éléments d’appréciation pertinents susceptibles d’éclairer les décisions des Organes de l’Union. Toutefois, au regard des coûts importants qu’elle pourrait engendrer, elle reste à la discrétion du département initiateur du projet d’acte et des autorités de la Commission, et ne revêt donc pas un caractère obligatoire. Une fois toutes les évaluations effectuées et la nécessité de recourir à une législation avérée, il est indispensable d’identifier l’instrument juridique le plus approprié pour légiférer dans l’Union. À cet effet, le guide de légistique rappelle dans une troisième partie, les différents critères liés au choix des actes, ainsi que la typologie de chaque acte pris au niveau de l’Union par la Conférence des Chefs d’État et de Gouvernement, le Conseil des Ministres, la Commission et le Président de la Commission, tout en explicitant l’objet et la portée de chaque acte. En effet, les choix des instruments juridiques communautaires que sont les Protocoles et Actes additionnels, les Règlements, les Directives, les Décisions, les Recommandations et les Avis sont généralement liés à la détermination des Organes compétents pour légiférer au regard des dispositions communautaires en vigueur et des objectifs poursuivis. Enfin, le guide de légistique s’appesantit, en dernier lieu, sur les techniques de rédaction des textes normatifs communautaires. Il s’agit, à ce niveau, de mettre par écrit dans un acte juridique, la norme pensée. Un accent particulier est mis sur la nécessité de bien circonscrire la matière normative devant figurer dans le projet d’acte, ainsi que sa densité normative (sa longueur et son degré de précision) au regard de sa substance, mais également du principe dit de la proportionnalité, qui prescrit la limitation des actions des Organes de l’Union à ce qui est strictement nécessaire pour atteindre les objectifs du Traité modifié de l’UEMOA. Les règles relatives à la rédaction des éléments constitutifs des actes communautaires, à savoir le titre, le préambule, le dispositif et éventuellement les annexes sont également mises en exergue. Les techniques de rédaction spécifiques au dispositif des actes sont formulées et explicitées dans cette dernière partie. Il s’agit notamment des dispositions finales, des références, des clauses abrogatoires, ainsi que des lignes directrices relatives à la rédaction des actes modificatifs. Enfin, une bonne rédaction des textes communautaires suppose la connaissance de règles générales de forme indispensables pour la formulation et une bonne compréhension de l’acte normatif. Dans ce cadre, l’énonciation des principes directeurs attachés au style légistique, au bon usage de la langue dans la rédaction des actes communautaires, ainsi qu’à la construction des phrases des textes normatifs dans le guide permet d’attirer l’attention de l’initiateur du projet d’acte sur certains écueils dont il doit se départir lors de la phase de rédaction.

Les droits des entreprises tierces dans les procédures alternatives du droit antitrust - Meron, Sophie (Université de Rennes, 2024)
Les entreprises sont souvent victimes des pratiques anticoncurrentielles de leurs concurrents, clients ou fournisseurs. Longtemps, elles ont été exclues des procédures alternatives qui se déroulent entre l’autorité de contrôle et les cartellistes. Récemment et de manière progressive, un statut a été ébauché. Le phénomène de fondamentalisation du droit des affaires et la jurisprudence en sont à l’origine. Cependant, la protection accordée demeure insuffisante. Pour l’améliorer et l’étendre, une modernisation de ces procédures, voire une réforme du système, peut être envisagée.
Keywords: Antitrust law; Cartel; Cartels; Company; Competencia; Competition law; Concurrence; Concurrence (droit); Droit des entreprises; Ententes; Entreprise; Negotiated procedures; Procédures alternatives; Third-Party; Tiers (droit)

Les assurances CIMA et les événements exceptionnels - ERSUMA - OHADA (2024)

L'émergence d'un droit de la compliance - Plane, Eugenie (Université de Montpellier, 2024)
La compliance est une notion qui ne fait pas consensus : tantôt désignée comme une simple démarche de conformité de l’entreprise à la loi, tantôt comme une méthode d’efficacité de la loi, elle a pu être associée à la responsabilité sociétale des entreprises et à l’éthique des affaires. Son développement exponentiel ces dernières années dans le paysage législatif français et européen en diverses matières et divers codes a rendu nécessaire l’organisation de la compliance en une véritable matière, voire une nouvelle branche du droit, pour laquelle il convient d’identifier un système cohérent de normes avec une méthode et des principes propres et de dégager un régime uniforme.
Keywords: Compliance (droit); Conformité; Corégulation; Supervision

Le nouveau visage de l’immunité d’exécution dans l’espace OHADA - ERSUMA - OHADA (Ecole régionale supérieure de la Magistrature, 2024)

L'admission des conventions extra-statutaires dans le droit de l'OHADA - Sene, Cheikh (International Journal of Accounting, Finance, Auditing, Management and Economics, 2024)
The revised uniform act governing the rights of commercial companies and economic interest groups did not create extra-statutory conventions. These existed well before its adoption. The OHADA legislator, wanting to prioritize the security of conventional relationships and the promotion of investments on African territory, proceeded to modify its uniform act of 1997 by adopting extra-statutory conventions. However, faced with the thorny question of the necessary respect for the principle of contractual freedom and the articulation between extra-statutory agreements, the provisions of the uniform act and the statutes, he finally ducked. Thus, he attempted to subtly embrace extra-statutory conventions through article 2-1 of his revised uniform act on commercial companies which came into force on January 30, 2014. Through his approach, he seems to want in an uncertain manner rectify an initial error or at least fill a legal void present in its old uniform act. It now establishes the supremacy of the legal provisions of the uniform act and the statutes over extra-statutory agreements and sets the legal requirements imposed on shareholders for the validity of their agreements. The review of  theoretical and empirical literature made to article 2 of the uniform act on commercial companies, the OHADA legislator has not succeeded in removing the doubt on the determination of the law applicable to extra-statutory agreements, these still remain gorverned, to a large extent, by provisions relating to contract law. However, the reform is not without interest in the Senegalese business environment, it strengthens the already existing system for securing business and promoting investments. L’acte uniforme révisé portant droit des sociétés commerciales et du groupement d’intérêt économique n’a pas créé les conventions extra-statutaires. Celles-ci existent bien avant son adoption. Le législateur OHADA, en voulant privilégier la sécurité des rapports conventionnels et la promotion des investissements sur le territoire africain, a procédé à la modification de son acte uniforme de 1997 en adoptant les conventions extra-statutaires. Toutefois, devant l’épineuse question du nécessaire respect du principe de la liberté contractuelle et de l’articulation entre les accords extra-statutaires, les dispositions de l’acte uniforme et les statuts, il s’est finalement esquivé. Ainsi, il a tenté d’épouser subtilement les conventions extra-statutaires à travers l’article 2-1 de son acte uniforme révisé sur les sociétés commerciales entré en vigueur le 30 janvier 2014. À travers sa démarche, il semble vouloir de façon incertaine rectifier une erreur de départ ou du moins combler un vide juridique présent dans son acte uniforme ancien. Il consacre désormais la suprématie des dispositions légales de l’acte uniforme et des statuts sur les accords extra-statutaires et fixe les exigences légales qui s’imposent aux actionnaires pour la validité de leurs conventions. La revue de littérature théorique et empirique a permis de constater que malgré les modifications apportées à l’article 2 de l’acte uniforme sur les sociétés commerciales, le législateur OHADA n’a pas réussi à lever le doute sur la détermination du droit applicable aux conventions extra-statutaires, celles-ci restent encore régies, dans une large mesure, par des dispositions relevant du droit des contrats. Néanmoins, la réforme n’est pas sans intérêt dans l’environnement sénégalais des affaires, elle vient renforcer le dispositif déjà présent de sécurisation des affaires et de promotion des investissements.
Keywords: Actionnaires; Associates; Associés; Conventions; Freedom of contract; Liberté contractuelle; Shareholders; Statutes; Statuts

Pratique de la coopétition dans les sociétés coopératives agricoles au Togo - Mafongoun, Dodji Moïse; Gbaguidi, Léandre; Biboum, Altante Désirée (Revue Internationale du Chercheur, 2024)
L’objectif de cet article consiste à identifier les pratiques de management stratégiques basées sur la stratégie de coopétition entre agriculteurs qui cohabitent dans les sociétés coopératives agricole (SCA) togolaises. Peu de recherches s'intéressent en effet, aux facteurs qui poussent les entreprises relevant de l’économie sociale et solidaire à recourir aux pratiques de coopétition. En outre, les travaux s'avèrent rares quant aux formes de coopétition adoptées par ce type d'organisations notamment agricoles dans les pays du sud. Il s’agit donc d’apporter un éclairage sur les pratiques de coopétition adoptées dans le contexte spécifique du Togo. La méthode de recherche qualitative a été adoptée. Cette approche a permis de rencontrer trente-deux agriculteurs. Les entretiens se sont déroulés auprès de treize SCA situées en région maritime. L’analyse thématique des discours met en exergue trois thèmes à partir des interventions recueillies. Les résultats montrent que la pratique de coopétition dans les SCA se traduit par une approche concurrentielle de différenciation et une approche de coopération fondée sur l’apprentissage organisationnel.
Keywords: Coopérative agricole; Coopétition; Management stratégique

La ley de comercio electrónico en el sistema contractual ecuatoriano - Palma, Vanessa Alexandra Henríquez; Toapanta, Angela Dayana Miranda; Navarrete, Cristobal Teodoro Veliz; Vega, Johana Alexia Fierro (Polo del Conocimiento, 2024)
El comercio electrónico es una nueva forma de comercio en auge, constituida por transacciones comerciales que se llevan a cabo por medio de Internet. En este sentido, el contrato electrónico es un acuerdo de voluntad que se establece mediante el uso de herramientas electrónicas en donde las partes se comprometen a cumplir lo que se establezca, conservando las características básicas del contrato tradicional y su contenido surte efecto legal. Ahora bien, el conjunto de leyes regulatorias es fundamental para garantizar la transparencia y la seguridad en las transacciones electrónicas, lo cual genera confianza entre las partes involucradas en las actividades de comercio electrónico. En consecuencia, y dada la importancia de la legislación en esta materia, el propósito de la presente investigación es plasmar las generalidades del sistema contractual del comercio electrónico en el Ecuador, específicamente su marco legal. El enfoque metodológico de la investigación es una revisión bibliográfico – documental. Las bases legales internacionales para el desarrollo de la normativa contractual en materia de comercio electrónico en Ecuador, tiene base en la Comisión de las Naciones Unidas para el Derecho Mercantil Internacional (CNUDMI) y el conjunto de textos legislativos emanados de este ente. Especialmente la Ley Modelo, la cual tiene el propósito de colaborar con los Estados en la reforma y modernización de sus leyes acerca del procedimiento arbitral. Igualmente, estas normas especiales se complementan con normas comunes a los contratos con fundamentos tradicionales en la incursión de esta nueva forma de expresar la voluntad de las partes, tales como la Constitución de la República del Ecuador, el Código Civil, el Código de Comercio, el Código Orgánico General de Procesos (COGEP), la Ley Orgánica de Defensa del Consumidor y, más recientemente, la Ley Orgánica para la Transformación Digital y Audiovisual.
Keywords: Comercio; Comércio Eletrônico; Contractual; Direito; Electronic commerce; Electrónico; Ley; Sistema

الحق في الحبس كضمان للبائع في عقد البيع - القادر, بركان عبد; ياسين, مهدي (جامعة مولود معمري تيزي وزو, 2024)
يتميز مجال العقود والالتزامات بأهم عنصر من وهو التقابل والتماثل في الحقوق والواجبات التي ترد على كل طرف، غير أنه من بين الحقوق التي يتمتع بها الطرف المتعاقد في حال تقاعس الطرف المتعاقد معه عن التنفيذ أو الامتناع عن ذلك، هو ممارسة الحق في الحبس سواءً كان الحابس بائعاً أو مشتري. يرد الحق في الحبس على كافة الأشياء التي تكون قابلة للحجز والتنفيذ، ولعل عدم قابليته للتجزئة يعد من أهم الخصائص التي تجعل منه ضمانة حقيقية للوفاء بالديون أو لأداء الالتزامات المتفق عليها بموجب العقد. يندرج الحق في الحبس ضمن الوسائل الدفاعية للدائن يلجأ إليها تجاه المدين، وفق ما نص عليها القانون من جهة، وما تم الاتفاق عليه في العقد من جهة أخرى، حيث يتطلب هذا الحق في وجوده توفر مجموعة من الشروط، ويترتب عن إعماله العديد من الآثار القانونية السارية على أطراف العلاقة التعاقدية، وينقضي بوسائل شتى تندرج من حيث الأهمية والأولوية في التطبيق بين الأصل والاستثناء.
Keywords: Bien immobilier; Bien meuble; Chose vendue; Créanciers; Droit accessoire; Droit de rétention; Exception d'inexécution; Exécution; Possession; Prix dû; Renonciation; Sûreté adéquate; التأمين الكافي; التنازل; الثمن المستحق; الحق التبعي; الحق في الحبس; الحيازة; الدائنين; الدفع بعدم التنفيذ; الشيء المبيع; العقارات; المنقولات; الوفاء

Multilateralism and Bilateralism in International Trade - Aro, Gilbert; Nwosu, Chiedozie; Ngene, Innocent; Nnadi, Samuel (African Journal of Politics and Administrative Studies, 2024)
The contemporary international system is dominated by international trade. Therefore, it is the fundamental and critical aspect of international economic relations. The study investigated the how African states participate in common bilateral and multilateral trade relations. Its core objective is to study whether trade barriers have been made less cumbersome among the participating countries in African continental region. Common trade and international trade justify the essence of globalization. The wave of globalization has necessitated the flux of multilateralism and bilateralism among the participating nations in the international trade. Methodologically, the study adopted comparative theory of international trade. Its method of data collection is documentary method and analyzed through interpretive studies. As the international trade continues to take the centre stage in the international economic relations; States continue to engage in multilateral and bilateral trade relations. The operations of Transnational Corporations (TNCs) and Multi-national Corporations (MNCs) as non-state actors also engage in multilateral and bilateral agreements with the host states. Several agreements led to the establishment of General Agreement on Tariff and Trade (GATT) and World Trade Organization (WTO) remains conspicuous products of multilateralism and bilateralism in the international trade in the recent time. African Continental Free Trade Area (AFCFTA) is a multilateral agreement enacted by fifty-four members of the African Union (AU) in 2019 to boost trade relations among them. Its core benefit is to facilitate free trade and removal of trade barriers in the region Therefore, this study is set to examine the advantages and impacts of AFCFTA and other multilateral and bilateral agreements in Africa and the world at large.
Keywords: AfCFTA; Bilateralism; International Trade; Multilateralism; Trade agreements; WTO

Termination of Commercial Sale Contracts under the OHADA Uniform Act Relating to General Commercial Law - Ataíde, Rui; Boura, Marta (Centro de Investigação de Direito Privado (CIDP) Research Paper, 2024)
The Uniform Act relating to General Commercial Law of the Organisation for Harmonisation of Business Law in Africa (hereinafter referred to as the OHADA Uniform Act) establishes a commercial sale regime applicable to any trader (natural or legal person), including any commercial companies whose place of business or registered office is located in the territory of a party to the Treaty on the Harmonisation of Business Law in Africa. In this study we propose to analyse the non-performance of commercial sale agreements, focused on its termination regime, by reflecting on the right of termination, the termination by judicial means, its grounds, exemption from liability and the effects of termination. The economic and legal relevance of the commercial sale contract justifies the opportunity to reflect on how legal standardisation process has been achieved overall, particularly with regard to termination regimes. Both OHADA Uniform Act and the Vienna Convention on Contracts for the International Sale of Goods of 1980 (CISG) were conceived as unification mechanisms to circumvent the constraints and legal uncertainty associated with cross-border trade. Therefore, this analysis aims to assess how OHADA rules embody the long process of evolution in French law, as well as the influence of the CISG.
Keywords: CISG; Commercial sale contracts; Comparative law; French law; International Organisations; Legal standardisation; OHADA; Portuguese law; Termination regime; Uniform Act relating to General Commercial Law for Harmonisation of Business Law in Africa

Employee’s Pilferage and Security in Beverage Manufacturing Companies in Lagos State, Nigeria - Attah, Edwin; Abdullahi, Liman; Yusuf, Usman (African Journal of Politics and Administrative Studies, 2024)
The purpose of this paper is to examine the relationship between employee pilferage of pilferage and security in beverage manufacturing companies in Lagos State. The study is anchored on the rational choice theory in order to understand the connection between pilferage and security in beverage manufacturing companies in Lagos State. The researcher adopted a mixed research method involving survey research and historical research designs. The population of this study is 8,595 staff. This comprises all employees of Promasidor Nigeria Ltd, Nigeria Bottling Company (Coca Cola), Cadbury Nigeria Plc, and Guiness Nigeria Plc. The sample size of the study was 400 determined using Rakesh Sample size formula. Data were collected from primary and secondary sources. Primary data were collected using questionnaires, while secondary data were collected from related works on pilferage and security in beverage manufacturing companies. Data collected from questionnaire were analyzed using absolute frequencies and simple percentages, while data from secondary sources were analyzed using relational-content analysis. Among other things, it was found that the higher the level of pilferage, the lower the level of security of employees in beverage manufacturing companies in Lagos State. Among other things, it was recommended that given that there is relationship between pilferage and security in beverage manufacturing companies in Lagos State, beverage manufacturing companies in the state should ensure that stealing is drastically reduced in their various organizations through employment, training and proper motivation of staff who must be full-time staff. This would largely make the employees committed to work and shun pilferage.
Keywords: Pilferage; companies; employee; manufacturing; security

Evaluation of Revenue Effect from Tax Components and Economic Growth in Nigeria - Atuma, Emeka; David, Amarachi; Nwibo, Nneamaka; Nkwagu, Chibuike; Udenta, Blessing; Njim, Sunday; Uwaeke, Uchechukwu (African Journal of Politics and Administrative Studies, 2024)
This research empirically examined the relationship between tax revenue and economic growth in Nigeria for the period 1994-2021. Ex-post facto research design was adopted in the investigation. Multiple regression analysis was employed, in which Auto-Regressive Distributed Lag (ARDL) model as the method of analysis was utilized in the research. The ARDL model evaluates long-run and short-run interactions among the specified variables. The unit root tests conducted using Augmented Dickey-Fuller (ADF) revealed that the time series variables used were stationary at level and the first difference, but none of the variables was stationary at the second difference. The ARDL – Bound test analysis revealed the existence of long-run equilibrium relationship between tax revenue and economic growth in Nigeria within the period of the study. The coefficient of error correction mechanism was statistically significant and also negatively signed. The results equally showed that both company income tax and value added tax were statistically significant and positively related to economic growth in Nigeria in both shot-run and long-run periods; whereas personal income tax was statistically insignificant and positively related to economic growth in Nigeria in both short-run and long-run. Based on the findings, the study therefore recommended tax authorities responsible for tax administration should upgrade the tax database to capture all potential tax-payers in order to broaden tax income.
Keywords: Autoregressive Distributed Lag Mode; Economic growth; Nigeria; Tax Revenue

Re-Evaluation of the Effectiveness of Exchange Rate Depreciation on Import Demand in Nigeria - Atuma, Emeka; Ebuka, Bright; Nwibo, Fidelia; Nkwagu, Christain; Nancy, Udenta; Njim, Robert; Ogbonna, Nkemdirim; Uwaeke, Uchechukwu (African Journal of Politics and Administrative Studies, 2024)
The study investigated the impact of exchange rate depreciation on import demand in Nigeria from 1986 to 2021. The data used was sourced from Central Bank of Nigeria. Ex-post facto research design was adopted in the investigation. Multiple regression analysis was employed, in which Auto-Regressive Distributed Lag (ARDL) model as the method of analysis was utilized in the research. The ARDL model evaluates short-run and long-run interactions among the specified variables. The unit root tests conducted using Augmented Dickey-Fuller (ADF) revealed that the time series variables used were stationary at level and the first difference, but none of the variables was stationary at the second difference. The ARDL – Bound test analysis revealed the existence of long-run equilibrium relationship between exchange rate depreciation and import demand in Nigeria within the period of the study. The coefficient of error correction mechanism was statistically significant and also negatively signed. The results equally found that exchange rate depreciation is statistically not significant and negatively impacted on import demand in Nigeria in the short-run. However, in the long-run, exchange rate depreciation is negatively impacted to import demand and statistically significant. Causal relationship does exist between exchange rate depreciation and import demand in Nigeria with causation running from import demand to exchange rate depreciation. On the basis of the findings, the researcher made the following recommendations among others: Government should consider inward looking to strengthen the imports substitution policies that ensure massive production of goods and services.
Keywords: Autoregressive Distributed Lag; Exchange Rate Depreciation; Import Demand; Mode; Nigeria

Nigeria-China Relations and Economic Development - Chiedozie, Nwosu; Aloh, Ngwuta; Ibiam, Okechukwu; Nwankwo, Felix; Ikpolo, Gabriel; Iwuala, Harrison (African Journal of Politics and Administrative Studies, 2024)
This work explored the dynamics of Nigeria-China relations from the political and economic points of view between 1999-2023. The primary concern of this paper is to discern the extent Nigeria-China relations is mutually beneficial and how Nigeria can stand to gain more if the relationship is properly aligned to Nigeria’s national interest. The central argument of this work is that Nigeria stands to gain more from China than from the West bearing in mind the fact that over one hundred years of Africa’s relationship with the West has been largely exploitative and disadvantageous. In this regard, the research employed both primary and secondary sources of data collection. The primary sources relied on first-hand information gathered from the Chinese Embassy as well as key actors within the Nigeria External Affairs Ministry and Key Informant Interviews on experts in Nigeria-China relations. The secondary sources relied on already existing information from libraries, text books, journals and the internet. The theoretical framework employed is the Complex Interdependence Theory. The conclusion drawn from this work is that Nigeria-China relations have not fully developed to the extent of being more beneficial to Nigeria economically and politically. What currently subsists is that China is gaining economically more in terms of trade to Nigeria’s disadvantage. However, politically and socio-culturally, the two countries are mutually benefiting due to various diplomatic protocols and cultural exchanges. The study recommended among others that Nigeria must strive to develop her techno-industrial export-oriented base to ensure more symmetric beneficial relationship with China.
Keywords: Bi-Lateral Relations; China; Development; Economic Development; Nigeria

The impact of ISDS arbitration claims and adjudication on cross-border direct investment - Du, Julan; Zhang, Yifei (Transnational Corporations Review, 2024)
This study investigates the impact of the arbitration cases under the Investor-State Dispute Settlement (ISDS) scheme on cross-border direct investment in the form of merger and acquisition deals. The initiation of ISDS claims has significant and negative effects on direct investment from the claimant home country to the developing or weak-institution responding country. Indirect expropriation claims often have stronger effects than direct expropriation claims. The investor-win arbitration cases produce a significant substantiation effect by reducing merger flows, while the state-win cases produce an acquittal effect that encourages the subsequent capital inflow to the respondent state. Both effects are more striking in weak-institution or less developed target countries. We also detect some spillover effects of ISDS arbitration.
Keywords: Arbitration decisions; Cross-border merger deals; Direct and indirect expropriations; ISDS claims

Digitalization and Tax Administration in the Gambia - Ogbeta, Oghenekevwe; Ayeni, Oluwadare (African Journal of Politics and Administrative Studies, 2024)
This study extensively explored the potential of digitalization in The Gambia Revenue Authority's tax administration, amidst concerns over the practical application of digital tools and their underutilization, which have hindered the realization of improved revenue mobilization and efficient tax processes in The Gambia. The research, adopting a mixed method design, aimed to understand the intricate relationship between digitalization and tax administration in The Gambia. With specific objectives, including identifying driving factors, examining effects, and evaluating the correlation with GRA's performance, the study adopted quantitative and qualitative analyses. Similarly, the study population is two thousand, one hundred and eighty-eight (2188). Using Krejcie and Morgan (1970) formula, out of 2188 population of the study, three hundred and twenty seven (327) were selected as the sample size. This encompassed individuals drawn from the Ministry of Finance and Economic Affairs, GRA staff, and corporate taxpayers using a stratified and proportionate-to-size sampling approach. Hypotheses analysis revealed a statistically significant and positive effect of digitalization on tax administration, indicating improved efficiency and GRA effectiveness. Also, Spearman's rank-order correlation affirmed a positive relationship between digitalization and tax administration. Furthermore, qualitative insights from stakeholder interviews highlighted drivers such as international financial body stipulations, modernization imperatives, trust-building, accurate record-keeping, and alignment with global standards. Recommendations include training programs for GRA staff, public awareness campaigns, and enhancing user experiences for e-payment systems, among others.
Keywords: Digitalization; Tax Administration; Tax Compliance; Tax Evasion; Taxation

Sustainable development clauses in international contracts through the lens of the Unidroit principles - Pannebakker, Ekaterina (Uniform Law Review, 2024)
Most transactions that leave an imprint on the environment and communities are organized by commercial contracts. However, little is known about the way in which parties reflect sustainable development in contractual clauses. How can parties to international contracts commit to respect sustainable development goals? What are the possible degrees of commitment? Which contractual mechanisms can apply to the monitoring of compliance? How does one establish a link between the failure to meet sustainable development goals and the contractual liability or termination of contract? This article identifies contractual clauses relating to sustainable development and analyses these clauses through the lens of the 2016 International Institute for the Unification of Private Law (Unidroit) Principles of International Commercial Contracts (PICC). Drawing inspiration from open access contracts, the analysis will demonstrate that Article 1.8 of the PICC, precluding inconsistent behaviour, and Articles 5.1.4 and 5.1.5, on the duty of best efforts and the obligation to achieve a specific result, as well as the provisions on liability, can assist contract drafters, judges, and arbitrators in drafting and interpreting such clauses.

The efficient enforcement challenge of secured transactions law reforms in civil law systems: self-help repossession, strict foreclosure, and other methods for the acceleration of enforcement of security interests - Tajti (Thaythy), Tibor (Uniform Law Review, 2024)
Although the forging of an efficient system for enforcement of security interest is one of the central expectations of secured transaction law reforms in civil law systems, the results hardly give reason for satisfaction. As the reforms tend to be supported and influenced by various international organizations’ projects (especially the World Bank, the European Bank for Reconstruction and Development, the International Institute for the Unification of Private Law, and the United Nations Commission on International Trade Law), most out-of-court methods of enforcement of security interests have played a central role. Yet due to civil law’s general hostility towards self-help as such, either the introduction of the concept has been rejected or the local limited-reach kin have been merely ‘paper tigers’. Similarly, although security interests on several types of collateral (accounts, investment property) or on the workhorse of the English financial system—the floating charge—have also been enforced extrajudicially (save the exceptions), little attention has been attributed to these enforcement modalities. The same applies to strict foreclosure in civil law systems still being prohibited, or restricted, and thus rarely resorted to, due to the inherited hostility towards the doctrine of lex commissoria. Rethinking local laws on preliminary and temporary court orders to match them with such globally known ex parte preliminary measures as the English Mareva Injunction or the French Saisie Conservatoire, which allow creditors to swiftly freeze debtors’ assets and thus substitute self-help repossession, has also been given short shrift. The enforcement segment, consequently, remains the Achilles’ heel of secured transaction law reforms in civil law systems. This article desires to contribute to reform literature by addressing these deficiencies and by offering tested, fully or partially fitting, functional equivalents of self-help repossession.

Repenser l'entreprenant en droit OHADA : une approche épistémologique constructive - Agbam, Komlanvi Issifou; Faye, Fodé David (Revue africaine de droit des affaires, 2024)
Le secteur informel, qualifié souvent de véritable moteur de la construction des villes et de l’animation de la vie urbaine en Afrique, a fait l’objet de nombreuses études dans lesquelles était décriée sa principale caractéristique, à savoir le fait qu’elle évolue en marge du cadre formel – légal et réglementaire – d’exercice des activités économiques. Fort de ce constat, le législateur de l’Organisation pour l’Harmonisation en Afrique du Droit des Affaires (OHADA) a entrepris une réforme afin d’attirer les acteurs de ce secteur vers une formalisation progressive. Ainsi, l’entreprenant a connu son entrée dans l’espace OHADA à travers la réforme de l’AUDCG opérée le 15 décembre 2010 à Lomé (Togo). L’un des objectifs assignés à cette réforme était la facilitation de la création d’entreprises individuelles et surtout l’incitation des entrepreneurs du secteur informel à un minimum de formalisation. Le statut de l’entreprenant devrait jouer ce rôle et être, ainsi, l’outil juridique efficace et indispensable de l’appréhension de l’économie informelle dans l’espace OHADA. Cette mission difficile assignée à ce statut est aujourd’hui loin d’être atteinte. L’ineffectivité de la contribution du statut de l’entreprenant à la structuration juridique et à la formalisation des petites et moyennes entreprises qui exercent leurs activités dans un secteur informel dans l’espace OHADA mérite d’être soulevée après plus d’une décennie d’inefficacité au regard de l’objectif fixé au départ. À travers une approche épistémologique constructive, cet essai vise à retracer les difficultés concrètes de la mise en œuvre du statut de l’entreprenant dans l’espace OHADA et à proposer des pistes d’amélioration.

Les qualités essentielles de l'arbitre en droit OHADA - Agbénoto, Koffi Mawunyo (Revue africaine de droit des affaires, 2024)

Vers une responsabilité internationale environnementale des Etats en matière de délinquance écologique transfontalières - Ben Ameur, Jihen Bouslimi (Université d'Angers, 2024)
L’objectif de cette thèse consiste à s’interroger sur la pertinence et la possibilité de mettre en place des mécanismes et des outils juridiques permettant de dépasser les faiblesses du régime classique de responsabilité internationale des États, fondé sur la responsabilité pour fait internationalement illicite, et de s’orienter vers une nouvelle théorie de la responsabilité des États en matière de délinquance environnementale transfrontalière fondée sur la responsabilité objective sans faute des États, plus efficiente en matière environnementale. L’évolution de la théorie de la responsabilité internationale des États vers un système objectif tenant compte de la spécificité du dommage écologique permettrait en effet d’améliorer la protection pénale de l’environnement contre la délinquance environnementale transfrontalière, qui ne cesse de se développer à un rythme plus rapide que la progression des mécanismes de protection environnementale. Compte tenu de l’impunité des atteintes graves à l’environnement, non seulement à la suite d’activités licites à risque, mais encore via la progression exponentielle de la délinquance écologique transfrontalière, la reconnaissance d’une infraction environnementale par la communauté internationale n’est plus une utopie et devient progressivement indispensable. Dans cette optique, la notion d’écocide pourrait être explorée, car elle désigne, selon un consensus certes encore flou, mais néanmoins convergent, l’infraction contre l’environnement considérée aujourd’hui comme étant la plus grave qui puisse être, dans la mesure où elle met en danger la sûreté de la planète et la survie de l’humanité. L’apport de cette thèse consiste à envisager une responsabilité internationale environnementale des États adaptée à la nature des dommages écologiques graves et irréversibles provoqués par la délinquance écologique transfrontalière, via la mise en place de mécanismes juridiques et institutionnels spécifiques permettant d’assurer une protection efficace de l’environnement à l’échelle planétaire. The objective of this thesis consists of questioning the relevance and the possibility of putting in place legal mechanisms and tools to overcome the weaknesses of the classic regime of international responsibility of States, based on responsibility for internationally wrongful acts, and to move towards a new theory of State responsibility with regard to cross-border environmental crime based on the objective liability without fault of States, more efficient in environmental matters. The evolution of the theory of international responsibility of States towards an objective system taking into account the specificity of ecological damage would indeed make it possible to improve the criminal protection of the environment against cross-border environmental delinquency, which continues to develop a faster pace than the progression of environmental protection mechanisms. Given the impunity for serious environmental crimes, not only following legal risky activities, but also through the exponential progression of cross-border ecological delinquency, the recognition of an environmental offense by the international community It's no longer a utopia and is gradually becoming essential. From this perspective, the notion of ecocide could be explored, because it designates, according to a consensus that is certainly still vague, but nevertheless convergent, the offense against the environment considered today to be the most serious that can be, in the to the extent that it endangers the safety of the planet and the survival of humanity.The contribution of this thesis consists of considering an international environmental responsibility of States adapted to the nature of the serious and irreversible ecological damage caused by cross-border ecological delinquency, via the establishment of specific legal and institutional mechanisms to ensure effective protection. Of the environment on a global scale.
Issue: 2024ANGE0069
Keywords: Activités dangereuses; Cross-Border environmental crime; Dangerous activities; Dommages environnementaux; Droit international; Délinquance environnementale transfrontalière; Environmental damage; Environmental justice; Environnement; Infractions contre l'environnement; Institutional mechanisms; International environmental responsibility of states; Justice environnementale; Mécanismes institutionnels; Planetary security; Responsabilité environnementale internationale des Etats; Responsabilité pour dommages à l'environnement; Responsabilité pénale (droit international); Sécurité planétaire; Tribunaux criminels internationaux; Écocide

Les actualités de l'arbitrage maritime - Delebecque, Philippe (Revue africaine de droit des affaires, 2024)

La démocratie actionnariale à l’épreuve des TIC en droit des sociétés OHADA - Looha Bongue Sosso, Stéphane (Revue africaine de droit des affaires, 2024)
Les TIC marquent une rupture technologique et parfois axiologique qui, comparée aux précédentes révolutions industrielles, a opéré un bouleversement de nos habitudes, y compris dans l’ensemble des branches du droit. Le droit des affaires OHADA n’a pas échappé à ce phénomène qui s’est subtilement introduit dans le champ très sinueux des sociétés commerciales au point d’impacter leur mode de fonctionnement, de gestion et surtout de prise de décisions. En effet, depuis l’avènement du numérique participatif et interactif, les associés ont davantage un accès permanent et éclairé à la vie sociétaire à telle enseigne qu’il émerge une sorte de gouvernance numérique, éthique et pérenne qui contribue au renforcement de la performance des entreprises et participe au développement durable des Etats.

Libres propos sur la mise en œuvre du droit de rétention dans l’acte uniforme OHADA portant organisation des sûretés - Mfini, Mon-espoir (Revue africaine de droit des affaires, 2024)
Droit reconnu au créancier de retenir un objet qu’il est pourtant tenu de restituer, jusqu’à ce qu’il ait été payé de tout ce que son débiteur lui doit, le droit de rétention est considéré comme une sûreté de très grande simplicité. Par le biais de cette livraison, l’auteur propose une analyse de la mise en œuvre du droit de rétention de l’Acte uniforme portant organisation des sûretés de 2010.

Panorama critique de l’arbitrage OHADA - Ngono, Véronique Carole (Revue africaine de droit des affaires, 2024)

The Enforcement of Settlement Agreements Under the Ohada Uniform Act on Mediation - Nshom, Kelese George (IUS LAW Journal, 2024)
On 23 November 2017, OHADA member states adopted the Uniform Act on Mediation. The Act lays down rules relating to mediation of disputes which, if successful, ends in a settlement agreement. Settlement agreements that are not freely respected by the parties will have no effect unless they are forcefully executed. Forceful execution is made with the help of a court or notably public who are empowered to insert an executory formula on the agreement after verification of its regularity. These local authorities involved in the enforcement process rely on domestic laws of member states which vary from state to state. This has the effect of tainting the harmonization process intended by the OHADA lawmaker and may be inimical to investors. This raises the problem of the suitability of the Act to dispute settlement as regards enforcement of settlement agreements. With the help of qualitative and comparative analysis, this article brings to limelight the intricacies of the enforcement of settlement agreements underOHADA. It concludes that enforcement of settlement agreements is rendered simple and rapid but faces serious drawbacks which could be alleviated by setting up OHADA mediation institution to oversee the entire mediation process, besides other recommendations.
Keywords: Agreement; Enforcement; Exequatur; MARD; Mediación; Mediation; Mediação; Médiation

Le traitement des investissements étrangers dans le Code des investissements de la RDC de 2002 - Nzohabonayo, Anaclet (Revue africaine de droit des affaires, 2024)
Cet article examine le traitement que le code des investissements de la République démocratique du Congo garantit aux investisseurs étrangers qui choisissent ce pays comme destination de leurs investissements. L’étude examine d’abord la portée dudit code en articulant son analyse sur sa philosophie afin de dégager les motivations du législateur et les objectifs que ce dernier lui a assignés. L’examen du champ d’application du code met l’accent sur sa portée ratione personae, ratione materiae et ratione loci. La réflexion explore ensuite les principaux mécanismes de traitement des investissements en démontrant que le code consacre un traitement non discriminatoire envers les investisseurs étrangers et qu’il adhère à l’orthodoxie des normes classiques de protection des investissements. L’étude analyse par ailleurs les incitatifs fiscaux et douaniers que le code concède aux investisseurs étrangers afin d’accroître la compétitivité de la destination congolaise parmi les investisseurs exportateurs de capitaux. Après analyse, l’étude conclut qu’en dépit de ses imperfections que nos analyses ont permis de mettre en lumière, le code des investissements de 2002 offre aux investisseurs étrangers un traitement globalement satisfaisant.
Keywords: Congo (République démocratique); Investissements; Investments

A renúncia a direitos fundamentais processuais na arbitragem: o caso particular do direito a requerer a anulação da sentença arbitral na arbitragem internacional - Teles, Joana Ataíde Cordeiro Galvão (Universidade Nova de Lisboa, 2024)
A arbitragem é um meio de resolução de litígios, que se alicerça na autonomia privada e é reconhecida, quer internacionalmente, quer nas constituições estaduais analisadas, como um modo de exercício, alternativo aos tribunais estaduais, do direito fundamental constitucional à tutela jurisdicional efetiva. A questão que se coloca é a de saber se, em primeiro lugar, as partes podem acordar renunciar, validamente, a direitos fundamentais processuais na arbitragem e, podendo, com que requisitos e dentro de que limites, para, em segundo lugar e em particular, aplicar os requisitos e limites referidos à (in)admissibilidade da renúncia ao direito a requerer a anulação da sentença arbitral na arbitragem internacional. Partindo da ponderação do âmbito, conteúdo e regime dos direitos fundamentais em confronto, de um lado, à tutela jurisdicional efetiva, incluindo o direito à arbitragem e outros direitos fundamentais processuais, como o de impugnar a sentença arbitral em determinados casos e, do outro lado, à autonomia privada, que fundamenta a renúncia, e sem prejuízo de a ponderação dever ser feita em cada caso concreto, concluo que a renúncia àqueles direitos é válida, se cumprir determinados requisitos subjetivos e objetivos, que identifico, incluindo os limites e os respetivos critérios para aferir da referida (in)validade. Quanto ao direito a requerer a anulação da sentença arbitral na arbitragem internacional, concluo que, sem prejuízo e com base nas soluções consagradas de jure constituto, a renúncia por acordo das partes é, do ponto de vista constitucional normativo e, de jure constituendo no direito português, válida, desde que se respeitem aqueles requisitos. Em particular, tem de existir um meio de impugnar a sentença arbitral, quando esta viole, de forma grave, direitos fundamentais processuais e/ou interesses de ordem pública de cada Estado, que não estão na disponibilidade das partes, nos casos e termos necessários a garantir o conteúdo essencial do direito fundamental à tutela jurisdicional efetiva. No entanto, há margem do legislador para adotar o regime mais adequado ao propósito referido. Na arbitragem internacional, do ponto de vista normativo-constitucional, podem as partes renunciar, total e/ou parcialmente, à anulação na sede, quando há a possibilidade de controlo último, pelo menos de violações graves de direitos fundamentais processuais e/ou interesses de ordem pública de cada Estado, aquando do reconhecimento e execução da sentença arbitral, sendo esta a solução legal que, na minha opinião, melhor se coaduna com a arbitragem internacional no seu todo. Arbitration is a dispute resolution mechanism rooted in private autonomy and internationally recognised, as well as in the national constitutions analysed, as an alternative means to state courts for exercising the constitutional fundamental right to effective judicial protection. The primary question of this dissertation is whether the parties can validly agree to waive fundamental procedural rights in arbitration, and if so, under what conditions and within what limits. Secondly, I specifically apply these conditions and limits to the (in)admissibility of waiving the right to seek annulment of the arbitral award in international arbitration. By weighing the scope, content and framework of conflicting fundamental rights – the right to effective judicial protection (encompassing the right to arbitration and other fundamental procedural rights, such as the right to challenge the arbitral award in certain cases), against private autonomy (which justifies the waiver) – and, without prejudice to the necessary case-by-case balancing, I conclude that the waiver of these rights is valid, provided that subjective and objective requirements, including the limits and criteria for assessing the (in)validity of the waiver, are met. Regarding the right to request annulment of the arbitral award in international arbitration, I conclude that, without prejudice to and relying on legal solutions established de jure constituto, the waiver by agreement of the parties is valid from a normative constitutional perspective and de jure constituendo under Portuguese Law, provided such subjective and objective requirements are respected. Specifically, there must be a means to challenge the arbitral award when it seriously violates fundamental procedural rights and/or public order interests of each State, which are beyond the parties’ disposal, in certain cases and under certain terms as necessary to protect the core essence of the fundamental right to effective judicial protection. However, the legislator retains discretion to adopt the most appropriate legal framework for this purpose. In the context of international arbitration, from a normative-constitutional perspective, the parties may waive annulment at the seat, in whole and/or in part, provided there is the possibility of ultimate oversight, particularly in cases involving serious violations of fundamental procedural rights and/or public order interests of each State at the stage of recognition and enforcement of the arbitral award. In my opinion, this legal solution is the one that best aligns with the global system of international arbitration.
Keywords: Annulment; Anulação; Arbitragem; Arbitragem Internacional; Arbitration; Autonomia Privada; Direitos Fundamentais Processuais; Fundamental Procedural Rights; International Arbitration; Private Autonomy; Renúncia; Waiver

L'amiable au service du sauvetage de l'entreprise en difficulté en droit OHADA : la médiation et la conciliation - Toe Adouabou, Laure (Revue africaine de droit des affaires, 2024)
L’acte uniforme originel sur les procédures collectives avait prévu une procédure préventive, le règlement préventif, au bénéfice des débiteurs qui traversent des difficultés sérieuses. La nécessité de la consécration d’une procédure à la fois amiable et préventive s’est imposée. C’est désormais chose faite depuis la révision de 2015. Le législateur a ainsi consacré les procédures de conciliation et de médiation à l’article 2-1 de l’Acte uniforme sur les procédures collectives d’apurement du passif (AUPC). Si pour la mise en œuvre de la première, il faut se référer à l’AUPC, la deuxième est règlementée dans l’Acte uniforme sur la médiation (AUM). Nous proposons donc dans cette étude, à la suite de la présentation de ces procédures amiables comme modes anticipatifs et efficaces de sauvetage d’entreprises, des pistes de réflexion afin de rendre effectif le recours à cet arsenal juridique.

L’autorité de la chose jugée dans l’arbitrage OHADA - Toe, Souleymane (Revue africaine de droit des affaires, 2024)

Réflexion sur l’effectivité des comités de recours dans le règlement des différends de la consommation au Cameroun - Wako, Alain Christian (Revue africaine de droit des affaires, 2024)
La simplification des procédures dans le système extrajudiciaire de la consommation a été une porte d’entrée favorable à la création des comités de recours en droit camerounais de la consommation. Depuis 2011, la vocation première, c’est le règlement des différends relatifs à la protection du consommateur. Au-delà d’une décennie de la consécration, il semble improbable de dire que le consommateur se satisfait de l’existence juridique d’une instance extrajudiciaire nettement taillée à son profit. Le questionnement rend fondamental de savoir si les comités de recours sont effectifs dans le système de règlement de la consommation au Cameroun ? Y répondre n’est pas sans équivoque. Pour cause, l’effectivité des comités de recours semble inachevée. Si une consécration est effective au plan formel, on note plutôt une timide expression de ceux-ci au plan matériel. L’élimination des obstacles à la pleine effectivité des comités de recours s’avère alors inévitable pour plus d’efficacité dans le règlement de la consommation au Cameroun. Dès lors, usant essentiellement de la méthode juridique dans son versant analytique du droit positif de la consommation, l’étude met en relief une constatation de l’effectivité des comités de recours à travers la consécration du mécanisme institutionnel et la spécification de la procédure devant l’instance. Elle observe, en revanche, que la concrétisation des comités de recours reste allégorique et invite à surmonter quelques entraves à l’efficacité de ceux-ci dans le règlement des différends de la consommation au Cameroun.
Keywords: Cameroun; Consumer dispute; Droit de la consommation

التضامن الصرفي في الأوراق التجارية - قلتة, محمد الأمين; بن شاعة, براهيم (Ibn Khaldun University of Tiaret, 2024)
يعد التضامن مبدأ من مبادئ القانون التجاري، وأحد أهم الضمانات التي يعتمدها قانون الصرف من أجل حصول حامل الورقة التجارية على قيمتها عند ميعاد استحقاقها، إذ يحق لهذا الأخير الرجوع على أي موقع أو على جميع الموقعين بكامل قيمة الورقة التجارية. تعد الأ وراق التجارية من وسائل الدفع التي تقوم مقام النقود في الوفاء، فهي تؤدي نفس الوظيفة التي تؤديها النقود، كما وأنها قابلة للتداول، ونظرا لأهمية هذه الأوراق في المعاملات التجارية ولكي تقوم فعلا مقام النقود في الوفاء فقد أحاطها المشرع الجزائري بمجموعة من الضمانات حماية للثقة والائتمان القائم بين التجار،ويعتبر التضامن الصرفي من أهم هذه الضمانات؛ إذ يحمي حامل الورقة التجارية ويشعره بالأمان والطمأنينة، والذي يجعل كل موقع عليها ضامنا للوفاء عند امتناع المسحوب عليه وبذلك يمكن للحامل الرجوع على الملتزمين الصرفيين منفردين أو مجتمعين والمطالبة بقيمة الورقة التجارية سواء كان ذلك في ميعاد استحقاقها أم قبل ذلك الميعاد، فكل موقع عليها يكون مسؤولا على وجه التضامن مع الملتزمين الآخرين Solidarity is one of the principles of commercial law, and one of the most important guarantees adopted by the exchange law in order for the holder of the commercial paper to obtain its value when it is due, as the latter has the right to recourse to any signatory or to all signatories for the full value of the commercial paper. Commercial papers are considered a means of payment that takes the place of money in fulfillment. They perform the same function that money performs, and they are also negotiable. Given the importance of these papers in commercial transactions, and in order for them to actually take the place of money in fulfillment, the Algerian legislator has surrounded them with a set of guarantees to protect trust and credit. existing between merchants, and exchange solidarity is considered one of the most important of these guarantees. It protects the holder of the commercial paper and makes him feel safe and reassured, which makes every signatory of it a guarantor of payment in the event of the drawee’s refusal. Thus, the holder can return to the exchange obligors individually or jointly and claim the value of the commercial paper, whether that is on its maturity date or before that date. Each signatory of it is responsible. In solidarity with other committed people.
Accepted: 2025-01-26T13:11:52Z

Taxpayer Confidentiality : implications of the tax secrecy provisions regarding illegal miners - Kgobe, Kgothatso (University of Pretoria, 2024)
Taxpayer confidentiality and its implications (if any), on illegal miners

La réparation devant la Cour pénale internationale : quel droit pour les victimes ? - Aké, Tchimou Yannick Kévin (Université de Montréal, 2024)
La Cour pénale internationale a été créée dans un but à la fois de répression et de réparation. Ces deux objectifs continuent de se concrétiser et sont clairement devenus indissociables de toute définition qu’on pourrait donner à la CPI. Cependant, si une égalité apparente pourrait exister entre ces deux objectifs, l’effectivité de la réparation s’est montrée, à bien des égards, dépendante de l’effectivité de la répression. La décision du 1er juillet 2016 rendue dans l’affaire Ruto et Sang a confirmé et renforcer cette dépendance. Malheureusement, les victimes sont celles qui paient le plus de frais de cette réalité. Il devient donc urgent pour la CPI de régler cette situation, ne serait-ce que pour offrir plus d’espoir aux victimes. Le salut pourrait venir d’une remise en cause des principes régissant les procédures devant la Cour. Sans rien inventer, la CPI pourrait grandement s’inspirer de certaines pratiques étatiques. D’abord, il pourrait être envisagé de dissocier et de rendre autonomes les procédures qui visent la condamnation pénale et celles qui visent la réparation, de sorte à rendre l’absence de condamnation pénale inopportune pour la détermination de la responsabilité civile de l’accusé. De plus, il pourrait être envisagé des alternatives lorsqu’il n’y a pas de civilement responsable, de sorte à offrir une reconnaissance juridique aux victimes et à leur donner une ordonnance de réparation. En ce sens, la CPI gagnerait peut-être à aller au-delà de la responsabilité individuelle. Enfin, les États devraient être mis un peu plus à contribution en renforçant leurs obligations respectives à l’égard des victimes. The International Criminal Court was created for the purpose of both repression and reparation. These two objectives continue to materialize and have clearly become inseparable from any definition of the ICC. However, if an apparent equality could exist between them, the effectiveness of reparation has been shown, in many aspects, to be dependent on the effectiveness of repression. The July 1st, 2016 decision in the Ruto and Sang case confirmed and reinforced this dependence. Unfortunately, the victims are the ones who bear the brunt of this reality. It is therefore becoming urgent for the ICC to resolve this situation to offer more hope to victims. This could come from questioning the principles governing procedures before the Court. Without inventing anything, the ICC could greatly draw inspiration from certain State practices. First, consideration could be given to dissociating and making independent the procedures aimed at criminal conviction and those aimed at reparation, so as to make the absence of criminal conviction inappropriate for the determination of the civil liability of the accused. In addition, it could be considered other alternatives when there is no civil liability, such as offering legal recognition to victims by giving them a reparation order. In this sense, the ICC might benefit from going beyond individual responsibility. Finally, States should be made a little more involved by strengthening their respective obligations towards victims.
Keywords: Cour pénale internationale; Droit international; International Criminal Court; International law; Reparation for victims; Réparation en faveur des victimes

Intelligence artificielle, la recherche d’un régime juridique : Contribution à l’étude de la compatibilité d’une approche par les risques et d’une approche par les droits - Renondin de Hautecloque, Stanislas (Université Paris Cité, 2024)
Bien que l'intelligence artificielle ait émergé dans les années 1950, elle n'a été considérée comme un objet juridique que récemment. Le récent vote du règlement IA par les institutions de l'Union européenne représente un jalon crucial vers l'établissement d'un cadre juridique spécifique à l'IA. Cette étude vise à explorer le parcours ayant conduit à l'adoption de ce règlement européen sur l'IA. Nous avançons que l'histoire de l'IA révèle d'importantes contradictions juridiques. Sa nature évolutive et la diversité des discours entourant sa science fondamentale, l'informatique, sont aussi cruciales que les développements techniques ayant mené à sa création. Cette complexité a persisté dans les efforts pour définir juridiquement l'IA. L'Union européenne a rencontré des difficultés pour préciser ce qu'est l'IA et pour formuler un régime réglementaire adéquat, mettant en lumière le défi de marier les approches fondées sur les risques et les droits dans sa régulation. Nous proposons de redéfinir l'IA en tant qu'objet sociotechnique et suggérons une série de mesures pour équilibrer le règlement IA entre les approches basées sur les droits et les risques.
Keywords: Artificial Intelligence; Definition; Droits de l'homme; Droits fondamentaux; Définition; Fundamental rights; Inteligência artificial; Intelligence Artificielle; Intelligence artificielle; Regulation; Risk; Risque; Risque (droit); Régulation

"Non erit innocens malus". Looking for Justice over maritime Crimes of International Concern. A tale of dichotomies - Guizzardi Righetti, Giampaolo (Université Côte d'Azur ; Università degli studi di Milano, 2024)
This dissertation is about dualities or dichotomies. In particular it investigates the interrelationships between two couple of dichotomies, the dichotomy between international and transnational crimes and the duality of land and sea as geographical and jurisdictional spaces in the attempt to answer the question of who does or should exercise its jus puniendi in case of maritime crimes of international concern. This dissertation is about dualities or dichotomies. In particular it investigates the interrelationships between two couple of dichotomies, the dichotomy between international and transnational crimes and the duality of land and sea as geographical and jurisdictional spaces in the attempt to answer the question of who does or should exercise its jus puniendi in case of maritime crimes of international concern.
Keywords: Compétence; Droit de l'homme; Droit de la mer; Justice maritime; Responsabilité (droit international); Violation des droits de l'homme; État

The Relevance of IFRS Accounting Information: Evidence from a Pure IFRS Environment - Abu Alia, Muiz; Amarneh, Khairieh; Abdeljawad, Islam (An-Najah University Journal for Research - B (Humanities), 2024)
The International Financial Reporting Standards (IFRS) are supposed to raise the value relevance of accounting information and thus ensure its usefulness for users. Most of the studies on the relevance of IFRS-based accounting information were conducted in countries that had previous accounting standards before the adoption of IFRS. However, the relevance of accounting information is influenced by the accounting traditions inherited from previous practices. This study provides distinctive evidence on the relevance of IFRS accounting information by examining the association between accounting information prepared by Palestinian companies and share prices. Palestine represents a pure IFRS environment since IFRS is its first financial reporting framework. The study estimates the impact of accounting information, including book value of equity per share, earnings per share, and operating cash flow per share, on the market value of the share. Totally, the results show that the accounting numbers prepared by Palestinian companies are relevant. Precisely, earnings per share and book value of equity per share are the important variables in determining the share market value. Notwithstanding, no significant impact of operating cash flow per share has been observed. Moreover, evidence supporting the existence of conformity and predictive relevance is obtained, but the overall predictive relevance is higher. To enhance the relevance of IFRS information, this paper recommends local regulators and policymakers to work on improving the readiness of the Palestinian environment to fully benefit from the adoption of IFRS. On the other hand, the International Accounting Standards Board should adequately consider the circumstances prevailing in underdeveloped countries when issuing its standards. For future research, larger samples from several countries with different prevailing factors should provide insights into the mechanisms of the relationship between book and market values.
Keywords: Conformity Value; IFRS; Predictive Value; The Palestine Exchange; Value Relevance

A responsabilidade das empresas transnacionais na preservação dos direitos indígenas - Alves, Alessandra Vanessa (Universidade Nove de Julho, 2024)
The present study aimed to identify the duties – expressed and implicit – that arise for transnational companies when their economic activities are conducted on indigenous lands or have an impact on them. To this end, identified the most recurrent violations of indigenous peoples' interests regarding the commercial exploitation of their lands or surroundings. Adopting the context of the Krenak people, it was identified that the Krenak, similar to other indigenous peoples, have experienced conflicts on multiple fronts due to large scale projects affecting their territoriality, access to natural resources (with prejudice to their subsistence), and their very way of life and existence. Reflecting on the commitment made to by political entities and their respective branches with the enactment of the Federal Constitution of 1988, the constitutional provisions were interpreted from a historical perspective. It was identified that economic exploitation of indigenous lands -contingent upon legislation - shall, if enacted (because it is not a constitutional duty but a mere possibility), adhere to the criteria previously outlined in the Constitution, including consultation with the peoples concerned, authorization by the National Congress, and the right to participate in the results of the extraction. Furthermore, the principles derived from these criteria include the exceptional nature of exploration, preservation of indigenous wealth - both material and immaterial - and recognition of indigenous thought as a decisive element. It was concluded that these principles entail an extensive list of duties for transnational companies concerning indigenous peoples, which must be implemented with consideration for indigenous worldviews - an underlying assumption for the application of indigenous rights. This list is not static; rather, it should evolve with human rights developments and ensure the ability to address new challenges arising from the relationship between transnational companies and indigenous peoples.
Accepted: 2024-09-11T17:42:54Z
Keywords: CSR; RSE; Responsabilidad Social; Responsabilité sociale de l'entreprise

L'audit interne et la gouvernance a l’ère de la transformation digitale - Boumeska, Mustapha; Allouli, Nadia (Revue des Études Multidisciplinaires en Sciences Économiques et Sociales, 2024)
Over the last decade, corporate governance has become crucial to solving agency problems and achieving objectives for organisational sustainability . At the heart of this governance, internal audit is recognised as an essential control mechanism for improving business performance. In the face of digitalisation, internal audit must adapt, presenting new challenges and opportunities. This paper explores the impact of digitalisation on the effectiveness of internal audit as a governance mechanism, developing a conceptual model through an extensive literature review.
Keywords: Audit interne; Digitalisation; Digitalization; Efficacité; Efficiency; Gouvernance; Governance; Internal audit

States and Regional International Organizations - Zouapet, Apollin Koagne (International Organizations Law Review, 2024)
Beyond the thorny, even insoluble question of the definition of a region and the definition of the criteria that should make it possible to apprehend the polymorphism of rio s, the raison d’être of these organizations, their mode of operation and their activities are at the heart of the debate on “international governance”. For many authors, the advent of RIO s has often been seen as a challenge to the state monopoly in the international legal order and a redefinition of the relationship between these particular organizations and states. It is this relational dynamic between the States and the RIO s that this contribution aims to describe and analyse. The aim is to examine the originality and specificity of the relationship between the RIO s and the States, compared to the latter’s relationship with the ‘classic/universal’ ios, which would reveal something about the very nature of regional organizations.
PDF: https://brill.com/downloadpdf/view/journals/iolr/21/1/article-p147_008.pdf
Keywords: Cooperation; Instrumentalism; Integration; Regionalism; Supranationalism; Universalism

Mobile money and financial inclusion in Africa: Emerging themes, challenges and policy implications - Osabutey, Ellis L. C.; Jackson, Terence (Technological Forecasting and Social Change, 2024)
Mobile money is purported to promote financial inclusion. The growing number of studies have largely focused on transactions and related benefits with limited attention to emerging challenges, policies and initiatives that address the relative needs of different stakeholders. Consequently, little has been done to probe the ‘bottom-of-the-pyramid’ paradigm that underpins these assumptions. There has been inadequate endeavour to examine ways that empirical research could shed more light on these challenges and how to overcome them. To address these gaps, this study reviews the emerging literature on mobile money that explores both benefits and challenges. From our study three main themes emerge that suggest areas where challenges to the efficacy of the mobile money-financial inclusion link still appears not to have been adequately addressed by policymakers: ensuring integrity, privacy and security; addressing resource and infrastructure constraints; and integrating stakeholder benefits. Yet we suggest merely addressing these challenges does not go far enough in safeguarding the needs of local communities, as major stakeholders. Evidence from our study suggests little direct benefit to the poorer sections of local communities, only to the strata above and to elites and external stakeholders. This has implications for development and social change through technology adoption.
Keywords: Africa; Bottom-of-the-pyramid; Financial inclusion; Fintech; Mobile money

Etude critique de l'opportunité des poursuites dans les législations française et béninoise - Batonon, Crépine Flore Sènan (Université Bourgogne Franche-Comté, 2024)
L'opportunité des poursuites est un principe qui permet au procureur de la république, après vérification de la constitution d'une infraction, de poursuivre ou non le délinquant en fonction des données de fait qu'il apprécie souverainement dans chaque affaire. En droit français tout comme en droit béninois, ce principe n'est nulle part formulé expressément. Mais l'article 40 alinéa 1 du code de procédure pénale français et l'article 38 du code procédure pénale béninois disposent que « Le procureur de la république reçoit les plaintes et les dénonciations et apprécie la suite à leur donner ». Cette formule peut être interprétée comme accordant à ce magistrat le pouvoir d'apprécier les poursuites. Ainsi, le législateur reconnait au procureur de la république un pouvoir d'appréciation. L'opportunité des poursuites est donc un privilège, une prérogative, une faculté, un pouvoir d'appréciation souveraine qui ne peut engager sa responsabilité. Elle joue au stade de l'engagement des poursuites. De cette appréciation, peut naître soit deux décisions, soit trois, selon qu'on soit en droit béninois ou selon qu'on soit en droit français. En droit béninois, le procureur peut à l'issue de la mise en œuvre de son pouvoir d'appréciation, décider de poursuivre ou de classer sans suite. Le législateur français quant à lui, outre ces deux possibilités, permet au procureur de la république de mettre en œuvre des mesures alternatives de poursuite. Il peut s'agir soit d'une médiation pénale ou d'une composition pénale. La décision de poursuite peut être mise en œuvre par une procédure de flagrant délit, par une saisine du juge d'instruction, par une citation directe, ou par une procédure de crime flagrant. La décision de classement sans suite est une décision administrative, elle n'est pas motivée, et est non susceptible de voies de recours. Cependant elle peut faire l'objet d'un recours hiérarchique devant le procureur général. Plusieurs arguments sont avancés pour justifier ce principe. Il s'agit - L'individualisation du criminel - Du maintien de l'ordre public - La Gestion efficiente et souple du tribunal - Du désengorgement des maisons d'arrêts. Malgré ces avantages, force est de constater que de nombreuses critiques peuvent être faites à ce système. - D'abord l'application de ce principe ouvre la voie à l'arbitraire : En effet, le procureur de la république de par sa décision de classement sans suite se comporte exactement comme un juge. Plus qu'une décision administrative, le classement sans suite peut être une véritable décision au fond d'abandon de charges car l'infraction étant bien constituée. Donc assimilable à une véritable décision juridictionnelle parce que traitant des questions de libertés. - Ensuite, elle ouvre la voie à l'injustice : Le principe de l'opportunité des poursuites conduit à une application à géométrie variable de la loi. Le procureur peut décider à la tête du client, ce qui rompt l'égalité devant la loi. Ces deux reproches majeurs ont été également dénoncés par le rapport Refonder la justice : Ce qui a conduit le groupe de travail à proposer une réforme du statut du ministère public. Outre ces critiques majeurs, l'on constate également que les justificatifs évoqués par les partisans de l'opportunité des poursuites sont vraiment impertinents. - D'abord l'impertinence du désengorgement des maisons d'arrêts : On considère que le désengorgement des maisons d'arrêts est une illusion parce la poursuite pénale n'appelle pas systématiquement le décernement d'un mandat de dépôt (c'est à dire que la poursuite ne se résout pas systématiquement à la détention provisoire). En outre, le principe qui gouverne la poursuite en matière pénale est la liberté et l'exception la détention. Ensuite l'impertinence du maintien d'ordre public : On considère également que l'argument du maintien d'ordre est impertinent parce que le pouvoir exécutif à l'armée et la police pour maintenir l'ordre. The opportunity for prosecution is a principle that allows the public prosecutor, after verification of the constitution of an offense, to pursue or not the offender according to the factual data that he sovereignly appreciates in each case. In French law as in Beninese law, this principle is nowhere expressly formulated. However, Article 40 paragraph 1 of the French Code of Criminal Procedure and Article 38 of the Penal Procedure Code of Benin stipulate that "the public prosecutor receives complaints and denunciations and assesses the follow-up to be given to them". This formula can be interpreted as granting this magistrate the power to assess the prosecution. Thus, the legislator recognizes to the public prosecutor of the republic a discretionary power. The opportunity for prosecution is thus a privilege, a prerogative, a faculty, a sovereign power of appraisal which can not engage its responsibility. It is at the stage of prosecution. From this assessment, there may be two decisions, three, according to whether one is in Beninese law or according to whether one is in French law. Under Beninese law, the prosecutor may, after the exercise of his discretion, decide to proceed or to classify without further action. The French legislator, in addition to these two possibilities, allows the prosecutor of the republic to implement alternative measures of prosecution. It can be either a criminal mediation or a criminal composition. The decision to prosecute can be implemented by a flagrante delicto procedure, a referral to the investigating judge, a direct summons, or a flagrant crime procedure. The decision to take no action is an administrative decision, it is not motivated, and is not subject to appeal. However, it may be the subject of a hierarchical appeal before the Attorney General. Several arguments are put forward to justify this principle. It's about: - Individualization of the criminal - The maintenance of public order - Efficient and flexible court management - The disengagement of the arresting houses. Despite these advantages, it is clear that many criticisms can be made of this system. - First, the application of this principle opens the way to arbitrariness: Indeed, the prosecutor of the republic of his decision of classification without follow-up behaves exactly like a judge. More than an administrative decision, the classification without follow-up can be a genuine decision on the merits of abandonment of charges because the offense being well constituted. Therefore, it is tantamount to a genuine jurisdictional decision because it deals with questions of freedoms. - Then it opens the way to injustice: The principle of the suitability of prosecution leads to a variable geometry application of the law. The prosecutor can decide at the head of the client, which breaks the equality before the law. These two major criticisms were also denounced by the report Refond la justice: This led the working group to propose a reform of the statute of the prosecution. In addition to these major criticisms, we also find that the justifications evoked by the proponents of the suitability of prosecution are really impertinent. First, the impertinence of the disengagement of the houses of arrest: It is considered that the relapse of arrest houses is an illusion because criminal prosecution does not systematically call for the warrant to be waived (ie the prosecution does not systematically resolve pre-trial detention). Moreover, the principle governing prosecution in criminal matters is freedom and the exception of detention. Then the impertinence of the maintenance of public order: It is also considered that the argument of maintaining order is impertinent because the executive power to the army and the police to maintain order. - Then the impertinence of the role of the courts: For the developing countries, it is estimated that this allows to respect the ratio judge / inhabitant.
Issue: 2024UBFCF003
Keywords: Criminal prosecution; Droits fondamentaux; Fundamental rights; Ministère public; Poursuite pénale; Principe de l'opportunité des poursuites; Principle of the advisability of prosecution; Public minister

Lessons for insolvency law from the emoluments attachment order experience - Grobler, Frederik (University of Pretoria, 2024)
Section 23(5) of the Insolvency Act poses an interesting challenge, namely vesting a portion of an insolvent’s post-sequestration income in the trustee of the insolvent estate without infringing on the insolvent’s constitutional rights. The income earned by the insolvent during sequestration is in general excluded from his estate and does not vest in the trustee, unless the Master determines that a portion of the insolvent’s income will not be required to maintain the insolvent and his dependents. In such a case, only the portion deemed to be surplus to requirements will be included in the insolvent estate and will vest in the trustee. The question of what role the insolvent’s income should play during the sequestration process, and therefore how section 23(5) should be interpreted and applied, has vexed the courts and numerous practical and constitutional issues arise. This study examines the application and shortcomings of section 23(5) during the administration phase of the sequestration process. It then explores the lessons learned during the recent constitutional scrutiny and subsequent amendment of the emoluments attachment process. Lastly, recommendations are made for possible law reform of section 23(5).

A comparative appraisal of creditor protection mechanisms under South African company law - Sibanda, Mandhlaenkosi (University of South Africa, 2024)
The study comparatively scrutinised creditor protection mechanisms entrenched in South African Corporate law to determine their effectiveness in advancing creditor interests in company affairs. The enquiry was triggered by the need for corporate laws to adapt to and align with the pace of global economic changes in open and democratic societies. The 2004 DTI Policy document on South African Corporate Law Reform (SACLR) proposed a shift from the traditional shareholder-centric view, which espouses shareholder importance in corporate governance, to a model that retains the supremacy of shareholder interests while simultaneously catering to the interests of other stakeholders (the enlightened shareholder value approach). In light of the DTI policy proposal, the parliament, in enacting the South African Companies Act 71 of 2008 (the Companies Act), reflected on the need to provide appropriate redress to investors' and third parties (creditors`) rights in the preamble to this piece of legislation. It was based on the forgoing expositions that this research work sought to establish whether the South African Corporate law had been adequately modelled to protect creditors and to look beyond the traditional company’s goal of profit maximisation for the shareholder at the expense of other stakeholders, such as the creditors, who equally have stakes in the success and continuation of the company. Thus, a comparative doctrinal and critical analysis of creditor protection laws from selected cognate jurisdictions was undertaken to determine the efficacy of the protection mechanisms accorded to creditors under the South African corporate jurisprudence. It is thus the researcher's findings that the South African provisions on mechanisms to protect creditors are set in motion and are, therefore, effective to a greater extent, subject to legislature dealing with some discrepancies as per lessons drawn from comparator jurisdictions and recommendations. Conclusively, the Companies Act should clearly include the creditor’s interests in those of the company and thus give a secondary duty to directors to ensure creditor interests, among other non-member stakeholders, are assertively safeguarded.
Keywords: Company controllers; Company law; Corporate entity; Corporate law; Corporate veil; Credit systems; Creditor interests; Creditor protection mechanisms; Creditors; Directors; Employees; Investors; Shareholders; Stakeholder constituencies; Stakeholder interests; Stakeholders; Third parties

La responsabilité des administrateurs dans le régime de sanctions administratives pécuniaires en matière de protection de l’environnement - Wang, Si Bo (Université de Montréal, 2024)
With the adoption of the Act to amend the Environment Quality Act in order to reinforce compliance in 2011, the legislator came to establish a system of administrative monetary penalties for the protection of the environment. This new regime aims for a faster sanction that can be issued directly by the administrative power. This new sanction not only strengthens the applicability of the Environment Quality Act, but it also adds an additional burden to Quebec businesses. The objective of this thesis is to understand to what extent the system of administrative monetary penalties impacts the liability of administrators. To do this, we will first present the Environment Quality Act, which mainly governs the protection of the environment in Quebec, and above all describe the nature and objective of this system of administrative monetary penalties. Next, we will deal with certain aspects of this regime which have implications for administrator's liability. Finally, we will attempt to briefly introduce some of the observations we have made regarding the challenges and limitations of this administrative regime. Avec l’adoption de la Loi modifiant la Loi sur la qualité de l’environnement afin d’en renforcer le respect en 2011, le législateur est venu instaurer un régime de sanctions administratives pécuniaires en matière de protection de l’environnement. Ce nouveau régime vise une sanction plus rapide qui peut être émise directement par le pouvoir administratif. Cette nouvelle sanction renforce non seulement l’applicabilité de la Loi sur la qualité de l’environnement, mais elle ajoute en même temps un fardeau supplémentaire aux entreprises québécoises. L’objectif de ce mémoire est de comprendre dans quelle mesure le régime de sanctions administratives pécuniaires impacte la responsabilité des administrateurs. Pour ce faire, nous allons d’abord présenter la Loi sur la qualité de l’environnement qui encadre principalement la protection de l’environnement au Québec et surtout décrire la nature et l’objectif de ce régime de sanctions administratives pécuniaires. Ensuite, nous traiterons de certains aspects de ce régime qui entraînent des conséquences au niveau de la responsabilité des administrateurs. Finalement, nous tenterons d’introduire brièvement certaines remarques que nous avons tirées concernant les défis et limites de ce régime administratif.
Keywords: Administrateur; Administrative monetary penalty; Administrator; Monetary; Penalty; Responsabilité; Responsibility; Sanction administrative pécuniaire

Os fundamentos da não distribuição do dividendo obrigatório nas sociedades por ações - Valentim, Raphael Matos (Universidade de São Paulo, 2024)
A repartição do lucro entre os sócios é um dos eventos mais relevantes de uma sociedade empresária, tanto é assim que as sociedades por ações possuem uma regra de distribuição obrigatória de dividendos. Entretanto, existem limites juridicamente definidos para que esta distribuição não seja realizada em prejuízo de outros interesses tutelados pela lei. Dividida em duas partes e se valendo da metodologia analítica dedutiva, esta dissertação investiga as hipóteses de não distribuição do dividendo obrigatório aplicáveis para as companhias, identificando as situações que ensejam este não pagamento, bem como analisando criticamente os seus fundamentos e os limites quanto à sua utilização pelas companhias. A primeira parte se divide em dois capítulos, que tratam de conceitos gerais aplicáveis às sociedades, tais como a finalidade lucrativa, o lucro e o direito do acionista ao dividendo, tal qual a sistemática dos dividendos à luz das finanças corporativas. Os quatro capítulos que integram a segunda parte desta dissertação realizam uma avaliação crítica das hipóteses que autorizam o não pagamento do dividendo obrigatório. Durante a análise são realizadas propostas de interpretação do texto legal para solucionar eventuais lacunas existentes na lei com relação a cada uma das hipóteses analisadas, naquilo que possível dentro das limitações da pesquisa. Entre outros resultados, a pesquisa traz contribuições para diferenciar a incompatibilidade da situação financeira da companhia e a crise financeira, confrontando interpretação anterior, que relacionava a incompatibilidade com a iliquidez. A pesquisa também contribui para uma interpretação científica das novas disposições relacionadas à não distribuição do dividendo obrigatório, trazidas pela Lei n. 14.112/20 e pela Lei Complementar n. 182/21, que restringem o pagamento de dividendos. The allocation of profit among shareholders stands as one of the most significant events within a business entity. This is evident in the existence of a mandatory dividend distribution rule in joint-stock companies. Nonetheless, legally defined boundaries exist to prevent such distribution from occurring to the detriment of other interests protected by the law. Split into two parts and employing deductive analytical methodology, this dissertation investigates the scenarios where the mandatory dividend is not distributed in companies, identifying situations that warrant this non-payment and critically analyzing its foundations and limitations concerning its utilization by these companies. The first part comprises two chapters addressing general concepts applicable to corporations, such as profit purpose, earnings, shareholder right to dividends, and the dividend system in light of corporate finance. The second part, composed of four chapters, conducts a critical assessment of the scenarios permitting the non-payment of mandatory dividends. Throughout the analysis, proposals for interpreting the legal text are made to address potential gaps in the law regarding each of the examined scenarios, as far as possible within the research limitations. Among other findings, the research provides insights to distinguish between a companys financial incompatibility and financial crisis, challenging previous interpretations that linked incompatibility solely to illiquidity. Additionally, the study contributes to a scientific interpretation of the new provisions related to the non-distribution of mandatory dividends introduced by Law 14,112/20 and Complementary Law 182/21, which restrict dividend payments.
Keywords: Corporate law; Direito societário; Dividendos; Dividends; Joint-stock company law; Lei das sociedades por ações; Lucros; Non-distribution; Profits; não distribuição

La titrisation - Chambon, Benoît (Université Paris-Est, 2024)
Près de dix ans après la crise des subprimes les opérations de titrisation connaissent un nouvel essor. Ce dernier fait suite notamment à des travaux de la Commission européenne qui, dès 2015, a fait part de son intention de réviser le corpus applicable à ces transactions dans la cadre de son plan d'action pour la construction de l'Union des Marchés de Capitaux. C'est ainsi qu'en 2017 un règlement portant sur les opérations simples transparentes et standardisées a été publié au journal officiel de l'Union européenne. Ce texte a vocation à être complété par un autre règlement relatif à l'opposabilité des cessions de créances. Au niveau international les règles de rétention de fonds propres applicables visant les expositions de titrisations ont été amendées afin de mieux prendre en compte les risques y attachés. En France le régime applicable à la gestion d'actif et au financement par la dette a été remanié. On peut se demander comment ces évolutions normatives ont influencé la manière dont les risques systémiques et idiosyncratiques sont créés, transférés et couverts dans le cadre des opérations de titrisation. Almost ten years after the subprime crisis, securitization transactions are experiencing a new boom. The latter follows notably work of the European Commission which, as early as 2015, announced its intention to revise the legal framework applicable to these transactions as part of its action plan for the Capital Market Union. This led in 2017 to the publication in the Official Journal of the European Union of a regulation on simple, transparent and standardized transactions. This text is intended to be supplemented by another regulation on the enforceability of assignments of receivables. At the international level, the capital retention rules applicable to securitization exposures have been amended to take better account of the risks associated to said exposures. In France, the legal framework applicable to asset management and debt financing has been revised. One can wonder whether the normative developments have influenced the way systemic and idiosyncratic risks are created, transferred and hedged in securitization transactions.
Keywords: Idiosyncratic risks; Risque idiosyncratique; Risque systémique; Securitization; Systemic risks; Titrisation

The development of explicit deposit insurance schemes in selected countries in Southern Africa - Moloi, Mbakiso Ndumiso (University of Pretoria, 2024)
This dissertation explores the evolution of explicit deposit insurance schemes (EDIS) in Southern African countries. It emphasises the important role of banks in the economy and their vulnerability to failures despite prudential requirements and supervision. Financial safety nets are essential for failing banks, and deposit insurance is the primary mechanism to protect depositors and maintain financial system stability in the event of a bank's failure. Originating in 1933 with the establishment of the Federal Deposit Insurance Corporation in the United States of America during the Great Depression, EDIS has become a global standard. Southern Africa, with its developing financial sector, faces many challenges including bank failures, causing depositors to lose funds. The region's high interconnectedness increases the threat of contagion if parent banks fail. The absence of deposit insurance raises the likelihood of fiscal authorities succumbing to political pressure to bailout failing banks during crises as seen during the 2007-09 Global Financial Crisis (GFC). The GFC prompted the International Association of Deposit Insurers and the Basel Committee on Banking Supervision to establish the Core Principles for Effective Deposit Insurance Systems. Issued in June 2009, these principles are used by jurisdictions as a benchmark for assessing the quality of their deposit insurance systems and identifying gaps in their deposit insurance practices. This research aims to evaluate international best practice standards for EDIS and extract lessons from the establishment of EDIS in the USA to address gaps in the implementation of deposit insurance schemes in Southern African countries. Examining ten Southern African countries, this research investigates varied progress in EDIS adoption. Case studies, particularly Zimbabwe as a pioneer of EDIS in the region and Namibia as a recent entrant, help to identify gaps and opportunities for enhancing deposit insurance frameworks in the region.

Transformative impact of blockchain technology and smart contracts on dispute resolution: legal challenges and other implications. - Christie, David; Mante, Joseph; Mak, Charles Ho Wang (Artificial intelligence: its applications, academic and practical legal implications, 2024)
This paper comprehensively analyses the potential of blockchain technology and smart contracts to revolutionise dispute resolution. As dispute resolution methods evolve, blockchain and smart contracts, which offer efficiency, transparency, and fairness, are becoming more critical. That is especially the case in mediation and construction adjudication, which are less traditionally formal and tend to be carried through much more quickly than other forms of dispute resolution. The opportunity of blockchain comes from its ability to demonstrate a tamper-proof, clear record, reducing risks of misunderstanding and bias. This facilitates the transfer and verification of evidence both in the carrying out of projects and during dispute resolution processes. Smart–digital contracts with terms coded indirectly- allow for automated contract enforcement. They execute automatically upon meeting specific conditions. This automation brings a new efficiency level, cutting the time and costs of conventional dispute resolution. Nonetheless, integrating blockchain and smart contracts in dispute resolution faces several challenges. The current limited understanding and acceptance of these technologies in the legal sector is an imminent issue. Legislative changes are necessary to provide a solid legal framework for these technologies in legal processes and to address potential inconsistencies of approach. Such reform requires strong cooperation among lawmakers, technologists, and legal experts to ensure implementation that adheres to legal and ethical norms and ensures that the technologies can be applied with confidence by the stakeholders within the process. This collective effort is crucial for seamlessly integrating blockchain and smart contracts into legal frameworks.
Publisher: Kuwait International Law School ISSN 2410-2237 https://rgu-repository.worktribe.com/output/2343788/transformative-impact-of-blockchain-technology-and-smart-contracts-on-dispute-resolution-legal-challenges-and-other-implications
Keywords: Blockchain technology; Dispute resolution methods; English law; Smart contracts

La gestion des risques inhérents au marché financier - Salim, Medromi; Zakariyae, El Adlouni (African Scientific Journal, 2024)
Aujourd’hui, le marché financier est considéré comme le bouc émissaire du monde des affaires puisqu’il est toujours culpabilisé et pointé de doigt comme la source du malaise et la cause directe de l’effondrement des systèmes économiques. La finalité des marchés financiers est tragiquement déviée dans la perception du grand public. Ce marché qui est censé être l’emblème d’épanouissement, d’entraide et de coopération, est devenu un lieu où règne la mauvaise foi et les manœuvres frauduleuses. Cette stigmatisation n’est pas due au hasard. En effet, le délit d’initié, la publication de comptes inexacts, les crises financières etc. constituent quelques-unes des questions qui ont alimenté le débat actuel autour de crépuscule de la régulation massive du marché financier. La gestion des risques liés aux marchés financiers est devenue une préoccupation majeure afin de se prémunir contre les risques financiers, réputationnels et opérationnels. Today, the financial market is regarded as the scapegoat of the business world, since it is always blamed and pointed at as the source of malaise and the direct cause of the collapse of economic systems. The purpose of financial markets is tragically skewed in the public perception. This market, which is supposed to be the emblem of self-fulfillment, mutual aid and cooperation, has become a place where bad faith and fraudulent maneuvers reign supreme. This stigmatization is no accident. Indeed, insider trading, the publication of inaccurate accounts, financial crises etc. are just some of the issues that have fueled the current debate surrounding the twilight of massive financial market regulation. Financial market risk management has become a major preoccupation in order to guard against financial, reputational and operational risks.
Keywords: Business ethics; Financial markets; Gestion des risques; Marché financier; Moralisation des affaires; Risk management

Droit de la compliance et gouvernance de l’entreprise : vers une approche éthique et responsable - Zakariyae, El Adlouni; Salim, Medromi (African Scientific Journal, 2024)
L’entreprise constitue une source incroyable d’innovations, de progrès, de créativité et d’enthousiasme. En effet, elle est l’outil le plus efficace de création d’un changement positif. Or, le fossé entre les entreprises et la société reste encore flagrant ainsi que la relation entre les pouvoirs publics et les entreprises est caractérisée par le manque de confiance et de lucidité. Le droit de la compliance apparaît comme la panacée à ces nouveaux défis, et se présente comme l’outil le plus perfectionné de gouvernance pour l’entreprise et qui permet de concilier entre l’intérêt de l’entreprise et celui de la société.Les entreprises sont tenues de respecter les ordres publics nationaux et supranationaux dans lesquels ils s'inscrivent, Les principes de compliance désignent les lois qui imposent un objectif d’intérêt général à l’entreprise tout en la laissant libre des moyens pour atteindre cet objectif. Les pouvoirs et les régulateurs publics ne font que surveiller la manière dont les opérateurs privés se conforment par eux-mêmes (self-policing, self-reporting, self-compliance et self-monitoring) et contrôler la stricte observance de leurs diligences, c’est-à-dire de leur « capacité à s’auto-policer». The enterprise constitutes an incredible source of innovations, progress, creativity as well as enthusiasm. Indeed, it is the most efficient tool of the creation of positive change. Yet, the gap between enterprises and society still remains obvious as well as the relation between the public powers and enterprises is characterized by the lack of confidence and clarity. The law of compliance seems to be the answer to these new challenges, it presents itself as the most ideal tool of governance for the enterprise and which allows to conciliate between the enterprise’s interests and those of society. Enterprises are required to respect the national and supranational public order which they are a part. The principles of compliance mean the laws that impose a goal of general interest for the enterprise while leaving it free the means to achieve this objective. Powers and public regulators only control the way in which private operators conform by themselves ( self-policing, self-reporting, self-compliance and self-monitoring) and control as well the strict observance of their diligence, that is to say, their self-policing ability.
Keywords: Blanchiment; Compliance; Corporate governance; Ethics; Ethique; Gouvernance d'entreprise; Money laundering

Dano moral por ricochete no Direito Civil: problemas de delimitação e de aplicação sob uma perspectiva histórica, empírica e comparada. - Barreto, Júlia D'Alge Mont'Alverne (Universidade de São Paulo, 2024)
A Tese aborda a reparação dos danos morais por ricochete no Direito Civil brasileiro a partir de perspectiva histórica, empírica e comparada. Objetiva-se contribuir para a definição de critérios da reparação sob dois aspectos: a legitimidade para postulação do ressarcimento e a quantificação do dano. Para tanto, investiga-se a construção da responsabilidade civil por danos morais por ricochete nos ordenamentos jurídicos francês, português e alemão e na jurisprudência de cada país e, depois, examina-se o histórico desta reparação no Direito Civil brasileiro. Em seguida, analisa-se o enfrentamento dos temas centrais pelo Supremo Tribunal Federal e pelo Superior Tribunal de Justiça, em virtude de na jurisprudência verificar-se a tentativa de definição de alguns parâmetros a regerem a reparação dos danos extrapatrimoniais por ricochete. Avalia-se os conceitos e fundamentos legal, doutrinário e jurisprudencial deste tipo de dano e os riscos e vantagens de estabelecer-se, no Brasil, critérios restritivos de indenização, à semelhança do que ocorre nos ordenamentos português e alemão. Por fim, conclui-se que não há critério efetivamente firmado no STJ a respeito da definição da legitimidade para postulação do ressarcimento, pelo que se sugere a adoção de modelo restritivo a partir da utilização da ordem de vocação hereditária estabelecida no artigo 1.829 do Código Civil, à semelhança dos modelos português e alemão, a fim de garantir segurança jurídica e estabilidade conceitual ao tema. A respeito da quantificação do dano, propõe-se não a utilização de tarifação, mas de regulação da quantificação, observando-se os elementos seguintes: (a) possibilidades econômico-financeiras de ofensor e vítima reflexa; (b) grau de culpa do ofensor; (c) extensão do dano reflexo; (d) quantidade de vítimas reflexamente atingidas pelo mesmo evento danoso; e (e) proximidade do vínculo de parentesco entre vítima direta e vítima reflexa.
Keywords: Civil liability; Dano moral por ricochete; Direito Civil; Legitimacy; Legitimidade; Moral damage by ricochet; Private law; Quantification; Quantificação; Responsabilidade civil

Entreprises et droit international humanitaire - Pizzetta, Scarlett (Université Côte d'Azur, 2024)
La mondialisation de l'économie de marché ouvre de nouveaux horizons aux entreprises commerciales en étant source de croissance, d'emplois et de prospérité, même si elle engendre aussi des risques, en particulier lorsque les entreprises développent des activités dans des zones en proie à des conflits armés, internationaux ou internes, ou dans des territoires occupés. Les entreprises sont incitées par la société civile et les organisations internationales à tenir de plus en plus compte du droit relatif aux droits de l'homme, qui s'applique tant en période de conflit armé que de paix. Le droit international humanitaire, alors même qu'il est spécifiquement conçu pour régir des situations de conflit armé, qu'il a des effets importants pour elles lorsqu'elles opèrent dans des pays qui connaissent de telles situations, leur est moins connu et fait moins l'objet d'attention par la doctrine, notamment francophone.Un certain nombre de contentieux récents ont soulevé des interrogations en la matière, tant sur le plan de la protection des entreprises par le corpus du droit international humanitaire, que sur celui de la soumission des entreprises à ces règles. Cette thèse analyse l'applicabilité du droit international humanitaire aux entreprises commerciales, à leurs salariés, leurs biens, leurs activités qui peuvent être à la fois des cibles, des victimes, des participants des conflits armés, voire des auteurs de violations du droit international humanitaire, soulevant des interrogations relatives à l'adaptation et la pertinence du DIH à ces entités.
Keywords: Business Enterprises; Criminal and civil liability; Droit humanitaire; Droit international humanitaire; Droits et protections; Entreprises – Droit; Entreprises commerciales; International humanitarian law; Obligations and risks; Obligations et risques; Personnes morale (responsabilité); Personnes morales (responsabilité pénale); Responsabilité civile et pénale; Rights and protections; Victimes et acteurs des conflits armés; Victims and actors of armed conflicts

Rethinking Environmental Obligations in Corporate Insolvencies: What New Role for Lenders? - Ebegbodi, Daniel Onyeje (University of Calgary, 2024)
Environmental reclamation obligations are statutory mechanisms designed to regulate environmental protection by corporate entities. Bankruptcy laws on the other hand are meant to offer insolvent corporations an opportunity to reorganize their affairs, satisfy creditors claims and make a fresh start. In practice, the application of bankruptcy laws can undermine key environmental reclamation objectives, leading many to ask whether a corporation undergoing restructuring with significant outstanding environmental reclamation obligations should be able to commence bankruptcy proceedings to satisfy creditors’ claims? By employing the doctrinal and comparative research methodologies, this research interrogates that inquiry. It argues that, despite the importance of bankruptcy protection for corporations undergoing financial distress, environmental protection should be paramount. Although sustainable finance (SF) instruments have been deployed by banks to enable creditors to mitigate environmental concerns in their investments, the persistent recurrence of environmental reclamation issues in the oil and gas sector particularly during insolvencies, underscores the need for financial investors to strengthen their investment policies to reflect best practices providing the desired protection for the environment. The research finds that, although SF and environmental, social and governance (ESG) approaches, are commendable, they are insufficient in instilling adequate regulatory impact on the environment compared to judicial control offered by the courts. The thesis concludes that whilst judicial control mechanism is not without concerns, with government’s deliberate financial policy and judicial control to complement SF and ESG efforts, ESG and SF mechanisms can be strengthened to compel greater significant influence on best practices in lending.

Current Issues of the Utilization of Online Dispute Resolution as a Method for International Trade Dispute Settlement - Rohmah, Nuzul Quraniati (Ipso Jure, 2024)
The transformation of international trade from conventional to digital impacts several things, including resolving international trade disputes. In order to realize an efficient and effective dispute resolution process, many countries have implemented ODR to settle international trade disputes. This study aims to analyze the implementation of ODR in various countries and examine issues with unclear guidelines based on international law. This research observes the development of ODR in Indonesia and the urgency for its implementation in Indonesia. The research is normative juridical, with a statutory and comparative approach. The results obtained in this study are model law arrangements relating to the standardization of ODR Providers aimed to protect the personal data of the parties, unification of ODR dispute resolution clauses, and formulation of national legal instruments to create legal certainty regarding ODR, including ODR proceedings, permits, and monitoring, as well as recognition and execution process of electronic ODR decisions.
Keywords: International Trade; ODR; Online Dispute Resolution; Regulation

Assimetria de poder juridicamente significativa : critérios e impactos na disciplina dos contratos empresariais. - Oliveira, Natália Marques de (Universidade de São Paulo, 2024)
O artigo 421-A do Código Civil justifica o afastamento da presunção de paridade e de simetria dos contratos empresariais mediante a presença de elementos concretos cujo teor, natureza e efeitos não são explicitados. A disposição é, via de regra, relacionada à possibilidade de intervir em contratos marcados pela assimetria de poder de barganha entre os contratantes. Dado que é natural que haja disparidade de poder entre as partes, eventual intervenção para conter ou sancionar os efeitos da liberdade contratual exercida no âmbito de uma relação obrigacional assimétrica apenas é justificada se comprometerem valores jurídicos, razão pela se compreende que nem todo desequilíbrio de poder é e deve ser juridicamente significativo. Portanto, propõe- se o conceito de assimetria de poder juridicamente significativa a partir da interpretação sistemática dos artigos 187, 421, caput e 421-A, caput do Código Civil. O objetivo do trabalho é investigar os critérios para qualificação das práticas contratuais derivadas da assimetria de poder juridicamente significativa, bem como seus impactos no cumprimento dos objetivos da disciplina jurídica aplicável aos contratos empresariais de promover segurança jurídica e confiança aos agentes econômicos. Para alcançar o objetivo proposto, a análise foi realizada a partir de dois recortes, um geral e um específico. Como Recorte de Análise Geral, considerou-se os contratos da cadeia agroalimentar (agronegócio) firmados entre o elo produtor e o segmento a jusante. O Recorte de Análise Específico correspondeu aos contratos firmados entre os citricultores e as indústrias processadoras de suco de laranja. Como resultados, defende-se que é juridicamente significativa a assimetria de poder nos contratos empresariais quando dela resultam práticas contratuais pelas quais o agente com poder superior de barganha transfere, total ou parcialmente, custos e riscos incidentes sobre a operação econômica formalizada pelo contrato à parte com desvantagem negocial, sem que seja justificada, do ponto de vista da estrutura jurídica e/ou econômica do negócio, a ausência de contrapartida para assunção de referidos custos e riscos, comprometendo, ao menos potencialmente, o cumprimento da função socioeconômica imediata e mediata dos contratos empresariais. Ademais, a assimetria de poder juridicamente significativa compromete o cumprimento dos objetivos da disciplina jurídica de conferir segurança jurídica e confiança aos agentes econômicos atuantes em dado mercado, razão pela qual não é efetiva para lidar a contento com a problemática. A partir dos resultados, concluiu-se que são necessárias adaptações a nível de direito material e instrumental para endereçamento dos impactos da assimetria de poder juridicamente significativa, que devem ser objeto de pesquisas futuras. Article 421-A of the Civil Code justifies challenging the presumption of parity and symmetry in business contracts through the presence of concrete elements whose content, nature, and effects are not specified. This provision is generally related to the possibility of intervening in contracts characterized by an asymmetry of bargaining power between the parties. Given that there is naturally a disparity of power between the parties, any intervention to contain or sanction the effects of contractual freedom exercised within an asymmetric obligational relationship is only justified if it compromises legal values. Therefore, it is understood that not every power imbalance is, or should be, legally significant. Hence, the concept of legally significant power asymmetry is proposed based on the systematic interpretation of Articles 187, 421, caput in light of Article 421-A, caput of the Civil Code. The objective of this study is to investigate the criteria for qualifying contractual practices resulting from legally significant power asymmetry and to assess their impacts on the fulfillment of the objectives of the legal framework applicable to business contracts in providing legal certainty and trust to economic agents. To achieve the proposed objective, the analysis was conducted through two scopes, a general one and a specific one. As part of the general analysis, contracts within the agri-food chain (agribusiness) between the producer and the downstream segment were considered. The specific analysis focused on contracts concluded between citrus growers and orange juice processing industries. As a result, it is argued that power asymmetry in business contracts is legally significant when it leads to contractual practices by which the party with superior bargaining power transfers, either entirely or partially, the costs and risks associated with the economic operation formalized by the contract to the disadvantaged party, without the absence of consideration being justified from the perspective of the legal and/or economic structure of the business, thereby compromising the fulfillment of the immediate and mediate socioeconomic function of business contracts. Furthermore, legally significant power asymmetry undermines the achievement of the legal framework\'s objectives to provide legal certainty and trust to economic agents operating in a given market, which is why it is ineffective in adequately addressing the issue. The results led to the conclusion that adjustments are required within both substantive and procedural legal frameworks to tackle the problem effectively, which should be further researched.
Keywords: Assimetria de poder de barganha; Bargaining power asymmertry; Business contracts; Contractual freedom; Contratos empresariais; Função social do contrato; Liberdade contratual; Social function of contracts

Fundamentos jurídicos para a atração de investimentos estrangeiros diretos - Botelho, Rodrigo Jacobina (Universidade de São Paulo, 2024)
A história moderna da humanidade vem demonstrando que jaz míope a visão de que determinado país e sua economia podem viver e sobreviver em estado de isolamento hermético ante a economia globalizada. Não é concebível que determinada sociedade possa se desenvolver sem interação com investidores estrangeiros. Mesmo em países que, por opção ideológica, há certo isolamento, vemos hoje a existência de investimentos estrangeiros, ainda que sejam originados em outros países com o mesmo viés ideológico. Desta forma, os países em desenvolvimento e, em especial para o trabalho que aqui se apresenta, o Brasil têm que compreender as possíveis estruturas jurídicas e econômicas, bem como de políticas públicas que expressam tais estruturas, para poder pretender se credenciar como atrativos destinos de investimentos estrangeiros, seja pela outorga de benefícios (diretos ou indiretos), seja pela segurança ao investidor. No Brasil, entretanto, essa atratividade deve ser sopesada com a preservação de valores fundantes de nossa Constituição, congruentes com o ordenamento jurídico nacional e, ainda, devem ser, depois de efetivado o investimento, acompanhado por um sistema que imponha transparência e solidez ao cumprimento das contrapartidas desejadas: notadamente a geração de emprego e renda e de contribuição para a criação da riqueza nacional. O ponto central do presente trabalho gira em torno dos fundamentos jurídicos para a atração e manutenção, bem como a construção de um possível sistema de aferição da solidez jurídica de políticas de incentivo ao capital estrangeiro.
Keywords: Acompanhamento; Attraction policy; Benefits; Benefícios; Convenience; Conveniência; FDI; Foreign direct investment; Foreign investment; Investimento estrangeiro; Investments; Monitoring; Política de atração

Plataformas de cuidados a mayores - Egea, Mercedes Navarro (Comares, 2024)
La esperanza de vida en nuestro país es una de las más altas del mundo. Se estima que en treinta años la tasa de dependencia de personas mayores con necesidades de cuidados en la UE alcanzará el sesenta por ciento.Este estudio aborda las cuestiones jurídico-tributarias que plantean las "plataformas digitales de cuidados" que operan en el ámbito nacional y que tienen por destinatarios a los mayores dependientes.Estas fórmulas empresariales, además del potencial que tienen para la generación de empleo y la innovación, contribuyen a mejorar la calidad del envejecimiento, pues la oferta de servicios (cuidados de larga duración, por períodos cortos o por horas) se adapta con mayor flexibilidad a las necesidades individuales de los mayores, preservando su independencia y autonomía en todo el ciclo de la vejez. Unos cuidados que han de ser de calidad, asequibles y accesibles.Interesa, por tanto, adentrarse en los aspectos más significativos de lo que podría ser una fiscalidad de plataformas, focalizada en aquellas que actúan como intermediarias conectando a vendedores o prestadores de servicios con usuarios, y que comprende medidas concretas en el IS y el IVA, así como nuevas obligaciones de suministro de información (DAC 7). En esta categoría de plataformas se reconocen la mayoría de las que operan en el ámbito de los cuidados. Y, puesto que se trata de un sector empresarial en crecimiento, presenta especial interés conocer en qué medida se pueden aprovechar las medidas fiscales introducidas para el fomento de las empresas emergentes (startups), así como para la atracción de inversión privada y la captación de talento extranjero.
https://orcid.org/0000-0001-7441-209X
Keywords: cuidadados; jurídico; mayores; plataformas; tributario

Atribuição de contrapartida em dinheiro nas operações de incorporação e incorporação de ações no direito brasileiro : admissibilidade e limites à luz dos interesses dos acionistas. - Hebling, Julia Corrente (Universidade de São Paulo, 2024)
Esta dissertação parte da seguinte indagação: a contrapartida em dinheiro no âmbito das operações de incorporação e incorporação de ações é admitida no ordenamento jurídico brasileiro? Para responder a essa pergunta, o trabalho examina, em primeiro lugar, de que forma a continuidade das participações societárias insere-se na disciplina dessas operações, constatando que a transposição dos sócios da companhia incorporada (ou cujas ações são incorporadas) para a sociedade incorporadora é tradicionalmente encarada com um traço essencial dessa modalidade de reorganização societária. Nada obstante a essa concepção, o trabalho se dedica a analisar em que medida essas operações são compatíveis com o ordenamento jurídico societário brasileiro, com o propósito de identificar se há fundamentos jurídicos a respaldar a dispensa do princípio da continuidade das participações societárias. Nesse contexto, busca identificar os riscos decorrentes da admissibilidade de operações de incorporação com pagamento em dinheiro sob a perspectiva dos acionistas das companhias envolvidas, avaliando se, diante de tais riscos, as salvaguardas oferecidas pelo ordenamento jurídico societário vigente são suficientes para endereçá-los, assinalando os pontos em que a disciplina jurídica poderia ser aprimorada e a necessidade da imposição de determinados limites à realização dessas operações. This dissertation seeks to answer the following question: is cash consideration in a merger permitted under Brazilian law? In order to answer that question, this study first examines how the participation in the equity of the surviving corporation is traditionally viewed within the legal framework of these transactions, concluding that the passage of the shareholders from the merged company (or whose shares are merged) to the surviving company is seen as an essential feature of mergers. Notwithstanding this conception, this study is dedicated to analyze to what extent such kind of merger is compatible with the Brazilian corporate legal system, with the purpose of identifying whether there are legal grounds to support its admissibility. In this context, the dissertation seeks to identify the risks arising from the admissibility of cash as consideration in mergers from the perspective of the shareholders of the companies involved in such transactions, assessing whether, in light of such risks, the safeguards provided by the current corporate legal system are sufficient to address them, pointing out where the legal framework could be improved and the need to impose certain limits on carrying out these transactions.
Keywords: Admissibilidade de pagamento em dinheiro; Cash as consideration; Cash-out mergers; Exchange ratio; Incorporação; Incorporação de ações; Merger; Merger of shares; Relação de substituição

Trabalhadores em plataforma digital e protagonismo do Direito do Trabalho. Entre intervenção do estado e autorregulação: qual a proteção adequada? - Jesus, Filipe dos Santos Silva (Universidade de São Paulo, 2024)
A presente tese tem por escopo analisar a proteção dos trabalhadores em plataformas digitais. Sob o viés específico, investiga como o Direito do Trabalho pode assumir seu protagonismo na tutela dos motoristas via aplicativos. O trabalho em plataformas digitais já é uma realidade tanto no cotidiano brasileiro quanto nos demais países. São milhares de trabalhadores espalhados por inúmeras atividades via plataformas digitais, havendo crescimento exponencial nessa seara, o que propicia oportunidades, avanços e desafios. Ocorre que, até o momento, ainda não foi definido o standard de proteção aplicáveis a esses trabalhadores, havendo vazio protetivo que gera precariedades, insegurança jurídica e controvérsias judiciais. Por tais razões, a regulação dessa nova forma de trabalho constitui desafio global. Questiona-se: qual é a proteção adequada para os trabalhadores em plataforma digital? Em busca de respostas coerentes, concebe-se que o Direito do Trabalho pode assumir sua eterna juventude, adaptar-se aos novos tempos e se reinventar para proteger também esses novos trabalhadores. A tese defende um regime jurídico moderno, compatível e pacificador, capaz de harmonizar proteção social e segurança jurídica, valor social do trabalho e livre iniciativa, dignidade da pessoa humana e meio ambiente de trabalho saudável. Essa justa medida pode ser encontrada entre a intervenção estatal mínima e a autorregulamentação das partes. Cabendo ao Estado assegurar a dignidade de todos os trabalhadores, no âmbito da livre iniciativa, identifica-se núcleo fundamental de direitos aplicáveis aos trabalhadores em plataformas digitais, levando-se em conta as transformações do mundo de trabalho; respeitada essa normativa mínima do tipo cláusula pétrea ou espaço vital e inflexível, caberá aos próprios atores sociais regular essa peculiar atividade laboral, o que confere maior efetividade, segurança jurídica e adaptação às transformações sociais. The purpose of this doctoral study is to analyze the issue of protecting workers on digital platforms. From a specific perspective, it will investigate how Labor Law can assume its leading role in protecting drivers via apps. In fact, working on digital platforms is already a reality in everyday life in Brazil and in other countries. There are thousands of workers spread across numerous activities via digital platforms, with exponential growth in this area, which provides opportunities, advances and challenges. It turns out that, to date, the protective standard applicable to these workers has not yet been defined, resulting in a protective void that generates precariousness, legal uncertainty and judicial controversies. For these reasons, regulating this new form of work constitutes a global challenge. The question is: what is the adequate protection for platform workers? In search of coherent answers, it is conceived that Labor Law can assume its eternal youth, adapt to new times and reinvent itself to also protect these new workers. It advocates the achievement of a modern, compatible and pacifying legal regime, capable of harmonizing social protection and legal security, the social value of work and free initiative, human dignity and an adequate working environment. This fair measure can be found between minimal state intervention and self- regulation of the parties. As the State is responsible for ensuring the dignity of all workers, within the scope of free enterprise, a fundamental core of rights applicable to workers on digital platforms will be identified, taking into account the transformations in the world of work. Respecting this minimum regulation of the stone clause or vital and inflexible space type, it is believed that social actors themselves will be able to regulate this peculiar work activity, which provides greater effectiveness, legal security and adaptation to social transformations.
Keywords: Appropriate regulation; Digital platform workers; Drivers via apps; Motoristas via aplicativos; Necessary protection; Protagonism of Labor Law; Protagonismo do Direito do Trabalho; Proteção necessária; Regulamentação adequada; Trabalhadores em plataforma digital

L'intérêt du créancier dans les procédures simplifiées de recouvrement et des voies d'exécution en droit OHADA - Ema'a Mofa, Jules Gérard (Université de Douala, 2024)
Le financement de l’économie de nos jours se repose sur le crédit. Pour le développement de leurs activités, les débiteurs se retournent inéluctablement vers les créanciers pour l’obtention des capitaux nécessaires. Cependant, à bien des cas, ce « mariage idyllique » finit par connaître des « jours sombres » par le fait des débiteurs indélicats, posant par là même l’épineux problème du recouvrement des créances. En guise de solution à ce problème, véritable gangrène des économies, le législateur OHADA a cru devoir faire oeuvre utile en secrétant un nouveau droit des affaires en général et celui des procédures contentieuses portant sur le recouvrement des créances et les voies d’exécution en particulier. Lesdites procédures devaient assurer le recouvrement de la créance querellée en toute simplicité, célérité, à moindre coût et dans le strict respect des droits du débiteur poursuivi. Ainsi, à l’échec d’un recouvrement volontaire, il est délivré au créancier poursuivant une ordonnance injonctive sur laquelle sera apposée une formule exécutoire ; afin qu’il procède dès lors à un recouvrement forcé au travers des voies d’exécution. Cependant, une vingtaine d’années plus tard, entre les lourdeurs procédurales et leur complexité, les insaisissabilités, les immunités d’exécution, etc..., les AUPSRVE ont étalé à suffisance certaines limites, qui mettent à mal l’intérêt du créancier dans lesdites procédures. Elles sont donc à repenser notamment au travers de leur recadrage systématique. Il passerait par exemple par la cyber justice, la suppression de l’exéquatur pour une libre circulation des titres exécutoires, l’instauration de l’obligation de transparence sur ses biens imposée au débiteur, la révision de l’assiette saisissable, la relativisation et mieux la suppression des immunités d’exécution chaque fois que les actes posés seront des actes de gestion et non de souveraineté, etc. Toute chose qui pourrait assurer une meilleure prise en compte de l’intérêt du créancier comme c’est déjà le cas pour les droits du débiteur. Ce serait le prix à payer pour un décollage tous azimuts de l’économie de l’espace OHADA.
Keywords: Claim; Creditor; Creditor's interest; Créance; Créancier; Debtor; Débiteur; Enforcement; Intérêt du créancier; OHADA; Procédure simplifiée; Recouvrement de créances; Recovery; Voie d’exécution

Transborder flow of personal data (TDF) in Africa: Stocktaking the ills and gains of a divergently regulated business mechanism - Babalola, Olumide (Computer Law & Security Review, 2024)
Technology-based transactions are inseparable from the routine exchange of data. These exchanges may not pose privacy problems until the movement takes extra-territorial turns thereby facing multiple levels of cross-border regulations. In the 80 s, the frequency of transfer of personal data beyond geographical boundaries in Europe precipitated the regulation of transborder data flows (TDF) beginning with the enactment of the Organization for OECD Guidelines. In Africa, the concept of TDF is more complex than usually viewed by the stakeholders and this is partly because neither the African Union nor other regional bodies have introduced legislation on TDF. Like many concepts in data protection, TDF is bereft of a generally accepted meaning. Regardless of the uncertainty, this paper approaches TDF as the transmission of personal data from one country to another country or international entity for the purpose of processing. The paper discusses some definitions of TDF as understood under African regional and national data protection legislation. In a comparative and normative approach, the paper analyses the barriers to TDF in Africa vis a vis the European experience and then concludes with recommendations for workable TDF within and outside the continent from an African perspective beginning with the harmonization of existing regional framework.
Keywords: Africa; Data Protection; ECOWAS; GDPR; Privacy; Transborder data transfer

The African Continental Free Trade Area (AfCFTA): Taking stock and looking ahead for international business research - Debrah, Yaw A.; Olabode, Oluwaseun E.; Olan, Femi; Nyuur, Richard B. (Journal of International Management, 2024)
The establishment of the African Continental Free Trade Area (AfCFTA) has opened new avenues of research interest in International Business and International Management. However, scholarly work in this fledgling area of research has been disparate and often lacking in the assessment of core international business implications of the emergence of the AfCFTA on member states as well as non-member states. This is because, as yet, no systematic attempt has been made to explore the AfCFTA in the context of IB research, or project future IB research directions. Hence, in this paper, using the PRISMA method we have systematically identified the current published research and scholarly work on the AfCFTA and provided a robust picture of the current state of knowledge and available literature on the AfCFTA while at the same time outlining potential areas for future international business research.
Keywords: AfCFTA; African Continental Free Trade Area; Informal cross-border trade; International business; Regional economic communities (RECs); Systematic literature review

L'obligation d’information en droit malien de la consommation - Harouna, Mohamed Albachar; Touré, Omorou Zackaria (Revue Internationale Maaya, 2024)
L’information du consommateur est l’une des obligations légales les plus accrues en matière contractuelle compte-tenu de l’expérience des parties en cause. Cette information est nécessaire aussi bien pour la formation du contrat projeté que pour sa bonne exécution. Elle est alors contractuelle ou extracontractuelle. Ainsi, la rétention de toute information est susceptible d’engager la responsabilité du professionnel vis-à-vis du consommateur. La mise en œuvre d’une telle responsabilité nécessite une action devant aboutir à des sanctions proprement dites à l’encontre du professionnel censé être le conseiller de son co-contractant. L’Etat doit y veiller à travers la lutte contre la fraude et les pratiques de concurrence déloyale. Le consommateur et ses ayants droits, l’association des consommateurs doivent pouvoir exercer leurs droits de recours devant les organismes de protection des consommateurs et juridictions compétents. Mieux, ces derniers doivent connaître leurs droits et obligations ainsi que les textes qui les protègent dans une langue accessible afin de leur permettre de prendre des décisions conformes à leurs intérêts légitimes dans la mesure où la mauvaise information peut non seulement les induire en erreur mais porter atteinte à leur sécurité.
Actes de la 1ère Edition Journées Scientifiques de l'INFTS (JS-INFTS-1) Revue Semestrielle de l’Institut National de Formation des Travailleurs Sociaux (INFTS)
Keywords: Consommateur; Consumer; Contract; Contrat; Droit de la consommation; Information; Sanction

Overview of the role of selected consumer protection bodies in the regulation of prices and access to redress under the Consumer Protection Act 68 of 2008 - Magau, Phemelo; Chitimira, Howard (Acta Universitatis Danubius. Juridica, 2024)
The Consumer Protection Act 68 of 2008 (CPA) seeks to promote the achievement and maintenance of a fair, accessible, efficient, sustainable and responsible market place for consumer products and services in South Africa. Moreover, the CPA seeks to provide an accessible, consistent, harmonised, effective and efficient system of redress for consumers. Notably, the CPA provides that the supplier should not supply or enter into an agreement to supply any goods or services at a price that is unfair, unreasonable, or unjust. This is generally aimed at combating any problems that are suffered by consumers when accessing goods and services in South Africa. Accordingly, various regulatory bodies and related role-players were established to enforce consumer rights and provide redress mechanisms to vulnerable and affected consumers. These consumer protection bodies and related roleplayers include the National Consumer Commission (NCC), the National Consumer Tribunal (NCT), provincial consumer courts, ordinary courts and other alternative dispute resolution agencies. These bodies and role-players are statutorily obliged to resolve consumer disputes in South Africa. However, there are some uncertainty challenges regarding the jurisdiction of ordinary courts and consumer protection regulatory bodies in relation to disputes that relate to the consumers’ right to fair, just and reasonable prices, terms and conditions of goods and services. This article discusses the role of the NCC, the NCT, provincial consumer courts, ordinary courts and other alternative dispute resolution agencies in the regulation of prices for goods, services and access to redress for affected consumers under the CPA. This is done to provide some recommendations that could resolve jurisdictional and regulatory challenges in relation to the price and access to goods and services under the CPA.
Keywords: Consumer Protection Act 68 of 2008 (CPA); Consumer protection; Consumer rights; Prices; Regulatory bodies; Vulnerable consumers

La fixation des prix du pétrole et le droit international - Ondongo, Sagesse Aimé (Afrilex : Revue d’étude et de recherche sur le droit et l’administration dans les pays d’Afrique, 2024)
Le présent article a pour objet d’apporter sa contribution à la doctrine sur la régulation du commerce international des ressources énergétiques à travers une étude sur la fixation des prix du pétrole. Sous l’angle du droit international, il répond principalement à la question de savoir quels sont les facteurs juridiques qui déterminent la valeur d’échange du pétrole sur les marchés internationaux. Tout en relevant les avancées et les faiblesses de la régulation y relative, la présente étude démontre que les prix pétroliers se révèlent déterminés par des marchés parfois spéculatifs suivant les variables d’une libre concurrence dont l’instauration tend à être favorisée par une règlementation incitative. Dans le même temps, l’évolution du niveau de ces prix subit pleinement l’influence des enjeux poursuivis par l’affirmation d’une souveraineté des États qui fait obstacle à l’établissement d’une concurrence parfaite. The purpose of this article is to contribute to the doctrine on the regulation of international trade in energy resources through a study on the setting of oil prices. From the perspective of international law, it mainly answers the question of what legal factors determine the exchange value of oil on international markets. While noting the advances and weaknesses of the related regulation, this study demonstrates that oil prices are determined by sometimes speculative markets depending on the variables of free competition, the establishment of which tends to be favored by an incentive regulation. At the same time, the evolution of the level of these prices is fully influenced by the issues pursued by the assertion of State sovereignty which obstructs the establishment of perfect competition.
Keywords: Competition law; Concurrence; Energy security; Oil; Price; Prix; Pétrole; Souveraineté; Sovereignty; Sécurité énergétique

Evaluating bank technical efficiency in SADC region - Abel, Sanderson; Mukarati, Julius; Manenge, Robson; Le Roux, Pierre (Heliyon, 2024)
Efficiency is generally defined as the capacity to deliver desirable results with little effort or input. A bank cannot afford to allocate limited resources at random in a competitive market. Only once the efficiency factors have been identified can resources be allocated in a conscious and effective manner. The study investigates the determinants of technical efficiency of banks in the SADC region. The study is significant in the SADC region as the block is trying to create a robust and stable banking system. This is driven by the desire to stay away from the current global financial system volatility and the region is working to develop an integrated banking system. The results show that the banks are relatively inefficient with the level of inefficiency around 40 percent. The efficiency of the banks is determined by the level of capitalisation, size of the bank, research costs and automation of the banks. The results of the study imply that that there is great scope for the banks in the SADC region to increase their efficiency. Improved efficiency will ensure banks provide services at a lower cost to clients. The study recommends adequately capitalizing banks, increasing the asset base of the banks, investing in research and the automation of the banking systems.
Keywords: Banks; Capitalisation; Data envelopment analysis; Technical efficiency; Tobit

A relação entre as normas de direito societário e a lei de recuperação judicial e falência : plano dos credores, aumento de capital e direito de retirada - Lamas, Victor Nader Bujan (Universidade de São Paulo, 2024)
A Lei de Recuperação Judicial e Falência, após a reforma de 2020, permitiu que a maioria dos credores, organizados em assembleia, possam impor medidas à empresa em recuperação judicial e aos seus sócios, nos termos do art. 56, § 4o e seguintes. Embora diversas medidas possam ser adotadas pelo plano dos credores, como é o caso das determinações de aspecto exclusivamente patrimonial e a alteração da administração da empresa em recuperação judicial, algumas providências não podem ser impostas sem que haja a anuência dos sócios, nos termos da legislação societária, como é o caso da fusão, incorporação e transformação. A capitalização dos créditos em recuperação judicial, inclusive com a alteração de controle, é expressamente admitida pela Lei de Recuperação Judicial e Falências, o que enseja, em determinados casos, o exercício do direito de retirada pelos sócios do devedor. O cálculo do recesso para fins de exercício do direito de retirada deve ocorrer mediante um critério exclusivamente patrimonial, sem que seja permitido que os sócios retirantes possam se valer da expectativa de lucratividade futura da sociedade no cálculo do valor da empresa para fins de recesso. O crédito decorrente do direito de retirada possui natureza extraconcursal e não se sujeita aos efeitos da recuperação judicial. Seu pagamento, entretanto, deve ocorrer de maneira compatível com a preservação da empresa, mediante a utilização de um percentual dos resultados futuros, sem que seja possível a venda de ativos da empresa em recuperação para pagamento dos sócios retirantes.
Keywords: Aumento de capital; Capital increase; Classification of credits; Classificação dos créditos; Direito de retirada; Judicial recovery plan; Judicial rehabilitation; Recuperação judicial; Right of withdraw; plano dos credores

The Extent of Social Responsibility among Libyan and Palestinian Telecom Companies in Mitigating the Effects of the COVID-19 Pandemic - Rashwan, Abdelrahman; Amarif, Suad (Jordan Journal of Applied Science-Humanities Series, 2024)
This study primarily aims to identify the social responsibility of Libyan and Palestinian telecommunications companies and their contributions to addressing the negative effects resulting from COVID-19. The study focuses on the companies’ efforts to alleviate the burden on the state and citizens, exploring the most significant social contributions made by these companies in response to the pandemic. To answer the research questions and test the hypotheses, the researchers employed a descriptive and analytical approach. After obtaining the necessary data, a validated and evaluated questionnaire was distributed to a sample of 53 individuals, including financial managers, internal auditors, financial analysts, and accountants working in Libyan and Palestinian telecommunications companies. The results of the study indicated that Libyan telecom companies did not contribute significantly to mitigating the negative effects of COVID-19 by activating their social responsibility roles. This conclusion is supported by the respondents' answers, which reflected a moderate degree of contribution, with a mean value of 3.08 and a relative weight of 61.69%, along with a standard deviation of 0.85 and a significance level (Sig) of 0.686. Similarly, Palestinian telecom companies also did not significantly contribute to mitigating the negative effects of the COVID-19 pandemic through their social responsibility roles. Respondents’ answers indicated a moderate level of contribution, with a mean value of 3.24, a relative weight of 64.85%, a standard deviation of 0.849, and a significance level (Sig) of 0.256. The study recommends that Libyan and Palestinian telecommunications companies should enhance their social roles in mitigating the negative effects of the COVID-19 pandemic by actively implementing social responsibility initiatives.
Keywords: COVID-19 Pandemic; CSR; Corporate Communications; Corporate Social Responsibility; Libya; Telecom Company

Influence of remuneration on organizational performance in co-operative banks in Kiambu, Kenya - Brian, Kasale; Abuga, Isaac Mokono (African Journal of Social Issues, 2024)
This study investigates the influence of remuneration on organizational performance in cooperative banks in Kiambu County, Kenya. Employing a mixed-methods approach, the research explores how compensation packages, salary reviews, and employee recognition impact performance. The study utilizes a descriptive research design with structured questionnaires to gather data from 94 participants. Findings indicate a significant correlation between competitive remuneration and enhanced organizational performance. The majority ofemployees are satisfied with salary increments and recognize the positive effects of frequent salary reviews on their motivation and job satisfaction. The study also highlights the importance of recognition and praise in boosting employee morale and engagement, contributing to overall organizational success. This research is grounded in Equity Theory, which posits that fair treatment in compensation leads to higher motivation and productivity. The conclusions drawn suggest that cooperative banks should implement equitable and competitive remuneration strategies, along with regular salary reviews and robust recognition programs, to enhance performance. The study provides valuable insights for policymakers andbank managers aiming to improve organizational effectiveness through strategic human resource practices.
Keywords: Co-operative Banks; Employee Motivation; Equity Theory; Organizational Performance; Remuneration

Le décompte du temps de travail - Girier-Timsit, Marianne (Université Paris 10, 2024)
À lire certains professionnels du droit, le décompte du temps de travail aurait fait son temps. Les cadres ne « compteraient pas leur temps », le décompte serait lié à la « civilisation de l’usine », et plus structurellement le temps ne serait plus un étalon pertinent de mesure du travail. À ces doutes, il s’agit d’affirmer l’utilité permanente du décompte du temps de travail. La question de l’importance du décompte du temps de travail est étroitement liée à celle du rôle et de la place du temps de travail. Ces interrogations relatives au décompte du temps de travail découlent principalement de la remise en cause du temps comme outil de mesure et de limitation du travail. Au contraire, c’est en affirmant la permanence du temps à pouvoir et à devoir remplir de telles fonctions que l’intérêt et l’importance du décompte du temps de travail se révèlent. Qu’il s’agisse de mesurer ou de limiter le travail, le temps ne peut remplir ces fonctions qu’à condition d’être décompté. Autrement dit, c’est le décompte du temps de travail qui permet au temps de remplir ses fonctions de mesure et de limitation du travail. L’intérêt du décompte du temps de travail se dévoile à l’aune de la fonction, générique, du temps comme unité de conversion. Le temps constitue en effet une unité de conversion objective et universelle, qu’il s’agisse de déterminer l’engagement du salarié, de déterminer et quantifier le salaire, de protéger par un salaire minimum horaire, ou encore de garantir la protection de la santé et des temps de liberté. Or, ces fonctions de mesure et de limitation du travail sont intrinsèquement liées à la nature du contrat de travail, défini et caractérisé par la subordination du salarié à l’employeur. S’interroger sur l’importance du décompte du temps de travail consistera à questionner le rapport qu’il entretient avec l’existence, la formation et la construction du contrat de travail tel que caractérisé par la subordination. Dans cette étude, on cherche à identifier les enjeux du décompte du temps de travail, les façons d’y procéder, les difficultés rencontrées et les solutions apportées. Pour déterminer si le décompte du temps de travail est une condition au contrat de travail, il y a d’abord besoin d’examiner dans quelle mesure le décompte du temps de travail s’avère utile au regard du droit du travail. Il s’agit d’affirmer la nécessité de procéder à un décompte du temps de travail, qui découle d’une multitude d’énoncés au service desquels le décompte du temps de travail intervient. Pour apprécier si le droit positif est à la hauteur de cette nécessité, il s’agit ensuite d’évaluer l’obligation de décompter le temps de travail, et de voir comment cette obligation est appréhendée, abordée et imposée par le droit du travail. Il en ressort que le décompte du temps de travail est un élément consubstantiel de l’idée de salariat et un élément structurant du droit du travail. Et il demeure tel, même s’il est aujourd’hui attaqué. Le droit du travail s’évertue donc à imposer le décompte du temps de travail. Il s’agit de l’une de ses dimensions essentielles. D’ailleurs, même lorsqu’il ouvre des brèches dans les frontières du temps de travail, comme avec le forfait-jour, il ne réussit pas à s’abstraire totalement de la nécessité du décompte, et même du décompte horaire. Le décompte résiste partout, puisqu’il doit résister, puisqu’il en va de l’essence de la subordination et donc de l’essence de la relation de travail salarié.Le décompte du temps de travail, même s’il contesté comme le sont tous les piliers du droit du travail, demeure et demeurera. Il est au cœur de la relation de travail, et il y restera tant que le travail subordonné existera.
Keywords: Contentieux des heures travaillées; Contrôle du temps de travail; Durée du travail; Décompte; Employee performance; Horaires de travail – Droit; Hours worked litigation; Prestation du salarié; Settlement; Temps de travail; Working hours; Working time; Working time control

Medidas de conservação nos negócios jurídicos condicionados - Lobato, Jose Cristobal Aguirre (Universidade de São Paulo, 2024)
A tese visou analisar o sentido e alcance do artigo 130 do Código Civil. Essa tarefa, no entanto, foi precedida por estudo da estrutura e função da condição dentro do quadro do negócio jurídico, provocando o debate sobre sua utilização, inclusive atípica. Analisou-se dogmaticamente o elemento condição na teoria geral do negócio jurídico, sob uma perspectiva crítica para, depois, estudar a fase de pendência e as obrigações dela decorrentes para os figurantes e as possibilidades em tema de atos conservativos, nessa etapa tão característica do negócio condicionado, oferecendo novos enfoques para o assunto. Isso se fez de modo propositivo, aproveitando ainda para ponderar sobre as implicações da cláusula geral de boa-fé nessa matéria. Por fim, apresenta rol de considerações de caráter operativo, tentando estabelecer a conexão entre os atos conservativos a que alude a lei civil, com as devidas repercussões processuais. The thesis aimed to analyze the meaning and scope of article 130 of the Civil Code. This task, however, was preceded by a study of the structure and function of the condition within the framework of the legal business, bringing up the debate on its use, including atypical use. It was carried out a dogmatic analysis of the condition element in the general theory of the legal business, from a critical perspective, in order to study the pendency phase and the obligations it entails for the parties and the possibilities in terms of conservative acts at this stage, which is so characteristic of the conditioned transaction, offering new approaches to the subject. This was done purposefully, taking the opportunity to consider the implications of the general clause of good faith in this matter. The final considerations were presented in an operative view, trying to establish the connection between the conservative acts referred to in civil law, with the appropriate procedural repercussions.
Keywords: Condition; Conditional Legal Transactions; Condição; Direito Civil; Fato Jurídico; Legal Fact; Negócios Jurídicos Condicionados; Private Law

La structuration de l'e-sport, étude en droit du numérique et de la propriété intellectuelle - Guedes, Emeline (Université Paris-Saclay, 2024)
L'e-sport est actuellement en phase de développement économique constant. Toutefois, au regard de la nouveauté de la pratique, le cadre juridique peine parfois à s'adapter afin de rendre la pratique e-sportive pérenne économique et stable au regard de son cadre juridique. Il est dès lors important de structurer juridiquement l'e-sport afin de lui offrir un cadre économique solide. Cette pratique spécifique appelle une structuration par le droit du numérique et le droit de la propriété intellectuelle, cette recherche consiste ainsi à trouver un modèle pérenne de cadre juridique pour l'e-sport en s'inspirant de régimes déjà existants (droit du sport, de la propriété intellectuelle, de la concurrence ou encore droit de l'audiovisuel entre autres) afin que la pratique se développe sans entrave économique et par le prisme des technologies numériques en constante évolution. Cette recherche fait appel à des mécanismes déjà existants en droit, à des règlementations déjà applicables mais aussi à l'aménagement de nouvelles règles de droit, adaptées à la pratique e-sportive.
Keywords: Competencia; Competition; Competition law; Concurrence; Digital; Droit des technologies de l'information et de la communication; E-Sport; Esports; Intellectual property; Liability; Médias numériques; Numérique; Propriedade intelectual; Propriété intellectuelle; Responsabilité; Sport électronique

Les jetons participatifs : contribution au droit de la finance participative - Aliyev, Novruz (Université de Rennes, 2024)
Au-delà de l’aspect numérique, Satoshi, fondateur anonyme du bitcoin, évoque l’organisation de « Pair à Pair » (P2P). Elle correspond à l’algorithmique répartie sur laquelle le registre décentralisé de ces nouveaux actifs se fonde. Mais le Règlement MiCA exclut la finance décentralisée et ne donne aucune définition satisfaisante des crypto-actifs. On étend cette observation aux actifs numériques, insuffisamment cernés en droit français. L’analyse de l’organisation P2P s’impose. On a identifié chez certains jetons une organisation participative, distincte des groupements et des contrats-coopération. Elle se caractérise par un degré et une forme d’indépendance nouvelle ainsi que par une socialité orientée vers un objet de nature impersonnelle, ouverte vers l’extérieur et sans structure (ni groupements ni contrats). Elle façonne ainsi la structure d’émission et la forme représentative et négociable de ces jetons. Ils sont des écrits représentant un bien ou un service et non un droit à l’encontre d’une personne émettrice. Ils sont émis dans une organisation participative : sans partage de pertes, de bénéfices, de chiffres d’affaires ou d’autres fruits. Leur qualification civiliste est le produit et non le fruit, contrairement aux titres financiers. L’organisation participative, elle, s’analyse comme un système, une nouvelle catégorie juridique que l’ordre juridique peut accueillir. L’ouverture du système vers l’extérieur nécessite la négociabilité des jetons. Elle concourt à la financiarisation de l’économie réelle. Comme la structure d’émission de ces jetons participatifs, leur infrastructure polycentrique de négociation appelle une régulation par l’organisation. Ces jetons sont aussi hybrides parce que participatifs et monétaires, et en tant que tels peuvent être considérés comme des unités de financement ; nouvelle définition de la monnaie que l’on propose, pour ne pas la réduire à sa seule fonction de paiement. Les jetons participatifs perturbent la summa divisio entre la monnaie et les instruments financiers ainsi que le concept même de droit subjectif.
Keywords: Crypto; Crypto-Actifs; Cryptomonnaie; Decentralised finance; Distributed ledger technology.; Finance décentralisée; Financement participatif; Jeton; Jetons-monnaie; Monnaie; Registre réparti; System; Système; Token

Le financement des entreprises dans l’espace OHADA - ERSUMA - OHADA (Ecole régionale supérieure de la Magistrature, 2024)

Dano informacional no mercado de valores mobiliários - Ronco, Felipe dos Santos (Universidade de São Paulo, 2024)
Ao acessar o mercado de valores mobiliários, atribui-se às companhias emissoras um dever de sempre informar, a tempo e modo, seus respectivos investidores, sejam eles atuais ou futuros, de modo a assegurar que todas as informações por elas divulgadas ao mercado, de forma voluntária ou obrigatória, sejam fidedignas. A despeito do efeito que possa produzir na decisão individual do investidor, a informação sempre terá um impacto na própria cotação dos valores mobiliários, uma vez que considerado seu ambiente de negociação (i.e., o sistema de pregão) e as forças de oferta e demanda do mercado. O efeito da informação na expectativa individual do investidor será irrelevante para a formação dos preços dos valores mobiliários, devendo o efeito do ilícito informacional ser apurado a partir de todo o conjunto de operações realizadas em bolsa. O dano informacional deve, assim, ser compreendido a partir da violação do interesse juridicamente tutelado do investidor nas informações prestadas pela companhia emissora, tendo em vista os efeitos que essas informações são capazes de produzir diretamente na cotação dos valores mobiliários. When accessing the securities market, issuers have the duty to inform, in a timely manner, their investors, whether current or future, in order to ensure that all information disclosed to the market, whether voluntarily or obligatory, is reliable. Regardless of the effect it may have on the investor\'s decision, the information will always have an impact on the price of the securities itself, once considered their trading environment (i.e., the trading system) and the forces of supply and demand of the market. The effect of the information on the investor\'s individual expectations will be irrelevant to the formation of securities prices, since the effect of unlawful wrongdoing must be determined based on the entire set of operations carried out on the stock exchange. Informational damage must, therefore, be understood as the violation of the investor\'s legally protected interest in information provided by the issuer, considering the effects that the information produces directly on the price of securities.
Keywords: Dano informacional; Dever de informação; Duty to inform; Informational damages; Investidor; Investor; Mercado secundário; Secondary market

Corporate Income Tax (CIT) and Capital - Agossadou, Stanislas Théodule Médard Dèwanou Comlan (International Journal of Accounting, Finance, Auditing, Management and Economics, 2024)
This research consists of verifying whether CIT has an effect on capital given the financing risk incurred. A review of several capital theories has shown that CIT is one of the main determinants of a firm's capital structure. The inclusion of CIT in capital structure models continues to divide the world of corporate finance. Debt interest deduction in computing CIT reinforces the controversy over the question of the capital structure that optimizes the tax savings provided by this deduction. The consequence is the existence of two opposing groups on the optimum capital structure: on the one hand, the group of those who believe that there is one and only one optimal capital structure, and on the other, the group of those who reject out of hand any possibility of an optimal capital structure. The sample starts with a case study of two hypothetical identical firms, one indebted and the other non-indebted, with the same profitable investment project over a period of time, and ends with 101 pairs of identical firms belonging to different classes of financing risk. The hypothesis of non-gratuity of cost and income is used, and capital markets are assumed to be pure and perfect. The results confirm that CIT has no effect on the structure, value, cost and return of capital for a given financing risk, and reveal the existence of a third source of financing called "public capital", whose cost is the corporate capital tax rate (CCTR). There is no longer any question of thinking about the optimum capital structure, which is a pure financial illusion. This paper is one of the first to show that CIT does not affect capital, and to propose a model that explains capital structure behavior in the presence of CIT. Paper type: Empirical Research Stanislas Théodule Médard Dèwanou Comlan AGOSSADOU, (Researcher) Laboratory for Research on Performance and Development of Organizations (LARPEDO) Faculty of Economics and Management (FASEG) University of Abomey-Calavi (UAC) - Benin,
Keywords: Capital structure; Financial integration of corporate tax; Firm value; Return on investment; Weighted average cost of capital (WACC)

L’effectivité du droit du travail djiboutien - Saïd Wais, Ilyas (Revue de droit comparé du travail et de la sécurité sociale, 2024)
La question de l’effectivité du droit du travail s’inscrit, dans une certaine mesure, dans la réalisation de l’un des objectifs de développement durable que se sont assignés les États membres de l’OIT, en l’occurrence celui d’un travail décent pour tous. Plus généralement, elle se rattache à la problématique générale de l’effectivité du droit. La République de Djibouti, jeune nation africaine qui n’a pas une longue tradition dans l’expérience du droit étatique se trouve confrontée, comme c’est le cas singulièrement en Afrique, à une situation d’ineffectivité du droit du travail. Cet article analyse les principaux symptômes de cette ineffectivité, en identifie les causes et explore les facteurs d’une meilleure application du droit du travail djiboutien.
Keywords: Djibouti; Défauts du droit; Economie informelle; Effectivité; Institutions du droit du travail; Libéralisation; Mimétisme juridique; violations de droits

Le consentement en droit des personnes : une approche critique - Demoule, Rébecca (Université Paris 1, 2024)
Consentement à l’acte médical, à l’adoption, au traitement de données personnelles, aux relations sexuelles : le terme de consentement occupe une place particulière en droit des personnes. Cette thèse propose d’apporter des réponses à cette problématique sociale fondamentale à partir d’une approche critique du droit. Un nouveau regard peut ainsi être porté sur le consentement en l’appréhendant à la fois comme un phénomène politique et comme une réalité sociale. Le consentement en droit français correspond en premier lieu à un phénomène politique. Loin de jouer le rôle libéral qui lui est classiquement prêté, il représente plutôt une norme idéologique humaniste. Norme également fonctionnelle, le consentement permet aux pouvoirs publics de préserver l’ordre social. Le consentement représente en second lieu une réalité sociale. Les théories générales civilistes ne permettent pas de se saisir de cette réalité car, malgré leur attrait, elles présentent des limites. Nous proposons de nous tourner vers les analyses de justice sociale. Elles permettent d’identifier les inégalités sociales intersectionnelles qui affectent les consentements. Des analyses de justice sociale offrent également un cadre pour y répondre juridiquement. Le consentement peut ainsi être conçu comme un processus de reconnaissance et être encadré comme tel en droit.
Keywords: Adoption; Consent; Consentement; Consentement (droit); Consentement sexuel; Droit des données à caractère personnel; Droit médical; France; Justice sociale; Libéralisme; Personnal data; Social justice; Volonté

A companhia engajada : disciplina dos atos societários de orientação social - Galizzi, Gustavo Oliva (Universidade de São Paulo, 2024)
Os acadêmicos divergem desde sempre a respeito do objetivo da companhia: atender ao interesse dos acionistas e buscar a maximização dos resultados ou, alternativa ou sucessivamente, atender ao interesse de outras partes interessadas? Porém, as linhas entre uma e outra correntes não são mais nítidas como antes. Com o crescente interesse nas chamadas métricas de ESG a sigla para Environmental, Social and Governance, modelos híbridos de governança têm sido pensados a partir da combinação de lucro e propósito. Nesse sentido parece evidente a consolidação de uma tendência no direito societário que, por falta de um termo melhor, possa ser qualificada como preponderantemente social. Sem prejuízo dessa evidência, o objetivo do trabalho não é o de defender uma ou outra corrente sobre a função da companhia. Num olhar pretensamente original, o estudo propõe outro enfoque: traçar a disciplina legal dos atos societários de orientação social, como materialização do interesse que os precede. Academics have always disagreed about the company\'s objective: to serve the interests of shareholders and seek to maximize results or, alternatively or successively, to serve the interests of stakeholders as other interested parties? However, the lines between one theory and another are no longer as clear as before. With the growing interest in the so-called ESG metrics the acronym for Environmental, Social and Governance, hybrid governance models are being designed based on the combination of profit and purpose. The consolidation of a trend in corporate law that, for lack of a better term, can be qualified as predominantly social is now clear. Notwithstanding the before, the objective of the study is not to defend one or another theory of the corporate objective. In an allegedly original perspective, the study proposes another approach: tracing the legal discipline of socially oriented corporate acts, as the externalization of the interest that precedes them.
Keywords: Atos societários de orientação social; Corporate objective; Corporate purpose; ESG; Interesse social; Propósito social; Socially oriented corporate acts

Internalização do interesse público na governança corporativa das empresas estatais - Nakasone, William Joji (Universidade de São Paulo, 2024)
A tese aborda as empresas estatais no contexto da Constituição Federal de 1988, destacando seu papel como instrumentos de ação do Estado na busca pela concretização dos objetivos constitucionais. O texto explora as características das empresas estatais, ressaltando sua submissão aos princípios da Administração Pública, bem como aos controles inerentes a essa esfera, como a tutela administrativa, o controle dos tribunais de contas e o controle jurisdicional. Destaca-se a importância do preenchimento do conteúdo do interesse público como guia para o exercício do poder de controle acionário e para a atuação dos órgãos sociais das empresas estatais. Nessa tarefa, propugna-se pela utilização de fontes legítimas de expressão do interesse público que, preferencialmente, e em alguma medida, passaram por processos de inclusão participativa daqueles afetos ao interesse público, seja direta ou indiretamente. Argumenta-se pela maior efetividade de políticas públicas que contam com essa natureza, baseados em experiência desenvolvimentista e na teoria da nova governança pública. Defende a organização e formalização do exercício do poder de controle societário, apoiando a criação de um colegiado para concentrar essa atividade, de modo a garantir formalização das orientações, devida consideração ao conteúdo do interesse público, e sopesamento da matéria vis-à-vis os demais interesses que o acionista controlador deve lealmente respeitar e atender. A tese destaca a necessidade de acomodar o interesse público nos órgãos da administração das empresas estatais, defendendo a nomeação de representantes dos titulares desse interesse no conselho de administração, assim como o estabelecimento de órgão interno com competência técnica de pesquisa, interação com a comunidade e elaboração de políticas relacionadas ao interesse público tutelado. Além disso, expõe sobre o conteúdo do interesse social da empresa estatal e aborda questões relacionadas aos deveres fiduciários do acionista controlador e dos administradores, enfatizando as peculiaridades resultantes da centralidade do interesse público no interesse social. Destaca os mecanismos de organização do exercício do poder de controle, para prevenção e controle de abusos de poder e situações de conflito de interesses. Destaca a contribuição dos mecanismos de tutela do interesse público no interior dos órgãos sociais da empresa estatal para o cumprimento dos deveres de diligência e lealdade dos administradores, prevenindo desvios de poder e assegurando a comutatividade nas operações da empresa estatal com partes relacionadas. The thesis addresses the state-owned enterprises within the context of the Brazilian Federal Constitution of 1988, highlighting their role as instruments of state action in pursuit of constitutional objectives. The text explores the characteristics of state-owned enterprises, emphasizing their adherence to the principles of Public Administration, as well as the controls inherent in this sphere, such as administrative supervision, oversight by audit courts, and judicial control. The importance of defining the content of the public interest as a guide for exercising shareholder control and the functioning of the corporate bodies of state-owned enterprises is emphasized. In this endeavor, the thesis advocates the use of legitimate sources for expressing the public interest that, preferably, to some extent, have undergone participatory inclusion processes of those affected by the public interest, either directly or indirectly. The argument is made for the greater effectiveness of public policies with this nature, based on developmentalist experiences and the theory of new public governance. The thesis advocates for the organization and formalization of the exercise of shareholder control, supporting the creation of a board to centralize this activity, ensuring formalization of orientations, due consideration of the content of the public interest, and weighing the matter against other interests that the controlling shareholder must respect and uphold within its duty of loyalty. The thesis highlights the need to accommodate the public interest in the administration of state- owned enterprises, advocating for the appointment of representatives of those holding this interest on the board of directors, as well as the establishment of an internal body with technical role for research, interaction with the community, and the formulation of policies related to the protected public interest. Additionally, it discusses the content of the company interest of the state-owned enterprise and addresses issues related to the fiduciary duties of the controlling shareholder and administrators, emphasizing the particularities resulting from the centrality of the public interest in the company interest. It emphasizes the mechanisms for organizing the exercise of share control power, for the prevention and control of abuses of power and conflicts of interest. The thesis highlights the contribution of mechanisms to protect the public interest within the corporate bodies of the state-owned enterprise to fulfill the duties of diligence and loyalty of administrators, preventing abuses of power and ensuring arms length basis in the operations of the state-owned enterprise with related parties.
Keywords: Company interest; Corporate governance; Empresas estatais; Empresas públicas; Governança corporativa; Interesse público; Interesse social; Mixed economy companies; Public companies; Public interest; Sociedades de economia mista; State-owned enterprises

O propósito específico nas sociedades empresariais - Andrade, Alexandre Soares (Universidade de São Paulo, 2024)
As sociedades de propósito específico (SPEs) não configuram um tipo societário próprio, mas sim mera categoria eficacial autônoma. A investigação histórica do instituto evidencia raízes desde os tempos romanos, tendo reverberado, ainda, nos arranjos típicos do período medieval e nas codificações oitocentistas, revelando sua essência como uma necessidade comercial da vida prática de separar patrimônios em função de um propósito específico, com projeções internas e externas que foram moldadas ao longo do tempo para viabilizar a consecução de empreendimentos de alto risco e promover o desenvolvimento econômico. No Brasil, está presente desde o Código Comercial de 1850, tendo sido adotada por diversas legislações esparsas ao longo dos últimos séculos para as mais diversas funções, servindo como mola propulsora ao desenvolvimento econômico. Como categoria eficacial autônoma que é, goza de flexibilidade para ser aplicada a qualquer tipo societário, modulando os efeitos típicos que lhes são assegurados aos seus ordenamentos societário, patrimonial e da atividade em função do propósito específico almejado. Não por outro motivo, seguindo o que nos parece ser a melhor técnica, o legislador tratou sua previsão normativa expressa no dispositivo de que trata do objeto social, restringindo-o em função de um propósito específico. Aos aplicadores do direito, diante do desenvolvimento histórico do instituto de seus efeitos, cabe saber distingui-los e aplicá-los, de modo a assegurar a efetividade da categoria em nosso ordenamento jurídico e o desempenho de sua função socioeconômica moldada ao longo de tantos anos.
Keywords: Activity structure; Asset structure; Autonomous efficacy category; Categoria eficacial autônoma; Corporate structure; Modulation of effects; Modulação de efeitos; Ordenamento da atividade; Ordenamento patrimonial; Ordenamento societário; Propósito específico; Sociedade de Propósito Específico (SPE); Special Purpose Entity (SPE); Specific purpose

A representatividade dos credores na recuperação judicial : uma análise da organização dos credores em classes na Lei 11.101/05 - Piva, Fernanda Neves (Universidade de São Paulo, 2024)
Esta Tese de Doutorado apresenta uma análise da legitimidade das deliberações em assembleias-gerais de credores em processos de recuperação judicial no Brasil, sob a ótica das normas estabelecidas pela Lei 11.101/05 e suas alterações pela Lei 14.112/20. O estudo é estruturado em seis capítulos. O primeiro capítulo corresponde à introdução. O segundo capítulo trata do papel dos credores na recuperação judicial, examinando os objetivos da recuperação judicial enquanto um processo de negociação estruturada. O terceiro capítulo aborda a estrutura rígida de divisão dos credores em classes, evidenciando problemas decorrentes da reunião de credores com interesses heterogêneos na mesma classe. Também no terceiro capítulo, a pesquisa analisa a criação de subclasses nas recuperações judiciais, com a possibilidade de tratamento diferenciado de credores, com vistas a avaliar se tais práticas mitigam o problema da legitimidade das deliberações quanto ao plano de recuperação judicial e atendem aos objetivos de uma recuperação judicial eficiente. O quarto capítulo analisa como a organização dos credores em classes ocorre em sistemas de outros países, buscando alternativas e soluções para os desafios identificados no sistema brasileiro. O quinto capítulo propõe soluções e medidas mitigatórias aos problemas identificados no estudo, visando a otimizar o processo deliberativo e garantir uma representação mais efetiva dos interesses dos credores, incluindo possíveis alterações legislativas. No último e sexto capítulo, serão sintetizadas as conclusões que podem ser extraídas do trabalho como um todo. This Doctoral Thesis presents an analysis of the legitimacy of deliberations in general meeting of creditors in judicial reorganization proceedings in Brazil, under the perspective of the norms of the Law 11.101/05 and its amendments by Law 14.112/20. The study is structured in six chapters. The first chapter corresponds to the introduction. The second chapter deals with the role of creditors in judicial reorganization proceedings, examining the objectives of a judicial reorganization proceedings as a proceeding of structured negotiation. The third chapter addresses the rigid structure of division of creditors into classes, highlighting problems arising from the gathering of creditors with heterogeneous interests in the same class. Also in the third chapter, the research analyzes the creation of subclasses in judicial reorganization proceedings, with the possibility of different treatment to creditors, to assess whether such practices mitigate the problem of the legitimacy of deliberations regarding the judicial reorganization plan and meet the objectives of an efficient judicial reorganization proceedings. The fourth chapter examines how the organization of creditors into classes occurs in systems of other countries, seeking alternatives and solutions to the challenges identified in the Brazilian system. The fifth chapter proposes solutions and mitigating measures to the problems identified in the study, aiming to optimize the deliberative process and ensure a more effective representation of the interests of creditors, including possible legislative changes. In the last and sixth chapter, the conclusions that can be drawn from the work will be synthesized.
Keywords: Assembleia Geral de Credores; Bankruptcy; Classes de credores; Classes of Creditors; Creditors; Credores; General Meeting of Creditors; Judicial Reorganization; Lei de Recuperação Judicial e Falências; Recuperação judicial

A mobilização de acionistas nas companhias abertas : interessados, finalidades e instrumentos - Fritz, Maximilian Kiderlen (Universidade de São Paulo, 2024)
Este trabalho tem por objetivo analisar a mobilização de acionistas para as assembleias gerais de acionistas das companhias abertas. Em caráter preliminar, são traçadas algumas premissas sobre o direito de voto, o princípio majoritário, o absenteísmo dos acionistas nas assembleias gerais e algumas considerações sobre dispersão acionária e certos aspectos das minorias societárias. Em seguida, dedicam-se algumas seções aos interessados na mobilização dos acionistas, que podem ser múltiplos e incluem o próprio controlador ou o bloco de referência da companhia, a administração da companhia, os acionistas minoritários na manifestação mais comum da mobilização , e outros interessados que podem consistir em empregados, credores ou membros da sociedade em geral. Feitas essas considerações, a dissertação trata das finalidades jurídicas mais comuns buscadas com a mobilização dos acionistas como, exemplificativamente, a própria convocação das assembleias gerais, tomada das contas, deliberação sobre as demonstrações financeiras, destinação de resultados, eleição de membros do conselho de administração, instalação e eleição dos membros do conselho fiscal, a responsabilização do controlador ou dos administradores e certos eventos que diluem a participação acionária dos acionistas. Por fim, a dissertação trata de alguns instrumentos disponíveis no ordenamento jurídico que podem ser utilizados para a mobilização dos acionistas, como as assembleias digitais ou híbridas, o boletim de voto a distância, a representação de acionistas, o pedido público de procuração, o pedido de lista de acionistas, as mídias sociais, os voting advisors, o empréstimo de ações e o usufruto de ações. This work aims to analyze the mobilization of shareholders for general shareholders\' meetings of publicly traded companies. Preliminarily, some assumptions and premises are outlined regarding the right to vote, the majority principle, shareholder absenteeism at general meetings, and considerations on share dispersion and certain aspects of minority interests. Subsequently, several sections are dedicated to the stakeholders involved in mobilizing shareholders, which may include the controlling shareholder or the company\'s reference block, the company\'s management, minority shareholders in the most common form of mobilization and other interested parties that may consist of employees, creditors, or members of society in general. With these considerations in mind, the dissertation addresses the most common legal purposes sought with the mobilization of shareholders, such as, for example, convening general meetings, approval of financial statements, determination of results allocation, election of members of the board of directors, installation and election of members of the fiscal council, holding the controller or administrators accountable, and certain events that dilute shareholders\' equity participation. Finally, the dissertation discusses some legal instruments available that can be used for shareholder mobilization, such as digital or hybrid assemblies, distance voting bulletins, shareholder representation, public proxy solicitation, shareholder list request, social media, voting advisors, stock lending, and share usufruct.
Keywords: Acionistas minoritários; Assembleias gerais; Companhias abertas; Corporate governance; Corporate law; Direito societário; General meetings; Governança corporativa; Minority shareholders; Mobilização de acionistas; Publicly traded companies; Shareholder mobilization

A comparative legal analysis of the accommodation of neurodiversity in the workplace : towards a universal right to reasonable accommodation - Conradie, Riana (Stellenbosch University, 2024)
Workforces are made up of individuals with differences in personal characteristics, differences that may be traced back to unique personality types and traits and – sometimes – neurodivergence. Due to the inherent subjectivity of the interpersonal relationships that form the foundation of a work environment, these differences in personal characteristics inevitably lead to tension. In addition, as part of managing a work environment employers frequently take decisions that may be influenced by views and perceptions regarding employees’ personal characteristics. This study starts with a descriptive examination of the meaning of personality and the influence that personality traits and types may have on employment. This is followed by a descriptive examination of neurodivergence, the various forms of neurodivergence, and the impact of these conditions on the work environment. Building on these descriptive and conceptual underpinnings, the legal implications of neurodiversity in the workplace are investigated by identifying which principles of the existing South African employment law framework may be utilised to provide protection and promote respect for neurodiversity and the neurodiverse differences between employees. This encompasses a discussion of the South African employment law rules relating to recruitment and selection of employees, some of the rules applicable to the day-to-day management of employees, and the rules relating to termination of employment that may be (in)directly influenced by considerations of neurodiversity. The focus thereafter shifts to consider the legal principles of employment discrimination law, where it is found that the listed ground of disability and an unlisted arbitrary ground may potentially be used as the applicable grounds of discrimination by employees if they are prejudiced due to their neurodiverse characteristics. In addition, the possibility that the rules on reasonable accommodation may be utilised as primary mechanism to properly regulate neurodiversity in the work environment and protect against prejudicial treatment of employees due to their inherent personal neurodiverse characteristics is also considered. The South African position and potential employment law rules that may apply to the management of neurodiversity in the work environment is compared to the position in the United Kingdom by focusing on the meaning of disability, the right to reasonable adjustments, and the right to request flexible working arrangements. Finally, the conclusions that may be drawn from this study are emphasised and are followed by some recommendations on how (reasonable) accommodation of neurodiversity in the work environment may appropriately be used as primary mechanism to provide employees with sufficient and appropriate protection of differences in neurodiverse characteristics. Even though this study focuses on neurodiversity and neurological differences between employees, the principles and recommendations from this study may be of value in relation to the appropriate management and regulation of all inherent differences between employees.
Keywords: Discrimination in employment; Diversity in the workplace; Employment; Labor laws and legislation; Neurodivergent people; Neurodiversity; People with disabilities

La vente de l'immeuble saisi en droits français et de l'OHADA - Dieme, Mamady (Université de Strasbourg, 2024)
La thèse analyse en profondeur la procédure de vente d’un immeuble saisi, en comparant les législations française, OHADA (Organisation pour l’Harmonisation en Afrique du Droit des Affaires) et alsacienne-mosellane. Elle montre que la saisie immobilière, bien que complexe, reste un instrument essentiel de recouvrement des créances pour les créanciers. Dans une première partie, l’auteur aborde la vente forcée, procédure judiciaire par laquelle le créancier poursuit la vente de l’immeuble du débiteur défaillant pour se faire payer. En droit français, la procédure est fortement judiciarisée : elle impose la saisine du juge de l'exécution, la rédaction d’un cahier des conditions de vente, une audience d’orientation, puis éventuellement une vente aux enchères. En droit OHADA, la procédure est moins détaillée mais tout aussi formaliste, avec une audience dite « des criées », mais sans équivalent à l’audience d’orientation. Le notaire joue un rôle plus important en Alsace-Moselle, où le droit local déjudiciarise la procédure, confiant à ce dernier la gestion des ventes.La deuxième partie traite des issues négociées, comme la vente amiable. En France, elle est encouragée sous autorisation du juge et permet d’éviter une adjudication souvent perçue comme brutale. Le droit OHADA, au contraire, ne prévoit pas explicitement la vente amiable, mais la pratique reconnaît parfois son utilité. L’auteur montre les tensions entre formalisme juridique et souplesse pragmatique, surtout quand la vente vise à préserver le logement familial du débiteur.L’approche historique enrichit l’analyse : en France, la saisie a évolué depuis les ordonnances royales, avec des réformes majeures en 1938, 1991, 2006 et la codification en 2012. En Afrique, l’OHADA, par l’adoption de l’AUPSRVE (Acte uniforme sur les procédures simplifiées de recouvrement et des voies d'exécution), a cherché à harmoniser et sécuriser les procédures civiles, souvent héritées du droit colonial français. Toutefois, la réforme de 2023 n’a pas permis de moderniser en profondeur la saisie immobilière, soulignant le besoin d’adaptation aux réalités socio-économiques africaines.Enfin, l’auteur propose une réflexion critique sur l’efficacité et l’humanité de la procédure, en insistant sur l’importance d’un équilibre entre le droit du créancier et la protection du débiteur. Il plaide pour une plus grande ouverture aux solutions amiables, notamment dans l’espace OHADA. This doctoral thesis offers a comparative legal study on the sale of seized real estate under French law, OHADA law, and the Alsace-Moselle local law system. The seizure and forced sale of property are key mechanisms for debt recovery, though they are often complex, lengthy, and emotionally charged.The first part focuses on forced sale procedures. In French law, this involves strict judicial control, including issuing an enforcement order, drafting terms of sale, holding an orientation hearing, and eventually organizing a public auction. In OHADA law, the process is also formalistic but lacks the nuanced judicial orientation stage seen in France. Instead, there is a “criée” hearing. In Alsace-Moselle, the process is unique: it is largely non-judicial, with the notary conducting the entire sale procedure after the initial court authorization.The second part explores negotiated outcomes, particularly the amicable sale. French law encourages out-of-court sales with judicial approval to avoid public auctions, which are often distressing for debtors. OHADA law does not formally allow for amicable sales, but informal practices sometimes accommodate them. The thesis highlights the tension between legal formalism and practical flexibility, especially when the debtor's home is at stake.The historical perspective strengthens the comparative study. France underwent several legal reforms: 1938, 1991, 2006, and the 2012 codification of enforcement procedures. In contrast, OHADA countries inherited fragmented colonial laws. The 1998 AUPSRVE was a major step toward legal harmonization across member states. However, the 2023 reform fell short of expectations, leaving key issues in seizure and sale processes unresolved, notably the lack of modernization and borrower protection.The author emphasizes the need for a fair balance between creditor rights and debtor protection. He advocates for greater use of amicable solutions, particularly in OHADA jurisdictions where formal options remain limited and social contexts differ significantly from European systems. The thesis suggests that legal systems should be both effective and humane, offering realistic tools adapted to each region’s economic and cultural realities.
Issue: 2024STRAA023
Keywords: AUPSRVE; Adjudication; Alsace-Moselle; Amicable sale; Comparative law; Créancier; Droit comparé; Droit français; Débiteur; Exécution forcée; Forced sale; French law; OHADA; Procédures simplifiées; Publicité foncière; Real estate seizure; Recouvrement de créances; Saisie immobilière; Vente amiable; Vente forcée; Voies d'exécution

Réflexion sur la protection du locataire-gérant en droit de l’OHADA - Okomen Tsague, Renaud Etiennis; Oba’A Atyam, Annick Mirabelle (Revue africaine de droit des affaires, 2024)
La location-gérance met aux prises le loueur de fonds et le gérant libre, le premier concédant au second la gestion libre d’un fonds contre paiement d’une redevance bien souvent composite. Cela étant, on peut à juste titre relever que le particularisme et l’enjeu de ce rapport juridique suscite tout l’intérêt d’une réflexion sur la protection du gérant libre dont la simple évocation invite à une tentative de caractérisation d’une telle protection en droit OHADA. Sur la question, l’analyse fait état de l’ambivalence qui caractérise la protection du gérant libre d’un fonds de commerce en droit OHADA. En effet, si l’arsenal mobilisable, aussi bien à la formation qu’à l’exécution du contrat de location-gérance, postule pour une protection remarquable du gérant, celle-ci n’en demeure pas moins discutable quand on envisage la situation en fin de contrat ou les hypothèses de mutation du droit de propriété sur le fonds loué en cours de contrat.

L'agence de régulation des télécommunications au Cameroun : un centre d'arbitrage d'une nature particulière - Silabing Ouethy, Jasmine Diane (Revue africaine de droit des affaires, 2024)
La Procédure de règlement des différends opposant les opérateurs de communications électroniques au Cameroun prévoit, en premier, la saisine de l’Agence de Régulation des Télécommunications (ART). Cette dernière devra tenter de concilier les parties. Si cette tentative de conciliation échoue, alors le dossier sera transmis au Comité de Règlement des Différends (CRD) qui devra trancher le litige. Au cas où la décision intervenue est contestée par une des parties, elle pourra saisir soit les juridictions de droit commun, soit l’arbitre. Cependant, le législateur de 2010 n’a pas résolu toutes les questions relatives à l’intervention de cet arbitre. Par exemple, qui le constitue ? Quelles règles gouvernent la procédure et sur la base de quelles normes doit-il trancher ? Où aura lieu l’arbitrage ? L’examen de la loi de 1998 qui a été abrogée par celle de 2010, plus explicite sur la question, nous livre un régime qui tantôt rapproche le régulateur d’un centre d’arbitrage sur certains aspects, tantôt l’éloigne sur d’autres.

La situation du créancier non-cité par son débiteur admis au bénéfice du règlement préventif en droit de l’OHADA - Toe, Souleymane; Mfini, Mon-espoir (Revue africaine de droit des affaires, 2024)
Le droit OHADA des procédures collectives connaît quatre procédures collectives, deux procédures préventives et deux procédures curatives. A ces procédures il faut ajouter des variantes, c’est-à-dire des procédures simplifiées, applicables aux entreprises de petite taille. Parmi les procédures préventives note-t-on le règlement préventif, qui a toujours existé, depuis le premier Acte uniforme OHADA portant organisation des procédures collectives d’apurement du passif. Mais, avec la réforme intervenue en 2015, cette procédure a connu de légers changements, qui invitent la doctrine à porter un regard sur ce qu’est devenu la procédure de règlement préventif. Les auteurs de ces lignes ont opté pour l’analyse de la situation du créancier non-cité par son débiteur admis au bénéfice du règlement préventif.

L'adaptabilité de l'arbitrage OHADA au contexte africain - Zakari, Amadou Hamani (Revue africaine de droit des affaires, 2024)
Le règlement des différends par les parties à une relation d’affaires, à travers l’arbitrage, n’est pas un fait nouveau dans les pays africains. Seulement, la nécessité était posée d’adapter ce mode alternatif aux réalités économiques africaines. Pendant longtemps, la majeure partie des contentieux dans lesquels les parties africaines sont impliquées, était réglée en dehors de ses frontières. Ce qui ne favorisait pas leur participation active. Mais la mise en place de l’OHADA et surtout, la création de la CCJA et plus tard son Centre d’arbitrage, suivis par les différents Centres d’arbitrage des Etats ont permis de faire de l’effectivité de l’arbitrage, une réalité. De l’arbitrage traditionnel, l’OHADA, a élargi le champ d’application de ce droit, en y incluant l’arbitrage des investissements, à l’occasion de la réforme du 23 et 24 novembre 2017. Actuellement, cette réforme fait l’objet de nombreuses critiques, notamment, sur le fait que pour certains, ce mécanisme favorise plus l’investisseur étranger que l’Etat partenaire, et que la notion même de l’investissement, n’a jusque-là pas fait l’objet d’une définition claire, tant en droit, en jurisprudence encore moins en doctrine. Pour mettre en œuvre l’arbitrage, les parties font recours à des arbitres, auxquels elles confient leurs différends suivant une convention d’arbitrage ou un instrument d’investissement qui détermine leur mission. Cette dernière peut être accomplie selon les cas, sous la forme d’un arbitrage institutionnel ou ad hoc, et finira par une sentence arbitrale, qui tranchera ce conflit. Comme dans la justice étatique, cette sentence est susceptible des voies de recours. L’arbitrage ne va pas sans écueils : de la constitution du tribunal arbitral à la sentence finale, plusieurs difficultés peuvent surgir.
Keywords: Arbitrage; Arbitragem; Arbitraje; Arbitration

Anotações sobre a agregação de credores em classes na recuperação judicial de empresas. - Martins, Aline de Toledo (Universidade de São Paulo, 2024)
Este trabalho tem por objetivo a análise da agregação dos credores em classes no âmbito da recuperação judicial, de acordo com a Lei n. 11.101/2005, e os impactos procedimentais e principiológicos neles englobados, tais como: a aprovação do plano de recuperação judicial, a agregação dos credores em classes, o sistema de votação e os princípios da par condicio creditorum e da preservação da empresa, extraindo desta análise lacunas e mecanismos criados que possam ter como consequência o desvirtuamento do fim almejado, sendo ao final apresentadas premissas e hipóteses de limitação e aplicação prática da agregação para evitar práticas abusivas. Dessa forma, são apresentadas breves noções introdutórias e fundamentais sobre a recuperação judicial acompanhada pela apresentação dos conceitos básicos referentes ao plano de recuperação judicial e a divisão dos credores em classes, demonstrando as origens, objetivos e expectativas do estabelecimento das classes na forma apresentada na Lei n. 11.101/2005. Ainda, são objetos específicos de estudo, a análise de como a divisão de classes de credores interfere na votação do plano de recuperação judicial e como tem sido tratada a possibilidade da criação de subclasses como é o caso do credor estratégico - e os efeitos diretos e indiretos ao procedimento e credores envolvidos. Em seguida, tem-se como objetivo verificar, no âmbito legal, as disposições sobre o tema a exemplo do artigo 41 da Lei n. 11.101/2005 -, as consequências e os impasses verificados ao longo dos anos de vigência de referida lei que demandam atenção e alterações para que o tratamento aos credores no âmbito da recuperação ocorra de forma mais justa e adequada aos interesses de todos os envolvidos. Assim, serão expostas soluções alternativas para a melhor condução do procedimento da recuperação judicial em relação às classes de credores e subdivisões em busca de garantir e preservar o objetivo da recuperação judicial, sempre considerando os fatores econômicos, políticos e sociais que influenciam para a análise da viabilidade econômica da empresa e que estão sempre em constante modificação. This work aims to analyze the aggregation of creditors into classes within the scope of judicial reorganization in accordance with Law No. 11.101/2005, as well as the procedural and principled impacts involved, such as the approval of the judicial reorganization plan, the aggregation of creditors into classes, the voting system, and the principles of par condicio creditorum and preservation of the company. It aims to identify gaps and mechanisms that may lead to the distortion of the intended purpose and presents premises and hypotheses for limiting and practically implementing the topic to avoid abusive practices. Thus, this work presents brief introductory and fundamental notions about judicial reorganization by the presentation of basic concepts related to the judicial reorganization plan and the division of creditors into classes, demonstrating the origins, objectives, and expectations of the establishment of classes as presented in Law No. 11.101/2005. Furthermore, specific study objectives include analyzing how the division of classes of creditors affects the voting on the judicial reorganization plan and how the possibility of creating subclasses - such as strategic creditors - has been addressed and its direct and indirect effects on the procedure and involved creditors. Next, this work verifies the legal provisions on the topic - such as Article 41 of Law No. 11.101/2005 as well as the consequences and impasses observed throughout the years of the law\'s existence that demands attention and changes to ensure that treatment of creditors in the context of reorganization occurs in a more just and appropriate manner for all parties involved. Thereby, alternative solutions will be presented for better management of the judicial reorganization procedure regarding creditor classes and subdivisions to ensure and preserve the objective of judicial reorganization, always considering the economic, political, and social factors that influence the analysis of the company\'s economic viability, which are constantly changing.
Keywords: Classification of claims; Classificação de Créditos; Judicial Reorganization; Par condicio creditorum; Recuperação Judicial

Les financements sur une blockchain : nouveaux défis du droit financier à l'aune de la finance décentralisée - Bonnet, Joris (Université de Strasbourg, 2024)
Alors que la finance traditionnelle peine à se renouveler, les nouveaux applicatifs de finance décentralisée proposent des services financiers basés sur des protocoles innovants, codés et entièrement gérés par les utilisateurs. Les classifications historiques de la finance sont largement inefficaces et des catégories telles que celle des instruments financiers ne permettent pas de construire un encadrement pertinent. Celles-ci doivent être dépassées pour pouvoir encadrer de façon plus inclusive tous les actifs décentralisés. La communication financière est rendue désuète et nécessite une refonte pour prendre en compte les nouvelles motivations des investisseurs et les impératifs environnementaux. Traditional finance is struggling to renew, new decentralized finance applications offer financial services based on coded protocols entirely managed by users. Historical classifications of finance are largely ineffective and categories such as financial instruments do not allow to construct a relevant framework. These must be overcome to be able to regulate all decentralized assets in a more inclusive manner. Financial communication has become obsolete and requires an overhaul to consider the new motivations of investors and environmental imperatives.
Keywords: Actif décentralisé; Asset; Blockchain; Chaine de blocs; Contract; Contrat; Crypto money; Crypto monnaie; Cryptoactif; Cryptomonnaie; DAO; DEEP; DLT; DeFi; Decentralized asset; Decentralized finance; Droit des affaires; Droit financier; Finance décentralisée; Finances; Financial law; Fundraising; ICO; Jeton; Levée de fonds; STO; Security; Token

Os deveres legais dos administradores de sociedades anônimas em crise - Lunardi Filho, Ferdinando Cesar (Universidade de São Paulo, 2024)
Este trabalho apresenta a tese de que, embora as normas constantes dos arts. 153 e seguintes da Lei no 6.404/76 continuem aplicáveis e o objeto dos deveres legais dos administradores de sociedades anônimas permaneça inalterado mesmo após a instauração de um cenário de crise econômico-financeira na companhia, em grande medida regrado pela Lei no 11.101/05, a instalação da referida crise causa uma modificação no conteúdo desses deveres. Para tanto, o trabalho adota como ponto de partida a jurisprudência e a literatura especializada norte-americanas, apresentando criticamente os casos mais recentes e relevantes julgados pelas Cortes de Delaware, bem como uma sistematização da literatura especializada pertinente. A análise crítica dos casos da jurisprudência norte-americana permite a compreensão da transição de um entendimento baseado na trust fund doctrine, segundo o qual, após a instauração da insolvência, mediante a aplicação da insolvency exception, haveria um shift por meio do qual os credores passariam a ser os destinatários dos deveres fiduciários dos administradores, para o entendimento mais recente de que o destinatário dos deveres fiduciários é apenas a companhia, ainda que devam ser levados em consideração pelos administradores os demais interesses que compõem o interesse social, tais como os interesses de credores, trabalhadores, consumidores. Em seguida, considerando que o conceito de crise econômico-financeira tem contornos incertos, o trabalho busca identificar instrumentos indicadores da instalação da crise. Para tanto, o trabalho não apenas revisita os conceitos clássicos de insolvência e insolvabilidade, mas também propõe novos enquadramento e sistematização, visando ao apontamento de elementos objetivos que, considerados em conjunto, permitam identificar com maior nitidez os contornos do estado de crise econômico-financeira. Posteriormente, o trabalho trata do tema central desta tese, começando pela lógica, os limites e a dinâmica da administração de sociedades anônimas em crise, especialmente diante da colidência de interesses de acionistas e de credores e da intensificação desses conflitos depois de instaurado o cenário de crise, passando pela contínua aplicabilidade da Lei no 6.404/76 e pelas razões que levam à alteração do conteúdo dos deveres legais dos administradores de sociedades anônimas em crise. A seguir, o trabalho demonstra que o ângulo mais adequado à análise dos deveres legais dos administradores de sociedades anônimas em crise no Brasil não é o da alteração do objeto dos deveres, nem o da alteração dos seus destinatários, tampouco o da alteração dos titulares de interesses contingentes na companhia, mas sim o da modificação do conteúdo dos referidos deveres. O trabalho adota, ainda, uma lente pragmática, buscando compreender a dimensão em que o conteúdo dos deveres é modificado após a instauração da crise, considerando uma lista exemplificativa das hipóteses mais relevantes, do ponto de vista prático e acadêmico, em que tais deveres entram em discussão: (i) dever de conhecer a situação econômico-financeira da companhia; (ii) deveres informacionais; (iii) dever de avaliar a adoção de medidas de reestruturação e de evitar o agravamento da crise; (iv) deveres relacionados à alienação e oneração de ativos; e (v) deveres relacionados à contratação de novos financiamentos. Por fim, o trabalho apresenta e discute a apuração da responsabilidade e outras possíveis consequências decorrentes do eventual descumprimento dos deveres legais dos administradores das sociedades anônimas em crise. This study presents the thesis that, although the norms set forth in articles 153 and following of Law No. 6,404/76 remain applicable and the object of the legal duties of administrators of public companies remains unchanged after the onset of a scenario of economic and financial crisis in the company, largely regulated by Law No. 11,101/05, financial distress causes a modification in the content of these duties. To this end, the study takes as its starting point the north American precedents and literature, critically presenting the most recent and relevant cases judged by the Delaware Courts, as well as a systematization of the relevant literature. The critical analysis of cases from north American jurisprudence allows the comprehension of the transition from an understanding based on the trust fund doctrine, according to which, after the onset of insolvency, through the application of the insolvency exception, there would be a shift whereby creditors would become the recipients of the fiduciary duties of directors, to the more recent understanding that the recipient of fiduciary duties is only the company, although directors should take into account other interests that compose company`s interest, such as the interests of creditors, workers, consumers. Next, the study investigates the concept of economic and financial distress. Considering that this concept has uncertain contours, the study seeks to identify indicative instruments of the installation of the economic and financial crisis. To do so, the study not only revisits classical themes, such as the concepts of insolvency and insolvability but also proposes new frameworks and systematization, aiming to highlight objective elements that, considered together, allow a clearer identification of the state of economic and financial crisis. Subsequently, the study addresses the central theme of this thesis, beginning with the logic, limits, and dynamics of the administration of companies in financial distress, especially in the face of the collision of interests between shareholders and creditors and the intensification of these conflicts after the onset of the crisis scenario, going through the continuous applicability of Law No. 6,404/76 and the reasons that lead to the alteration of the content of the legal duties of directors of companies in financial distress. Afterwards, the work demonstrates that the most appropriate approach to analyzing the legal duties of administrators of companies in crisis in Brazil is not that of changing the duties\' scope, nor altering their recipients, nor changing the holders of contingent interests in the company. Instead, the work advocates for examining the modifying content of these duties. The work also adopts a pragmatic lens, seeking to understand the extent to which the content of these duties is altered after the onset of the crisis, considering an illustrative list of the most relevant hypotheses, from practical and academic points of view, in which such duties come into discussion, namely: (i) duty to know the economic and financial situation of the company; (ii) informational duties; (iii) duty to assess the adoption of restructuring measures and to avoid the worsening of the crisis; (iv) duties related to the alienation and encumbrance of assets; and (v) duties related to the contracting of new financing. Finally, the study presents and critically discusses aspects related to the determination of responsibility and other possible consequences arising from the eventual non-compliance with the legal duties of managers and directors of companies in the brink of insolvency.
Keywords: Administradores; Corporation; Deveres fiduciários; Directors; Direito da empresa em crise; Fiduciary duties; Insolvency law; Judicial restructuring; Managers; Recuperação judicial; Sociedade anônima

Aspects of substantial compliance and strict compliance as applied to demand guarantees - Sikobi, Nkanyiso (University of South Africa, 2024)
Demand guarantees are essential for purposes of commerce and are used to secure the performance of the contractor. South African courts have held that demand guarantees are akin to letters of credit. Despite the independent nature of demand guarantees to the underlying contract, in circumstances where the beneficiary has made a fraudulent claim, the guarantor may dishonour the demand or claim. South African courts have indicated that if the underlying contract is illegal, courts may intervene by granting an interdict to stop payment under the guarantee. The South African law recognises traditional guarantees (often called suretyship) where the beneficiary, when making a demand or claim, must demonstrate liability on the part of the contractor. There are instances where courts have held that guarantees were of a nature akin to suretyship. In South Africa, parties entering into a demand guarantee contract are subject to the common law of contract. The Uniform Rules for Demand Guarantees, adopted by the International Chamber of Commerce, are only applied by explicit reference in the demand guarantee failing which such rules do not apply. Non-implementation of these rules has resulted in rigorous litigation in the recent years on this subject-matter. A demand must be supported by documents and require strict conformity. However, strict compliance with the prerequisites of the demand guarantee has not been applied consistently in South Africa. South African courts have recently been applying substantial compliance, in certain circumstances finding that a term in a guarantee is just directory and not obligatory. Furthermore, on many occasions, courts have deviated from strict compliance holding that a term in a guarantee does not make commercial sense thus such term is not mandatory. In this way, courts apply the most business-sensible interpretation when interpreting demand guarantees.
Keywords: Autonomous; Beneficiary; Contractor; Demand guarantees; Demand or conditional guarantee; Documentary letters of credit; Employer; First written demand; Fraud and illegality exception; Guarantor; Independence; Performance guarantees; Security for performance; Strict compliance; Substantial compliance; Suretyship; Underlying contract; Uniform rules for demand guarantees

La normalisation comptable et les enjeux de l’information financière dans l’espace OHADA - ERSUMA - OHADA (2024)

Le nouveau cadre juridique du recouvrement des créances et de l'exécution forcée entre en vigueur - ERSUMA - OHADA (Ecole régionale supérieure de la Magistrature, 2024)

The Impact of the United Nations Human Rights Treaties on the Domestic Level: Twenty Years On - Heyns, Christof; Viljoen, Frans Jacobus; Murray, Rachel (Brill, 2024)
This collection of chapters tracks and explains the impact of the nine core United Nations human rights treaties in 20 selected countries, four from each of the five UN regions. Researchers based in each of these countries were responsible for the chapters, in which they assess the influence of the treaties and treaty body recommendations on legislation, policies, court decisions and practices. By covering the 20 years between July 1999 and June 2019, this book updates a study done 20 years ago.
PDF: https://brill.com/downloadpdf/edcollbook-oa/title/38945.pdf
Keywords: Comparative Social Sciences; Human Rights; Human Rights and Humanitarian Law; Humanitarian Law; International Law; International Law: Regional Perspectives

The Impact of the United Nations Human Rights Treaties on the Domestic Level in Senegal - Kane, Ibrahima (The Impact of the United Nations Human Rights Treaties on the Domestic Level: Twenty Years On, 2024)
"Chapter 16 The Impact of the United Nations Human Rights Treaties on the Domestic Level in Senegal" published on 09 Feb 2024 by Brill | Nijhoff.
Section: The Impact of the United Nations Human Rights Treaties on the Domestic Level: Twenty Years On
Keywords: Comparative Social Sciences; Human Rights; Human Rights and Humanitarian Law; Humanitarian Law; International Law; International Law: Regional Perspectives; Social Sciences

Loi type de la CNUDCI sur l'utilisation et la reconnaissance internationale de la gestion de l'identité et des services de confiance - United Nations Commission on International Trade Law (United Nations, 2024)

Os Dispute Boards e sua função social: conflitos empresariais em contratos complexos - Possato, Karim Regina Nascimento (Universidade Nove de Julho, 2024)
El estudio de los Dispute Boards (DB) y su función social reflejada a través de la prevención y resolución de conflictos empresariales en contratos complejos es el tema central de este estudio. El problema de investigación planteado, en este contexto, es si los Dispute Boards son institutos capaces de desempeñar una función social basada en la prevención y resolución de conflictos en contratos mercantiles complejos. Así, el tema se desarrolla con base en el método dialéctico de la producción científica, apoyado en investigaciones bibliográficas y documentales, además de investigaciones de campo, con encuestas cuantitativas y cualitativas sobre el uso de los DBs. Para ello, el estudio busca contextualizar los conceptos que involucran al mercado, la empresa y la función social como factores que permean contratos comerciales complejos, caracterizados por incertidumbres y riesgos relacionados con la ejecución contractual que deben ser gestionados a través de la implementación de una gobernanza guiada. por principios que implementen la eficiencia de la relación comercial. La referencia a estándares internos en el ámbito de la administración pública también se utiliza para guiar el estudio, que también se abarca en la aplicación del gobierno corporativo, identificando los DBs como vectores para implementar contratos complejos y, en consecuencia, promover y entregar valor sostenible a las empresas. y otras partes interesadas, concluyendo que son mecanismos relevantes para promover la función social, prevenir y resolver conflictos, especialmente en contratos complejos. De la misma manera, se identifica la necesidad de potenciar el instituto DB, atribuyendo personalidad jurídica, además de la contractual, a sus decisiones, con el fin de potenciar su propia función social basada en la seguridad jurídica de los dictámenes deliberantes vinculantes emitidos, presentando, al final, una propuesta de proyecto de ley con el objetivo de iniciar el proceso legislativo para implementar esta realidad jurídica, siguiendo el ejemplo del instituto de arbitraje.
Keywords: Complex business contract; Contractual governance; Contrato comercial complejo; Contrato empresarial complexo; Dispute Board; Função social; Gobernanza contractual; Governança contratual; Papel social; Social function

Islamic Law Aspect on in Valuation and Execution Intellectual Property (IP) Asset as Bank Collateral in Creative Economy - Margono, Suyud (International Journal of Social Science Research and Review, 2024)
One of the issues faced by many creative economy actors in this relatively newly established industry is the lack of supporting infrastructure, such as the limited access to financing and one of the prominent issues is banks’ reluctance to accept intellectual property (“IP”) as collateral to secure loans including problems concerning valuation of IP Asset as Collateral which has implications several regulation concerning Intellectual Property. In the spirit of furthering the creative economy, the Government has recently issued Government Regulation Number 24 of 2022 on Intellectual Property-Based Creative Economy Financing. This matters includes in relation with IP assets that are exposed and exploited their product (goods or services) on the basis of exclusivity in financing and loan contractual scheme as collateral. This article normative legal research in which intended for studies that are literary and practical works which is Intellectual Property (IR) system in relation with valuation and execution as bank collateral either Indonesia prevailing law and Islamic (Syariah) Law. The result of this research that IP owners often deal with complex contractual relationships that involve different forms of cooperation in research, production or commercialization. most important aspect concerning capacity and competency with comprehensive knowledge deal with IP Asset as Collateral before Banks, and others financial institution, execution of guarantees as applied to Islamic banking has adopted many syariah law, in the practice, there are still many problems the implementation of guarantees as applied to Islamic banking has adopted many Islamic laws. However, in the practice, there are still many problems that arise from the Islamic law scope the concept of justice and the philosophy of maslahah.
Keywords: Creative Economy Valuation and Execution Asse; Intellectual Property (IP) Collateral; Islamic (Syariah) Law

Corporate law, governance, and sustainability : the public turn in the global socio-ecological transition - Junqueira, Gabriela de Oliveira (Universidade de São Paulo, 2024)
The overlap of financial, economic, ecological, and political crises has pushed the consensus on the need to promote a socio-ecological transformation, or, in short, a green transition. The discontent with the corporate world for its contributions to those crises has taken a central stage, with calls for greater corporate responsibility being articulated under a sustainability imperative. In the context of a new round of debates on the purpose of companies, this thesis examines the turning of corporate law and governance into a site for advancing a new capitalism. More specifically, the research investigates institutional changes occurring under the label of the public turn in corporate law, addressing the following questions: what constitutes the so-called public turn? What are its drivers and the perspectives on it? Which structural features led to targeting corporate law and governance to push for responsible corporate conduct? How does the public turn in corporate law relates to the broader set of actors and norms that shape corporate governance? Guided by critical approaches to the green transition and by political theories of corporate governance, the thesis resorts to different scholarships to examine the current wave of public oriented corporate governance mechanisms from within and from without corporate law. On the one side, the thesis offers a taxonomy of corporate law strategies being employed as well as a rich account on the multiple dimensions assumed by the new tools, placed at the intersection of human rights and environmental protection, corporate social responsibility, and global value chains. On the other, the thesis embeds corporate laws public turn within the unfolding of global capitalism, as the field evolves from corporate law to corporate governance to sustainable corporate governance. The thesis argues that the public turn in corporate law, caught in between the global and the local, enables the investigation of changing roles of states, businesses, and civil society within the political and epistemic terrain of the transition to a more just and sustainable economy. A sobreposição de crises financeiras, econômicas, ecológicas e políticas impulsiona o consenso sobre a necessidade de uma transformação socioecológica, ou, em resumo, uma transição verde. O descontentamento com o mundo corporativo assume centralidade, motivando demandas por mais responsabilidade corporativa, articuladas em torno de um imperativo de sustentabilidade. No contexto de uma nova rodada de debates sobre o interesse social, esta tese examina a transformação do direito societário e da governança corporativa em um locus de promoção de um 'novo capitalismo'. Mais especificamente, a pesquisa investiga as mudanças institucionais ocorrendo sob "a virada pública no direito societário", abordando as seguintes perguntas: o que constitui a esta virada? Quais são seus impulsionadores e perspectivas? Quais características estruturais levaram a mirar o direito societário e a governança para promover conduta corporativa responsável? Como a virada pública no direito societário se relaciona com o conjunto mais amplo de atores e normas que moldam a governança corporativa? Guiada por abordagens críticas da transição verde e por teorias políticas da governança corporativa, a tese recorre a diferentes correntes acadêmicas para examinar a atual onda de mecanismos de governança corporativa orientados para o público, de dentro e de fora do direito corporativo. Por um lado, a tese oferece uma taxonomia das estratégias do direito societário utilizadas, bem como um relato abrangente sobre as múltiplas dimensões assumidas pelas novas ferramentas, na interseção de direitos humanos, proteção ambiental, responsabilidade social corporativa e cadeias de valor globais. Por outro lado, a tese contextualiza a virada pública do direito societário nos desdobramentos do capitalismo global, à medida que o campo evolui do direito societário para a governança corporativa para a governança corporativa sustentável. A tese argumenta que a virada pública no direito corporativo, situada entre o global e o local, permite a investigação das mudanças nos papéis dos estados, empresas e sociedade civil no terreno político e epistêmico da transição para uma economia mais justa e sustentável.
Keywords: Corporate governance; Corporate law; Corporate sustainability; Direito societário; Economia política; Governança corporativa; Political economy; Private regulation; Regulação privada; Sustentabilidade corporativa

L’autonomie du bail à usage professionnel renouvelé en droit OHADA - Dibas-Franck, Éric Olivier Sébastien (Revue d’étude et de recherche sur le droit et l’administration dans les pays d’Afrique, 2024)
La stabilité des relations d’affaires ne peut se concevoir sans un contrat de bail durable. Fort de ce constat, il est indispensable d’examiner l’importance de l’autonomie du contrat de bail renouvelé. A ce propos, le contrat mérite une protection contre les abus du bailleur. L’analyse du bail renouvelé met en orbite la question de la poursuite des relations contractuelles à l’expiration de la durée prévue par les parties, ce renouvellement engendre-t-il une simple prorogation du bail originaire ou donne-t-il naissance à un nouveau bail ? Il s’agit de répondre à la question de l’autonomie du bail renouvelé qui se présente d’abord comme une réalité eu égard à ses caractères et à l’étendue limitée des garanties données par le locataire. Mais à l’observation, cette autonomie n’est qu’apparente en ce que le bail renouvelé maintient dans son exécution les clauses du bail initial et prévoit des changements qui sont des concessions édictées par l’économie contractuelle. Business relations stability it’s impossible without a lasting lease contract. In this regard, it is essential to examine the importance of the autonomy of the renewed lease contract. About it, the contract deserves protection against abuse by the lessor. The analysis of the renewed lease puts into orbit the question of the continuation of contractual relations at the duration planned by the parties, does this renewal result in a simple extension of the original lease or does it give rise to a new lease? This involves examining of the autonomy of the renewed lease which first presents itself as a reality given its characteristics and the limited extent of the guarantees given by the tenant. Indeed, this autonomy is only apparent in that the renewed lease maintains in its execution the clauses of the initial lease and provides for changes which are concessions decreed by the contractual economy.
Keywords: Bail; Bail à usage professionnel

Les sûretés sur le bien d'autrui - Dibas-Franck, Éric Olivier Sébastien; Mfini, Symphorin Angy Mon-espoir (Revue d’étude et de recherche sur le droit et l’administration dans les pays d’Afrique, 2024)
Les sûretés sur le bien d’autrui sont assurément un sujet passionnant, mais qui au demeurant n’a pas donné lieu à une doctrine abondante, que l’on songe au droit français ou au droit de l’OHADA. Pourtant, il est possible d’entreprendre une telle étude, sous l’angle des deux législations évoquées, même s’il va se révéler que la jurisprudence de l’OHADA est marquée au coin de l’absence. Ainsi, pour mener à bien cette étude, il conviendra d’envisager les sûretés choisies en tant que droit réel, en analysant la relation directe entre le créancier et le bien donné en garantie. C’est dire que les sûretés réelles, « puisque notre livraison s’arc-boute sur celles-ci », trouvent leur substance à partir de l’exercice d’une des utilités conférées par la propriété d’un bien, notamment sa valeur économique ou valeur de crédit. En l’absence de tout droit de propriété au constituant, il ne peut exister ni hypothèque, ni gage, ni nantissement, moins encore cession fiduciaire. L’affirmation est cependant sujette à discussion à propos du droit de rétention. Partant, les sûretés sur le bien d’autrui peuvent être aisément neutralisées, sur le terrain du jeu de la propriété, indépendamment de la question de la nullité contractuelle. Cependant, de façon exceptionnelle, des effets peuvent être reconnus aux sûretés sur le bien d’autrui, particulièrement sur le terrain des exigences de l’équité et de la protection des tiers de bonne foi.
Keywords: Biens; Sûretés

La citoyenneté communautaire dans l’espace juridique de la CEMAC - Effague Sing, Diyani (Afrilex : Revue d’étude et de recherche sur le droit et l’administration dans les pays d’Afrique, 2024)
À l’inverse de son ancêtre, l’Union douanière et économique de l’Afrique centrale (UDEAC), la Communauté économique et monétaire de l’Afrique centrale (CEMAC) envisage la possibilité d’une Union politique et, en filigrane, celle d’une citoyenneté communautaire. Instrument essentiel par lequel se matérialisent les politiques d’intégration régionale à travers le monde, la citoyenneté communautaire trouve son fondement à travers les objectifs d’union ou d’intégration. Elle ne vient pas remplacer la citoyenneté nationale, mais la compléter en accordant de nouveaux droits au-delà des frontières étatiques. Les indices de cette citoyenneté, qui sont perceptibles dans les textes organisant la CEMAC, montrent que la construction juridique de la CEMAC n’est pas seulement un projet d’ordre économique et monétaire, mais aussi un projet politique. Mais la citoyenneté communautaire, au sens où il y aurait une identité et un patrimoine entre la CEMAC et chacun des ressortissants des États membres, demande bien plus que des attentions textuelles, si nous admettons l’hypothèse que la citoyenneté communautaire ne consiste pas seulement dans la reconnaissance de droits, mais aussi les garanties de leur plein exercice. Unlike its ancestor, the Central African Customs and Economic Union (UDEAC), the Central African Economic and Monetary Community (CEMAC) envisages the possibilility of political union and, in the background, that of a community citizensgip. And essential instrument for regional integration policies throughout the world, community citizenship is founded on the objectives of union or integration. It does not replace national citizenship, but complements it by granting new rights beyond state borders. The indications of this citizenship, which are quite perceptible in the texts organizing the CEMAC, show that the legal construction of the CEMAC is not only a project of economic and monetary order, but also a political project. But community citizenship, in the sense that there is an identity and a heritage between the CEMAC and each of the nationals of the member states, requires much more than textual attention, if we accept the hypothesis that community citizenship consists not only in the recognition of rights, but also the guarantees of their full exercise.
Keywords: Citoyenneté communautaire; Community citizenship; Community practice; Intégration régionale; Nationality; Nationalité; Pratiques communautaires; Regional integration; Supranationality; Supranationalité

The legal framework regulating the duties of insurance intermediaries - Sithole, Eugine (University of Pretoria, 2024)
In South Africa, before the Financial Advisory and Intermediaries Services Act (FAIS Act) and other insurance laws came into existence, intermediary services regarding the rendering of insurance products have always been regulated by the law of agency and mandate. This means that the Roman-Dutch principles provided for the standards to which the conduct of intermediaries was to comply with when rendering insurance services. The mandate of intermediaries in terms of the Roman-Dutch Principles also included the fact that they had to act with care, skill and in good faith. When the FAIS Act came into operation, it introduced several detailed rules and minimum standards for insurance intermediaries to comply with, and these minimum standards are not limited to qualifications, experiences and characteristics of honesty and integrity that an intermediary must comply with, but they also stipulated in detail what an intermediary must do when discharging insurance intermediary duties. The FAIS Act is the leading legislation when it comes to the regulation of intermediary services. The FAIS Act, under section 16, provides for a General Code of Conduct for Authorised Financial Services Providers and their Representative (GCC), which contains a set of rules that are applicable to all intermediaries. These rules under the GCC are aimed at ensuring that insurance customers are provided with material facts that will enable them to make a prior informed decision and that their reasonable financial needs concerning insurance products will be carefully considered so that they can be provided with a product that will be suitable to satisfy their needs. Furthermore, in terms of South African laws and practices, intermediaries play an essential role in the creation of legally binding insurance contracts. Insurance businesses are concluded through intermediaries. Considering that many insurance companies are juristic persons, and they can only conduct business by means of human agents, insurance laws make it compulsory for intermediaries to have skills, knowledge, and experience regarding insurance products that they are rendering to insurance customers. It is commonly believed that intermediaries with skills, knowledge and experience, they always act in the best interest of the client, and they ask relevant questions to assist the clients to disclose all material facts, and they always make sure that material facts are clearly communicated/disclosed to the insurer and insured to avoid future conflicts. The legal framework placed a duty on the intermediary to assist the insured to disclose all material facts and to explain all clauses contained in the insurance contract which may lead to the insurer repudiate its liability. Furthermore, an intermediary is at all material times expected to first consider the financial situation of the potential insured before determines a cover that will be best suitable for the insured’s needs. However, despite the best guidelines outlined by applicable insurance laws and regulations, mistakes are still being made by intermediaries, which lead to insurance customers to suffer the consequences of impractical intermediary services, and that has resulted in numerous complaints, legal disputes, debarments, and other regulatory actions. As a result of intermediaries’ continuous misconduct, insurers have been repudiating claims, and it has created a presumption that insurers conduct businesses to enrich themselves instead of protecting the interests of their customers as required by regulating legal framework. Therefore, so many people have lost confidence in the insurance industry due to unlimited court cases and complaints arising from misconduct or omissions of intermediaries, such as their failure to disclose material facts to the parties. Once it is found that material facts were not fully disclosed between the insurer and insured, both parties would have been deprived of their right to make an informed decision before consenting or signing a legally binding contract. Therefore, a need is created for intermediaries to be educated of their legal duties when rendering insurance services and that will help strengthen or restore the confidence of the public towards insurance industry.

Insurrection juridictionnelle au Sénégal - Soma, Abdoulaye (Afrilex : Revue d’étude et de recherche sur le droit et l’administration dans les pays d’Afrique, 2024)
Keywords: Décision d’annulation; Dédit jurisprudentiel; Evolution constitutionnelle; Fonction de régulation; Inédit juridictionnel; Révolution jurisprudentielle

La déjudiciarisation à l’aune de la compliance - Wane, Sadou (Afrilex : Revue d’étude et de recherche sur le droit et l’administration dans les pays d’Afrique, 2024)
Les mutations évolutives et fulgurantes du droit en général, du droit des affaires en particulier, sous-tendues par la recherche justifiée de performance, de célérité et confidentialité ont substantiellement pénétré la corporate governance, constituant, de ce fait, un pilier fort de la régulation.L’exploration par la sortie du circuit judiciaire sous le prisme de la compliance révèle une dynamique complexe par laquelle les deux notions interagissent par un emboîtement intrinsèque qui se révèle, par moment antagoniste. Les processus de dénormalisation et de normalisation, induits par la compliance mettent en lumière l’utilité et la nécessité d’instaurer des standards unifiés. La nécessité de la régulation par le biais de la compliance est axée autour de la prévention et de la responsabilisation proactive des acteurs. The lightning evolutionary changes in law in general, and business law in particular, underpinned by the justified quest for performance, speed and confidentiality, have substantially penetrated corporate governance, thereby constituting a strong pillar of regulation.Exploring the judicial circuit through the prism of compliance reveals a complex dynamic in which the two concepts interact through an intrinsic interlocking that is at times antagonistic. The processes of denormalisation and standardisation brought about by compliance highlight the usefulness and necessity of establishing unified standards. The need for regulation through compliance is centred on prevention and proactive accountability.
Keywords: Affaires; Business; Compliance; Conformité; Corporate law; Droit économique; Entreprise (gouvernance); Governance; Liability; Responsabilité

The legitimacy of dismissals for off-duty misconduct in South African labour law - Phulu, Thandekile (University of Pretoria, 2024)
The main aim of this thesis is to solve the uncertainties brought about by dismissals for off-duty misconduct. First, it should be acknowledged that the world as we know it has changed and continues to evolve. Dismissals have been significantly impacted by the use of social media outside the workplace. The legalisation of the use of cannabis by an adult person has also brought uncertainties in the way dismissals are handled, especially in cases where an employee consumes cannabis off-duty. These two aspects have significantly influenced dismissals for off-duty misconduct in South Africa, with employees alleging that their rights to privacy, dignity and freedom of expression are infringed. The thesis reveals that regardless of these modern changes, off-duty misconduct dismissal is still governed by the generic provisions of the Labour Relations Act 1995 and its Code of Good Practice: Dismissal. The thesis underscores the lack of clarity regarding the regulation of dismissals for off-duty misconduct in South Africa. Furthermore, despite the judiciary’s establishment of tests (the nexus test and the breakdown of the employment relationship), challenges in adjudicating off-duty misconduct cases persist. This thesis analyses the South African legal framework governing dismissals for off-duty misconduct. The research investigates the evolution of South African dismissal law, tracing its development from the pre-democratic era to the post-democratic era. This investigation scrutinises the shifts in the legal landscape regarding dismissals for off-duty misconduct. The analysis encompasses a range of legal instruments pertinent to South Africa, including legislation, international law, common law, and judicial precedent. The current need for a Code of Good Practice for off-duty misconduct dismissal is highlighted. This rationale is prompted by a comparative examination of other countries where, despite the absence of specific codes addressing off-duty misconduct, a proactive stance has been adopted to safeguard employees’ off-duty rights by enacting relevant legislation. These chosen states have statutes regulating employees’ off-duty conduct and clarifying which conduct is protected and in which circumstances. Consequently, the thesis proposes a Code of Good Practice: Dismissal for Off-duty Misconduct. This Code would assist in the uniformity of application of relevant aspects in determining the fairness of dismissals for off-duty misconduct, thus alleviating labour suits concerning this type of dismissal. The Code would also provide employers with guidelines on how to draft off-duty misconduct policies without infringing employees’ constitutional rights.
URI: https://repository.up.ac.za/handle/2263/97021
Keywords: Cannabis use; Dismissal; Labour law; Misconduct; Off-duty; Social media; South Africa

L'interopérabilité comme outil de la régulation asymétrique des marchés numériques - Martin-Lafay, Florent (Université Paris 1, 2024)
La concentration des marchés numériques autour d’une poignée d’opérateurs de plateforme numérique structurante, notion développée dans l’étude, tend à soulever des problèmes économiques et sociétaux. En matière de concurrence, en premier lieu, de nombreux économistes ont mis en exergue les défaillances des marchés sur lesquels interviennent ces acteurs (i.e. effets de verrouillage tels que les effets de réseau et la capture des données, économies d’échelle et d’envergure) ainsi que les effets néfastes pour la liberté de choix des utilisateurs et l’innovation. Les problèmes de concurrence interplateforme et intraplateforme s’accompagnent de problèmes plus sociétaux liés à la concentration des flux d’information autour des écosystèmes construits par ces opérateurs et au sein desquels les utilisateurs sont maintenus captifs. Les opérateurs de plateforme numérique structurante ont acquis une position incontournable sur l ’internet leur conférant un rôle de quasi-régulateur des activités en ligne. Cette situation tend à affaiblir la liberté d’expression et d’information des utilisateurs, leur liberté d’association et liberté de réunion ainsi que leur droit au respect de la vie privée. Fort de ce constat, qui a appelé de nombreuses réponses législatives de la part des pouvoirs publics, en Europe particulièrement, l’étude analyse plus spécifiquement l’interopérabilité comme un outil permettant, lorsque c’est nécessaire et proportionné, d’ouvrir les écosystèmes des opérateurs de plateforme numérique structurante afin de promouvoir la liberté de choix des utilisateurs, la concurrence et l’innovation. Raisonnant par analogie avec le droit des communications électroniques ainsi que d’autres régimes ayant mis en place ce type de remède d’accès (e.g. droit de la concurrence, règlement sur les marchés numériques, droit bancaire, droit des transports), les bénéfices de l’interopérabilité pour renforcer l’autonomie des utilisateurs sont mis en exergue. L’étude s’intéresse aussi aux implications de l’adoption d’un tel remède en droit positif et son effet notamment sur les droits des débiteurs (e.g. propriété intellectuelle) et des tiers concernés (e.g. vie privée). Elle s’intéresse également aux difficultés de mise en œuvre de l’interopérabilité qui comporte une forte dimension technique et qui serait amenée à être imposée sur des marchés présentant d’importantes asymétries d’information. S’inspirant des solutions dégagées au sein de différents instruments juridiques, l’étude propose des pistes pour assurer une application efficace du remède.
Keywords: Communications électroniques; Competencia; Concurrence; Digital platform; Droit d'auteur et informatique; Ecosystems; Intellectual property; Interoperability; Interopérabilité; Numérique; Ouverture; Plateforme; Propriedade intelectual; Propriété intellectuelle; Technologies de l'information et de la communication – Droit – France; Écosystème

Interesse público em atos de concentração : a defesa da segurança econômica nacional - Tokuzumi, Pedro Yukimitsu Ribeiro (Universidade de São Paulo, 2024)
A narrativa da globalização é ambígua, visto que, em âmbito internacional, o discurso é de liberalização dos mercados para que as empresas mais eficientes e inovadoras prosperem; contudo, no plano doméstico, os Estados Nacionais procuram controlar minuciosamente a entrada de capital estrangeiro em seu território. Em especial, esse controle recai sobre a aquisição de empresas nacionais, já que essas operações econômicas podem transferir o controle de: (i) mercados nacionais (ii) tecnologia crítica e know-how; (iii) infraestrutura estratégica; e (iv) informações e dados sensíveis. Trata-se de elementos que, individualmente ou em conjunto, influenciam a soberania de um país. Por força do discurso liberalizante da globalização, é comumente propagado que a análise antitruste no controle de estruturas deve ser neutra e focada no trade-off entre eficiência e os efeitos deletérios unilaterais, coordenados e de fechamento de mercado que eventualmente possam existir em um ato de concentração. Dessa forma, a presente tese de doutorado investiga fenômenos jurídicos que fogem do consenso do direito concorrencial ortodoxo, a saber: (i) a incidência de inúmeros interesses para bloquear investimento estrangeiros indesejáveis em empresas e ativos nacionais; (iii) os efeitos dos subsídios estatais em empresas privadas (campeões nacionais) e públicas (empresas estatais) para disputa de mercados alienígenas, e, consequentemente, melhor posicionar os seus respectivos Estados Nacionais na ordem econômica internacional. Sustenta-se que, hoje, o direito concorrencial pátrio se encontra paralisado pelo discurso liberalizante da globalização; contudo, existem elementos suficientes para uma nova teoria antitruste do dano para tutela da soberania econômica nacional, tendo em vista que o art. 219 da Constituição Federal de 1988 protege o mercado interno como patrimônio nacional, capaz de viabilizar o desenvolvimento cultural e socioeconômico por meio da endogeinização dos centros de decisão nas empresas nacionais. Por fim, defende-se que nova teoria do dano demanda adaptações e flexibilizações às ferramentas tradicionais do direito concorrencial, especialmente em relação à análise: (i) da nacionalidade das pessoas jurídicas envolvidas no ato de concentração; e (ii) das estratégias de financiamento para aquisição da empresa alvo (o abuso de poder econômico- financeiro em atos de concentração); e (iii) do conceito de grupo econômico de empresas estatais. The narrative of globalization is ambiguous, whereby at the international level, the discourse pertains to liberalizing markets so that the most efficient and innovative companies prosper; however, at the domestic level, nations seek to control, meticulously, the entry of foreign capital into their territory. This is particularly evident when considering the merger review with domestic companies, as these economic operations can transfer control of: (i) domestic markets (ii) critical technology and know-how; (iii) strategic infrastructure; and (iv) sensitive information and data. These are elements that individually or together influence the sovereignty of a country. Due to the liberalizing discourse of globalization, it is commonly propagated that antitrust analysis of mergers must be neutral and focused on the trade-off between efficiency and the antitrust damages that could potentially arise. Therefore, this doctoral thesis investigates legal phenomena that deviate from the consensus of orthodox competition law, that is: (i) the incidence of numerous public interests in antitrust legislation; (ii) the instrumentalization of competition law to block undesirable foreign investment in domestic companies and assets; (iii) the effects of state subsidies on private (national champions) and public (state-owned companies) companies to compete for foreign markets, and, consequently, better position their respective nations in the international economic order. It is argued that, today, Brazilian Competition Law is paralyzed by the liberalizing discourse of globalization, however, there are sufficient elements for a new antitrust theory of damage to protect national economic sovereignty, considering that article 219 of the Brazilian Constitution protects the internal market as a national asset, capable of enabling cultural and socioeconomic development through the endogenization of decision-making centers in domestic companies. Finally, it is argued that the new theory of damage demands adaptations to and flexibility of the traditional tools of competition law, especially in relation to the analysis of: (i) the nationality of the companies involved in the merger or acquisition; and (ii) financing strategies involved in mergers and acquisitions (the abuse of economic-financial power); and (iii) the concept of economic group of state-owned companies.
Keywords: Ato de concentração; Foreign direct investment; Fusion acquisition; Fusion-acquisition; Interesse público; Intérêt public; Merger review; National economic security; Public interest; Segurança econômica nacional; Subsidies; Subsídios e investimento direto estrangeiro; Sécurité économique

La variabilité du capital social en droit OHADA à la lumière du droit français - Ouoba, Lambouado Raymond (Université de Perpignan Via Domitia, 2024)
Le législateur OHADA s'est inspiré du droit français pour fixer le cadre juridique de la variabilité du capital social ; d'où l'étude orientée vers une approche comparatiste. Cette approche a permis une confrontation entre deux (02) systèmes juridiques, en vue de dégager les problèmes de droit et d'envisager une amélioration du cadre juridique de la variabilité du capital en droit OHADA ; l'objectif étant de dégager une contribution à l'amélioration du droit OHADA à travers le droit comparé. A l'analyse, il ressort que la variabilité du capital social comporte des facteurs attractifs pour les acteurs économiques. En effet, elle constitue un mécanisme de financement des sociétés, en raison d'une part, de sa capacité à renforcer les capitaux propres sans charge financière et, d'une part, de sa capacité à constituer un actionnariat spécifiquement orienté sur la rentabilité des sociétés. De même, elle pourrait susciter un intérêt pour les investisseurs intéressés par la célérité et l'efficacité dans les opérations de financement des entreprises. L'efficacité du financement de la société par la mise en œuvre de la clause de variabilité du capital est tributaire, entre autres, de son attractivité auprès des acteurs économiques de manière générale, des investissements et des professionnels du droit en particulier. Cependant, plusieurs facteurs ne militeraient pas en faveur du recours à la variabilité du capital. Parmi ces facteurs figurent les risques découlant de la réduction du capital et la méconnaissance des acteurs économiques et des praticiens du droit de l'existence et/ou du fonctionnement du mécanisme de la variabilité du capital. Or, ces risques ne sont pas irrémédiables, dans la mesure où il existe des mécanismes juridiques appropriés pour y faire face. En somme, l'analyse du fonctionnement du mécanisme de la variabilité du capital social a mis en évidence ses capacités de mobilisation de financement, de recapitalisation de la société, de restructuration de la société et d'apporter une contribution à l'amélioration du cadre juridique des sociétés à capital variable. Elle a également permis de démontrer l'insuffisance de la justification ou du fondement du désintérêt des acteurs économiques et des praticiens du droit à l'égard de la variabilité du capital social
Keywords: Approche comparée; Augmentation de capital; Capital increase; Capital reduction; Capital social; Droit OHADA; Droit français; French Law; OHADA Law; Réduction de capital; Share capital; Sociétés à capital variable

Contribution à l'étude de la Couverture maladie universelle (CMU) au prisme du droit à la santé en droit social ivoirien - Seri, Bi Neatien Urbain Victorien (Université de Bordeaux, 2024)
L'accès aux soins de santé, notamment des plus pauvres, est une préoccupation au coeur des réflexions dans tous les systèmes politiques et juridiques nationaux. La question se pose davantage sur le continent africain où il existe peu de mécanismes de couverture santé. Les différents projets de Couverture maladie universelle initiés dans un certain nombre de pays africains tentent d'y apporter des solutions, mais peinent encore à se déployer. C'est le cas en Côte d'Ivoire depuis l'entrée en vigueur, le 1er octobre 2019, de la loi n°2014-131 du 24 mars 2014 instituant la Couverture maladie universelle. En dehors des travailleurs salariés et des fonctionnaires en activité ou à la retraite, les populations intègrent lentement et difficilement la CMU pourtant obligatoire pourtous. Il faut dire que le projet fait l'objet de critiques et de peu d'adhésion de la part de la population. Il pèche également par ses dispositions qui alimentent ces critiques, notamment sur la durée du délai de carence s’imposant à l’assuré, le caractère obligatoire de l'activité professionnelle pour les étrangers, le manque d'ouverture à d'autres formes de médecine telle que la médecine traditionnelle. Cela dit, l'exercice du droit fondamental à la santé dans un environnement marqué par un secteur informel important et une population à majorité pauvre passe par un système obligatoire et solidaire de mutualisation du risque comme la CMU. Reste à déterminer le modèle adéquat, notamment en termes de financement, afin de mettre en adéquation son objectifd’universalité et le contexte dans lequel il est mis en oeuvre.
Keywords: Basket of care; Care pathway; Co-payment; Couverture maladie universelle; Côte d'Ivoire; Droit social; Droit à la santé; Délai de carence; Panier de soins; Parcours de soins; Realisation of the right; Right to health; Réalisation du droit; Ticket modérateur; Universal Health Cover; Universality; Universalité; Waiting period

Comportement d’investissement des entreprises camerounaises : analyse en données de panel 2015-2022 - Metangmo, Janvier; Nankap Seujib, Alexis (Finance & Finance Internationale, 2024)
L’objectif de cette étude est de déterminer les facteurs influençant le comportement d’investissement des entreprises camerounaises par une approche microéconomique. En effet, malgré un taux de profit élevé (l’EBE représente environ 60% de la valeur ajoutée), le taux d'investissement privé au Cameroun demeure très faible (18% du PIB) et risque de compromettre l'atteinte du stade de pays émergent à l'horizon 2035. En se basant sur le modèle théorique accélérateur-profit, nous avons estimé un modèle de panel dynamique grâce aux données de 381 entreprises sur la période 2015-2022, par la méthode des moments généralisés (GMM). Les résultats obtenus identifient la demande sur le marché (effet accélérateur) comme principal facteur qui agit positivement et significativement sur l’investissement. A contrario, le profit, la dette ou les capitaux propres n’ont pas une influence significative sur le comportement d’investissement des entreprises camerounaises. En outre, même en cas de demande importante, le comportement d’investissement des entreprises camerounaises est influencé par leur statut juridique, leur taille, leur activité principale et l’état sécuritaire de la zone d’implantation. Cela illustre à souhait l’importance d’améliorer l’environnement des affaires et d’encourager les entreprises camerounaises à muter vers des modes d’organisation leur garantissant non seulement un développement rapide mais aussi une pérennisation. The aim of this study is to determine the factors influencing the investment behavior of Cameroonian companies, using a microeconomic approach. Indeed, despite a high profit rate (EBITDA represents around 60% of value added), the private investment rate remains very low (18% of GDP) and risks compromising the country's ability to reach the stage of an emerging country by 2035. The covid 19 crisis, the Boko Haram security crisis in the northern part of the country and the secessionist crisis in the English-speaking regions all add to an already unfavourable business climate. These observations lead us to reflect further on the factors that explain the investment behavior of Cameroonian companies. Based on the theoretical accelerator-profit model, we estimated a dynamic panel model using data from 381 companies over the period 2015-2022, using the generalized method of moments (GMM). The results obtained identify market demand (accelerator-effect) as the main factor acting positively and significantly on investment. Conversely, profit, debt or equity do not have a significant influence on the investment behavior of Cameroonian companies. Other variables such as the company's legal status, size and activity also have an effect on investment. The company's geographical location in a zone of insecurity, such as the northern and western regions of Cameroon, also has a negative effect on investment behavior, no doubt due to the uncertainty and irreversible nature of the investment.
Keywords: Accelerator-profit model; Cameroon; Cameroun; Effet de levier; Entreprises; Firms; GMM; Investissements; Investments; Modèle accélérateur-profit; Q de Tobin; Tobin's Q

How can the rule of law under the WTO framework ensure sustainable fishery governance through fishery subsidies? A study from the perspective of special and differential treatment - Bai, Jiayu; Wu, Yuting (Heliyon, 2024)
Background Considering the declining situation of sustainability in global marine fisheries, World Trade Organization (WTO) members successfully concluded the Agreement on Fisheries Subsidies(AFS) after 21 years of negotiations in 2022. As an the integral part of these negotiations, special and differential treatment (SDT) provisions provide developing countries with special rights and developed countries with the possibility to treat developing countries more favorably than other WTO members. Objective This study analyzed the role of SDT for fisheries subsidies in ensuring sustainable fishery governance by the rule of law, as well as the reflection of SDT under the AFS, to explore whether SDT can support sustainable fishery governance under the WTO framework. Methods This study is primarily based on official data and critical legal studies and used normative analysis and historical analysis to expose the essence of the SDT issue in the AFS as a political game in the legal form. Results The practical challenges in the implementation of SDT may affect the compliance willingness of member states. To overcome the obstacles, such as ambiguity and inefficiency, that impede the legalization process of sustainable global marine fishery governance, it is necessary to emphasize the value of SDT for the common interests of the WTO members in marine fisheries legislation. This will benefit the developing countries, especially the small island developing states, in the short term; and the common interests of developed and developing countries in the long term. Policy implications SDT facilitated the consensus between the developing and developed countries on issues such as illegal, unreported, and unregulated fishing subsidies and overfishing subsidies. However, current SDT practices have deviated from the original intention of the fairness and democratic approach of global marine fisheries governance, which should take into consideration the specific situation of developing countries.
Keywords: Agreement on fisheries subsidies; Overfishing; Rule of law; Special and differential treatment; Sustainable fishery governance; World Trade Organization

Articulation between Soft Law and Hard Law in the Award of Public-Private Partnership Contracts through Unsolicited Bids in Burundi: Towards Harmonization with International Practice - Amani, Jean Pierre (Open Journal of Social Sciences, 2024)
The awarding of public-private partnership (PPP) contracts through unsolicited bids is characterized by flexible domestic law, with the involvement of public and private players aiming to achieve the general interest objective of public infrastructure development and, by extension, national development. These players are helping to build the normative framework for PPP project activities by spontaneous offer, given their increasingly widespread use on the bangs of positive law, while their standards are classically deprived of the binding force attached to hard law. Marked by its normative guarantee, the flexible law of unsolicited bids is situated at the threshold of the mandatory, and is essential to PPP law. It produces legal effects by linking up with the hard law of PPP contracts, which is the law of the parties. This link between soft law and hard law has a major legal impact on the transformation of the law and legal certainty, for the benefit of investment confidence, especially international investment confidence. Faced with the limitations of positive law on the award of PPP contracts in unsolicited bids, and the difficulties of interpreting soft law and hard law standards, there is a need for harmonization with international practice. To this end, the instruments of the United Nations Commission on International Trade Law (UNCITRAL) on PPPs are being used to link up with Burundian hard law through a transposition mechanism. It is therefore possible that our positive approach to PPP contracting could be improved, highlighting the principle of competition and the exception of non-competition, while taking into account the win-win principle, risk sharing and performance. Finally, the article considers the adjustments to the hard law that would be necessary if Burundi were to decide to revisit the legal framework to make it more attractive to investment, and thus ensure the completion and financing of PPP contracts by spontaneous bidding.
Number: 1
Keywords: Articulation of Law; Competition Principles; Hard Law; Harmonization Principles; Legal Certainty; Mutation of Law; Soft law; Spontaneous Offer

De la gestion de la redevance minière due aux entités territoriales décentralisées et ses problèmes en droit congolais : Cas des entités territoriales décentralisées du Haut-Katanga et du Lualuaba - Sephin, Sefu Ramazani (International Journal of Social Sciences and Scientific Studies, 2024)
Les redevances minières locales constituent à ce jour un enjeu national important dans le contexte de la RDC où les ETD perçoivent directement leurs quotités pour le financement des projets et infrastructures d’intérêts communautaires suivant l’esprit du législateur du Code minier. Pour l’heure, force est de constater que la redevance minière impacte peu sur le développement socio-économique des ETD. En effet, les indicateurs sociaux recueillis dans la Chefferie des Bayeke, dans la Commune rurale de Kambove, dans la Chefferie de Basanga, dans la Commune de Panda et dans la Commune de Shituru renseignent que, dans ces zones, les populations locales ne profitent que peu, sinon pas du tout, des effets d’entrainement du développement. D’où l’intérêt de la présente étude qui tend à rechercher les mécanismes juridiques susceptibles d’impulser une gestion rationnelle de cette redevance pour le développement socio-économiques de ces ETD ENGLISH Local mining royalties constitute to this day an important national issue in the context of the DRC where the ETDs directly receive their quotas for the financing of projects and infrastructures of community interest following the spirit of the legislator of the Mining Code.For the moment, it is clear that mining royalties have little impact on the socio-economic development of ETDs. Indeed, the social indicators collected in the Chiefdom of Bayeke, in the rural commune of Kambove, in the Chiefdom of Basanga, in the commune of Panda and in the commune of Shituru indicate that, in these areas, the local populations only benefit little, if any, developmental ripple effects.Hence the interest of this study which tends to seek the legal mechanisms likely to stimulate rational management of this fee for the socio-economic development of these ETDs.
Keywords: Congo; Droit minier; Redevance minière

A bibliometric review of IFRS adoption and compliance research in Africa - Effah, Nana Adwoa Anokye (Journal of Business and Socio-economic Development, 2024)
Purpose This article aims to identify and review existing studies on the adoption and compliance of Internat ional Financial Reporting Standards (IFRS) in Africa. Design/methodology/approach The methodology involves a sole focus on studies conducted with an African sample, using a bibliometric method and data from the Web of Science (WoS) database. Visualizations from VOSViewer and Biblioshiny software are employed to identify the dominant authors, journals and countries contributing to research in the region. Findings The findings reveal existing collaborations among authors in the field. However, the study emphasizes the need for additional research to enhance the intellectual structure of the research domain, as the majority of related documents are concentrated within twenty articles with at least one citation. Practical implications The practical implications underscore the importance of collaboration in practice, emphasizing the need for cooperation among corporations, experts and regulatory agencies involved in IFRS adoption and compliance in Africa. By fostering collaborative efforts and knowledge-sharing among corporations, experts and regulatory agencies, practitioners can enhance their understanding, streamline implementation processes and improve compliance methods. Originality/value This review is one of the few to explicitly conduct a bibliometric review of IFRS adoption and compliance studies in Africa, providing a foundation for future research to determine the current direction of IFRS studies in this region.
Keywords: Africa; IFRS adoption; IFRS compliance; Web of science database

Accessibilité des sociétés commerciales de droit étranger à l'espace OHADA sur la reconnaissance de leur personnalité juridique selon la jurisprudence de la CCJA - Lumingu, Yves-Junior Manzanza; Ayikaba, Jules Masuku (Rabels Zeitschrift für ausländisches und internationales Privatrecht, 2024)
The Access of Foreign Commercial Companies to the OHADA Area - Recognition of Legal Personality under CCJA Case Law. The Organization for the Harmonization of Business Law in Africa (OHADA) is striving to make its geographical area more attractive, particularly to foreign investors and foreign commercial companies. This should be achieved by adopting, at a supranational level, uniform and modern legal standards which can be readily embraced by the business community and by ensuring legal certainty through the establishment of the Common Court of Justice and Arbitration (CCJA). To date, however, OHADA has not yet adopted any provision recognizing the legal personality of companies operating throughout its region. However, the recognition of such entities is essential with regard to their participation - particularly as shareholders or partners - in a commercial company incorporated under OHADA law or in relation to the establishment of branches or subsidiaries within OHADA member states. The CCJA has, however, issued a number of rulings on this issue. This study examines these decisions and recommends the adoption of an OHADA-wide procedure for recognizing the legal personality of foreign commercial companies.
OpenAlex: https://openalex.org/W4391456920

Du caractère suranné de l’immunité d’exécution vis-à-vis des personnes publiques à activités privées en Droit OHADA - Mpoyi Wembo, André (Revue de l'UKA, 2024)
Le droit OHADA d’exécution forcée est devenu, à la lumière de l’évolution juridique et jurisprudentielle, dépassé et fait planer une insécurité juridique. Le législateur, en prévoyant l’immunité d’exécution en faveur des personnes morales de droit public, voulait protéger l’intérêt général qui serait en conflit avec ceux des particuliers. Mais cette protection immunitaire devrait se limiter à une catégorie des personnes publiques et non à celles intervenant dans la sphère économique, qui normalement sont en compétition avec les privés. Ainsi la révision de l’article 30 s’impose avec acuité afin de le conformer à la réalité juridique et jurisprudentielle actuelle et de protéger par ricochet les intérêts des particuliers cocontractants de l’Etat.
Keywords: Créancier; Débiteur; Entreprise publique; Exécution forcée; Immunité; Jurisprudence; OHADA; Personne morale de droit public; Reformulation; Révision

Internationalisation patterns of African sharing economy companies: The role of gateway markets - Ochieng, Irene Achieng; Thornton, Heidi Coral; Owusu, Richard Afriyie (Journal of Business Research, 2024)
Sharing economy companies (sharecoms) have been internationalising rapidly, including entering African markets. Little research has been conducted on the strategies and behaviours of African sharecoms. Questions have been raised as to whether existing theories adequately explain the internationalisation of African firms. Thus, we analyse the internationalisation patterns of six African sharecoms, focusing on time, speed, and scope. The findings indicate that firms apply unique combinations of various internationalisation models. A novel pattern of internationalisation where the firms use “foreign gateway markets” as strategic “launchpads” before rapidly internationalising was also uncovered. Locational advantages, strategic networks, and relative technological advancement characterise the foreign gateway markets. We also propose the concept of “complex regional context” to define the context of emerging regions with many neighbouring countries with the potential for high levels of internationalisation but low levels of international business due to the lack of common enabling frameworks and institutions.
Keywords: Emerging African markets; Foreign gateway markets; Internationalisation; Patterns; Sharing economy

L’histoire du droit des obligations : les principales étapes diversement appréciées d’une discipline en constante construction - Cissouma, Sékou Faco (Revue des Réflexions Constitutionnelles : Revue mensuelle de publication en droit constitutionnelle, 2024)
Les rapports de créancier (celui à qui on doit) et de débiteur (celui qui doit) ont historiquement évolué de la possible mise à mort du débiteur à la saisie de ses biens pour les faire vendre et se payer voire s’en approprier en passant par l’esclavage, l’enchainement en prison. Le débiteur a connu et continue de connaitre des infortunes plus ou moins graves. Les continents notamment l’Europe et l’Afrique n’ont pas connu ou vécu les mêmes parcours dans la gestion des obligations en tant que lien juridique entre un créancier et son débiteur, même si de nos jours les deux entités ayant des relations historiques, partagent une grande partie autour des obligations en l’occurrence dans le maniement des notions de Shuld et Haftung. Des vieux auteurs (historiques) Domat, Pothier aux auteurs modernes en Europe Alain BENABENT, Ghestin ou Sékou Faco CISSOUMA en Afrique, le droit des obligations s’est régulièrement et progressivement poli avec l’aide de la loi (textes) et de la jurisprudence.
Keywords: Code civil; Contrainte (par corps) contrat; Convention solidarisme (contractuel); Histoire; Loi (poetelia papira) esclave; Obligation; Patrimoine

Domestication of the African Continental Free Area Trade (AfCFTA) among member States: An Assessment of its implementation in perspectives in Cameroon - Abang Mvo, Calistus (Revue Africaine des Réflexions Juridiques et Politiques, 2024)
Cameroon commercial relations with other African countries, just as that of other countries with Cameroon, had heretofore stood at the queue of controversies as businesses suffered from exorbitant duties and related levies on their goods and services prior to the Agreement on the African continental Free Trade Area (AfCFTA). Considered to be a great game changer, the AfCFTA has the capacity to significantly transform African Economies thereby increasing its tentacles to the global business hub. In order to achieve this, Cameroon needs to actively carry out reforms both policy wise and complimentary structures. This will help mitigate the constraint and fiscal adjustment costs that may accrue with the new Agreement. This will equally lead to a positive win-win continental trade-integration outcome. This article assesses how Cameroon accommodates the implementation phase of the AfCFTA as a member State.
Keywords: AfCFTA; African Continental Free Trade Area; Assessment; Domestication; Implementation; ZLECAf

Le contrat face à l'imprévision dans les pays francophones d'Afrique subsaharienne : essai d'une analyse normative socio-économique - Agbam, Komlanvi Issifou (Université Laval, 2024)
À rebours des droits originellement africains, les droits modernes africains, tel qu'ils ont été hérités de la colonisation peinent à satisfaire l'aspiration des sociétés africaines à un minimum de normativisation des relations sociales. Le refus du juge d'adapter le contrat déséquilibré en cas d'un changement de circonstances imprévisible en droit civil des pays francophones d'Afrique au Sud du Sahara, résultant du mimétisme du Code civil français de 1804, en témoigne. Par son refus obstiné, le juge poursuit une politique coloniale, en dépit de l'indépendance des pays concernés. Le Code civil français de 1804 qui s'applique presque intégralement dans les pays francophones d'Afrique au Sud du Sahara, a été profondément réformé en 2016. S'est ainsi créé, un fossé considérable entre le droit contractuel africain resté fidèle au Code civil français de 1804 et un droit des obligations français en modernisation et en adéquation avec les pratiques contractuelles de la société française. À la différence du nouveau droit français des contrats, les systèmes juridiques des pays francophones d'Afrique au Sud du Sahara, ne reconnaissent pas le pouvoir au juge d'adapter le contrat surpris par le fait imprévisible. Or, en Afrique traditionnelle tout comme moderne, il ne fait aucun doute que la relation contractuelle est plus solidaire et moins individualiste. Au Québec, la réforme du Code civil en 1994 a marqué une avancée de la justice contractuelle sur la stabilité contractuelle. Cependant, tout comme le C.c.B.C dont la rédaction a été influencée par le Code civil français de 1804, le Cc.Q ne prend pas en considération la théorie de l'imprévision. Cette étude vise à démontrer d'une part que le refus de l'imprévision dans le droit civil africain résulte du mimétisme du Code civil français de 1804. Elle vise à démontrer d'autre part que la prise en considération de l'imprévision dans les sociétés africaines, par le biais de la théorie relationnelle du contrat, est en harmonie avec les pratiques contractuelles des sociétés africaines.
Keywords: Contrats; Droit souple; Décolonisation; Force majeure; Soft law

La protection des gens de mer à l'épreuve de l'activité des agences de fourniture de main-d'œuvre maritime - Agbavon, Kokougan Désiré (Université Laval, 2024)
L'industrie maritime a connu de profondes mutations qui ont non seulement influé sur les rapports commerciaux liés au transport maritime, mais aussi sur les relations de travail qui se créent à l'occasion de l'emploi des gens de mer à bord des navires. Une manifestation concrète de ces mutations a été le recours par les armateurs à des structures spécialisées dans la fourniture d'équipage. Dénommés agences de *manning* ou fournisseurs de main-d'œuvre, ces structures facilitent les procédures de recrutement pour les armateurs et constituent par la même occasion de véritables pourvoyeurs d'emploi pour les gens de mer. Toutefois, certains comportements des agences de *manning* peuvent mettre en péril la protection des gens de mer et de leurs droits. De ce fait, l'activité de fourniture de main-d'œuvre maritime a nécessité un encadrement. Bien qu'un ensemble de règles internationales et nationales participe à cet encadrement, des questions demeurent. Celles-ci sont relatives non seulement aux situations conflictuelles de lois et de juridictions que pose l'activité en raison de son caractère international, mais aussi aux difficultés relatives à la détermination de l'employeur véritable du travailleur dans le cadre de la relation de travail tripartite qui naît. La libre immatriculation des navires et le phénomène de complaisance ont conduit à une remise en cause du rôle premier que devraient jouer les États du pavillon dans la protection des gens de mer qui travaillent à bord des navires qu'ils immatriculent. Les États fournisseurs de main-d'œuvre, eux, semblent rechigner à l'idée de la mise en place d'une réglementation rigoureuse et rigoureusement appliquée à l'égard des agences qu'ils accueillent, en raison des considérations économiques (qui semblent prévaloir). Dans de telles circonstances, les États du port sont devenus de véritables remparts en matière de protection des gens de mer. Cette recherche propose une réflexion sur des mécanismes, y compris des mécanismes de responsabilisation des agences de *manning*, afin de faire émerger un ensemble de procédés devant permettre de garantir un travail décent des gens de mer recrutés par l'intermédiaire de ces agences. The maritime industry has undergone far-reaching changes that have affected not only commercial relationships associated with shipping, but also labor relations that arise when seafarers are employed on board ships. One concrete manifestation of these changes has been the use by shipowners of entities specializing in the supply of crew members. Known as manning agencies or manpower suppliers, these entities facilitate recruitment procedures for shipowners, and at the same time act as job providers for seafarers. However, some of the behaviour of manning agencies can jeopardize the protection of seafarers and their rights. As a result, activities of manning agencies have called for a legal framework. Despite the existence of international and national rules that form an impressive framework, some questions remain. These relate not only to the conflict of laws and jurisdictions posed by the international nature of the activity of manning agencies, but also to the difficulties involved in determining the true employer of the worker within the framework of the tripartite employment relationship that arises. The free registration of ships and the phenomenon of flags of convenience have called into question to the primary role that flag states play in protecting seafarers working on board the ships they register. Labour-supplying states, for their part, seem reluctant to introduce thorough regulations and apply them thoroughly to the agencies they host, given the economic considerations. As a consequence, port states have assumed bulwark functions when it comes to protecting seafarers. This research proposes an examination of mechanisms, including accountability mechanisms of manning agencies, with the aim to put forward a set of processes that guarantee decent work for seafarers recruited through these agencies.
Cotutelle : Université du Littoral et de la Côte d'Opale, Dunkerque, France
Keywords: Bureaux de placement; Conditions de travail; Contrat de travail; Droit international privé; Marin; Marin (droit); Marin (marine marchande); Sécurité; Sécurité du travail; Travail temporaire

Tax Behavior and Financing Behavior of Corporate Managers: Case of Banks and Decentralized Financial Systems (DFSs) in Benin - Agossadou, Stanislas T. Médard D. C. (Journal of Economics, Finance and Management, 2024)
This paper aims to analyzing the influence of tax behavior on financing (financial leverage) behavior of corporate managers. The paper applies the generalized method of moments (GMM) to dynamic panel data. The sample used covers 21 firms, i.e. 11 banks for the period from 2011 to 2020 and 10 DFSs for the period from 2016 to 2021. It turns out that financial leverage behavior is influenced more positively by corporate income tax (CIT), then by dividends (DIVIDEND); and negatively by interest on debt (INTEREST), by cash flow (CASH_FLOW) and by past financial leverage (LEVERAGE(‑1)). This paper is one of the first to extend the literature by identifying the main determinants of financing behavior, notably the positive effect of corporate income tax (CIT).
Keywords: Corporate income tax behavior; Corporate income tax savings; Financial objectives; Leverage behavior; Tax objectives

The duty of bank confidentiality and the safeguarding of financial privacy - Ahmed, Kousar Bibi (University of KwaZulu-Natal, 2024)
Abstract available in PDF.
Keywords: Banks and privacy; Customer confidentiality; Duty of confidentiality; Protection of personal information

Sermaye piyasası hukuku bakımından Mortgage - Aktaş, Mehmet Murat (Ankara Üniversitesi, 2024)
Türk mortgage sistemi veya mortgage menkul kıymetleştirmesi ve İpoteğe Dayalı Menkul Kıymetler-İDMK ihracı, sistemsel bütün olarak ilk kez uygulamada "Mortgage Kanunu" olarak da anılan 5582 sayılı "Konut Finansmanı Sistemine İlişkin Çeşitli Kanunlarda Değişiklik Yapılması Hakkındaki Kanun" (Konut Finansmanı Kanunu) ile 2007 yılında düzenlenmiştir. Meri'i düzenlemeler bakımından İDMK ihracı 6362 sayılı Sermaye Piyasası Kanunu (SerPK) madde 58 ve III-58.1 sayılı Varlığa ve İpoteğe Dayalı Menkul Kıymetler Tebliği (VİDMK Tebliği) ile düzenlenmiştir. Çalışmamızın amacı ve kapsamı, bünyesinde tek bir çalışmada ele alınması olanaksız sayıda hukuki düzenleme, kavram, kurum ve ilişki barındıran mortgage sistemini sermaye piyasası bakış açısıyla mevzuat tekrarlarından arındırılmış özlü tespit ve değerlendirmeleri esas alacak şekilde ele almaktır. Çalışmamızda mortgage sistemi kavramsal olarak gerçek anlamı ile ortaya konulacak ve ayrıca sistemin varlık nedeni ve özünü oluşturan sermaye piyasası unsuru olarak İDMK'ya ilişkin tespit, değerlendirme ve öneriler yer almaktadır. Mortgage ifadesi dar anlamda, Anglo-Sakson hukukunda kullanılan mortgage rehni ve mortgage teminatlı finansman alacaklarını ifade etmektedir. Mortgage terimi, sermaye ve finans piyasaları bakımından ise mortgage teminatlı alacakların İpoteğe Dayalı Menkul Kıymetler (İDMK/mortgage-backed securities-MBS) ihraç edilerek menkul kıymetleştirildiği (securitization) sistemi anlatmaktadır. Mortgage sistemi veya menkul kıymetleştirmesi ve İDMK ihracı ilk olarak Amerika Birleşik Devletleri (ABD) hukukunda uygulanmıştır. Mortgage sisteminin varlık nedeni, sermaye piyasalarından İDMK ihracı yoluyla en az maliyetle ve güvenilir bir şekilde finansman sağlanmasıdır. İDMK ihracı, mortgage (ipotek) teminatlı finansman alacaklarının, mortgage sistemi içerisinde gerçek satışa (true sale) dayalı olarak bilânço dışına çıkarılması ve menkul kıymetleştirilmesi ile gerçekleştirilmektedir. Bu nedenle İDMK, gerçek satışa dayalı bilânço dışı olarak gerçekleştirilen gerçek (geleneksel) menkul kıymetleştirme ürünü bir menkul kıymet niteliğindedir. Toplam beş bölümden oluşan Tez çalışmamızın ilk bölümünde, mortgage sistemi kavramı teknik anlamıyla değerlendirilecek, sistemin tarihi gelişim süreci ve ilişkili düzenlemeler ve niteliği olarak menkul kıymetleştirme ele alınacaktır. Çalışmamızın ikinci bölümünde, mortgage sisteminin işleyişi, sistemde kullanılan varlıklar ve safhaları, sistemin özgün terminolojisi berberinde değerlendirilecektir. Çalışmamızın üçüncü bölümünde ise mortgage sisteminde yer alan kuruluşlar gene sistemin kendine özgü kavram ve gereklilikleri dahilinde değerlendirilecektir. Çalışmamızın dördüncü bölümünde sistemin hedefi ve varlık sebebi olan İDMK tanımı türleri ve benzeri menkul kıymetler beraberinde ele alınacaktır. Çalışmamızın beşinci ve son bölümünde ise İDMK ihracı ile sağlanan sebepler ve ihracını güçleştiren sebeplere dair tespit ve önerilerimiz topluca yer alacaktır. Tezimizin sonuç kısmında ise gerçek anlamıyla uygulanması halinde ülkemizin hızlı ve sürdürülebilir bir biçimde kalkınmasını sağlayabilecek niteliği haiz bir sistem olan mortgage sistemi ve onun ürünü menkul kıymet olan İDMK'nın ihracı bakımından tespit ve çıkarımlarımız yer alacaktır. Tezimiz genel olarak Türkiye'nin finansal kurumlara, İDMK'yı, iç pazardaki ekonomik kalkınmayı hızlandırmak için sermaye piyasalarından fon sağlamak için kullanma önerisi de getirmektedir. Bu tez ile Türkiye'de finans kurumlarının MBS ihraçları için alternatif bir finansman kaynağı olarak dikkat çekilmesi de amaçlanmaktadır. Burada kamusal bir gelişme olarak ifade edilecek olursak, "Yeni Ekonomi Program", finansal derinliğin ve istikrarın sağlanması için Türkiye'deki menkul kıymetleştirmelerin (İDMK ihraçları dahildir) desteklenmesi tedbirini de içermektedir. The Turkish mortgage system, mortgage securitization, and the issuance of Mortgage-Backed Securities (MBS), collectively referred to as the "Mortgage Law," were initially regulated in 2007 by Law No. 5582, also known as the "Law on Various Amendments Regarding the Housing Finance System" (Housing Finance Law), commonly referred to as the "Mortgage Law" in practical application. In terms of secondary regulations, the issuance of MBS is governed by Article 58 of the Capital Markets Law No. 6362 (CML) and the Communiqué on Asset-Backed Securities and Mortgage-Backed Securities (ABS-MBS Communiqué). The aim and scope of this study involve a comprehensive examination of the mortgage system, which encompasses numerous legal regulations, concepts, institutions, and relationships. The focus is on providing concise assessments and evaluations, free from legal redundancies, based on the perspective of capital markets. The study conceptually presents the mortgage system in its true sense, addressing the essence and purpose of the system, particularly focusing on Mortgage-Backed Securities (MBS) as a capital market element, along with relevant findings, evaluations, and recommendations. In a narrow sense, the term "mortgage" refers to the mortgage lien and financing receivables secured by mortgages in Anglo-Saxon law. In the context of capital and financial markets, the mortgage system refers to the securitization of mortgage-backed receivables by issuing Mortgage-Backed Securities (MBS). The mortgage system, its securitization, and MBS issuance were initially implemented in the United States (US) legal framework. The raison d'être of the mortgage system lies in obtaining financing from capital markets through the issuance of MBS at minimal cost and in a reliable manner. MBS issuance involves transferring mortgage-backed financing receivables out of the balance sheet through a true sale mechanism within the mortgage system, facilitating their securitization. Therefore, MBS represents a security of a true sale-based, off-balance-sheet, and traditional nature. The thesis comprises five sections. The first section evaluates the concept of the mortgage system in technical terms, discussing its historical development, related regulations, and its nature as securitization. The second section delves into the operation of the mortgage system, the assets used, stages involved, and the system's unique terminology. The third section examines the institutions within the mortgage system, considering their specific concepts and requirements. The fourth section covers the objective of the system and the definition of MBS, its types, and similar securities. The fifth and final section consolidates our findings and recommendations regarding the reasons for MBS issuance and the challenges hindering it. In the conclusion, we highlight the potential of the mortgage system and its product, MBS, as a system capable of fostering rapid and sustainable development in Turkey when implemented in its true sense. The thesis suggests that financial institutions in Turkey consider MBS issuances as an alternative source of funding, aiming to accelerate economic development in the domestic market. Additionally, the study aligns with the "New Economic Program," which includes measures to support securitizations in Turkey, including MBS issuances, to ensure financial depth and stability.
Tez N°865004
Keywords: Capital market; Hypothèque; Menkul kıymetleştirme; Mortgage; Mortgage Backed Securities; Securtization; Sermaye Piyasası Hukuku; Sûretés; İpoteğe Dayalı Menkul Kıymetler

Part XV Chapter 2, Conciliation beyond the courts: aspirations and limits of mandated and voluntary court mediation programmes from a multi-jurisdictional perspective - Ali, Shahla (Comparative Procedural Law and Justice, 2024)
Keywords: Convention on the Recognition and Enforcement of Foreign Arbitral Awards (1958); International commercial arbitration; MARD; Mediación; Mediation; Mediação; Médiation; UNCITRAL Arbitration Rules; UNCITRAL Model Law on International Commercial Arbitration (1985)

L’annulation des décisions judiciaires nationales par la Cour Commune de Justice et d’Arbitrage - Balla Kalto Loutou, Amina (Revue Africaine des Réflexions Juridiques et Politiques, 2024)
La prérogative de l’annulation des décisions des juridictions nationales est dévolue à l’institution juridictionnelle supranationale, qu’est la C.C.J.A, qui assure la sécurité juridique et judiciaire par l’exercice de ses fonctions juridictionnelle, consultative et arbitrale. Outre, le contrôle de l’application effective des règles du droit OHADA par les juridictions nationales de fond (recours en cassation), elle veille sur le fondement de l’article 18 du Traité OHADA au respect de ses compétences par l’exercice de son pouvoir d’annulations des décisions des juridictions nationales de cassation ou des juridictions du fond statuant en dernier ressort ou sur des sentences arbitrales en violation des règles de compétence, de procédure ou d’ordre public. Lorsqu’elle annule les décisions des juridictions nationales sur le fondement de ce texte, la C.C.J.A rend des arrêts par lesquels, elle déclare ces décisions nulles et non avenues les décisions incriminées. Les arrêts d’annulations que rend la C.C.J.A sont exécutoires et doivent être exécutés dans les ordres juridiques internes et communautaires pour pouvoir s’imposer aux parties, aux juridictions en cause et aux Etats parties de l’espace OHADA.
Keywords: Autorité de la chose jugée; Circulation des arrêts de la CCJA; Compétence exclusive; Compétence générale; Dessaisissement; Force exécutoire; Intégration juridique; Intégration juridique annulation; Supranationalité; Sécurité juridique

Uniform Law: Legal Responses to Globalisation - Basedow, Jürgen; Max-Planck-Institut für Ausländisches und Internationales Privatrecht (Hamburg, Germany) (Mohr Siebeck, 2024)
International conference proceedings
Keywords: COMMERCIAL LAW; Economic Analysis; PRIVATE INTERNATIONAL LAW; Uniform law

Procedural Justice in Online Dispute Resolution: An Empirical Enquiry - Beretta, Rachele (University of Antwerp, 2024)
The surge in online interactions has led to a parallel rise in civil and commercial disputes that transcend geographical boundaries. As traditional dispute resolution mechanisms face challenges adapting to this evolving paradigm, conflicts increasingly migrate to online platforms. Within this proliferating landscape, it is crucial to recognize the scarcity of research devoted to Online Dispute Resolution (ODR) providers and the myriad types of services they currently offer to users worldwide. Despite the ongoing geographical expansion of ODR, the inquiry into how procedural justice principles manifest in these digital dispute resolution systems remains notably under-explored. A growing body of literature underscores that procedural justice is critical for building users’ trust, enhancing the legitimacy of organizations among communities, and fostering compliance with outcomes. The ability of ODR providers to meet users' expectations in terms of procedural justice can significantly shape users' perception of ODR institutions as trustworthy and dependable. This bears paramount implications for the ongoing development of ODR, whose acceptance varies widely across jurisdictions. This doctoral thesis delves into the intricate intersections of procedural justice within the realm of international civil and commercial ODR, examining the nuanced dynamics that emerge in virtual spaces. Ultimately, it seeks to understand how procedural justice principles, rooted in the notion of fairness, manifest and evolve in the context of ODR, exploring the impact of digital interventions on the perceived fairness of dispute resolution processes. Understanding procedural justice in ODR is not merely an academic pursuit; it holds profound implications for legal practitioners, policymakers, and society at large. This research aims to contribute valuable insights that can inform the design of fairer and more effective ODR systems.
Keywords: Dispute Settlement; Justice; ODR; Online Dispute Resolution; Procedure (Law); UNCITRAL Arbitration Rules

La problématique de la répression des infractions commises par les entreprises multinationales en droit pénal congolais - Betu Kumeso, Jenny (Revue Africaine des Réflexions Juridiques et Politiques, 2024)
La répression des entreprises multinationales constitue un défi pour le droit pénal dans la mesure où elles sont avant tout une donnée économique, de prime à bord insaisissable par le droit pénal. Le droit pénal qui est l’expression de la souveraineté nationale semble dépasser face à la délinquance collective qui traverse les frontières dans un monde globalisé, mais composé d'États souverains. La puissance et la capacité des entreprises multinationales à supplanter les États font de ces entités, une nébuleuse pour laquelle la régulation étatique apparaît comme un vœu pieu. Cette étude vise, d’une part, à analyser les obstacles qui empêchent le droit pénal de saisir la délinquance des entreprises multinationales et d’autre part, à démontrer, que le droit pénal n’est pas totalement désarmé ou dépassé, il dispose des ressources nécessaires lui permettant de réprimer de manière efficace et efficiente la délinquance de ces entreprises.
Keywords: Crimes internationaux; Droit pénal; Entreprises multinationales; Environnement; Richesses naturelles; Victimes

Evaluating the International Arbitration of Oil and Gas Investment Dispute Settlement in Nigeria - Bisina, Lucky N. (African Journal of International Energy & Environmental Law, 2024)
This paper examined international arbitration as a tool for resolving investment disputes in Nigeria’s oil and gas sector, a critical industry that contributes significantly to Nigeria’s Gross Domestic Product (GDP), foreign exchange earnings and government revenues. This sector is marked by high-risk investments and complexity and often faces disputes arising from regulatory changes, fluctuating global prices, environmental concerns and contractual breaches. Arbitration, particularly in cross-border investments, provides a neutral, efficient and flexible mechanism for resolving such disputes. Using a doctrinal research methodology, the study analysed statutes, case law, international treaties, and academic sources. Findings revealed that while arbitration offers benefits such as neutrality and enforceability, there are still some challenges that must be addressed as a matter of urgency. Issues include resistance to enforcement of arbitral awards by Nigerian courts on grounds of national interest, high arbitration costs and biases favouring foreign investors. Nigeria’s legal framework, including the Arbitration and Mediation Act 2023 and the Petroleum Industry Act 2021, supports arbitration but lacks procedural clarity, leading to delays and inefficiencies. The paper concluded that legal reforms are essential to strengthen arbitration processes, enhance enforcement mechanisms and align Nigeria’s framework with international standards. Such reforms would foster investment stability and improve Nigeria’s attractiveness as an investment destination by reducing legal uncertainties. The paper recommended legislative and judicial improvements in order to achieve these goals.
Keywords: Dispute Settlement; International Arbitration; Investment Dispute; Oil and Gas Investment

Climate Litigation and Justice in Africa - Bouwer, Kim; Etemire, Uzuazo; Field, Tracy-Lynn; Jegede, Ademola Oluborode (Bristol University Press, 2024)
This volume brings together an international team of contributors to provide a much-needed examination of climate litigation in Africa. The book outlines how climate litigation in Africa is distinct as well as pinpointing where it connects with the global conversation. Chapters engage with crucial themes such as human rights approaches to climate governance, corporate liability and the role of gender in climate litigation.
Keywords: Africa; Climate adjudication; Climate governance; Climate justice; Climate litigation

L’affaire du magiun de prunes de Topoloveni, Roumanie. Ou le moment où une marque ultérieure réussit à coexister avec une indication géographique protégée - Budileanu, Cristina (Revue francophone de la propriété intellectuelle, 2024)
On trouve sur le marché une multitude de signes utilisés par les commerçants pour se distinguer de leurs compétiteurs ou pour mettre en avant la qualité de leurs produits. Ces différents signes sont régis par des systèmes de protection distincts pouvant souvent entrer en conflit. Cet article vise à présenter un cas de conflit entre une indication géographique protégée roumaine et une marque nationale individuelle Roumaine enregistrée ultérieurement One finds in trade a multitude of signs with the help of which traders try to distinguish themselves from their competitors or to distinguish the qualities of their products. These signs have different protection systems and often come into conflict. The purpose of this article is to present such a conflict between a protected geographical indication from Romania and a subsequent individual national trademark from Romania.
Keywords: Indication géographique; Intellectual property; Marque de commerce

Arbitration in the era of e-commerce: A comprehensive overview - Buhuri, Kristi (World Journal of Advanced Research and Reviews, 2024)
Technology is continuously evolving and has changed human interaction. It is consequently changing the ways disputes are solved. International dispute resolution procedures, and international arbitration, more specifically, are considerably influenced by the rapid expansion of innovative technologies. Years after the dot-com boom, Online Dispute Resolution (ODR) emerged and evolved considerably. Due to the digitalization of ODR methods, remote arbitration (or e-arbitration) is expanding. Arbitration is of particular interest due to its formal and binding nature, from a theoretical perspective. E-arbitration, as other ODR methods have attractive features as well as drawbacks, which are addressed in this document. The purpose of this paper is three-fold: providing an overview of e-arbitration and the different considerations of this method, presenting the e-arbitration models of the European Union (EU), the United States (US), and the People’s Republic of China (PRC) and suggesting recommendations to improve international e-commerce arbitration, notably through a revision of the UNCITRAL Model Law on International Commercial Arbitration (UNCITRAL Model Law).
Keywords: Arbitrage; Arbitragem; Arbitraje; Arbitration; Digitalization; Innovative Technologies; ODR; Online Dispute resolution; e-Arbitration

Arbitration rules: In force as from 15 January 2024 - Cairo Regional Centre for International Commercial Arbitration (CRCICA, 2024)

Corporate mergers: a comparative analysis of the Italian and American legal systems - Carboni, Ludovica (LUISS Guido Carli, 2024)
Mergers in the Italian and European legal system. The Italian legal landscape for mergers. Applicable regulations. Stages of the merger process. The first phase: the merger plan. The second phase: the merger resolution. The third phase: the merger deed. The protection of creditors. The invalidity of the merger. The FIAT-Chrysler merger. Evolution of the legal nature of mergers in the Italian legal system: legislative and jurisprudential perspectives. The extinguishing-successory orientation. The evolutionary–modifying orientation. Court of cassation ruling no. 2637 of 2006. Return to the extinguishing-successory orientation: judgement no. 21970/2021. Debate surrounding judgement 21970/2021: criticism and support. Mergers in the American legal system. The American legal landscape for mergers. The evolution of the US corporate law of mergers. Sources of corporate law. The merger process. Economic motives for mergers. Steps of the merger procedure. The merger plan. Merger between parent and subsidiary or between subsidiaries. Articles of merger. Effects of merger. Abandonment of a merger or share exchange. The ExxonMobil merger. Comparative analysis of the Italian and American legal systems. Historical and constitutional influences on Italian and American legal systems. Differences and similarities in the merger process. Comparison of FIAT Chrysler and ExxonMobil mergers.

Chronique de droit du dommage corporel (janv.-déc. 2023) - Cayol, Amandine (Bulletin Juridique des Assurances, 2024)
Aniciennement Actuassurance

Règlement d'arbitrage : En vigueur à compter du 15 janvier 2024 - Centre régional du Caire pour l’arbitrage commercial international (CRCICA, 2024)

COFOLA 2024: Sborník příspěvků mladých právníků, doktorandů a právních vědců. Část 1, Daňové právo v proměnách času - Czudek, Damian (Masarykova Univerzita, 2024)
Sborník příspěvků zabývajících se aplikací a interpretací daňového práva, tvorby daňového práva ve smyslu jeho stability a předvídatelnosti, jak z pohledu daňových subjektů (zejména podnikatelů, ale i fyzických osob nepodnikatelů, ale také státu a jemu podřízených organizací (z pohledu předvídatelnosti příjmů do veřejných rozpočtů a stability veřejných financí).
Keywords: Droit fiscal; E-knihy; Elektronické knihy; Fiscalité; Knihy; Tax law; Čítárna

The protection of executory contracts in restructuring proceedings - Dejoux-Pasdeloup, Lea Francoise Paulette (Mikolas Romeris University, 2024)
This thesis focuses on the relationship between contract law and corporate insolvency law as it investigates the idea and protection of executory contracts within restructuring proceedings. However, preserving these agreements frequently necessitates taking legal action against established contract law tenets like the freedom of contract and the duty to perform. The study looks at how difficult it can be to keep debtor and creditor interests in balance, especially when there are disruptions brought on by insolvency. The study suggests ways to improve the efficacy of restructuring proceedings by analysing the EU Directive on restructuring and insolvency, contrasting practices in various jurisdictions, and evaluating the impact on stakeholders. The goal of this study is to protect the rights of all parties involved in corporate restructuring while advancing the creation of legal frameworks that facilitate effective restructuring.
Keywords: Creditor; Cross-border Insolvency; Darbuotojai; Debtor; Employees; Insolvency; Kreditorius; Nemokumas; Restructuring proceedings; Restruktūrizavimo bylos; Skolininkas

La saisie-vente du fonds de commerce - Dembele, Nabedjomon Massa (Revue Africaine des Réflexions Juridiques et Politiques, 2024)
Le nouvel Acte uniforme sur les procédures simplifiées de recouvrement et des voies d’exécution du 15 novembre 2023 offre désormais aux créanciers la possibilité de saisir vendre le fonds de commerce appartenant à leur débiteur. Cette nouvelle mesure d’exécution renforce ainsi leurs garanties de recouvrement. Celles-ci ne sont cependant pas gagnées d’avance. Certains éléments incorporels du fonds de commerce, tel que la clientèle, le nom commercial et le bail se prêtent difficilement à la saisie. De plus, le débiteur, par l’exercice d’une procédure collective ou d’une demande de grâce, peut contourner la mesure. À ceux-là, s’ajoutent le fait que d’une part les droits de l’adjudicataire du fonds de commerce sont moins préservés que ceux de l’acquéreur classique en ce qu’il ne bénéficie pas, à l’instar de toute vente aux enchères publiques, de garantie contre les vices cachés et dans une moindre mesure contre l’éviction et d’autre part, le fait que les droits du locataire- gérant ou du sous-locataire peuvent s’en retrouver compromis par l’opération de la saisie-vente.
Keywords: Enforcement; Fonds de commerce; Garanties; Goodwill; Guarantees; Saisie-vente; Seizure-sale; Voie d’exécution

(R)evolution of insolvency law under the impact of artificial intelligence (AI): transformative technologies - challenges and perspectives - Didea, Ionel; Ilie, Diana Maria (Legal and administrative studies, 2024)
Keywords: AI; Artificial Intelligence; Bankruptcy; Cross-border Insolvency; Insolvency; Inteligência artificial; Intelligence Artificielle; Technology; UNCITRAL Model Law on Cross-Border Insolvency (1997)

L’OHADA et les ressources naturelles - Dieudonné, Barnabas (Revue Africaine des Réflexions Juridiques et Politiques, 2024)
Les ressources naturelles occupent une place prépondérante dans le commerce international. L’Afrique en est riche. Par contre, le problème de leur gestion se fait sentir sur le continent au point que des chercheurs ont évoqué la « malédiction des ressources naturelles ». Le droit de l’OHADA ne les a pris en compte que timidement. Cette insuffisance de règlementation dans le droit communautaire a des incidences tant sur le commerce de ces produits dans l’espace OHADA que sur la jouissance de certains droits humains. Les tentatives de règlementation de certains aspects de ce secteur d’activité de la part d’autres organisations internationales et de certains États montrent la nécessité de les intégrer correctement dans le corpus juridique de l’OHADA. Un Acte Uniforme serait susceptible d’atténuer, au sein des États parties, la « malédiction des ressources naturelles » aussi bien que les atteintes aux droits de la personne résultant de leur exploitation comme le droit à un environnement sain et les droits économiques et sociaux.
Keywords: Acte uniforme; Droits humains; Ressources naturelles; Règlementation

La régulation de la chaîne de blocs par la propriété intellectuelle et le droit de la concurrence : approche comparative et prospective des droits canadien et américain - Diop, Rokhaya (Bulletin de droit économique, 2024)
Keywords: Approche comparée; Blockchain technology; Chaine de blocs; Competencia; Competition law; Concurrence; Intellectual property; Propriedade intelectual; Propriété intellectuelle; Régulation

Milletlerarası özel hukukta iflâs - Dorken, Oğuz (Galatasaray Üniversitesi, 2024)
This study aims to provide a detailed and comprehensive legal analysis of international bankruptcy and related issues by drawing on comparative law and private international law. In this context, this thesis aims to determine the legal qualifications of the transactions that fall within the framework of international insolvency and to address the problems related to these issues in detail. This study consists of five chapters. The first chapter examines the specific aspects of insolvency in the fields of debt enforcement, procedural law, and substantive law. The main argument in this chapter is that bankruptcy law has its own normative scope. In this framework, bankruptcy law and enforcement law regulate areas that can be analytically distinguished from each other. The law of debt enforcement regulates all actions and procedures based on the state's sovereignty and power to use force. On the other hand, bankruptcy law can be characterized as a multi-layered and unique branch of substantive law that has features related to the law of obligations or commercial law, depending on the context. The first chapter begins with an etymology of the concept of insolvency across various languages. The Turkish word "iflâs" is highlighted, which comes from the Arabic word "fls" (fels), indicating a state of destitution and insolvency. In English, the term "bankruptcy" has historical origins that trace back to medieval Italy, where merchants who couldn't pay their debts had their trading benches physically broken, a practice referred to as "banca rotta." The main goal of this analysis is to emphasize that historically, insolvency has been perceived as a condition of incapacity and deficiency resulting in disgrace, even in the mildest scenarios. In terms of the severity of Roman law, penalties such as enslavement or death for bankrupt individuals illustrate how grave the offense of bankruptcy was considered. Furthermore, during the Middle Ages, those in financial distress were scorned by society. Meanwhile, with the modernization of legal systems, efforts have been made to alleviate the negative social perception of individuals who become insolvent. These efforts have led to changes in the law and the emergence of new terminologies. Over time, legal terminology across different countries has evolved. For example, in the US, the terms "debtor" and "insolvency" are now more commonly used in place of "bankrupt" and "bankruptcy" respectively, in the context of insolvency law. In line with these changes in terminology, reform efforts at both the comparative and international law levels aim to diminish the stigma attached to insolvent individuals and companies, striving to provide them with the opportunity for a fresh start within the economic order. Moving on, the first section distinguishes between the narrow and broad meanings of the concept of insolvency in comparative law and international instruments. Throughout this study, bankruptcy in its narrow sense refers specifically to procedures that involve the liquidation and distribution of a debtor's assets and/or the dissolution of their legal personality to satisfy creditors in accordance with applicable laws. In contrast, the broad sense of insolvency encompasses the debtor's objective inability to pay, the formal declaration of this predicament by a competent authority, body, or the debtor themselves, as well as all subsequent actions taken to settle claims and manage the debtor's assets. Within this expansive interpretation of insolvency, the study underscores the principle of collectivity, which is critical in administering bankruptcy procedures. Additionally, it conceptualizes bankruptcy as a wide-ranging framework, starting from liquidation in the narrowest scope and extending to include debt restructuring and non-judicial workout solutions. Furthermore, this study primarily considers insolvency law as substantive law. It supports the notion that while insolvency contains procedural elements, these are not its defining features. The focus here is on the processes associated with the initiation, execution, management, and conclusion of bankruptcy proceedings. The second chapter of the study is dedicated to the conceptual framework and theoretical perspectives of international insolvency. The term "international insolvency" refers to various situations in which a debtor may have a cross-border element—such as operating in more than one country, being domestic with creditors located abroad, being a foreign entity with domestic creditors, or having assets dispersed over multiple countries. In this section, the chapter elaborates on various theoretical approaches to the legal framework governing international insolvency. These approaches include territorialism, which is based on the principle of territoriality or locality; universalism, which advocates for consistent practices and standards in cross-border insolvencies; and the hybrid approach. Due to the practical difficulties encountered with universalism, mixed approaches have been developed, offering alternatives such as cooperative territoriality, multilateralism, contract theory, universal proceduralism, and modified universalism. The examination of these approaches, each presenting distinctive advantages and challenges, provides significant insights into the ongoing and potential resolutions for issues in international insolvency. Chapter Three outlines a general framework that defines the relationship between international insolvency and the law. In this chapter, the legal nature of international insolvency law is first explained, and a reminder is provided of the modern insolvency law approach introduced in the first chapter. Within this framework, the aim of insolvency law is to develop a collective procedural structure founded on the principles of justice that considers the interests of all parties involved. It seeks to maximize the value of the debtor's assets, minimize waste, ensure the rescue of viable businesses, and develop appropriate techniques for these purposes. The transnational aspect of bankruptcy introduces an additional layer of complexity to the existing definition and framework. Consequently, international insolvency law is evolving into a distinct system within private international law, specifically catering to transnational insolvency cases. This system often described as "sui generis" strives to fulfill the objectives of insolvency in scenarios that transcend national borders. The growing field of transnational insolvency anticipates the effective centralization of proceedings that are acknowledged and aided by foreign authorities. The goal is to maximize asset values and ensure business recovery while carefully considering the interests of all affected parties, regardless of their location. In international insolvency cases, it's important to balance the interests of creditors and debtors. Factors like nationality or foreign status, as well as the role of the state as an entity under international law, should be considered in this balance. In order to establish this balance, it is of great importance to explore harmonious and effective solutions by evaluating these interests in a holistic framework. Practices in international insolvency and comparative law have tended towards a perspective that aims to harmonize and coordinate different interests. In fact, this is the main concern of the modified universalism approach. From this perspective, the final section of the third chapter examines various legal frameworks or regimes for international insolvency. This includes a study of the ecosystem of Model Laws related to insolvency, with particular emphasis on the 1997 UNCITRAL Model Law, as well as the regulations in force within the European Union, the United States, and Latin American countries. The fourth chapter delves into international insolvency by addressing traditional concepts of international procedural law. It evaluates the criteria for international jurisdiction in insolvency proceedings, the recognition of foreign insolvency judgments, and the determination of applicable law. These topics are scrutinized using a comparative legal framework, drawing from the UNCITRAL Model Law, regulations in the U.S. and the EU, and various national laws, which the third chapter discusses. Techniques from comparative and private international law are employed to analyze these issues, which can be summarized as follows: Firstly, in the realm of international insolvency and private international law, a common challenge involves identifying the competent court for the proceedings. This issue is often resolved using the principle of the Center of Main Interests (COMI). COMI refers to the primary location of a company's or legal entity's operational activities in the context of insolvency or debt restructuring. It is typically associated with the site of the debtor's main administrative office, the place where significant operations are conducted, or the location where crucial commercial decisions are made. Additionally, the issue of forum shopping often arises in discussions of international jurisdiction and represents the second significant concern. In the context of international insolvency, 'forum shopping' is the practice where an internationally active company selects a jurisdiction that is perceived to offer the most favorable legal environment for its restructuring or insolvency processes. The company then takes steps to establish its case in the chosen jurisdiction in hopes of benefiting from its laws in the event of insolvency. The modified universalism approach argues for a legal framework where the primary insolvency proceedings are initiated in the debtor's Center of Main Interests (COMI), while ancillary proceedings may occur in other jurisdictions. Such a framework aims to curb the practice of forum shopping. Both the UNCITRAL Model Law and the EU Insolvency Regulation embrace this approach, thus promoting a more orderly and predictable system for handling cross-border insolvencies. The second issue addressed in Chapter Four is the recognition of the effect of foreign insolvency procedures. This section scrutinizes how foreign insolvency procedures interrelate with existing cross-border insolvency frameworks and evaluates the limitations imposed by such frameworks on the ability of these procedures to be recognized and enforced. Initially, the discussion focuses on how international frameworks handle the concept of a foreign procedure, beginning with standards set by the Model Law and then proceeding to the foreign insolvency procedures outlined in the EU Insolvency Regulation. The characteristics of the procedures in these two contexts are compared, and the techniques foreign courts apply to recognize, enforce, or reject them are examined. The third issue explored in the fourth chapter is the rules concerning the applicable law, with a focus on the principle of Lex fori concursus. This concept is rooted in the broader lex fori principle, a cornerstone of private international law. Under the Lex fori principle, a court typically applies its own domestic law—the law of the forum—to decide both procedural matters and, in the context of insolvency, the substantive rules governing the proceedings. This application of domestic law aligns with the state's sovereignty, as procedural law is deemed an extension of a nation's public law framework. According to the principle of Lex fori concursus, the law of the country where the insolvency proceedings are initiated typically governs the insolvency process and any related legal actions. This principle is formalized as a general rule in Article 7 of the EU Insolvency Regulation. Nevertheless, the regulation also delineates specific exceptions to this principle in subsequent provisions. These exceptions, as articulated in the EU Insolvency Regulation, include the following: (1) Third parties' rights in rem; (2) set-off; (3) reservation of title; (4) contracts relating to immoveable property; (5) payment systems and financial markets; (6) contracts of employment; (7) rights subject to registration; (8) detrimental acts of the debtor; (9) effects of insolvency proceedings on pending lawsuits or arbitral proceedings and 10) Protection of third-party purchasers. Furthermore, public policy is also recognized as an exception. It is a general principle that when foreign court proceedings are concerned, the Lex fori concursus - the law of the place where the insolvency proceedings are occurring -should be applied by the local court. The public policy exception, however, might place restrictions on this principle. This safeguard, which bars the application of foreign laws that are in conflict with the fundamental principles of the local law, enables the local court to give preference to its own laws over those of another country under specific, limited circumstances in bankruptcy cases. Nevertheless, it is important to underline that the concept of public policy does not grant countries unfettered discretion. UNCITRAL emphasizes that for the exception to the lex fori concursus to be invoked on public policy grounds, the contravention must be "manifestly" evident, leaving no room for doubt. Chapter 5 explores the specific challenges associated with international insolvency, such as the identification of the debtor's assets, the imposition of insolvency seizures, the prioritization of claims, and the annulment of detrimental transactions intended to disadvantage creditors. Furthermore, the chapter examines the procedures governing insolvency and the complexities surrounding the insolvency of multinational corporations. Among these problems, under the section titled 'Determination of the Debtor's Assets and Insolvency Seizure,' the text mentions the difficult task of monitoring and recovering assets internationally in the digital age, where goods can rapidly move across borders. Variations in practices among different countries contribute to inconsistencies in this area and exacerbate challenges in insolvency cases. International commercial activities and cross-border bankruptcies further complicate the process of tracing and recouping assets and can result in conflicts between laws. The absence of a universal legal framework, applicable across all countries, poses a significant impediment to protecting assets and maximizing their recovery in the course of insolvency proceedings. In this context, there is a pressing need to cultivate global cooperation and establish mechanisms that address critical issues such as the identification of assets, the temporary seizure of assets, and the prevention of unauthorized transfers. For instance, the use of 'freezing orders'—the authority to impose temporary restrictions on the transfer, sale, or disposal of assets under foreign jurisdictions—has proven effective in safeguarding assets. Within the European Union, Articles 19(1) and 20(1) of the EU Insolvency Regulation mandate that an EU-wide suspension of transactions automatically takes effect upon the initiation of substantive insolvency proceedings in any Member State. Another issue discussed in the fifth chapter concerns the annulment of transactions made with the intent to harm creditors, an issue commonly referred to as 'avoidance.' This term describes any actions that undermine the debtor's ability to fulfill its obligations, thus impairing the rights of creditors by devaluing the debtor's assets or rendering them unreachable for creditor claims. The UNCITRAL Model Law on Cross-Border Insolvency and the EU Insolvency Regulation both seek to offer various solutions to this problem. Nevertheless, avoidance laws can differ significantly from one country to another, where legal systems have disparate criteria for assessing the validity of such transactions. A transaction that is deemed fraudulent in one jurisdiction could be considered valid in another. The chapter also addresses "conflicts of priorities" which present analogous challenges. The matter of creditor priority in international insolvency law underscores the absence of standardized regulations and systems, consequently impeding cooperation among courts and complicating the adjudication process. Considerable variations exist in the interpretation of equitable treatment for domestic and foreign creditors during insolvency proceedings, as well as in how such equity should be guaranteed. These complexities span from determining the sequence of repayment to more granular concerns regarding the handling of various types of creditors and their respective claims. These difficulties obstruct efforts to establish a consistent and harmonized framework for international insolvency law. In international insolvency cases, the varying legal traditions, economic levels of different countries, and cultural norms that shape business and economic practices necessitate a flexible framework capable of accommodating all alternatives—judicial and extrajudicial—to manage insolvency effectively. The prevailing trend in cross border insolvency law, as reflected in internationally recognized instruments, aligns with the general evolution of insolvency and restructuring law. This trend entails examining the compatibility of evolved insolvency procedures, which offer solutions for early-stage financial distress, with the mechanisms for recognition, cooperation, and legal assistance provided by international frameworks. Moreover, the impact of these procedures' implementation within the context of such frameworks is thoroughly considered. Chapter 5 concludes with a discussion on the insolvencies of multinational corporations, which have significantly grown in complexity due to the global economic downturns experienced over the past three decades. These insolvencies have carved out a distinct and intricate niche within international insolvency law, necessitating detailed scrutiny. The collapse of such large, cross-border enterprises highlights some of the most challenging facets of insolvency cases and has a profound influence on the global economic landscape. As this area intersects with the broader issues explored earlier in the study, it stands out as a fertile ground for legal innovation and swift progression, drawing upon advancements in legal theory, comparative law practices, and international regulations. The ongoing efforts and developments in this sector are proving essential in tackling these multifaceted challenges day by day. In conclusion, this study provides a thorough examination of the foundations, distinguishing traits, and practical applications of international insolvency law, framed within comparative and private international law. Its principal aim is to enrich the legal and theoretical discourse on cross-border insolvency by meticulously investigating the multifaceted procedures of insolvency in their global context. The historical development of insolvency and its integration into modern legal systems are explored, recognizing the profound influence of international insolvency's complexities on various legal frameworks. With a particular focus on two salient issues, the study confronts challenging topics such as the recognition and interrelationship of insolvency proceedings, their alignment with collaborative mechanisms and judicial support, the expansive definition and scope of insolvency across jurisdictions, and the intricate insolvencies faced by multinational corporations.
Tez N°863799
Keywords: Insolvency; International bankruptcy; International law

Les obligations accessoires dans l’expédition de marchandises par route - Endjilidi, Hubert (Revue Africaine des Réflexions Juridiques et Politiques, 2024)
Le contrat de transport routier de marchandises dans son exécution impose des obligations accessoires aux parties. Ces obligations sont essentielles au transporteur pour une bonne préparation de l’envoi. Par ailleurs, ce dernier conclut un contrat avec le manutentionnaire pour effectuer les opérations de chargement et de déchargement moyennant le versement d’une somme supplémentaire d’argent par l’expéditeur. La mauvaise opération de manipulation des objets engage la responsabilité de l’auteur du dommage. La solution retenue peut être le partage de responsabilité ainsi que le mode de réparation afin d’assurer l’équilibre financier entre le transporteur et le manutentionnaire.
Keywords: Expéditions; Marchandises; Obligations; Route; Routier; Transport

Lumières sur la petite et moyenne entreprise en Afrique : les spécificités de quelques législateurs - Enoga, Laurent François (Revue Africaine des Réflexions Juridiques et Politiques, 2024)
La petite et moyenne entreprise demeure une réalité à travers laquelle l’initiative privée s’exprime en Afrique et les législations nationales ont prévu divers textes pour en assurer l’encadrement. L’examen au pif de divers morceaux choisis des cadres juridiques nationaux nous a semblé particulier pour en cerner les contours définitionnels et leurs implications. Au clair, trente-sept ans après la 72e session de la Conférence Internationale du Travail, de nombreux législateurs africains ont légiféré sur les micros, petites et moyennes entreprises en abordant les aspects fondamentaux dont entre autres la qualité de PME, qui dispose d’un statut différent de celui de la grande entreprise. Dès lors, au terme de cette lecture profonde et considérant les avancées de l’entrepreneuriat en Afrique, il serait intéressant pour les juristes de se pencher sur le cadre juridique de ce type d’entreprises fortement enracinées dans le secteur informel, dont le potentiel d’emplois et de contribution au produit intérieur brut dans les pays africains est non négligeable.
Keywords: Législateurs; PME; Petites et moyennes entreprises

Vers une historicité de la promotion des petites et moyennes entreprises en droit camerounais - Enoga, Laurent François (Revue Africaine des Réflexions Juridiques et Politiques, 2024)
Pendant que la littérature en sciences économiques et de gestion abonde sur la question des petites et moyennes entreprises, en sciences juridiques la recherche est pauvre. C’est sans doute pour pallier ce vide que le présent article y consacre un intérêt fécond, pour plonger le lecteur dans les méandres historiques de la promotion des PME au Cameroun. Après les vingt premières années post indépendances marquées par la marginalisation de l’initiative privée locale, les PME ont connu une période de restauration au début des années 1980 avec l’avènement du deuxième code des investissements de juillet 1984, induisant un réaménagement juridique aux incidences controversées. Une vingtaine d’années après, tirant les leçons de l’enlisement tumultueux des PME marqué entre autres par un ancrage considérable de l’économie informelle, le dispositif juridique national s’est enrichi d’une loi consacrant exclusivement la promotion des PME. Certes que cet acquis marque une avancée notable, mais elle n’est pas encore suffisante pour impulser la croissance économique.
Keywords: Historicité; PME; Petites et moyennes entreprises; Promotion

Genişletilmiş toplu lisanslama - Erçal, Hi̇lal (Ankara Yıldırım Beyazıt Üniversitesi, 2024)
Teknolojik ilerlemenin bir sonucu olarak internet, telif hakkına konu fikri ürünlerin dağıtımının yapıldığı ana mecra haline gelmiştir. Dijital teknolojinin birçok yerde ve çok yönlü birçok kişi ya da kurum tarafından kullanılması, özellikle telif haklarına konu fikri ürünleri etkilemiştir. Avrupa Birliği (AB) ise Dijital Tek Pazar oluşturma stratejisi kapsamında düzenlemelerine 2019/790 sayılı Dijital Tek Pazarda Telif Hakları ve Bağlantılı Haklar Yönergesini eklemiştir. Söz konusu direktifin 8 ve 12. maddelerinde ise genişletilmiş toplu lisanslama (GTL) düzenlenmiştir. GTL özellikle kitlesel olarak dijital mecrada kullanımın yoğun olduğu müzik, işitsel-görsel, sinema vb. eserlerin teliften arındırılmış şekilde kullanılmasına olanak sağlayan bir sistemdir. Özellikle televizyon yayınlarında olduğu gibi bazı kullanımların çok miktarda eser veya telif unsuru içermesi nedeniyle, tüm hak sahipleri ile görüşülerek kullanım izinlerinin alınması dijitalleşen dünyada hem çok maliyetli hem de oldukça zahmetli ve hatta çoğu zaman imkânsız bir hal almaktadır. Fikri ürünler üzerinde hak sahibi olanların, telif haklarını kullanma yetkisini herhangi bir meslek birliğine ya da toplu hak takibi yapan bir organizasyona vermemesi, başka bir deyişle oranın bir üyesi olmaması halinde söz konusu kullanımlar için izin alınması hem kullanıcılar açısından oldukça külfetli, hem de hak sahiplerinin menfaatlerini koruma noktasında daha da büyük bir sorun teşkil etmektedir. Bunun yanında kültürel mirasın korunmasıyla yükümlü olan kurumlar açısından en önemli zorluklardan biri, telif hakkı sahiplerinin kimliklerinin belirlenmesi ve telif hakkı içeren eserlerin kullanılması için yetki ya da lisans alınması gibi telif hakkı temizliğine ilişkin süreçlerdir. Özellikle sınır ötesi online kullanımlar açısından düşünüldüğünde bu çok daha karmaşıktır. GTL düzenlemesi ile dijital çağda herhangi bir toplu hak yönetimi organizasyonuna üye olmayan eser ve bağlantılı hak sahipleri açısından da meslek birlikleri ile kullanıcılar arasında yapılan lisans sözleşmelerinin geçerli olmasını sağlayacak bir sistem öngörülmüştür. As a conclusion of technological progress, the Internet has named as the main channel where the intellectual products subject to copyright are distributed. The use of digital technology by many people or institutions in many places and in many ways has especially affected the products that are subject to copyright. On the other hand The European Union (EU), within the scope of the Digital Single Market creation strategy, has added the Digital Signal Market Directive EC 2019/790 to its regulations. Extended Collective Licensing (ECL) is regulated in 8th and 12th articles of the mentioned directive. ECL is a system that enables the copyright permisson obtained use of works such as music, audio-visual, cinema, etc., which are massively used in digital media. As some uses especially like television broadcasts include a large amount of copyright items or works, in the digitalized world, it becomes costly as well as tough and even imposibble obtaining authorisations from right-holders by negotiating with all of them. If the rightholders of the intellectual products don't give authorisation of the exercise of their rights to a collecting society in another words, ıf they are not member of this organisation, obtaining permission for such uses would be very hard and transaction costs would be very high for the users and creates a greater issue as for the protection of benefits of the right-holders. Besides that the largest copyright challenge for Cultural Heritage Instutitions is the process of identification of right holders of copyright and clearence of rights, i.e obtaining authorization of licences for use of in-copyright works. When it's considered for cross-border online uses, it is more complex. In the digital age with the regulation of ECL, a system has been predicted to ensure that the licence agreements made between collecting societies and users are valid for authors and related-right holders who are not members of any collective rights management organisations.
Tez N°892117
Keywords: Copyright; Extended Collective Licensing; Extended Effect; Genişletilmiş Etki; Genişletilmiş Toplu Lisanslama; Intellectual property; Telif Hakkı

Les mesures provisoires devant la Commission et la Cour africaines des droits de l'homme et des peuples - Fall, Marie (Université de Genève, 2024)
La protection provisoire devant la Commission et la Cour africaines des droits de l’homme et des peuples est l’un des domaines du système africain de protection des droits et des peuples jusque-là loin d’être défriché de manière exhaustive. Pourtant, la mise en œuvre du dispositif des mesures provisoires dans le contexte africain remonte à l’établissement de la Commission africaine. Cette thèse propose de scruter le régime juridique exact des mesures provisoires et les contours de la pratique. La thèse ici défendue est que malgré les difficultés que peut poser le régime des mesures provisoires, la Commission et la Cour africaines en font un mécanisme au service de la protection effective des droits fondamentaux des requérants. Toutefois, la concrétisation de cette finalité est compromise par le taux élevé d’inexécution de ces mesures en raison des insuffisances dont souffre la procédure devant ces organes auxquelles s’ajoute la mauvaise volonté des États parties. Cette thèse formule ainsi des solutions qui permettent à la Cour et à la Commission d’exploiter le potentiel du régime des mesures provisoires comme instrument au service de la garantie effective des droits fondamentaux des individus protégés par la CADHP.
Keywords: CADHP; Intégration régionale

The Influence of Corporate Sustainability Laws on Multi-Stakeholder Initiatives to Eliminate Forced and Child Labour in Supply Chains - Fanou, Temisan (McMaster University, 2024)
An array of governance initiatives has emerged to address forced labour and labour exploitation in global value chains (GVCs). Drawing on the transnational business governance interactions theoretical framework, as well as Timothy Bartley’s place-conscious transnational governance model, this thesis examines the interaction between two of these hybrid forms of governance: multi-stakeholder initiatives and corporate sustainability laws. I conduct a case study of the cocoa sector, and specifically of the multinational company, Nestlé, using multiple qualitative research methods including legal analysis, key informant interviews, and documentary analysis. My research suggests that the layering of corporate sustainability laws, and particularly the French Duty of Vigilance Law, on top of CSR and MSIs in the cocoa sector, is not addressing the governance gap that permits corporations to evade accountability for human rights abuses in their supply chain. I find that the introduction of corporate sustainability laws may have contributed to a decrease in Nestlé's efforts to address labor violations in certain areas, while in others, it appears to have supported the continuation of existing practices. This raises implications for the continuous efforts in various jurisdictions to introduce these laws as a solution to the shortcomings of private, voluntary rule-making systems. Further research is required to explore how these governance mechanisms are interacting in other sectors, in companies of different sizes, and within various types of MSIs. This will help identify the factors that influence interactions and shed further light on the path forward for policymakers.

L’impact du droit OHADA sur le droit national congolais des affaires - Fanzal, Jacques-Octave Kabemba (KAS African law study library, 2024)
Après le sombre tableau du climat des affaires peint par le Rapport Doing Business, la RDC ressentit la nécessité de se débarrasser des règles sur les affaires jugées vétustes et responsables de l’insécurité juridique et judiciaire. Entre adopter une nouvelle législation avec le coût qu’elle devait entraîner et intégrer une organisation qui disposait déjà des règles adaptées aux affaires à l’instar de l’OHADA, la dernière possibilité fut privilégiée dans la perspective non seulement de faire bénéficier le cadre juridique congolais des affaires des règles simples, sûres et adaptées que l’OHADA met en place, mais aussi de tirer profit de la primauté de la sécurité juridique et judiciaire vantée pour attirer les investisseurs étrangers. Plus d’une décennie après son entrée en vigueur, la question de l’effet produit par ces normes juridiques, surtout son utilisation comme appât pour attirer les investisseurs étrangers, se pose encore avec acuité en RDC.

Rechtsformneuschöpfungen im in- und ausländischen Gesellschaftsrecht - Fleischer, Holger (Mohr Siebeck, 2024)
Gesellschaftsformen bilden die Essenz des Gesellschaftsrechts. Der vorliegende Band untersucht, welche Bereicherungen das Rechtsformentableau in jüngerer Zeit erfahren hat. Als Untersuchungsgegenstand dienen ihm rund 20 ausgewählte Rechtsformneuschöpfungen aus dem In- und Ausland, deren Entstehen und Entwicklung im Einzelnen aufbereitet werden. Wichtige Leitfragen lauten: Wann und warum haben Reformgesetzgeber neue Gesellschaftsformen eingeführt? Von wem stammte die Anregung zu ihrer Einführung? In welcher Hinsicht unterscheiden sie sich von den traditionellen gesellschaftsrechtlichen Gussformen? Wie haben sie sich seither im nationalen und internationalen Rechtsformenwettbewerb behauptet? Durch diese akribischen Einzelstudien entsteht ein facettenreiches Bild des Ideenreichtums in- und ausländischer Reformgesetzgeber mitsamt ihren Wegbereitern aus Unternehmenspraxis, Anwaltschaft, Notariat, Rechtspolitik und Rechtswissenschaft.
Keywords: Commercial law; Comparative law; Conflict of laws

التحكيم وفقًا لاتفاقية الأمم المتحدة بشأن نقل البضائع عن طريق البحر (هامبورغ، 1978) - Ghassan, ali; Haidara, jaber (Tishreen University journal of research and scientific studies -economic and legal sciences, 2024)
International maritime transport represents the backbone of international trade in our current era, for many reasons, such as low costs and the ability to transport large quantities of goods at once. The United Nations Convention on the Maritime Transport of Goods of 1978, known as the Hamburg Convention, represents a qualitative shift in regulating the rules of maritime transport of goods. Among the important topics regulated by the agreement is the subject of arbitration, as it is the most important means of settling disputes related to international trade contracts, especially the contract for the maritime carriage of goods. Accordingly, this research studies the rules of the Hamburg Convention related to arbitration as a means of settling disputes related to the contract for the maritime carriage of goods. يمثل النقل البحري الدولي عصب التجارة الدولية في عصرنا الحالي، ألسباب عديدة كانخفاض التكاليف والقدرة عمى والمعروفة 1978 نقل كميات كبيرة من البضائع دفعة واحدة، وتمثل اتفاقية األمم المتحدة لمنقل البحري لمبضائع لعام ىامبورغ، نقمة نوعية عمى صعيد تنظيم قواعد النقل البحري لمبضائع، ومن بين الموضوعات اليامة التي باسم اتفاقية نظمتيا االتفاقية، موضوع التحكيم، باعتباره أىم وسائل تسوية النزاعات المرتبطة بعقود التجارة الدولية، وخاصة عقد د اتفاقية ىامبورغ المتعمقة بالتحكيم كوسيمة لتسوية النزاعات النقل البحري لمبضائع، وبناء عميو يتناول ىذا البحث قواع ال
Keywords: Arbitration; Bill of lading; Bills of lading; Carriage of Goods by Sea (1978); Hamburg Convention; Hamburg Rules; International commercial arbitration; Maritime carriage contract; Maritime transport; UN Convention; اتفاقية ىامبورغ; التحكيم; سند الشحن; عقد النقل البحري

La relación cooperativa entre las grandes empresas y la Administración Tributaria - Guerrero Pappalardo, Alba Mª (Universidad de Sevilla, 2024)

Girişim şirketlerinin finansmanının hukuki çerçevesi - Günay, Yavuz Selim (Ankara Hacı Bayram Veli Üniversitesi, 2024)
Girişimcilik hem ülkemiz hem de dünya ekonomisi için, ekonomik gelişme sağlaması, istihdamı artırması gibi bir çok sebeple, son derece önemlidir. Girişimcilik ekosisteminde uygulanan finansman yöntemleri, sözleşmeler, hukuk kuralları gibi unsurlar dinamik ve esnek yapısı dolayısıyla geleneksel yöntem ve kurallardan ayrışmaktadır. Girişimcilerin banka kredisi gibi geleneksel finansman yöntemlerine erişememesi dolayısıyla kitle fonlaması, gölge pay, aile ve arkadaşlar, girişim sermayesi ve melek yatırımcı gibi yenilikçi finansman yöntemleri ortaya çıkmıştır. Bu finansman yöntemlerinden en yaygın ve yapısal olarak kullanılanı girişim sermayesidir. Girişim sermayesi, çeşitli fonlar ve şirketlerden toplanan kaynakların, büyüme potansiyeli gösteren ve gelecek vadeden girişim şirketlerine, pay karşılığı yatırım yapılmasını ifade etmektedir. Girişim şirketleri bakımından finansman haricinde de bir çok faydası bulunan girişim sermayesi, Türk hukukunda SPK tarafından GSYO ve GSYF yapıları altında düzenlenmiştir. Girişim sermayesi uygulamasında en çok sorun teşkil eden hususlardan biri ise girişimci ile yatırımcı ilişkileridir. Girişimci ile yatırımcı arasında hem yatırım öncesinde hem de yatırım sonrasında bilgi asimetrisinin ve menfaat farklılaşmasının söz konusu olması, girişimci ile yatırımcı arasında yönetilmesi zorunlu hale gelen bir menfaat çatışması yaratmaktadır. Bu menfaat çatışmasının olumsuz etkilerinin en aza indirilememesi ve yönetilememesi sadece girişim şirketi için değil ülke ekonomisi için de olumsuz sonuçlar doğuracaktır. Girişimci ile yatırımcı arasındaki bu menfaat çatışmasının pay devir sözleşmesi, pay sahipleri sözleşmesi, paya dönüştürülebilir borçlanma araçları gibi çeşitli sözleşmesel düzenlemelerle yönetilmesi mümkündür. Ayrıca, girişimci ile yatırımcının kendi aralarında gerçekleştirecekleri sözleşmesel kurumsal yönetim düzenlemeleri de girişimci ile yatırımcı arasındaki menfaat çatışmasının yönetilmesinde etkili olacaktır. Entrepreneurship is important for both our country and the world economy for many reasons such as providing economic development and increasing employment. Elements such as financing methods, contracts and legal rules applied in the entrepreneurship ecosystem differ from traditional methods and rules due to their dynamic and flexible structure. Since entrepreneurs cannot access traditional financing methods such as bank loans, innovative financing methods such as crowdfunding, phantom share, venture capital and angel investors have emerged. The most widely and structurally used of these financing methods is venture capital. Venture capital refers to the investment of resources collected from various funds and companies in return for shares in promising venture companies with growth potential. Venture capital, which has many benefits other than financing for venture companies, is regulated by the CMB under the structures of GSYO and GSYF in Turkish law. One of the most problematic issues in venture capital implementation is the relationship between the entrepreneur and the investor. The fact that there is information asymmetry and interest differentiation between the entrepreneur and the investor both before and after the investment creates a conflict of interest between the entrepreneur and the investor that must be managed. Failure to minimize and manage the negative effects of this conflict of interest will have negative consequences not only for the venture firm but also for the national economy. It is possible to manage this conflict of interest between the entrepreneur and the investor through various contractual arrangements such as share transfer agreements, shareholders' agreements, convertible debt instruments. In addition, contractual corporate governance arrangements between the entrepreneur and the investor will also be effective in managing the conflict of interest between the entrepreneur and the investor.

Bireysel iş uyuşmazlıkları bakımından dava şartı arabuluculukta taraflar - Güngör, Tuba (Kırıkkale Üniversitesi, 2024)
Türk hukukunda, özellikle iş uyuşmazlıkları bakımından arabuluculuğun dava şartı olarak kabul edildiği tarihten bu yana, arabuluculuk kurumundan beklenen faydanın elde edilip edilmediği bir yana bırakılırsa öğreti ve uygulamada halen tartışıla gelen birçok konu bulunmaktadır. Bunlardan biri, çalışma konumuzu oluşturan bireysel iş uyuşmazlıkları bakımından dava şartı arabuluculukta işçi ve işveren tarafların doğru ve tam olarak teşkilinin sağlanmasıdır. Alternatif çözüm yollarından biri olan arabuluculuğun dava şartı olarak düzenlenmesi, arabuluculuk faaliyetini yargılamanın ön şartı ve ayrılmaz bir parçası haline getirmiştir. Bu bakımdan arabuluculuk sürecinin doğru işçi veya işveren tarafla yürütülmemesi yargılamayı doğrudan etkileyecektir. İş uyuşmazlıkları bakımından işçi sıfatının belirlenmesi özellikle işçi olup olmadığı konusunda tereddüt yaşanan çalışanlar açısından önemlidir. İşveren tarafının doğru belirlenmesi ise, arabuluculuk faaliyetinin yanlış veya eksik işverenle yürütülmesinin ardından, yargılama sürecinde bu durumun tespit edilmesi halinde işveren tarafında değişiklik yapılamaması bakımından önem arz etmektedir. Arabuluculuk dava şartı olarak düzenlendiğinden, yargılama sırasında tamamlanabilmesi olanaklı değildir. Sürecin bu şekilde işlemesi ise mahkemeye erişim hakkının önünde engel teşkil edebileceği gibi, gerek iş güvencesi gerekse işçinin alacağına kavuşma noktasında hak kaybına ve mağduriyetine yol açabilecektir. In Turkish law, especially since the adoption of mediation as a condition for litigation in terms of labour disputes, there are still many issues that are still debated in the doctrine and practice, let alone whether the expected benefit of the mediation institution has been achieved. One of these issues is to ensure that the employee and employer parties are accurately and fully constituted in the mediation as a condition for litigation in terms of individual labour disputes, which is the subject of our study. The regulation of mediation as a condition of litigation, which is one of the alternative remedies, has made the mediation activity a prerequisite and an integral part of the proceedings. In this respect, failure to conduct the mediation process with the right employee or employer party will directly affect the proceedings. In terms of labour disputes, the determination of the employee party is especially important for employees who are in doubt as to whether they are employees or not. The correct determination of the employer party is important in terms of not being able to make changes on the employer side if this situation is detected during the proceedings after the mediation is carried out with the wrong or incomplete employer. Since mediation is regulated as a condition of litigation, it is not possible to complete it during the proceedings. This process may constitute an obstacle to the right of access to the court, and may lead to loss of rights and victimisation in terms of both job security and the employee's receivables.
920954
Keywords: Dava şartı arabuluculuk; Employee; Employer; Iş uyuşmazlığı; Işveren; Labour dispute; Mediation; İşçi

La qualification juridique de la cybercriminalité maritime en droit pénal comorien - Hamidou, Said Ali (Revue Africaine des Réflexions Juridiques et Politiques, 2024)
La numérisation du navire, celle des activités maritimes et très récemment la mise en vigueur des Directives FAL.5/Circ.42/Rev.3 de l’Organisation Maritime Internationale obligeant les Etats membres d’utiliser, à partir du 1er janvier 2024, une plateforme numérique et centralisée ou « guichet unique maritime » pour collecter et échanger des informations avec les navires est indispensable au développement du secteur maritime. Les acteurs des transports maritimes soulèvent aujourd’hui la question des outils techniques et juridiques capables de prévenir et réprimer les cyberattaques visant la nouvelle tendance de la transformation numérique du secteur maritime. Si des mesures répressives ont été prises contre la cybercriminalité en générale, la cybercriminalité maritime qui tend à compromettre la sécurité de la navigation se trouve dans une ambigüité entre le régime du Code de la marine marchande et le régime régissant la cybersécurité et la lutte contre la cybercriminalité en Union des Comores.
Keywords: Cybercriminalité maritime; Infractions maritimes; Infractions spécifiques aux TIC

L’illusoire protection du travailleur en droit camerounais - Hamoa, Hamidou (Revue Africaine des Réflexions Juridiques et Politiques, 2024)
Le droit du travail, destiné à protéger les travailleurs contre les abus de l’employeur, ne joue pas effectivement son rôle au Cameroun. Le droit camerounais du travail manque de terminaisons juridiques. Que de dispositions consacrées à l’effet de bénéficier aux travailleurs, mais sans véritables issues judiciaires. Dans ces conditions, l’employeur, fort de ses prérogatives de chef d’entreprise se retrouve en posture de monarque qui ne respecte les droits du travailleur que lorsque cela lui est loisible. Cet état de chose a pour effet de favoriser des injustices dans les rapports de travail où l’employé n’est pas effectivement protégé contre les abus de l’employeur. La justice sociale dans ce cas passera nécessairement par une vigoureuse implication de l’Etat dans les relations du travail. A ce titre, l’inspection du travail en tant que service public de l’Etat la plus indiquée est appelée à jouer un rôle central sur le terrain social. Ainsi pensons-nous qu’une subdivision en son sein doit être instituée pour garantir les droits des employés, en premier chef le payement des salaires, droit principal des travailleurs. En plus, nous en appelons à une réforme de la procédure contentieuse, laquelle doit conférer pleins pouvoirs à l’inspecteur du travail pour qu’il puisse faire appliquer effectivement les lois et règlements dans les rapports du travail.
Keywords: Inspecteur du travail; Justice; Législation; Protection; Réforme; Travailleur

Anonim şirketlerde yönetim kurulu iç yönergesi - İlgün Çamli, Zehra (Kırıkkale Üniversitesi, 2024)
Anonim şirket organları, özel hukuktaki sözleşme özgürlüğünün bir sonucu olarak kendi yetki alanlarına giren konuları iç yönerge ile düzenleyebilirler. Anonim şirket yönetim kurulu da yetki alanına giren konularda iç yönerge çıkarmak suretiyle düzenleme yapabilir. Türk Ticaret Kanunu'nda yönetim kurulunun yönetim yetkisini devrettiği ve sınırlı yetkili ticari vekil ve diğer tacir yardımcıları atadığı durumlarda bu işlemleri bir iç yönerge çıkararak gerçekleştirmesi zorunlu tutulmuştur. Bununla birlikte anonim şirket yönetim kurulu iç yönergesinde iç yönerge çıkarma zorunluluğu doğuran bu iki durum dışında yetki alanına giren diğer birçok konuyu düzenleyebilir. Bu kapsamda belirli durumlarda çıkarılması zorunlu olan bu iç yönergelerin zorunlu içeriğinin dışında, iç yönergede, yönetim kurulunun görevleri, çalışma usulü, yönetim kurulu üyelerinin ve yönetim yetkisinin devredildiği kişilerin hak ve yükümlülükleri gibi birçok husus yer alabilir. Bu düzenlemelerin sınırını da ilk başta Türk Ticaret Kanunu ve diğer kanunların emredici hükümleri oluşturur. Yönetim kurulunun Türk Ticaret Kanunu'nda çizilen yetki sınırları da bu çerçevede yönetim kurulu iç yönergesinin azami içeriğini belirler. Çalışmamızın ilk bölümünde anonim şirketlerde iç yönerge terimi açıklanmaya çalışılmış, ardından yönetim kurulu iç yönergesi terimi yetki devrinden ve sınırlı yetkili ticari vekil ve diğer tacir yardımcısı atanmasından bağımsız şekilde yönetim kurulunun çıkardığı düzenleyici bir metin olarak ele alınmıştır. Çalışmamızın ikinci bölümünde anonim şirket yönetim kurulu iç yönergesinin içerebileceği düzenlemeler ve bunların iç yönergede ne şekilde düzenlenebileceği incelenmiştir. Çalışmamızın son bölümünde ise yönetim kurulunun kendi çıkardığı iç yönergeyi ihlal etmesinin sonuçları gibi iç yönergeye ilişkin diğer meseleler ele alınmıştır. The organs of a joint stock company, as a result of the freedom of contract in private law, can regulate matters within their jurisdiction through internal directives. The board of directors of a joint stock company can also regulate matters within its jurisdiction by issuing internal directives. According to the Turkish Commercial Code, it is mandatory for the board of directors to execute transactions, such as delegating management authority and appointing limited authority commercial representatives and other merchant assistants, through the issuance of an internal directive. However, beyond these two instances where issuing an internal directive is mandatory, the board of directors can regulate many other matters within its jurisdiction through an internal directive. In this context, aside from the mandatory content in specific situations, an internal directive can include many issues such as the duties of the board of directors, working procedures, and the rights and obligations of board members and those to whom management authority has been delegated. The boundaries of these regulations are primarily determined by the mandatory provisions of the Turkish Commercial Code and other laws. The authority limits outlined in the Turkish Commercial Code also define the maximum content of the board's internal directive. In the first part of our study, the term "internal directive" in joint stock companies is explained. Subsequently, the term "internal directive of the board of directors" is examined as a regulatory document issued by the board, independent of authority delegation and the appointment of limited authority commercial representatives and other merchant assistants. In the second part of our study, the potential regulations that could be included in the internal directive of the board of directors of a joint stock company and how these can be arranged within the internal directive are analyzed. In the final part of our study, other issues related to internal directives, such as the consequences of the board of directors violating its own internal directive, are discussed.
Keywords: Authority of the Board of Directors; Board of directors; Delegation of Management; Droit des sociétés commerciales; Internal Directive; Limited Authority Commercial Representative; Sınırlı Yetkili Ticari Vekil; Working Procedures of the Board of Directors; Yönetim Kurulu; Yönetim Kurulunun Yetki Alanı; Yönetim Kurulunun Çalışma Usulü; Yönetimin Devri; İç Yönerge

ISDS 2.0: Time for a Doctrine of Precedent? - Jarrett, Martin (Journal of international economic law, 2024)

Développements juridiques d’intérêt en droit de la publicité et du marketing - Jonnaert, Caroline (Les Cahiers de propriété intellectuelle, 2024)
RÉSUMÉ Au cours de l’année 2023, plusieurs projets de loi, décisions administratives et judiciaires ont marqué le droit de la publicité et du marketing au Canada, tout comme au Québec.Cet article brosse un portrait général des principaux développements en la matière.Spécifiquement, il discute de certains développements législatifs, administratifs et judiciaires en matière de : (1) publicité fausse ou trompeuse ; (2) concours publicitaires ; (3) cookies et publicité ciblée ; (4) exigences linguistiques ; et (5) publicité sur les aliments et les boissons. MOTS-CLÉS Droit de la publicité et du marketing – Publicité fausse ou trompeuse – Concours publicitaires – Cookies – Publicité ciblée – Charte de la langue française – Publicité sur les aliments et les boissons ABSTRACT In 2023, several bills, administrative and judicial decisions have impacted advertising and marketing law in Canada and Quebec.This article provides a general overview of the main developments in this area.Specifically, it discusses legislative, administrative, and judicial developments related to: (1) false or misleading advertising; (2) promotional contests; (3) cookies and targeted advertising; (4) language requirements; and (5) food and beverage advertising. KEY WORDS Advertising and marketing law – False or misleading advertising – Promotional contests – Cookies – Targeted advertising – Charter of the French language – Food and beverage advertising

Vers une responsabilisation accrue ? A. B. contre Google et l’avenir de la régulation des services en ligne - Kablan, Serge; Oulaï, Arthur (Les Cahiers de propriété intellectuelle, 2024)
RÉSUMÉ Dans cet article, nous analysons la décision de 2023 rendue par la Cour supérieure du Québec dans l’affaire A. B. c.Google, l’une des rares décisions québécoises qui explorent la responsabilité des plateformes en ligne sous l’angle de la Loi concernant le cadre juridique des technologies de l’information (LCCJTI).Cet examen vise à déterminer si le jugement représente une évolution significative dans l’interprétation de la faute civile imputable à ces entités numériques, en vertu de l’article 22 LCCJTI.Bien que le jugement apporte certaines clarifications en enrichissant la jurisprudence existante, il introduit également des ambiguïtés qui rendent le régime de responsabilité des plateformes à la fois flexible et d’une sévérité relativement modérée. MOTS-CLÉS Éditeur – Faute extracontractuelle – Injonction – Moteur de recherche – Moralité publique – Responsabilité civile – Services informatiques interactifs ABSTRACT In this article, we analyze the 2023 Quebec Superior Court decision in A. B. v.Google, one of the few decisions to explore the liability of online platforms under the Act to establish a Legal framework for information technology (IT Framework Act).The purpose of this review is to determine whether the judgment represents a significant evolution in the interpretation of civil fault attributable to these digital entities, under section 22 of the IT Framework Act.While the judgment brings certain clarifications by enriching existing jurisprudence, it also introduces ambiguities that make the liability regime for platforms both flexible and relatively moderate in severity. KEYWORDS Editor – Extracontractual fault – Injunction – Search engine – Public morals – Civil liability – Interactive computer service
Keywords: Civil liability; Editor; Extracontractual fault; Faute extracontractuelle; Injonction; Injunction; Interactive computer service; Moralité publique; Moteur de recherche; Public morals; Responsabilité civile; Search engine; Services informatiques interactifs; Éditeur

Pazarlamacılık sözleşmesi - Kaya, Servecan (Üniversitesi Ankara, 2024)
Ticari hayatta duyulan ihtiyaç sonucu ortaya çıkmış sözleşmelerden birisi olan pazarlamacılık sözleşmesi, sıklıkla uygulanan sözleşmelerden olması ve hizmet sözleşmesinin özel bir türü olmasına karşın farklılaştığı hususların önemi sebebiyle kanun koyucu tarafından Türk Borçlar Kanunu içerisinde hizmet sözleşmesinden ayrı olarak düzenlenmiştir. Kanuni bir tanımının da bulunmasının etkisiyle tarafları ve unsurları rahatlıkla belirlenebilir mahiyettedir. Pazarlamacılık sözleşmesi unsurları; bağımlılık, süreklilik, iş yeri dışı faaliyet alanı ve ücret olan, rızai ve tam iki tarafa borç yükleyen bir isimli sözleşmedir. Pazarlamacılık sözleşmesinin taraflarından sözleşmeye de ismini vermiş olan pazarlamacı aynı zamanda bağımlı bir tacir yardımcısıdır. Bu bağlamda pazarlamacılık sözleşmesinin benzer olduğu birçok sözleşme bulunduğu gibi pazarlamacının da benzer olduğu birçok tacir yardımcısı bulunmaktadır, ancak her ikisinin de özüne inildiğinde benzer noktalardan ziyade diğerlerinden farklı karakteristik özellikleri bulunduğu rahatlıkla anlaşılacaktır. Tarafların hakları ve yükümlülükleri genel itibariyle pazarlamacılık sözleşmesinde birbirlerine karşılık gelmektedir, sözleşme böylece taraflar arasında kurulur, sürer ve sona erer. Pazarlamacılık sözleşmesinin sona ermesinde hizmet sözleşmesine ilişkin sona erme hallerinin söz konusu olduğu gibi kendine has sona erme halleri de söz konusudur. Her sözleşmede olduğu gibi sona erme halinde bunun da meydana getireceği sonuçlar taraflar özelinde kendisini gösterir. Ticaret hukuku ve borçlar hukuku özellikleri gösteren bir sözleşme olan pazarlamacılık sözleşmesi, özellikle belirli sektörlerde sıklıkla uygulanması, uyuşmazlıklara konu olması haricinde pazarlamacının sözleşmenin diğer tarafı olan işverene bağlı olarak faaliyet göstermesi sebebiyle de iş hukuku özelliği de gösteren bir sözleşmedir. Traveling salesman, which is one of the contracts that emerged as a result of a need in commercial life, has been arranged separately from the contract of service in the Turkish Code of Obligations, due to the importance of the matters that differentiate it, although it is one of the most frequently applied contracts and it is a special type of contract of service. With the effect of having a legal definition, its parties and facts can be easily identified. Traveling salesman is a consensual and bilateral contract with its elements which are dependency, continuity, non-operational field of business and fee. Traveling salesman as one of the parties of traveling salesman contract, who has given its name to the contract, is also a dependent tradesman assistant. In this context, as there are several contracts that traveling salesman is similar to, there are several tradesman assistants that traveling salesman is similar to, but when the essence of both is examined, it will be easily understood that they have various characteristics from the others. The rights and obligations of the parties generally correspond to each other in traveling salesman, so the contract is concluded, continued and terminated between the parties. In the termination of traveling salesman, there are specific termination cases as well as the termination cases related to contract of service. As with every contract, the consequences of termination in the event of termination will manifest themselves in particular to the parties. Traveling salesman is a contract that has the characteristics of commercial law and law of obligations, and also is a contract that has labor law characteristics, especially since it is frequently applied in certain sectors, is the subject of disputes, and because the traveling salesman operates under the employer, the other party of the contract.
Tez N°871625
Keywords: Code of Obligations; Commercial traveller; Contract; Traveling salesman

Hava Kargo Taşımacılığının Ülke Refahına Etkisi: OECD Ülke Analizi - Kelek, Bura Sabiha (İstanbul Ticaret Üniversitesi, 2024)
Bu çalışmanın amacı, ülkelerin rekabet güçleri açısından oldukça önemli olan lojistik performansları ile insani gelişmişlik düzeylerinin hava kargo ve küresel rekabet faktörlerinin nasıl ilişkili olduğunu ortaya koymaktır. Bunu ifade etmek için, 29 OECD (Ekonomik İş birliği ve Gelişme Teşkilatı) ülkesinin lojistik performanslarını hava taşımacılığının kargo göstergeleri ile ilişkilendirip ve sonuçları bahsi geçen ülkelerin insani gelişmişlik düzeyine etkisi açısından yorumlamaktır. Verilerin tüm ülkeler için eşit olmasına dikkat edilmiştir. Kullanılan puanlamaların zaman serisi 2010, 2012, 2014, 2016, 2018 yıllarını kapsamaktadır. Sonuçların analizi, kullanılan verilerin SPSS ile ortaya çıkarılarak oluşan yapısal eşitlik modellemesinin (YEM) üzerinden, çalışan ve çalışmayan regresyonların belirlenip ortaya hava taşımacılığı açısından etki eden verilerin bulgusuna erişmek ve yapılan analiz ile bu verilerin göstergesi ışığında hava lojistiği performansıyla ilişkili olup olmadığını göstermeye çalışılmaktadır. Çalışmada özellikle elde edilmek istenen bulgular bahsi geçen ülkelerin gayri safi milli hasıla ile kişi başına düşen milli gelirin hava taşımacılığının doğrudan veya dolaylı yoldan hem küresel rekabete olan etkisi hem de GSYİH’ye olan katkısıdır. Çalışma da lojistik kavramı ile birlikte ülkelerin ticaretleri ele alınarak dünya üzerindeki ticari üstünlüklerine değinilmiştir. Literatür araştırması, insani açıdan yetkin ülkelerin lojistik endüstrisine bakış açıları değerlendirilmiş ve lojistik alanındaki yükselişleri ile bağlantılı kalkınmasına işaret edilmiştir. Kullanılan veriler güvenilirlik açısından Dünya Bankası’ndan alınmış ve kullanılan endeksler çalışmanın kapsamında bulunan bütün parametreler ile analiz edilmiştir. Bunun sonucunda kurulan model de hava kargo taşımacılığının dolaylı olarak küresel rekabete etkisi ile Gayri Safi Yurtiçi Hasıla’ya ve aynı zamanda insani rekabet performanslarının lojistik performans endeksi ile anlamlı bir ilişki kurduğu ortaya çıkmıştır.
Keywords: Hava Kargo; Küresel Rekabet; Lojistik Performans; Lojistik Yönetimi; Milli Gelir

Le conjoint in bonis et la procédure collective en droit OHADA - Kingue Bebe, Lilliane Grace (Revue Africaine des Réflexions Juridiques et Politiques, 2024)
L’ouverture d’une procédure collective, notamment celle après la cessation des paiements entraine la saisie collective des biens du débiteur au profit de ses créanciers. Le conjoint in bonis peut voir ses biens engloutis dans une procédure collective qui ne le concerne pas. Dans le souci de préserver le patrimoine du conjoint in bonis et par là la cellule familiale, le législateur OHADA a prévu des mécanismes de protection, qui pour une meilleure efficacité doivent être combinés aux solutions proposées par le droit civil.
Keywords: Collective procedure; Collective seizure; Conjoint in bonis; Creditors; Créancier; Debtor’s property; Débiteur; Procédure collective; Saisie collective; Spouse in bonis

COFOLA 2024: Sborník příspěvků mladých právníků, doktorandů a právních vědců. Část 2, Výzvy současné sociální politiky - Komendová, Jana; Smejkal, Michal; Tomášková, Eva; Janovec, Michal (Masarykova Univerzita, 2024)
Bezprostřední návaznost pracovněprávních vztahů při posuzování nároku na dovolenou Sociální pojištění a dohoda o provedení práce dle konsolidačního balíčku Implementuje česká právní úprava dostatečně požadavky práva evropské unie na institut zkušební doby? Výzvy sociálnej politiky v kontexte dane z nehnuteľností Lege artis v ohrožení? Výpověď bez udání důvodu aneb jak zvýšit flexibilitu českého pracovního trhu Slovenská právna úprava ochrany oznamovateľov protispoločenskej činnosti z pohľadu rovnakého zaobchádzania v zamestnaní Rovné odměňování zaměstnanců ve skupině společností pohledem českého a evropského práva Výpověď bez udání důvodu jako hybatel pracovního trhu? Prioritizácia manželstva v práve sociálneho zabezpečenia Jak oběti domácího násilí propadávají systémem sociálního zabezpečení Sociální fondy: Co přinášejí zaměstnancům vysokých škol? Revize sociálních dávek Nesezdané soužití – přehlížená sociální realita?
Keywords: Agreement on Work Activity; Agreement on Work Performance; Directive; E-knihy; Elektronické knihy; Immediate Continuity; Knihy; Leave; Čítárna

La propriété privée à l’épreuve de la crise du logement au Cameroun - Koungoue Ndop, Suzanne (Revue Africaine des Réflexions Juridiques et Politiques, 2024)
Au Cameroun, le problème de la propriété privée du logement mérite une attention particulière. En effet le logement est considéré comme une propriété privée que chaque citoyen voudrait bien en avoir pour sa stabilité, sa protection contre les intempéries et aléas de la vie. Cependant, plusieurs difficultés empêchent cet épanouissement, à savoirs la demande massive du logement d’une part, et la hausse des prix de locations d’autre part, qui selon les bailleurs se justifieraient par les coûts élevés des matériaux de construction. Par ailleurs, pour pallier cette crise de logement, il est impérieux que les pouvoirs publics s’impliquent dans les relations bailleurs-locataires. Pour cela, des dispositions ont été prises en vue de réguler les rapports locatifs. Pour la même raison, l’Etat devra également prendre un certain nombre de mesures pour soutenir les projets de construction engagés tant par les agences immobilières que par les particuliers.
Keywords: Bailleur; Cameroun; Crise; Locataire; Logement; Propriété

COFOLA 2024: Sborník příspěvků mladých právníků, doktorandů a právních vědců. Část 5, Dopravní a přepravní právo v mezinárodním a evropském rozměru - Křepelka, Filip; Richterová, Anna (Masarykova Univerzita, 2024)
Problematika kontrolního vážení v České republice Trestání přestupků v dopravě v evropském rozměru Zajištění dostatečné dopravní obslužnosti Elektromobily jako údajné bezpečnostní riziko v parkovacích domech. Má právo nějak reagovat? AI v oblasti silniční dopravy
Keywords: E-knihy; Elektronické knihy; Knihy; Čítárna

The International Tax Regime Complex: Understanding Change in Global Tax Governance - Kuhn, Katharina; Cadzow, Lucinda; Heitmüller, Frederik; Hearson, Martin; Randriamanalina, Tovony (Institute of Development Studies, 2024)
Keywords: Global tax governance; International tax; Legitimacy; Low-income countries; Regime complex; UN Framework Convention on International Tax Cooperation

La mediación y la cultura del acuerdo - Lagones, Delcy de Anglim (Deconstruyendo la justicia, 2024)
Keywords: China; Dispute Settlement; MARD; Mediación; Mediation; Mediação; Médiation; UN Convention on International Settlement Agreements resulting from Mediation (2018); UNCITRAL Model Law on International Commercial Conciliation (2002)

Antitrust policy and EU labour markets : lessons from the US and comparative prospects - Langlois D'estaintot, Isaure (European University Institute, 2024)
Recent empirical evidence suggests that labour markets are not as competitive as previously thought. In that context, mobilizing antitrust policy has been discussed as a possible solution. The proposition sounds counterintuitive, however. If workers are paid below the competitive level, doesn’t this promote consumers’ outcomes by reducing downstream prices? Given that antitrust policy promotes consumer welfare, why would antitrust authorities intervene against such a state of affairs? Besides, why would stepping up on antitrust enforcement improve workers’ outcomes? Their interests have traditionally been protected through their exclusion from the scope of antitrust enforcement, not by the enforcement of antitrust rules to their benefit. This thesis demonstrates that those spontaneous assumptions do not hold. Consumer welfare does not speak against the defence of workers’ interests. First, the focus on consumers is a by product of methods: it does not prevent consideration of other types of market participants. Moreover, consumers benefit from competitive labour markets. The welfare effects of monopsony power simultaneously worsen workers and consumers’ outcomes. As for the promotion of workers’ interests, it can be achieved through both positive and negative enforcement of antitrust. So far, the EU Commission has been less proactive than the American DOJ and FTC on the issue of antitrust enforcement in labour markets ( although the state of affairs is evolving). While this difference may stem from EU workers benefitting from higher levels of social protection than US workers, those higher levels of protection may not negate the usefulness of antitrust ’s intervention. The low levels of antitrust enforcement in EU labour markets may result from legal uncertainty and case law inconsistency more than an absence of harm. Just like the merger control apparatus, Article 101 and 102 TFEU can be used to scrutinize labour markets. While doing so involves some practical complexities, they can be overcome.
Accepted: 2024-04-08T07:03:10Z
Keywords: Antitrust law; European Union countries; Labor laws and legislation; Unfair competition

État de la situation sur les impacts sociétaux de l'intelligence artificielle et du numérique - 2024 - Obvia; Langlois, Lyse (Observatoire international sur les impacts sociétaux de l'IA et du numérique, 2024)
L'État de la situation sur les impacts sociétaux de l'intelligence artificielle et du numérique fait état des connaissances actuelles sur les impacts sociétaux de l'IA et du numérique, structurées autour des sept axes de recherche de l'Obvia : santé, éducation, travail et emploi, éthique et gouvernance, droit, arts et médias, et transition socio-écologique. Hypertrucages, désinformation, empreinte environnementale, droit d'auteur, évolution des conditions de travail… Le document recense les grandes questions de recherche soulevées par le déploiement progressif de ces nouvelles technologies, auxquelles viennent s'ajouter des cas d'usages et de pistes d'action. Il s'impose ainsi comme un outil complet et indispensable pour accompagner la prise de décision dans tous les secteurs bouleversés par ces changements.

The Rotterdam Rules Convention: United Nations Convention on Contracts for the International Carriage of Goods Wholly or Partly by Sea 2008 - Laurijssen, Peter (CMI, 2024)
Keywords: MARITIME LAW; UN Convention on Contracts for the International Carriage of Goods Wholly or Partly by Sea (2008)

Property in goods and the CISG - Maier-Lohmann, Till (Fachmedien Recht und Wirtschaft, dfv Mediengruppe, 2024)
Keywords: CONTRACTS; INTERNATIONAL SALE OF GOODS; UN Convention on Contracts for the International Sale of Goods (1980)

Les intérêts économiques du cyberconsommateur à l’épreuve de l’offre électronique - Majilo Pombou, Linda Judith (Revue Africaine des Réflexions Juridiques et Politiques, 2024)
Le commerce électronique peut s’effectuer par le biais d’un acte juridique appelé contrat. Le contrat peut être entendu comme un acte qui constate une convention entre deux ou plusieurs personnes. À l’origine de tout contrat électronique, il existe une offre électronique. Cette offre électronique renferme un certain nombre de spécificités. La problématique de cette étude vise à savoir si les mécanismes juridiques encadrant l’offre électronique sont propices à la sécurisation du consommateur qui contracte par voie électronique Cette étude sur la protection du consommateur à l’épreuve de l’offre électronique a eu pour objectif de montrer l’effort législatif effectué en vue de protéger le consommateur qui recourt au contrat électronique. La méthodologie a porté sur la collecte et l’analyse documentaire, pour saisir les dimensions de cette protection. Les résultats indiquent, que, les textes adoptés tendent à sécuriser les transactions en ligne et surtout à assurer au consommateur un niveau de protection considérable.
Keywords: Consommateur; Consumer; Electronic offer; Intérêt; Offre électronique; Protection

La réforme des dommages dans le règlement des différends entre investisseurs et États et la question de la réparation intégrale - Marzal, Toni (Investment Treaty News, 2024)
Keywords: Dispute resolutions; Dispute settlement; Investissements; Investments; Règlement des différends

Derecho penal económico y de la empresa - Mata Barranco, Norberto J. de la; Dopico Gómez-Aller, Jacobo; Lascuraín Sánchez, Juan Antonio; Nieto Martín, Adán (Dykinson, 2024)

Climate Change Litigation in Civil Law African Countries: An Assessment of Barriers and Potentialities in Cameroon - Mbarga, Daniel Armel Owona (Climate Litigation and Justice in Africa, 2024)
It seems like a long time ago that there were only a handful of climate lawsuits. Since the first climate lawsuits were filed in the United States in 1990,² a myriad of litigation has emerged at the national, regional and global levels. According to the Grantham Research Institute on Climate Change and the Environment, as of May 2021 the databases on climate litigation around the world contained 1,841 cases that were either in progress or had already been decided.³ This shows the exponential development of the phenomenon through which civil society organizations, public law legal entities and private individuals are
Keywords: Africa; Cameroun; Civil Law; Climate change; Litigation

La protection juridique des mesures techniques de protection des créations de l’esprit dans l’espace OAPI - Mbarga, Pascal (Revue francophone de la propriété intellectuelle, 2024)
Face à la contrefaçon cybernétique, les mesures techniques de protection des créations de l’esprit sont apparues comme la solution indispensable à la préservation des droits de propriété intellectuelle dans l’environnement numérique. Toutefois, au-delà de leur grande diversité et au fur et à mesure de leur évolution, les techniques de contournement ont suivi. Face à ces utilisateurs habiles, il est apparu essentiel de consacrer une protection juridique des mesures techniques de protection. C’est l’approche adoptée par le législateur OAPI qui aménage une protection juridique des mesures techniques de protection à deux niveaux : une protection en amont, marquée par la prohibition des actes visant à porter atteinte aux mesures techniques de protection des créations de l’esprit ; et une protection en aval, marquée par l’aménagement des sanctions à la fois civiles et pénales lorsque les actes prohibés sont posés.
Keywords: Intellectual property

Le caractère des obligations essentielles dans le bail à usage professionnel. Réflexions à l’aune du droit OHADA et du droit français - Mbida Balla, Philibert (Revue Africaine des Réflexions Juridiques et Politiques, 2024)
La présente recherche s’intéresse au caractère attaché aux obligations essentielles dans le bail à usage professionnel. Tant du point de vue de leur contenu que du point de vue de leur agencement dans les phases du contrat, les systèmes juridiques OHADA et français semblent se rejoindre. En droit OHADA, les dispositions normatives qui encadrent le bail à usage professionnel seraient d’un caractère intangible. Celles qui régissent le bail commercial en droit français constituent un ensemble connu sous l’appellation de régime des baux commerciaux et qualifié de rigide. Il semble alors que l’intangibilité et la rigidité transparaissant dans les dispositions normatives confèrent un caractère d’ordre public aux obligations essentielles dans le bail à usage professionnel. Ce trait de caractère serait garanti par certains mécanismes prévus dans les deux systèmes juridiques. Ce qui fait du bail à usage professionnel, un contrat qui offre peu d’espace à la liberté mais dont le caractère conféré aux obligations essentielles constitue un mécanisme de sécurité juridique.
Keywords: Bail à usage professionnel; Essential obligation; Inflexibility; Intangibilité; Lease for professional use; Obligation essentielle; Ordre public; Public order; Rigidity; Rigidité

La bonne administration de la justice arbitrale en droit OHADA - Megou Ebock, Jocelyne Yvonne (Revue Africaine des Réflexions Juridiques et Politiques, 2024)
La résolution d’un litige passe généralement par la justice étatique habilitée à faire appliquer les lois, à corriger et réparer les injustices subies. Rendre justice suppose que certains moyens soient réunis afin de garantir une bonne administration de la justice. Mais de plus en plus la justice étatique est concurrencée par une forme de justice ayant pour principaux acteurs les parties : il s’agit de la justice arbitrale. Cette forme de justice semble être la parfaite incarnation d’une bonne administration de la justice dans la mesure où elle renvoie à un emploi équilibré des moyens de justice en conformité avec les objectifs de célérité de la justice arbitrale. Justice rendue sur la base d’une convention d’arbitrage, la justice arbitrale s’accommode bien du respect des exigences d’un procès équitable et garantie la bonne administration de la justice. S’agissant de la bonne administration de la justice arbitrale OHADA, tout parait plus simple dans la mesure où le législateur en a fait un mode privilégié de règlement des différends contractuels et un instrument juridique adapté aux exigences d’une justice de qualité. Ainsi, la préoccupation majeure de cette étude est celle de savoir dans quelle mesure la justice arbitrale pourrait être considérée comme la « pierre philosophale » de la bonne administration de la justice arbitrale en droit OHADA. C’est à travers l’analyse d’un corpus juridique entièrement rénové le 23 novembre 2017 que la justice arbitrale est considérée comme la pierre angulaire de la bonne administration de la justice. Ceci se justifie par la double assertion selon laquelle elle respecte les principes généraux de bonne administration de la justice et qu’elle demeure une justice ancrée sur le respect des principes spécifiques à la justice arbitrale.
Keywords: Administration; Arbitrage; Arbitragem; Arbitration; Arbitre; Good administration; Justice; Proceeding; Procès équitable

IA et fouille de textes et de données : retour sur la souplesse de l’exception japonaise à l’ère de l’IA générative - Migliore, Elodie (Revue francophone de la propriété intellectuelle, 2024)
Les exceptions de fouille de textes et de données sont souvent évoquées dans les discussions juridiques autour des systèmes d’intelligence artificielle. Si les exceptions prévues par le droit européen sont souvent critiquées, elles sont également comparées aux exceptions d’autres pays. Cet article vise ainsi à préciser l’exception de fouille de textes et de données japonaise dans le contexte de l’IA générative, revenant notamment sur son apparente souplesse. This article focuses on the notion of «freedom to link» and its apprehension abroad (especially by countries of Romano-Germanic legal tradition) to draw the limits of this freedom. Second, it focuses on the identification of means for the protection of intellectual property rights affected by hypertext links when they are neither regulated nor well regulated/apprehended by the jurisprudence in Brazil.
Keywords: Intellectual property

Jus Mundi Arbitration Review - Mistelis, Loukas; Fan, Kun (Jus Mundi, 2024)
Articles The Seven Cardinal Sins of Investment Dispute Settlement Investment Arbitration in the New Era: Engine or Obstacle in the Fight Against Climate Change? The UNIDROIT Principles as a Tool for the Internationalisation of Contracts by Arbitral Tribunals AI: The Modern Tribunal Assistant – Impact on Enforceability of Arbitral Awards under the New York Convention Automation & Augmentation: Artificial Intelligence in International Arbitration The IBA Guidelines on Conflicts of Interest in International Arbitration 2024 CIETAC: Overview of Dispute Resolution in the Digital Environment in China Swiss Supreme Court rejects CJEU’s Komstroy ruling Romania’s Supreme Court Decides that Associations and Foundations Based in Romania Can Only Set Up Arbitral Institutions if Authorized by Law Book Review – On Arbitration: V. V. Veeder QC, Selected Writings and Contributions to the Development of Law (Wordsworth & Veeder (eds), OUP 2023) Book Review – Investment Arbitration and Climate Change (Ipp & Magnusson (eds), Kluwer 2024)

Digitization and sustainability: Practical convergences of two leading discussions in business law - Mittwoch, Anne-Christin (Beiträge zum Transnationalen Wirtschaftsrecht, 2024)
Until now, digitization and sustainability have stood side by side in the discussion of business law. As leading discourses of the present-day business scene, both topics are leading to profound change in companies and are influencing each other in the process - a circumstance that can no longer be ignored by corporate management. The article shows the guiding ideas behind both discussions, as well as their convergences and interactions, and asks about the effects they have on management's duty to act.
Keywords: Corporate Digital Responsibility; Corporate Sustainability; Digitization; Directors' Duties; Sustainability

Questions spéciales du droit pénal fiscal d’entreprise - Muanda Nkole wa Yahve, Don José; Dashkevich, Zh V. (Esquisse du Droit pénal fiscal congolais, 2024)
T

Le contrat de prêt à usage portant sur l’immobilier dans le contexte familial congolais - Mukwayakala Tatiku, Taty (Revue Africaine des Réflexions Juridiques et Politiques, 2024)
Le Droit commun des obligations, régi principalement par le Code Civil Congolais Livre troisième (CCCL III), permet à tout propriétaire de céder certains de ses droits (fructus et usus) sur son bien immobilier à une personne tierce et ce, sans en tirer profit. Dès lors, le propriétaire et l’usufruitier ne sont liés par aucun contrat de bail. En République démocratique du Congo, nombreux sont les congolais qui habitent gratuitement les appartements ou maisons appartenant aux membres de leurs familles respectives. Si cette pratique relève de la solidarité entre membres d’une même famille, elle n’est par ailleurs pas à l’abri de conflits. En effet, a pratique a montré que le recours au prêt à usage immobilier engendre de tensions au sein de familles congolaises. L’une des raisons demeure la culture qui consisterait à croire qu’un bien appartenant à un membre de la famille serait un bien commun (propriété de la famille). Ainsi, à la suite de ce constat, cette réflexion se veut une contribution pour un bon usage du commodat immobilier au sein des familles congolaises.
Keywords: Conflits familiaux; Prêt à usage immobilier; Solidarité familiale; Sécurité juridique

A comprehensive outline towards conciliation in the contemporary world of E-commerce - N, Vinod; Gupta, Poonam (World Journal of Advanced Research and Reviews, 2024)
Since the start of the millennial era, technical advancements have led to exponential growth in electronic commerce, or e-commerce. According to the United Nations Conference on Trade and Development (UNCTAD), e-commerce sales reached about US$25 trillion globally in 2021 [1] and are expected to grow at a compound annual growth rate of 9% through 2027, which is twice as fast as the 4% annual growth rate predicted for traditional in-person retail [2]. Online dispute resolution (ODR) techniques that aim to settle disagreements and lower the likelihood of expensive lawsuits are becoming more and more necessary as both individuals and corporations use online shopping platforms. Due of its legally binding nature, arbitration is the most formal method, as was briefly discussed [3]. Online arbitration is carried out using electronic methods, like email and digital tools designed to make the duties of arbitrators and parties to a dispute easier. It adheres to the same rules and processes as traditional arbitration. On the plus side of e-arbitration, advancements in technology allow for time and cost savings without sacrificing the ease of remote filing. The conclusion of e-arbitration agreements raises several negative issues, including privacy and data protection issues for the consumer signing the agreements and power imbalances between corporate entities and the consumer. The degree to which artificial intelligence (AI) is effectively and sufficiently analysing a dispute between parties is up for debate because it's unclear how new this adjudication process is.
Keywords: Arbitrage; Arbitragem; Arbitraje; Arbitration; Artificial Intelligence; Conciliation; E-Commerce; Inteligência artificial; Intelligence Artificielle; ODR; OECD

Squaring up with workplace bullying - Naidoo, Natashia (University of Pretoria, 2024)
Workplace bullying is not considered a form of harassment that is commonly acknowledged nor does it attract specific legislative protection. The aim of this mini-dissertation is to ascertain the degree to which victims of workplace bullying are protected by South African labour legislation and whether other measures are necessary to ensure that employees are adequately protected. A comparative analysis between South Africa and the United Kongdom's legislative frameworks that governs workplace violence and harassment and, by implication, bullying is a critical aspect of this mini-dissertation.

Architecture organisationnelle de l’assemblée générale et structure actionnariale de l’entreprise publique au Cameroun - Ngasga Menyomo, Laurentine (Revue Africaine des Réflexions Juridiques et Politiques, 2024)
Au Cameroun, les entreprises publiques ont un rôle déterminant dans la mise en œuvre des politiques publiques. Ces entreprises sont constituées sous la forme de société anonyme. Elles fonctionnent avec trois (03) organes sociaux. Il s’agit de l’assemblée générale, du conseil d’administration et de la direction générale. L’assemblée générale se positionne comme l’organe suprême légalement habilité à prendre les décisions en lieu et place des apporteurs des capitaux. Dans les entreprises privées, l’assemblée générale n’est exigée que dans les sociétés anonymes à actionnariat multiple. Le problème qui se pose pour les entreprises publiques est celui de l’ajustement de l’architecture organisationnelle de leur assemblée générale à leur structure actionnariale. Dans les entreprises publiques à actionnariat multiple, le rôle de l’assemblée générale doit être consolidé et les compétences des représentants des entités publiques renforcées. Dans ce type d’entreprise, l’assemblée générale réunit plusieurs actionnaires ou leurs représentants pour discuter et statuer en dernier ressort sur les décisions les plus importantes de l’entreprise. Par contre, pour ce qui est des entreprises publiques à actionnariat unique, l’assemblée générale peut être supprimée, car elle n’est pas un organe social essentiel.
Keywords: Architecture organisationnelle; Assemblée générale; Entreprise publique; Structure actionnariale

La crise de la justice étatique camerounaise - Ngassa Ngebdjo, Salomon C. (Revue Africaine des Réflexions Juridiques et Politiques, 2024)
La justice étatique camerounaise est en crise. Ce constat provient d’un certain nombre de facteurs qui détériorent la justice au sein de l’Etat du Cameroun. Il s’agit des facteurs qui affectent l’identité de la justice et sa crédibilité. Face à cela, le justiciable cherche à faire protéger ses droits en faisant recours à une justice négociée. Cette dernière qui lui permet de contourner les méfaits du dysfonctionnement de la justice au Cameroun, tend à devenir de plus en plus attractive. Cela est dû au fait que la justice négociée, qui est soumise à la volonté des parties, semble répondre aux critères de qualité de la justice.
Keywords: Cameroun; Corruption; Crédibilité; Erreur judiciaire; Justice; Justice négociée

Summary survey on publishing contract in the OAPI space - Ngombé, Laurier Yvon (The Journal of World Intellectual Property, 2024)
The OAPI member states constitute a space for theharmonization of copyright in Africa. This harmonizationis yet to be completed, as attested by the conventionalrules relating to the publishing contract. In addition,investigating about the publishing contract in the OAPIspace requires an examination of both the text of theBangui Agreement and that of the national laws of the 17member states. Some differences must be pointed outkeeping in mind the question of possible conflict of laws.
Published by John Wiley & Sons Ltd.
Keywords: ARIPO; Conflict of laws; Contract; Copyright

Pour une harmonisation du droit maritime en Afrique : réflexions autour d’un droit OHADA du transport maritime - Ngoue, Nicodème Arsène (Revue Africaine des Réflexions Juridiques et Politiques, 2024)
Bien que le droit maritime fasse partie intégrante du droit commercial, qui relève de la compétence matérielle de l'OHADA, on constate qu'il ne fait pas l'objet d'un droit uniforme, ni adopté, ni en préparation. Cependant, la mission de l'OHADA est de lutter contre l'incertitude juridique et judiciaire liée aux conflits juridiques en dotant ses États membres de règles communes simples et modernes adaptées à leurs réalités économiques. L’absence d’une Loi uniforme sur le droit de la mer au sein de l’OHADA ne peut donc être justifiée au motif qu’elle n’est pas nécessaire. C’est ce que vise à démontrer cet article afin d’alerter les décideurs du secteur OHADA sur la nécessité d’intégrer le droit maritime dans le processus de normalisation du droit commercial. En effet, les différences entre les législations maritimes dans l’espace OHADA, les conflits juridiques qui en résultent, ainsi que les complexités juridiques et judiciaires liées à la coexistence du droit maritime et du droit uniforme sont autant d’éléments favorables à une telle initiative.
Keywords: Compétence juridictionnelle; Conflict of laws; Conflicts of jurisdiction; Conflits de lois; Droit maritime; Espace OHADA; Intégration Judiciaire; Intégration juridique; Judicial integration; Legal integration; Maritime law; Maritime law uniformisation; OHADA area; Uniformisation du droit maritime

Le point de départ de la personnalité juridique d’une société commerciale dans le droit OHADA - Njutapvoui, Zakari (Revue Africaine des Réflexions Juridiques et Politiques, 2024)
Le point de départ de la personnalité juridique d’une société commerciale est fonction de la théorie de la personnalité considérée. Pour la théorie de la fiction, la personnalité juridique d’une société apparait spontanément à partir de l’immatriculation au RCCM. Néanmoins, elle peut toujours remonter avant l’immatriculation et se construire de façon progressive. Par contre, pour la théorie de la réalité, cette personnalité apparait spontanément à partir de la signature de l’acte créateur de la société. Néanmoins, elle peut toujours remonter avant la signature de l’acte et se construire de façon progressive. The starting point of legal personality depends on the theory of personality considered. According to the fiction theory, the legal personality of a commercial company arises spontaneously from the registration of the company in the commercial and credit register. However, it can date back before registration and be built progressively. On the other hand, according to the reality theory, legal personality arises spontaneously from the signing of the act creating the company. Nevertheless, it can still date back before the signing of the act and be built progressively.
Keywords: Commercial company; Immatriculation; Legal personality; Personnalité juridique; Point de départ; Registration; Signature des statuts; Signing of the articles of association; Société commerciale; Starting point

Combinaison des apports des cadres conceptuels américain, français et IASB au système comptable OHADA - Nkangi Mbadika, Olivier; Makwala Yanukwa, Octave; Pindi Mayila, Serge; Mantempa Nzinunu, Jocelyn (Mouvements et enjeux sociaux, 2024)
Le Système Comptable OHADA est préconisé afin de répondre aux attentes et satisfaire aux besoins des entités évoluant dans les Etats-parties et des utilisateurs de leurs états financiers annuels. L’analyse faite dans ce papier de recherche consiste à montrer que le Système Comptable OHADA apparaît comme une combinaison des apports positifs du plan comptable général français, des normes internationales (IAS/IFRS) et des normes américaines (US GAAP). Ainsi, il est souvent présenté comme un référentiel qui a connu des avancées notables par rapport aux anciens référentiels comptables africains (Plan comptable général congolais, Plan OCAM, SYSCOA, etc.) pour avoir bénéficié des apports comptables des modèles susmentionnés. Ceci traduit son caractère dynamique au regard de l’évolution de la vie des affaires tant au niveau régional qu’à l’échelle mondiale. La prise en compte des apports positifs des cadres conceptuels dominants a le mérite d’anticiper l’unification du langage comptable dans le monde dans un contexte caractérisé par la mondialisation des économies.
Keywords: Accountability; Comptabilité; Framework; IASB; Norme comptable; Système comptable

Concurrent Investor-State Claims Before Domestic Courts and Investment Treaty Arbitration Tribunals: Philip Morris, Vattenfall and Beyond - Nottage, Luke; Stendel, Robert (Virginia journal of international law, 2024)
Keywords: Arbitrage; Arbitragem; Arbitration

La capacité commerciale de la femme mariée en droit OHADA - Nsimba Baweno, Paul (Ziglôbitha, 2024)
Résumé : Le droit congolais soumet la capacité juridique de la femme mariée à certaines restrictions. Cette situation l’affecte dans l’exercice des activités professionnelles où l’autorisation maritale est requise. C’est ainsi que d’aucuns voient dans l'adhésion de la République Démocratique du Congo (RDC) à l'OHADA une planche du salut en faveur de la femme mariée, toutes les dispositions de droit interne se cramponnant sur l’incapacité juridique de cette dernière étant automatiquement abrogées parce que supposées contraires aux Actes uniformes, en l’occurrence à l’Acte uniforme relatif au droit commercial général (AUDCG). Cet article essaie d’analyser méticuleusement le prétendu apport résultant du droit de l’OHADA et arrive à démontrer que le statut de la femme mariée en matière professionnelle en RDC reste inchangé. Une première victoire pourrait résulter de l’AUDCG s’il reconnaissait à la femme mariée la capacité à exercer le commerce. Malheureusement la disposition correspondante de ce texte ne traite que du statut du conjoint d’un commerçant, laissant ainsi la question de la capacité juridique en matière commerciale aux législations nationales des Etats membres. Même si l’on admettait une certaine avancée en droit commercial, cela ne saurait être transposé à d'autres professions régies par des normes de droit interne non concernées par des Actes uniformes. D’où la nécessité d’une véritable réforme en vue de libérer la femme mariée du régime d’autorisation maritale. Mots-clés : capacité, commerçant, immatriculation, incapacité et femme

L’intérêt du développement dans les accords de promotion et de protection des investissements - Nyeck, Emmanuel Noé (Revue Africaine des Réflexions Juridiques et Politiques, 2024)
La conclusion des accords de promotion et de protection des investissements a pour fonction d’augmenter significativement les investissements directs étrangers dans les pays en développement afin de les sortir du sous-développement. Ces accords sont donc envisagés comme la panacée contre le sous-développement en raison de l’échec des solutions traditionnelles de lutte contre le sous-développement. Cependant, fort est de constater que le développement auxquels ils renvoient ne peut être élevé au rang d’une véritable obligation juridique dans la mesure où la notion de développement est elle-même est ancré dans la soft law.
Keywords: Bilateral Investment Treaties (BITs); Contentieux de l’investissement; Droit international de l’investissement; Droit international du développement; Droits de l’homme; Human rights; International Investment Law; International development law; Investment litigation; Traités bilatéraux des investissements

Evaluation du projet d’assainissement de la gestion collective du droit d’auteur et des droits voisins au Cameroun - Obama Mindzie, Nicole Thérèse (Revue Africaine des Réflexions Juridiques et Politiques, 2024)
La gestion collective existe au Cameroun sous l’égide de la loi 2000/11 du 19 décembre 2000 relative au droit d’Auteur et aux droits voisins, depuis l’année 2018 on note une restructuration marquée par une palette de textes dans le but d’effectuer un assainissement dans la gestion collective prescrite par le Chef de l’Etat suite aux multiples remouds connus dans le secteur. L’auteur de l’article s’interroge sur la situation actuelle dans le secteur six ans après la relance des activités accompagnée du dispositif normatif et administratif jugé fiable en amont pour accomplir la mission de rendre la gestion collective efficace et capable d’épanouir les détenteurs de droits d’Auteurs et de droits voisins ainsi que leurs ayants droit au Cameroun. Au bout du compte, il faut constater avec regret que si le dispositif normatif (en plus d’être inapproprié par son inadaptation) et administratif mis en place pour accompagner la loi 2000 elle-même déjà désuète jusqu’ici n’a fait qu’accentuer l’ingérence apparente de l’Etat déjà décriée plus tôt en plus de rendre béant les manquements causés par la non-objectivité de certains de ces textes. Plus loin encore, le climat et la pratique quotidienne ne font que démontrer davantage les lacunes qui devraient pourtant être au centre du projet d’assainissement au niveau structurel et de la ressource humaine comme au plan administratif. Il sera donc important de revenir sur l’applicabilité de certains textes et la mobilisation des critères humains, administratifs, techniques et surtout juridiques pour réaliser l’épanouissement effectif du secteur de la gestion collective toujours primitive à son stade actuel.
Keywords: Cameroun; Copie privée; Droit d’auteur; Gestion collective; Organisme de gestion collective (OGC); Partage inter social; Perception; Redevance; Répartition

Taxing the digital economy: Options available for African countries - Oluwatuyi, Oluwasikemi (University of Victoria, 2024)
Tax authorities have always assessed and enforced taxes based on the physical address of businesses over the years. Nevertheless, the idea of tax jurisdiction has taken on a new meaning with the development of information and communication technology, and its profound impact on every facet of human existence – including but not restricted to trade and business. This development has undoubtedly increased capital mobility, especially in corporate form, and exposed more the weaknesses in national tax laws by enabling the artificial relocation of important economic components and potential exemption from taxes. Since it is getting harder to separate the digital economy from the rest of the economy for taxation reasons, the process of digitalization has emerged as one of the primary growth drivers. This expansion, together with aggressive tax planning strategies used by multinational enterprises (MNEs) to move revenues to low-tax jurisdictions and the development of business models requiring less physical presence, has increased the workload for tax administrators; furthermore, it has reduced governments’ capacity to raise funds in the traditional manner. In this regard, I assess how “adequate” the selected African countries’ frameworks are vis-à-vis the ongoing OECD and UN negotiations. Beyond the consultations, I call for a more inclusive and Africanised approach and the need for African countries to improve their tax administration mechanisms.
https://hdl.handle.net/1828/20312
Keywords: Digital economy; International taxation; OECD; Tax

Les contrats dans le secteur de l'édition : Guide à l'intention des auteurs et des éditeurs - Organisation mondiale de la Propriété intellectuelle (OMPI, 2024)
Keywords: Contrat d'édition; Droits d'auteur; Editeur; Edition

La communautarisation du droit des dessins et modèles dans l’espace OAPI : étude du droit africain à la lumière des droits français et européen - Ouedraogo, Peingdeweindé Jean (Revue francophone de la propriété intellectuelle, 2024)
La principale qualité d’un texte qui a vocation à uniformiser le droit des dessins et modèles dans l’espace communautaire est d’être complet. Or, la comparaison avec le droit français et européen révèle que l’Annexe IV qui régit le domaine dans l’espace OAPI est loin de revêtir une telle qualité. A travers cette étude, nous nous proposons alors de réunir les mesures complémentaires nécessaires. La réflexion s’étend également à l’interprétation uniforme de l’accord commun. Pour y parvenir, la création d’une juridiction d’intégration parait indispensable, l’application uniforme de l’Annexe IV ne pouvant être attendue des dix-sept juridictions nationales seules. The main quality of a text which is intended to harmonize design law in the Community is that it is comprehensive. However, a comparison with French and European law reveals that Annex IV, which governs the issue in the OAPI area, is far from having such a quality. We then propose to bring together the necessary additional measures. The reflection also extends to the uniform interpretation of the common agreement. To achieve this, the creation of an integration court seems essential, since the uniform application of Annex IV cannot be expected from the seventeen national courts alone.
Keywords: Intellectual property

La probité du débiteur en droit des procédures collectives OHADA - Palgo, Diane Horélie (Revue Africaine des Réflexions Juridiques et Politiques, 2024)
Le droit des procédures collectives permet de traiter les difficultés que les entreprises traversent en permettant leurs redressements lorsque cela est encore possible. L’objectif est de trouver des solutions afin d’éviter la liquidation d’un grand nombre d’entreprises. La bonne continuité des activités d’une entreprise est un gage d’une bonne économie du marché et d’un monde des affaires florissant. Prévenir les difficultés des entreprises et organiser leur redressement nécessite un comportement adéquat et une certaine probité du débiteur. Ainsi, l’honnêteté du débiteur est cruciale car elle favorise la continuité des activités de l’entreprise et une bonne marche de l’économie nationale et mondiale. Le droit OHADA n’a cependant pas prévu expressément l’exigence d’une probité du débiteur. En effet, cette exigence se constate implicitement d’une part, lors de la constitution du dossier de demande d’ouverture des procédures et d’autre part, pendant l’exécution ou la mise en œuvre des mesures tendant à sauvegarder la continuité de l’activité. Des incriminations prévues par le droit communautaire, permettent de sanctionner des comportements déloyaux traduisant également une consécration implicite d’une obligation de probité à l’égard du débiteur. The law of insolvency proceedings makes it possible to deal with the difficulties that companies are going through by allowing them to recover when it is still possible. The aim is to find solutions to avoid the liquidation of a large number of companies. Good business continuity is a guarantee of a good market economy and a thriving business world. Preventing companies' difficulties and organising their recovery requires appropriate behaviour and a certain probity on the part of the debtor. Thus, the honesty of the debtor is crucial because it promotes the continuity of the company's activities and the smooth running of the national and global economy. The OHADA law, however, did not expressly provide for the requirement of probity of the debtor. This requirement is implicit, on the one hand, when the application for opening proceedings is being filed and, on the other hand, during the execution or implementation of measures designed to safeguard the continuity of activity. The incriminations provided for by Community law make it possible to sanction unfair conduct which also reflects an implicit commitment of a duty of probity towards the debtor.
Keywords: Collective preventive proceedings; Collective remedial proceedings; Debtor; Dirigeant; Débiteur; Loyalty; Loyauté; Manager; Procédures collectives curatives; Procédures collectives préventives; Sanctions

Global Common: The Rights and Responsibilities of the State and the Investor in Renewable Energy Foreign Investment - Pang, Hui (UNSW Sydney, 2024)
States poured millions of dollars to attract foreign renewable energy investments for climate change mitigation, however, when it becomes too hefty for some states, they have modified regulations to reduce the level of support. These regulation changes have led to dozens of investors filing arbitrations against the host states, alleging breaches of investment treaty obligations. This thesis examines whether the current investor-state dispute settlement (‘ISDS’) regime adequately addresses environmental concerns when adjudicating renewable energy investment cases. While renewable energy investments can help protect a global common (the atmosphere) and mitigate climate change, the regulation changes also seek to protect a domestic public good (financial stability of the host state). Therefore, when the protection of a global common conflicts with a domestic public interest in renewable energy ISDS cases, what are the rights and obligations of the host state and the investor? Are the existing approaches of the ISDS regime toward environmental concerns and other public interests fair and adequate, and if not, what interventions can be made? This thesis explores these questions by conducting doctrinal analysis on more than 60 renewable energy cases and the arbitral jurisprudence regarding international environmental obligations. It uses the constitutionalisation of international law to break the self-contained regime of international investment law and argues that common values should be regarded as equally important as investment protection goals in ISDS. This thesis finds that the ISDS regime considers international environmental obligations to be insignificant in supporting the host state’s defences in non-compliance of bilateral investment treaties or the investor’s claims for investment protection. This thesis shows that the current approach furthers discrepancies between climate change mitigation and international investment law. Not only does this approach fail to acknowledge the environmental connections of renewable energy investment, but it also creates opportunities for fossil fuel investors to seek compensation against environmental regulation changes using the same arguments. As an intervention against the current approach, this thesis proposes to reconstrue the concept of legitimate expectations to place common values on equal grounds with investment protection incentives. This thesis makes two significant contributions to knowledge. Firstly, it extends existing analyses of the conflicts and synergies between international investment law and environmental protection and contributes to the growing body of scholarship on this topic. Research on this topic has mainly focused on how the state safeguards environmental interests against investor protection claims. While this narrative comprises many cases, it does not capture the full picture and overlooks the possible contributions of private parties in protecting global commons. Instead, this thesis examines whether international environmental obligations can serve as a ‘shield’ for the state’s non-compliance in investment protection, or as a ‘sword’ for investors to compel the state to fulfil its international obligations. Secondly, this thesis makes an intervention to reconstrue ‘legitimate expectations’, where common values are reinforced and not only the interests of investors are protected but also the ‘legitimate expectations of a responsible investor’ from the state and local communities are taken into account.

Vergi ceza hukukunda muhasebe hileleri ve hukuki sonuçları - Parlak, Mehmet Ali (İstanbul Üniversitesi, 2024)
Bu çalışma, Vergi Usul Kanunu'nun 359. maddesinin (a) fıkrasının birinci bendinde düzenlenen "hesap ve muhasebe hileleri yapmak" hükmünün, suç ve cezada kanunilik ilkesini karşılayıp karşılamadığı temelinde suçun kapsamı, özellikleri, unsurları ve sonuçlarının doktrin, içtihat ve mevzuat hükümleri ışığında incelenmesini konu edinmektedir. Muhasebe hilesi geniş anlamda, işletmelerde meydana gelen değer hareketlerinin belgelendirilmesinden faaliyet sonuçlarının raporlanmasına kadar olan süreçte, işlemlerin gerçeği yansıtmayacak şekilde değiştirilmesidir. Bu itibarla muhasebe hilesi muhasebe, denetim, ticaret hukuku gibi farklı disiplinlerin inceleme alanlarına giren genel bir kavramdır. Bunun yanında vergi kaçakçılık fiili olarak vergi hukuku doktrininde de önemli bir yer tutan tartışma konusudur. Vergi hukukundaki tartışmalar, hükümdeki muhasebe hilesi kavramının tanımsız, torba suç, kaçakçılık suçlarının en geneli ve işlevsiz bir suç olup olmadığına yöneliktir. Bu tartışmaların kaynağı kanun koyucunun maddede suçun kurucu unsurlarına yer vermemesi ve herhangi bir soyut tipe dair belirleme yapmamasıdır. Bu bakımdan çalışmada farklı disiplinler bakımından muhasebe hilesinin kapsamı, yöntemleri, sebep ve sonuçları karşılaştırmalı olarak ele alınmış; tümden gelim yöntemiyle vergi hukukundaki muhasebe hilesi suçunun içeriği tespit edilmeye çalışılmıştır. Çalışmada ulaşılan sonuç; "hesap ve muhasebe hileleri yapmak" hükmünün suçu tanımlamak bakımından "belirlilik" ilkesini karşılamadığıdır. Dolayısıyla adli ve idari mercilerin subjektif değerlendirmelerinin önüne geçilmesi, hukuki kesinlik ve eşitliğin temini, hukuki güvencenin sağlanabilmesi ve normun işlerlik kazanabilmesi için bir düzenlemeye ihtiyaç duyulmaktadır. This study examines the scope, characteristics, elements and consequences of the crime in the light of doctrine, jurisprudence and legislation on the basis of whether the provision of "committing accounting and accounting fraud" regulated in the first paragraph of paragraph (a) of Article 359 of the Tax Procedure Law meets the principle of legality in crime and punishment. It is about to be examined. Accounting fraud, in broad terms, is changing transactions in a way that does not reflect reality, from the documentation of value movements in businesses to the reporting of activity results. In this respect, accounting fraud is a general concept that falls into the fields of investigation of different disciplines such as accounting, auditing and commercial law. Discussions in tax law are about whether the concept of accounting fraud in the provision is undefined, an omnibus crime, the most general of smuggling crimes, and whether it is a dysfunctional crime. The source of these discussions is that the legislator does not include the constitutive elements of the crime in the article and does not specify any abstract type. In this regard, the scope, methods, causes and consequences of accounting fraud in terms of different disciplines were discussed comparatively in the study; The content of the crime of accounting fraud in tax law has been tried to be determined by deductive method. The result reached in the study; The provision of "committing account and accounting fraud" does not meet the principle of "specificity" in terms of defining the crime. Therefore, a regulation is needed to prevent subjective evaluations of judicial and administrative authorities, to ensure legal certainty and equality, to provide legal assurance and to make the norm functional.
Tez N°857786
Keywords: Accounting; Finance; Fraud; Fraude fiscale; Maliye; Tax fraud

Pour l’adoption d’une règlementation propre à la location gérance du fonds de commerce en droit OHADA - Pelerin, Noar; Makindunda, Muwawa (Mouvements et enjeux sociaux: Revue internationale des dynamiques sociales, 2024)
Cette réflexion plaide pour l’adoption d’une réglementation propre, étoffée et détaillée en faveur de la location-gérance partant de son importance dans le monde des affaires. Cette convention par laquelle le propriétaire du fonds de commerce, personne morale ou physique concède en location est donc un palliatif pour le propriétaire lorsqu’il ne veut ou ne peut plus exploiter ses fonds pour ne percevoir que des redevances. Actuellement, il n’existe que très peu des dispositions particulières principalement deux textes : le Décret du 30 juillet 1888 et le titre premier de l’acte uniforme relatif au bail à usage professionnel. D’où, la nécessité d’une réglementation adéquate.
Keywords: Adoption; Commerce; Fonds de commerce; Gérance de fonds de commerce; Location de fonds de commerce

La propriété intellectuelle liée au folklore, aux savoirs traditionnels et aux expressions culturelles traditionnelles : un enjeu en voie de résorption - Petit, Jérémie (Revue francophone de la propriété intellectuelle, 2024)
L’attribution d’une protection comparable à la propriété intellectuelle (droit d’exclusivité, droits patrimoniaux et droits moraux) à des expressions du folklore correspond à une demande ancienne des pays du Sud, mais se heurte à deux difficultés : l’inadéquation de systèmes n’offrant qu’une protection limitée dans le temps, pour des savoirs et des expressions dont la durée de vie en tant que traditions vivantes de communautés peut être très longue ; et l’intérêt légitime du public à pouvoir utiliser des savoirs et expressions appartenant au domaine public. Deux conférences diplomatiques de l’OMPI en 2024 se penchent sur l’inclusion de clauses de divulgation de l’origine de ressources génétiques, de savoirs traditionnels ou d’expressions culturelles traditionnelles lors du dépôt des brevets et de l’enregistrement de dessins et modèles, avant que les discussions ne reprennent dans le cadre du Comité intergouvernemental sur la propriété intellectuelle en rapport avec les ressources génétiques, les savoirs traditionnels et le folklore (IGC) sur l’opportunité de négocier un ou plusieurs nouveaux instruments juridiques visant la création d’un système de protection sui generis sur ces questions. Une prise en compte des travaux dans d’autres enceintes internationales comme l’UNESCO, favoriserait l’identification d’un point d’atterrissage The granting of protection comparable to intellectual property (right of exclusivity, property rights and moral rights) to expressions of folklore corresponds to a long-standing request from countries in the South but faces two difficulties: the inadequacy of systems offering only limited protection in time, for knowledge and expressions whose lifespan as living traditions of communities can be very long; and the legitimate interest of the public in being able to use knowledge and expressions belonging to the public domain. Two diplomatic conferences held by WIPO in 2024 consider the inclusion of a disclosure requirement of the origin of the genetic resources, traditional knowledges or traditional cultural expressions in patent and design applications, before discussions resume in the Intergovernmental Committee on Intellectual Property and Genetic Resources, Traditional Knowledge and Folklore (IGC) on negotiating one or more new legal instruments to create a sui generis system of protection for these subject matters. Taking account of the work of other international bodies, such as UNESCO, would help to identify a landing point.
Keywords: Expression culturelle traditionnelle; Folklore; Intellectual property; Intellectual property rights; Propriedade intelectual; Propriété intellectuelle; Savoir traditionnel

Una aproximación al régimen jurídico del contrato de transporte multimodal - Piloso Moreira, Verónica Alexandra; Serrano Cañas, José Manuel (Espacio Abierto. Cuaderno Venezolano de Sociología, 2024)
El transporte multimodal ha sido un recurso comercial ampliamente utilizado por los países para facilitar el intercambio de productos. Este estudio se enfocó en analizar la aplicación práctica del régimen jurídico del contrato de transporte multimodal internacional de mercancías, y considerar su importancia frente a los desafíos relacionados con la globalización económica y política. A pesar de los esfuerzos por establecer una regulación uniforme en los mercados internacionales, dicho régimen aún no satisface completamente las necesidades de los participantes en estas transacciones, por lo que debilita las tendencias sociológicas a la interconexión, proyevendo de debilidades adicionales a los subsistemas nacionales. Organismos internacionales como MERCOSUR, la CAM, la ALADI, el SICA, la OEA, las Naciones Unidas (a través de su Comisión Económica para América Latina y el Caribe) y la UNCITRAL han trabajado en la formulación de soluciones para las principales controversias surgidas en este proceso. Sin embargo, esto ha resultado en un régimen jurídico incompleto, fragmentado y poco eficaz, que favorece principalmente a los países miembros de estos organismos internacionales emisores de regulaciones. Además, estas soluciones no siempre pueden extrapolarse como reglas generales o como soluciones efectivas para las consecuencias derivadas del incumplimiento de las cláusulas contractuales. Multimodal transportation has been a widely used commercial resource by countries to facilitate the exchange of goods. This study focused on analyzing the challenges related to the practical application of the legal framework of the international multimodal transport contract. Despite efforts to establish uniform regulation in international markets, this framework still does not fully meet the needs of participants in these transactions, therefore, it weakens social tendencies towards interconnection, providing additional weaknesses to national subsystems. International organizations such as MERCOSUR, CAM, ALADI, SICA, OAS, the United Nations (through its Economic Commission for Latin America and the Caribbean), and UNCITRAL have worked on formulating solutions to the main controversies that have arisen in this process. However, this has resulted in an incomplete, fragmented, and inefficient legal framework, which primarily benefits the member countries of these international organizations issuing regulations. Additionally, these solutions cannot always be extrapolated as general rules or effective solutions for the consequences of non-compliance with contractual clauses.
Keywords: Clause contractuelle; Cláusulas contractuales; Contractual clauses; Global governance; Gobernanza global; International organizations; Legal framework; Multimodal transportation; Organismos internacionales; Régimen jurídico; Sistema-mundo; Transport multimodal; Transporte multimodal; World-system

La réforme de la législation marocaine sur les droits d’auteurs et droits voisins : avancées et limites - Rharrabi, Hanane (Revue francophone de la propriété intellectuelle, 2024)
La réforme de la loi n° 2-00 du 15 février 2000 sur les droits d’auteurs et droits voisins s’est imposée depuis quelques années en raison des changements rapides et croissants induits par la révolution numérique. Aussi, les amendements de la loi n° 66-19 du 24 mai 2022 se sont focalisés sur l’encadrement de l’exploitation en ligne des œuvres en étendant le contrat d’édition aux œuvres numériques, en instaurant des droits reprographiques sur les copies numériques et en responsabilisant les prestataires de partage de contenu sur Internet. Un quatrième droit voisin a même été créé afin de concilier les intérêts des intermédiaires éditoriaux et des infomédiaires. En dépit de ces amendements, l’analyse détaillée de chacune de ces innovations fait ressortir un bilan mitigé sur l’efficacité des dispositions législatives et soulève des interrogations sur les défis à relever. The rapid and growing changes brought about by the digital revolution have made it necessary to reform Law No. 2-00 of 15 February 2000 on copyright and related rights. Amendments to law No. 66-19 of 24 May 2022 therefore focused on regulating the online exploitation of works. This involves extending the publishing contract to digital works, imposing reprographic rights on digital copies and making Internet content-sharing providers more accountable. Additionally, a fourth neighbouring right has even been created to reconcile the interests of editorial intermediaries and infomediaries. Despite these amendments, a detailed analysis of each of these innovations reveals a mixed picture of the effectiveness of the legislative provisions and raises questions about the challenges ahead.
Keywords: Intellectual property

Desenvolvimento Profissional e Afiliação à Ordem dos Contabilistas na Guiné-Bissau: Motivações e Desafios - Sambú, Luís (Instituto Politécnico de Santarém, 2024)
Objetivo: Esta pesquisa tem como objetivo compreender as motivações que levam os contabilistas acreditados da Guiné-Bissau a se afiliarem à Ordem dos Contabilistas, bem como identificar e compreender as barreiras enfrentadas pelos contabilistas que não são afiliados, com o intuito de propor estratégias que incentivem a afiliação e promovam o desenvolvimento profissional do contabilista no país. Método: Foi utilizada uma abordagem qualitativa. Entrevistas semiestruturadas foram conduzidas com contabilistas acreditados e não acreditados para explorar suas percepções e experiências. A análise de conteúdo foi empregada para interpretar os dados, destacando as motivações para a afiliação e as barreiras enfrentadas pelos não afiliados. Resultado: Os resultados demonstram que os contabilistas acreditados entrevistados não consideram a existência de barreiras. Já os contabilistas não inscritos na ordem mostram-se motivados para se inscreverem na ordem, uma vez que isso lhes permite ter acesso à formação contínua e alcançar estatuto como profissionais de qualidade. Contribuição: A contribuição desta pesquisa consiste em enriquecer o estudo da profissionalização da contabilidade. Igualmente, irá contribuir para uma melhor compreensão do estado da profissão contabilística na Guiné-Bissau. Além disso, dada a inexistência de literatura sobre o tema, este estudo irá ajudar a aumentar o conhecimento das difíceis situações com que os contabilistas acreditados e não acreditados se deparam no exercício das suas funções na Guiné-Bissau.
Keywords: Afiliação; Desafios; Desenvolvimento profissional; Guiné-Bissau; Motivaçoes; Ordem dos contabilistas

COFOLA 2024: Sborník příspěvků mladých právníků, doktorandů a právních vědců.. Část 8, Regulace, dohled a inovace na finančních trzích a v bankovním sektoru - Schweigl, Johan; Holubářová, Nikol (Masarykova Univerzita, 2024)
- Právní aspekty zavedení Centrální bankovní digitální měny (CBDC) v Evropě: výzvy a; - Novinky ve světě fintech; - Riziko praní špinavých peněz v kryptoprostoru; - Povolenie na poskytovanie služieb kryptoaktív podľa nariadenia MiCA – vybrané regulačné aspekty v podmienkach Slovenskej republiky; - Nekalé obchodní praktiky a nekalosoutěžní jednání v bankovním marketingu; - Finančné inovácie ako determinant súčasnej a anticipovanej regulácie na finančnom trhu v kontexte neoprávneného podnikania; Outsourcing marketingových aktivit v bankovním sektoru; Několik poznámek k dlouhodobému investičnímu produktu.

COFOLA 2024: Sborník příspěvků mladých právníků, doktorandů a právních vědců. Část 3, Aktuální otázky náhrady škody - Schweigl, Johan; Holubářová, Nikol; Janovec, Michal (Masarykova Univerzita, 2024)
Sborník příspěvků z konference. OBSAH - Kdo odpovídá za škodu způsobenou zvířetem? Otázka odpovědnosti a náhrady škody ve vztahu k živočišné říši - Náhrada nemajetkové újmy na zdraví: smíření s Metodikou, návrat k prováděcím předpisům nebo třetí cesta? - Náhrada škody v případech věcí, které jsou předmětem zvláštní obliby - Náhrada škody v případě neprodejnosti výrobků obsahující hhc látky a celkový dopad na podnikání jednotlivců - Právo na zadostiučinění v souvislosti s rozhodováním orgánů družstva - Újma způsobená neprodloužením života závažně nemocné osoby
Keywords: E-knihy; Elektronické knihy; Flipbook; Knihy; Masarykova univerzita; Munipress; Čítárna

L’activisme actionnarial : Genèse, influence contemporaine et cadre juridique - Shareghi, Nima (Bulletin de droit économique, 2024)

Réflexion à propos du contradictoire dans les procédures collectives en droit OHADA - Simo Kamgang, Crépin Giresse (Revue Africaine des Réflexions Juridiques et Politiques, 2024)
Les procédures collectives ont toujours entretenu des rapports complexes et conflictuels avec d’autres branches du droit privé. Cela n’est guère démenti lorsqu’on confronte la matière avec le droit processuel. La présente réflexion vise dans une analyse explicative et démonstrative à présenter la situation de l’un des principes cardinaux du procès qu’est le contradictoire lorsque s’ouvre une procédure collective. A l’analyse et à l’observation, s’il est certes vrai qu’on note une forte perception du contradictoire dans les procédures préventives, ce principe connait un recul dans les procédures de traitement des difficultés des entreprises du fait de la forte intervention du juge.
Keywords: Contradictoire; Juge; Procédure collective

The Individual in International Law: History and Theory - Sparks, Tom; Peters, Anne (Oxford University Press, 2024)
978-0-19-889891-7
Keywords: Humanisation; Individual; Individualisation; International law; Legal history; Legal theory

Perspectives africaines sur le statut du travail - Supiot, Alain (Revue de droit comparé du travail et de la sécurité sociale, 2024)
Dans son livre Repenser le statut du travail. Une contribution africaine, le professeur Ousmane O. Sidibé appelle à repenser le statut du travail à l’aune des sociétés dans lesquelles il s’inscrit. Sans idéaliser les systèmes normatifs hérités de la tradition, il donne à voir le « travail informel », les savoirs empiriques ou encore les solidarités traditionnelles, autrement que par le prisme d’un modèle occidental qui les a longtemps réduits à l’archaïsme. En invitant à mieux comprendre les spécificités de la culture juridique africaine, il ouvre la voie à un statut du travail effectif, vers plus de justice sociale. In his book Repenser le statut du travail. Une contribution africaine, Professor Ousmane O. Sidibé calls for a rethink of the labour’s legal framework in the light of the societies in which it is embedded. Without idealising the normative systems inherited from tradition, he shows “informal work”, empirical knowledge and traditional solidarity in a different light from that of a Western model that has long reduced them to archaism. By inviting us to gain a better understanding of the specific features of African legal culture, he opens the way to a status for effective work, towards greater social justice.
Keywords: Africa; Afrique; Culture juridique; Globalisation; Legal Culture; Legal Framework for Labour; Mondialisation; Statut du travail

Du « contrat » dans le droit répressif - Tchejip Tchathouang, Rodrigue (Revue Africaine des Réflexions Juridiques et Politiques, 2024)
La montée en puissance de la justice dite négociée entraine des changements dans la structure du contrat traditionnel et permet un éventuel rapprochement avec le type de rapport que l’on rencontre lors de la mise en œuvre du processus de négociation en matière pénale. L’absence d’égalité entre les parties ainsi que le défaut de libre détermination du contenu de l’accord en matière pénale n’exclut pas la notion de contrat puisque celui-ci est formé par un échange de consentement et qu’il peut reposer sur l’utile et le juste. C’est dans cet esprit qu’est menée la réflexion sur la thématique « du contrat dans le droit répressif » lorsqu’on sait que le droit pénal post-moderne est de plus en plus dominé par les courants de la justice restaurative.
Keywords: Contrat; Droit répressif; Poursuite; Sanction

La compétence du for de situation de l’immeuble face aux conventions de juridictions - Tchouankeu Djeuda, Claudia (Revue Africaine des Réflexions Juridiques et Politiques, 2024)
L’admission d’une maitrise par les parties de la compétence internationale par des clauses de juridictions ; notamment des conventions d’élection de for, des conventions d’arbitrage ou de médiation, amène à s’interroger sur l’efficacité réelle de ces accords. Pour ce qui est de la matière immobilière, le fort attachement de l’Etat aux questions de territoire et les considérations de proximité entre litige et le for du situs ont pour effet d’empêcher toute dérogation à la compétence directe du for de situation de l’immeuble ; tant lorsque l’immeuble est situé sur le for du juge saisi que lorsqu’il est situé à l’étranger. Toutefois, l’observation d’un possible fléchissement de l’exclusivité de ce critère de compétence conduit à un plaidoyer en faveur de l’efficacité, quoique encadrée, des conventions juridictions en la matière.
Keywords: Autonomie de la volonté; Autonomy of will; Compétence internationale des juridictions; Convention de juridiction; Immovable property’s location; International jurisdiction; Jurisdiction agreement; Lieu de situation de l’immeuble; Matière immobilière; Real estate matters

Arabuluculuk faaliyetinin anlaşma ile sona ermesi - Terzi̇ Kahraman, Si̇bel (Kadir Has Üniversitesi, 2024)
Arabuluculuk kurumundan beklenen avantajların ortaya çıkabilmesi arabuluculuk faaliyeti sonunda anlaşmaya varılması ile mümkündür. Mevzuatta sürekli değişiklikler meydana gelmekte ve kurumun kapsamına aldığı uyuşmazlıklar hızla genişletmektedir. Uygulamanın yerleşmesi ve zaman zaman doktrinde görüş ayrılıkları yaşanması kaçınılmazdır. Mevzuatta daha detaylı ya da değiştirilerek düzenlenmesine ihtiyaç duyulan alanlar bulunmaktadır. Tez, mevzuatta yapılan son düzenlemeleri de kapsayarak anlaşmayı tüm yönleriyle ele almayı ve kurumun daha iyi anlaşılmasına hizmet etmeyi amaçlamaktadır. Yapılan bu çalışmanın ilk bölümde arabuluculuğun kurumsal çerçevesi ortaya konulmuştur. Bu bölümde amaç arabuluculuk kurumunu ve arabuluculuk faaliyetinin işleyişini anlatabilmektir. Bu amaçla arabuluculuğun kapsamı, türleri, arabuluculuğun karşılaştırmalı hukukta ve Türk hukukunda gelişimi, yargı ve tahkimden farkı, med-arb uygulaması anlatılmıştır. İkinci bölümde sona erme halleri tek tek ele alınmış, sona erme hallerinin mevzuatta dağınık halde düzenlendiği hususuna dikkat çekilmiş ve başkaca sona erme halleri de dikkate alınarak tek bir madde halinde düzenlenebilmesi hususu önerilmiştir. Arabulucunun, faaliyeti sona erdirme yönünde inisiyatif almasının sona erme hali olarak düzenlenmesi yönünde de öneri getirilmiştir. Üçüncü bölümde anlaşmanın terminoloji sorununa ve benzer kavramlardan farkına değinilmiştir. Arabuluculuk faaliyeti sonunda varılan anlaşmanın esaslı unsurları tespit edilmiştir. Bu kapsamda, sözleşme serbestisi, şarta bağlı edim düzenlenip düzenlenemeyeceği gibi önemli hususlara yer verilmiştir. Anlaşmanın nasıl düzenleneceğine ilişkin öneride bulunulmuştur. Anlaşmanın hukuki niteliği, anlaşılan hususlara karşı dava açılamayacağı, anlaşmanın hukuka uygun düzenlenmediği takdirde karşılaşılabilecek sonuçlar anlatılmış ve anlaşmanın arabuluculuğa elverişli olmamasına rağmen düzenlenmesi, dava şartı kapsamına girmeyen bir hususta faaliyetin yürütülmesi ve anlaşmaya varılması, yanlış dava türünden yapılan başvuru sonucu anlaşmaya varılması, arabulucunun uzmanlık alanına girmeyen bir konuyla ilgili anlaşma sürecini tamamlaması, hukuka uygun arabuluculuk faaliyeti yürütülmemesi sonucunda anlaşmaya varılması, arabulucunun arabuluculuktan çekilmesi gerekirken yine de anlaşma yapması gibi anlaşmadan kaynaklı sorunlara yer verilmiştir. Dördüncü bölümde anlaşmanın yerine getirilmemesi durumunda icra edilebilirlik şerhi alınması hususu, mahkemeye başvuru, yargılama usulü, mahkemenin incelemesi, şarta bağlı olarak yapılan anlaşmaya şerh verilmesi, icra edilebilirlik şerhi alınan anlaşmanın icrası, anlaşmayla ilamlı ve ilamsız takip yapılması gibi önemli hususlar ele alınmıştır. Son olarak, arabuluculuk sonucunda elde edilen uluslararası ticari anlaşmaların icra edilmesini kolaylaştırması amacıyla hukukumuzda da kabul edilen Singapur Konvansiyonu incelenmiştir. The expected advantages of the mediation institution can be realized through reaching an agreement at the end of the mediation process. There are continuous changes in the legislation, rapidly expanding the scope of disputes covered by the institution. The thesis aims to comprehensively examine the agreement reached at the end of the mediation process, including recent legislative amendments, to better understand the institution and its operations. The first part of this study outlines the institutional framework of mediation, explaining its scope, types, development in comparative law and Turkish law, differences from judiciary and arbitration, and the practice of med-arb. The second part discusses the various termination conditions, highlighting the scattered nature of these conditions in legislation and proposing their consolidation into a single provision. It also suggests granting mediators the initiative to terminate the process as a termination condition. In the third part, attention is given to the terminology issues and distinctions from similar concepts regarding the agreement reached through mediation. The essential elements of such agreements are identified, covering issues like contractual freedom and the regulation of conditional obligations. Recommendations are made on how agreements should be drafted. The legal nature of the agreement, restrictions on litigation concerning agreed-upon matters, consequences of improperly drafted agreements, and issues arising from inappropriate mediation activities are discussed. The fourth part addresses the issue of obtaining enforceability endorsements for agreements not fulfilled, court applications, trial procedures, court reviews, endorsement of conditional agreements, enforcement of endorsed agreements, and procedures for enforcement with and without judgments. Finally, the study explores the Singapore Convention, adopted in our legal system to facilitate the enforcement of international commercial agreements resulting from mediation.
884007
Keywords: ADR; Agreement termination; Alternative dispute resolution; Anlaşmazlık; Arabuluculuk; Executability Annotation; Kanunlar 6325 sayılı; Laws 6325 numbered; Mandatory mediation; Mediation; Mediator; Médiation; Singapore Convention; Zorunlu arabuluculuk

L’assiette de la saisie en droit OHADA - Tinwo Fonkouo, Simplice Emmanuel (Revue Africaine des Réflexions Juridiques et Politiques, 2024)
Le recouvrement des créances a été une préoccupation majeure pour tout législateur. Il permet au créancier, de bénéficier par voie judiciaire ou extrajudiciaire, le paiement de sa créance. C’est pour cela que, le législateur OHADA a édité des normes juridiques, susceptibles de contribuer au recouvrement des créances avec efficacité. La saisie a été consacrée par ce dernier, comme une mesure susceptible, de permettre au créancier de rentrer, en possession de sa créance. La saisie est une procédure d’exécution. Elle permet au créancier, de rendre indisponible les biens de son débiteur. Ces biens peuvent être vendus, en vue de désintéresser le créancier. Elle est mise en œuvre sans l’intervention du juge. C’est un acte extrajudiciaire. Ainsi, l’assiette de la saisie présente un double visage. Il s’agit d’un visage affirmé d’une part et d’un autre éprouvé d’autre part. Le législateur OHADA a affirmé l’assiette, de la saisie à travers la consécration de la saisie, des biens du débiteur défaillant. Les biens avenir et les biens présents, du débiteur peuvent faire l’objet d’une saisie. Il s’agit des biens, immobiliers et mobiliers d’un débiteur défaillant. En outre, les biens conditionnels et ceux à termes ne sont pas épargnés. Toutes fois, le législateur a éprouvé ces mesures juridiques. Il a exclu de cette assiette de saisie, certains biens du débiteur. Dès lors, certains biens considérés comme insaisissable et d’autres indisponibles sont exclus de l’assiette de saisie.
Keywords: Assiette; Creditor; Créancier; Debtor; Débiteur; Saisie; Seizure

Réflexion sur la gouvernance des sociétés d’Etat en Côte d’Ivoire - Touré, Bêh Mohamed (Revue Africaine des Réflexions Juridiques et Politiques, 2024)
La constitution de sociétés commerciales – sociétés d’Etat – vise la recherche d’un profit pécuniaire susceptible de l’aider à faire face à ses charges. A l’instar de toutes les sociétés commerciales, les sociétés d’Etat sont gouvernées par des personnes physiques représentants l’Etat actionnaire unique. Cette gouvernance est censée permettre à l’Etat de réaliser des bénéfices dont les populations pourront profiter. Pourtant, le constat est amer, dans la mesure où l’état de cette gouvernance n’est pas reluisant pour les sociétés d’Etat de nationalité ivoirienne. Le diagnostic de leur état montre une organisation inadaptée de la gouvernance due à un mode de désignation inadéquat des gouvernants et surtout d’une confusion de leurs pouvoirs. Face à cette gouvernance malaisée, il est nécessaire, d’emblée, de réformer le mode de désignation, clarifier les pouvoirs des différents gouvernants. L’amélioration de cette gouvernance ne saurait se faire en marge d’un traitement égalitaire des gouvernants indélicats, tant dans la mise en oeuvre de leur responsabilité que dans la sanction correspondante. Cette progression permettra une gouvernance efficace des sociétés d’Etat ivoiriennes.
Keywords: Gouvernance; Governance; Modalités de désignation; Mode of appointment; Organisation inadaptée; Sociétés d’Etat; State-owned companies; Unsuitable organization

Sermaye şirketlerinde zorunlu arabuluculuk - Ulusan, Banu (Galatasaray Üniversitesi, 2024)
Çalışma 06.12.2018 tarihinde 7155 sayılı Kanun ile Türk Ticaret Kanunu'na eklenen TTK m. 5A hükmüyle getirilmiş zorunlu arabuluculuğun, sermaye şirketleri çerçevesinde incelenmesini konu almaktadır. TTK m. 5A hükmüyle önce, ticari davalardan, konusu bir miktar paranın ödenmesi olan, alacak ve tazminat davalarının zorunlu arabuluculuğa tabi olduğu düzenlenmiştir. Daha sonra, 28.02.2023 tarihli ve 7445 sayılı Kanun ile yine ticari dava olmaları kaydıyla, menfi tespit, itirazın iptâlî ve istirdat davalarını da zorunlu arabuluculuk kapsamına almıştır. TTK lafzıyla dava şartı arabuluculuk olarak da nitelendirilen zorunlu arabuluculuk kavramı, Türk hukuku bakımından yeni bir kavram sayılabilir. İlk olarak 2017 yılında 7036 sayılı Kanun ile iş uyuşmazlıkları için düzenlenen zorunlu arabuluculuk kavramı, daha sonra ticari uyuşmazlıklar ve tüketici uyuşmazlıkları için de düzenlenmiştir ve Türk hukukunda zorunlu arabuluculuğun uygulama alanı git gide genişleme eğilimi göstermektedir. Bu sebeple, doktrinde pek çok eleştiriye de uğrayan zorunlu arabuluculuk kavramının, özellikle sermaye şirketleri bağlamında incelenmesi amaçlanmıştır. Her ne kadar Türk hukukunda yeni bir kavram olsa da, karşılaştırmalı hukukta zorunlu arabuluculuk uzun zamandan beri uygulanan ve tartışilânbir konu olagelmiştir. Karşılaştırmalı hukuk bağlamında bir inceleme yapıldığında öncelikle, özellikle zorunlu arabuluculuğun menşei sayılabilecek Amerikan hukukunda, konu özellikle doktrinde farklı açılardan ele alınmıştır. Çalışmanın birinci bölümünde bu çerçevede bir inceleme yapılmış, zorunlu arabuluculuğun tabi olması gereken kıstaslar ortaya konulmaya çalışılmıştır. Bu kıstaslar, çalışmanın ilerleyen bölümlerinde yapılacak değerlendirmeler için de önem taşımaktadır. Bunun yanı sıra zorunlu arabuluculuğun türleri ve zorunlu arabuluculuğa aykırı davranışlara bağlanan yaptırımlar üzerinde de durulmuştur. Zorunlu arabuluculuğun ve benzeri uygulamaların farklı hukuk sistemlerinde ne şekilde yer aldığı değerlendirilmiştir. Bu değerlendirmeler kapsamında Alman hukuku bakımından ZPO §278 ile EGZPO §15a incelenmiştir. İsviçre hukuku bakımından ise ZPO §197 vd. hükümleri incelenmiştir. Her iki hukuk sistemi de zorunlu arabuluculuğu düzenlememiş, bunun yerine medeni usûl kanunlarında davanın görüleceği mahkemeler nezdinde uyuşmazlık çözüm sürecini düzenlemiştir. İtalya ve Fransa'da ise zorunlu arabuluculuk uygulamaları mevcut ise de bu, Türk hukukunun aksine, son derece sınırlı bir şekilde gerçekleşmiştir. Zorunlu arabuluculuğun kaynağı olan Amerikan hukukunda ise arabuluculuk, zorunlu tutulan tek uyuşmazlık çözüm yöntemi olmamıştır. Ayrıca zorunluluk hususu kanunla değil, genellikle her bir dava için mahkemenin yönlendirmesiyle sağlanmaktadır. Tüm bu ülkelerin ortak özelliği ise ticari uyuşmazlıkları zorunlu arabuluculuğa ya hiç tabi tutmamaları ya da çok dar bir kapsamda tabi tutmalarıdır. Arabuluculuk her ne kadar bir yargılama faaliyeti olmasa da zorunlu arabuluculuk dava öncesinde yer alan bir aşama olduğundan, kanaatimizce medeni usûl hukukuna hâkim olan ilkeler bakımından da incelenmelidir. Bu kapsamda zorunlu arabuluculuğun öncelikle adil yargılanma ilkesi ve mahkemeye erişim hakkı kapsamında tartışmalara sebep olduğu görülmektedir. Bunun yanı sıra usûl ekonomisi ilkesi, aleniyet ilkesi, tasarruf ilkesi ve dürüst davranma yükümlülüğü bakımından da değerlendirmelere yer verilmiştir. Aleniyet ilkesi bağlamında arabuluculuğa hâkim olan ilkelerden gizlilik ilkesinin ticari uyuşmazlıklar bakımından bir avantaj oluşturduğu söylenebilir. Tasarruf ilkesinde yapılandeğerlendirme maddî hukuk ve usûl hukuku çerçevelerinde yapılmıştır. Ayrıca zorunlu arabuluculuğun menşei Amerikan hukukunda hâkimin ve avukatların rolleri de dikkate alınarak, zorunlu arabuluculuğun Türk hukukundaki hâkimin yargılamayı sevk ve idaresi ilkesiyle tamamen bağdaşmadığı sonucuna varılmıştır. Dürüstlük ilkesi bakımından yine maddî hukukla da bağlantı kurularak bir değerlendirme yapılmış, zorunlu arabuluculuk süreci sonunda varılacak anlaşmanın dürüstlük kuralına uygun yapılması için yeterli mekanizmaların bulunmadığı kanaatine varılmıştır. Bunun dışında HUAK m. 18A/11 hükmü uyarınca zorunlu arabuluculuk sürecinin ilk toplantısına mazeretsiz katılmayan tarafın her durumda yargılama giderlerinin tümünden sorumlu olması ve lehine vekalet ücretine hükmedilememesinin orantısız bir yaptırım olduğu, ayrıca bu sebeple hiçbir durumda yargılama giderlerinden sorumlu olmayacağını bilen tarafın, açılacak dava sürecinde davayı uzatacak veya yanlış yönlendirecek ve dürüstlük kuralına uymayacak her tür davranışı yapabileceği kanaatine varılmıştır. Çalışmanın ikinci bölümü TTK m. 5A hükmünün uygulama koşullarına yoğunlaşmaktadır. Bu kapsamda, ticari davalar bakımından karşılaştırmalı bir değerlendirme yapılmak istenmiştir. Türk hukukunda TTK m. 4 hükmüyle ayrıca düzenlenen ticari davalar, diğer hukuk sistemlerinde ticaret mahkemeleriyle ilişkili olarak düzenlenmiştir. Bu değerlendirmede dikkat çeken husus, davaların ucuz, hızlı ve etkin bir şekilde sonuçlandırılmasının amaçlandığı diğer hukuk sistemlerinde hukukçu olmayan hâkimlerin de görev yaptığıdır. Türk doktrininde ise böyle bir uygulamanın uygun olmayacağı haklı olarak belirtilmiş, bu bağlamda zorunlu arabuluculuk uygulamasının daha uygun olduğu kanaatine varılmıştır. Ticari davalarda dava şartını düzenleyen TTK m. 5A hem medeni usûl hukuku hem de ticaret hukuku bakımından incelenmiştir. Medeni usûl hukukun bakımından yapılanincelemede dava şartı kavramı ve hükmün dava türlerine göre gösterdiği özellikler incelenmiştir. Ticaret hukuku bakımından ise, arabuluculuk süreci sonucunda varılacak anlaşmanın bir maddî hukuk sözleşmesi oluşundan da yola çıkarak basiretli tacir kavramı incelenmiştir. Ayrıca zorunlu arabuluculuğun HUAK m. 5 hükmü ve gizlilik ilkesi nedeniyle göstereceği özellikler nedeniyle, ticari sırların korunması bağlamında da bir değerlendirme yapılmıştır. Çalışmanın üçüncü ve son kısmı sermaye şirketlerinde zorunlu arabuluculuğun incelenmesine ayrılmıştır. Bunun için öncelikle Alman hukukunda pay sahipleri davaları olarak adlandırilândavalar hakkında değerlendirme yapılmaya çalışılmıştır. Bu değerlendirmeyle adi şirketlerden farklı olarak pay sahipleri davalarının genel olarak ortağa değil şirket tüzel kişiliğine yöneltilmesi gerektiği, bunun yanı sıra pay sahiplerinin şirketin menfaatleri için dava haklarını kullanabildiği görülmüştür. Bu değerlendirmenin, sermaye şirketleri uyuşmazlıklarında zorunlu arabuluculuk sürecinde başvuru yapacak taraflar ve anlaşmanın etkileyeceği kişilerin tespitinde yararlı olduğu kanaatindeyiz. Bu değerlendirmenin ardından TTK m. 5A kapsamına girebilecek sermaye şirketi uyuşmazlıkları tespit edilerek, her biri için zorunlu arabuluculuğun göstereceği özelliklerin belirlenmesine çalışılmıştır. Bu belirleme yapılırken her bir uyuşmazlık konusu hakkında genel bir çerçeve sunulmuş, açılabilecek davalar hakkında bilgi verilmiş ve bu bilgiler ışığında zorunlu arabuluculuğun uygulama koşulları ile doğurabileceği sakıncalar üzerinde durulmuştur. Son olarak, yapılantüm değerlendirmeler ışığında sermaye şirketlerinde zorunlu arabuluculukla ilgili de lege ferenda görüşümüze yer verilmiştir. Bu kapsamda sermaye şirketleri uyuşmazlıklarının, dava konularının şirketler hukuku kısıtlarına ve emredici kurallara tabi olması sebebiyle, zorunlu arabuluculuğa her zaman uyumlu olmayabileceği sonucuna varılmıştır. Üstelik, bazı arabuluculuk türlerinde yapılması elzem hukuki denetimin ve arabulucunun bu denetimi yapamayacak olmasının yaratacağı sakıncalara da değinilmiştir. Bunun sonucunda İsviçre ve Almanya örneklerinde olduğu gibi mahkeme bağlantılı uyuşmazlık çözümlerinin düzenlenmesinin daha uygun olduğu kanaatine varılmıştır. İflas bakımından bir değerlendirme yapıldığında ise, İİK m. 226 hükmü nedeniyle doğabilecek sorunlara dikkat çekilmiş, bu bağlamda zorunlu arabuluculuğa başvuru kapsamında düzenleme yapılması önerilmiştir. Son olarak zorunlu arabuluculuk ile varılmak istenen amaçlar da dikkate alındığında, bu amaçlara ulaşmak için taraflara arabuluculuk dışında uyuşmazlık çözüm yollarına başvurabilmelerine imkân verilmesi gerektiği kanaatine varılmıştır. Bu şekilde hem çabuk ve ucuz bir şekilde uyuşmazlıkların çözümü amacına ulaşabilecek, hem de tarafların ihtiyaçlarına daha uygun bir yöntem seçmelerine imkân tanınacaktır. […] This study focuses on application of Turkish Commercial Code Art. 5A, which is amended with Code Nr. 7155 in 2018, to equity companies. TCC Art. 5A regulated mandatory mediation for commercial cases with monetary claims at the beginning. However, through amendment with Code Nr. 7445 in 2023, negative declaratory actions, actions for annulment of objections and actions for restitution were taken into scope of this regulation. Mandatory mediation, which can also be named mediation as cause of action according to TCC m. 5A, can be deemed as a new context in Turkish law. Regulated for the first time for some labour law conflicts with Code Nr. 7036 in 2017, mandatory mediation is regulated also for commercial conflicts as well as consumer law conflicts. Thus, it can be observed that scope of mandatory mediation in Turkish law has a tendency to spread within time. Therefore, as a concept subject to various critics, mandatory mediation is to be evaluated in context of equity companies within this study. Although mandatory mediation is considered to be a relatively new concept in Turkish law, in frame of comparative law, it has a long history of application and has been subject to critics for a long time. It is observed that in comparative law, especially in American law, which can be considered as the source, mandatory mediation has been taken into consideration with many aspects. The first chapter of this study conducts an evaluation within this frame and aims to set the criterias for a better application of mandatory mediation. These criterias are important for evaluation in following chapters of this study. In addition, the variations of mandatory mediations and sanctions applied to the acts contrary to mandatory mediations are observed. Mandatory mediation and similar applications in different law systems are also examined. Within light of this examination, ZPO §278 and EGZPO §15a in German law is taken into consideration, as well as ZPO §197 ff. in Swiss law. Both systems do not regulate mandatory mediation and instead, regulated dispute resolution process within their Civil Procedure Codes. Although mandatory mediation is regulated in Itâlîan and French law systems, these regulations have strictly limited scope. American law, the origin of mandatory mediation, applies other means of dispute resolution as well. Moreover, mandatory mediation in American law is not regulated by a code; it is court oriented in general. The common point of these countries is that none of them applies mandatory mediation within a wide scope on commercial disputes. Although mediation cannot be considered as an act of judication, since mandatory mediation is a step before courts, it should be evaluated with regard of principals of civil procedure law. In this context, it is observed that mandatory mediation gave reason to many arguments related to fair trial and access to court. In addition, evaluations on principals pf procedural economy, publicity, power of disposition and honesty are conducted. With regard of principal of publicity, it can be considered that principal of confidentiality of mediation is an advantage. The evaluations on principal of power of disposition are made in frame of substantial and procedural law. Furthermore, taking the features of American civil procedure law, it is concluded that mandatory mediation is not compatible with the role of judge in Turkish law. With regard of principal of honesty, an evaluation in the light of substantial law is also made and it is concluded that rules to maintain honesty in mandatory mediation are not sufficient in Turkish law. As an addition, it is also stated that sanction in Code of Mediation Art. 18A/11 is unproportionate in context of principal of honesty before courts. The second chapter of this study focuses on conditions of TCC Art. 5A. With this regard, a comparative evaluation on commercial actions is made. Commercial actions, regulated with TCC Art. 4 in Turkish law, are regulated in relation with commercial courts in other law systems. With this evaluation, it is noted that in commercial courts, which aims to solve disputes in a cheap, quick and effective manner, gives place to judges who have not a judicial notion in other law systems. In Turkish literature, it is rightly emphasized that such an application is not appropriate for Turkish law. TCC Art. 5A is also examined within frame of civil procedure and commercial law. Within civil procedure law frame, the concept of cause of action is examined, as well as features of TCC Art 5A in relation to claim in actions. Within commercial law frame, since the agreement concluded within mediation is a contract in context of substantial law, the notion of prudent merchant is evaluated. Furtermore, for mandatory mediation demonstrates features within light of Code of Mediation Art. 5 and principal of confidentiality, an evaluation of trade secrets are also conducted. The third and last chapter concentrates on examination of mediation as a cause of action in equity company disputes. Thus, an action named shareholders' action in German law, which is clarified using notion of actio pro socio, is evaluated. According to this evaluation it is concluded that, unlike simple partnerships, shareholders shall submit their claims against legal entity of equity companies and not against other shareholders. Neverthless, it is also observed that in some cases shareholders are entitled to submit the tools of defence of equity companies for interests of company. This evaluation is essential in order to determine the parties of dispute and the persons effected from the agreement reached at the end of mandatory mediation process. Following this evaluation, the kinds of disputes in equity companies, which fall into scope of TCC Art. 5A, are determined and the features demonstrated by them in context of mediation as a cause of action are defined. In order to comply with this evaluation, information on each subject of action is given, features of the relevant actions are explained and in the light of all evaluations, conditions of application of mediation as a cause of action are explained. Finally, in light of evaluations made within this study, our de lege ferenda opinions on mandatory mediation in equity companies are set. Within this frame, since dispute in equity companies are subject to limitations on equity company law and compulsory legal rules, it is stated that they might not always compatible with mediation as a cause of action. In addition, possible problems arisen from lack of legal supervision in mediation process are also mentioned. As a result, it is concluded that, it would be more convenient to regulate court annexed dispute resolution tools, similar with examples of Germany and Switzerland. With regard to bankruptcy proceedings, it is concluded that possible problems in relation to Turkish Code of Bankruptcy and Enforcement Art. 226 are highlighted and it is suggested that, in order to eliminate such problems, necesarry regulations by legislator should be made. Lastly, taking the goals of mediation into consideration, in order to reach these goals effectively, the importance of giving parties the opportunity to be able to choose other means of dispute resolution apart from mandatory mediation, is found to be essential. Thus, dispute resolution process will take place in a quick and cheap manner and parties will have the chance to be able to choose a dispute resolution method that suits their needs and interests.
Keywords: MARD; Mediación; Mediation; Mediação; Médiation

UNCITRAL Model Clause on Adjudication - UNCITRAL (United Nations, 2024)
The UNCITRAL Model Clauses on Specialized Express Dispute Resolution (SPEDR) (2024) (the “Model Clauses”) have been developed and adopted by the United Nations Commission on International Trade Law. The Model Clauses, accompanied by explanatory notes, offer customized solutions designed to be adapted and adjusted to suit the particular circumstances and preferences of the parties, building on the UNCITRAL Expedited Arbitration Rules. Designed as a resource for businesses and practitioners engaging in international dispute resolution, especially when speed and technical expertise are crucial factors, the Model Clauses provide parties with tailored means to settle disputes in an expeditious manner, ensuring the integrity and effectiveness of their dispute resolution processes, while catering for their unique needs. The Four Model Clauses presented are: Model Clause on Highly Expedited Arbitration Model Clause on Adjudication Model Clause on Technical Advisers Model Clause on Confidentiality

UNCITRAL Model Clause on Confidentiality - UNCITRAL (United Nations, 2024)
The UNCITRAL Model Clauses on Specialized Express Dispute Resolution (SPEDR) (2024) (the “Model Clauses”) have been developed and adopted by the United Nations Commission on International Trade Law. The Model Clauses, accompanied by explanatory notes, offer customized solutions designed to be adapted and adjusted to suit the particular circumstances and preferences of the parties, building on the UNCITRAL Expedited Arbitration Rules. Designed as a resource for businesses and practitioners engaging in international dispute resolution, especially when speed and technical expertise are crucial factors, the Model Clauses provide parties with tailored means to settle disputes in an expeditious manner, ensuring the integrity and effectiveness of their dispute resolution processes, while catering for their unique needs. The Four Model Clauses presented are: Model Clause on Highly Expedited Arbitration Model Clause on Adjudication Model Clause on Technical Advisers Model Clause on Confidentiality

UNCITRAL Model Clause on Highly Expedited Arbitration - UNCITRAL (United Nations, 2024)
The UNCITRAL Model Clauses on Specialized Express Dispute Resolution (SPEDR) (2024) (the “Model Clauses”) have been developed and adopted by the United Nations Commission on International Trade Law. The Model Clauses, accompanied by explanatory notes, offer customized solutions designed to be adapted and adjusted to suit the particular circumstances and preferences of the parties, building on the UNCITRAL Expedited Arbitration Rules. Designed as a resource for businesses and practitioners engaging in international dispute resolution, especially when speed and technical expertise are crucial factors, the Model Clauses provide parties with tailored means to settle disputes in an expeditious manner, ensuring the integrity and effectiveness of their dispute resolution processes, while catering for their unique needs. The Four Model Clauses presented are: Model Clause on Highly Expedited Arbitration Model Clause on Adjudication Model Clause on Technical Advisers Model Clause on Confidentiality

UNCITRAL Model Clause on Technical Advisers - UNCITRAL (United Nations, 2024)
The UNCITRAL Model Clauses on Specialized Express Dispute Resolution (SPEDR) (2024) (the “Model Clauses”) have been developed and adopted by the United Nations Commission on International Trade Law. The Model Clauses, accompanied by explanatory notes, offer customized solutions designed to be adapted and adjusted to suit the particular circumstances and preferences of the parties, building on the UNCITRAL Expedited Arbitration Rules. Designed as a resource for businesses and practitioners engaging in international dispute resolution, especially when speed and technical expertise are crucial factors, the Model Clauses provide parties with tailored means to settle disputes in an expeditious manner, ensuring the integrity and effectiveness of their dispute resolution processes, while catering for their unique needs. The Four Model Clauses presented are: Model Clause on Highly Expedited Arbitration Model Clause on Adjudication Model Clause on Technical Advisers Model Clause on Confidentiality

UNCITRAL, HCCH, Unidroit Guida giuridica agli strumenti uniformi in materia di contratti commerciali internazionali, con particolare attenzione alle vendite - United Nations; UN Commission on International Trade Law (Giuffre Francis Lefebvre, 2024)
Keywords: Hague Principles on Choice of Law in International Commercial Contracts; International sale of goods; UN Commission on International Trade Law; UN Convention on Contracts for the International Sale of Goods (1980); UNIDROIT Principles of International Commercial Contracts (2016)

Décisions marquantes de l’année 2023 en matière de vie privée et de protection des renseignements personnels - Uzan-Naulin, Julie; Monnier, Soleïca; Griffith, Iara; Shapiro, Alexander (Les Cahiers de propriété intellectuelle, 2024)
Cet article examine et commente les décisions marquantes de l’an 2023 rendues par la Cour supérieure, la Cour fédérale et d’autres instances administratives quant au respect de la vie privée et la protection des renseignements personnels.Ces décisions touchent à la diffusion de contenus diffamatoires en ligne, à l’utilisation et la communication de renseignements personnels à des fins d’expulsion, de prospection commerciale et de profilage politique, ainsi qu’à l’analyse de risques identificatoires. MOTS-CLÉS Droit à la vie privée – Droit à la réputation – Responsabilité civile – Responsabilité des intermédiaires – Dommages-intérêts punitifs – LCCJTI – Loi 25 – Généalogie génétique commerciale – Consentement – Nécessité – Communication de renseignements personnels – Portée de l’obligation de protection – Renseignements personnels sensibles – Attentes raisonnables – Anonymisation – Dépersonnalisation – Risques identificatoires ABSTRACT In this article, the authors examine and comment on the landmark decisions of 2023 issued by the Superior Court, the Federal Court and other administrative bodies regarding privacy and the protection of personal information.These decisions touch on the dissemination of defamatory content online, the use and communication of personal information for expulsion purposes, commercial prospecting and political profiling, as well as identification risk analysis. KEY WORDS Right to privacy – Right to reputation – Civil liability – Liability of intermediaries – Punitive damages – ALFIT – Law 25 – Commercial genetic genealogy – Consent – Necessity – Disclosure of personal information – Scope of security obligations – Sensitive personal information – Reasonable expectations – Anonymization – Deidentification – Identifying risks

Mégadonnées, concurrence et abus de position dominante - Warby, Gustave (Bulletin de droit économique, 2024)
Keywords: Abus de position dominante; Competencia; Competition law; Concurrence; Concurrence déloyale; Mégadonnées

La consolidation de la zone de libre-échange continentale africaine (ZLECAF) par la souveraineté des états membres. Recherche sur l’apport de la souveraineté des États membres à l’émergence de la ZLECAf - Yamsoumouna Ndimma, Joël (Revue Africaine des Réflexions Juridiques et Politiques, 2024)
La souveraineté des États membres est la condition d’existence de la zone de libre-échange continentale africaine (ZLECAf). Par conséquent, l’avenir de cette dernière dépend de la capacité des États membres à imposer le respect de l’Accord suscité et à empêcher toute violation des règles et principes établis en vertu de la ZLECAf. Ceci serait une action susceptible de conduire l’Afrique vers son indépendance économique et sortir l’Union africaine de sa dépendance de l’aide internationale. Dès lors, la capacité des États à imposer le respect de l’Accord précité crée un climat favorable à une coopération commerciale renforcée et permet la réalisation d’une complémentarité économique performante au sein de la ZLECAF. L’emploi effectif de la souveraineté des États parties démontre leur volonté de participer au développement de l’Afrique. Car ils sont passés de la gestion individuelle des activités commerciales à la gestion collective de la chose commune.
Keywords: AfCFTA; Capacité souveraine; Commerce intra-africain; Continental Free Trade Area; Intra-African Trade; Political Will; Souveraineté de l’État; Sovereign Capacity; State Sovereignty; Volonté politique; ZLECAf; Zone de libre-échange continentale

La révision du procès pénal : compte rendu d’une rencontre entre la sécurité et la vérité - Ydahad, Benoit (Revue Africaine des Réflexions Juridiques et Politiques, 2024)
La révision du procès pénal est une procédure particulière permettant de remettre en question une décision judiciaire devenue définitive au détriment du principe de l'autorité de la chose jugée. En effet, le législateur a voulu donner une chance à la vérité quitte à égratigner légèrement la sécurité juridique. Il devient intéressant de savoir comment le législateur articule la cohabitation entre la sécurité et la vérité dans le régime de la révision en matière pénale. La rencontre entre les deux impératifs est en réalité celle de l’autorité de la chose jugée et d’un droit quasi absolu à la justice, d’où la tension observée dans un premier temps. Un consensus est trouvé entre la sécurité et la vérité pour une poignée de main sans étreinte dans la mesure où le législateur a su trouver un juste milieu permettant à chaque impératif de s’exprimer dans des limites concises.
Keywords: Chose jugée; Droit à la justice; Legal certainty; Right to justice; Sécurité juridique; Truth; Vérité; res judicata

Arabulucu mesleki sorumluluk sigortası bir uygulama - Yildirim, Ferhat (Marmara Üniversitesi, 2024)
Riskleri bertaraf etmenin çeşitli yolları olmakla birlikte sigorta bu yöntemler içerisinde en bilinen ve tercih edilenidir. Risklerin çeşitliliği, farklı sigorta türlerinin oluşumuna neden olmaktadır. Duyulan ihtiyaçlara, mevcut risklere göre sigortanın şekillenmesi, öznelleştirilmesi mümkündür. İfa edilen meslek nedeniyle üçüncü kişilere verilecek zarardan ötürü oluşan sorumluluğun sigortacıya devrini esas alan mesleki sorumluluk sigortası da farklı sigorta türlerinden sadece bir tanesidir. Alternatif uyuşmazlık çözüm yöntemlerinden olan arabuluculuk, 2012 yılında 6325 sayılı Hukuk Uyuşmazlıklarında Arabuluculuk Kanunu ile Türk hukuk sistemine dahil olmuştur. Kanunun yürürlüğe girdiği tarihten bu yana arabuluculuk yönteminin kullanımı hızla yaygınlaşmış ve uyuşmazlığın taraflarınca tercih görmesi, arabuluculuğu en popüler alternatif uyuşmazlık çözüm yöntemlerinden biri haline getirmiştir. Buna bağlı olarak da Türkiye'de arabulucu sayısı gün geçtikçe artış göstermeye devam etmektedir. Arabulucular siciline kayıtlı arabulucuların, arabuluculuk uygulamalarında karşı karşıya kaldıkları risklerin varlığı, yasal düzenleme dışında da bir takım koruyucu mekanizmaların devreye girmesini zaruri kılmaktadır. Özellikle mesleğin ifası esnasında meslek nedeniyle üçüncü kişilere karşı sorumluluğun doğumuna yol açan hallerin varlığında sigorta önemli bir enstrüman olarak görülmektedir. Çalışma ile İstanbul ilinde (Avrupa-Anadolu yakasında) aktif olarak faaliyet gösteren ve Arabuluculuk Daire Başkanlığı tarafından tutulan arabulucular siciline kayıtlı olan 30 arabulucu ile yapılan derinlemesine görüşme neticesinde, arabuluculuğun katılımcıların çoğunluğu tarafından meslek olarak görülmesi, mehaz olarak kabul edilen Avusturya Hukuk Uyuşmazlıklarında Arabuluculuk Federal Kanunu uygulamasında yer alan ve mesleğin ifası için ön koşul olarak sunulan arabulucu mesleki sorumluluk sigortasının Türkiye açısından ne denli uygulanabileceği ve tercih göreceği sorusunu ortaya çıkarmış ve böyle bir sigortanın tesis edilmesi durumunda arabulucuların bu sigortaya duydukları ihtiyaç ve yaklaşımları ele alınmış ve irdelenmiştir. While there are various ways to eliminate risks, insurance is the most well-known and preferred one among such methods. The diversity of risks leads to the occurrence of different types of insurance. It is possible to shape and subjectivize insurance depending on the needs and existing risks. Professional liability insurance, which is based on the transfer of liability to the insurer for damage to third parties due to the profession being performed, is just one of the different types of insurance. Mediation, one of the alternative dispute resolution methods, was introduced to the Turkish legal system in 2012 with the Law No. 6325 on Mediation in Civil Disputes. Since the date the law came into force, the use of the mediation method has become widespread rapidly and its preference by the parties to the disputes has rendered mediation one of the most popular alternative dispute resolution methods. Accordingly, the number of mediators in Türkiye continues to increase day by day. The existence of risks faced by the mediators registered with the registry of mediators in mediation practices necessitates the introduction of certain protective mechanisms in addition to the statutory provisions. Insurance is considered as an important instrument, particularly in the existence of cases that lead to the emergence of liability against third parties due to the profession while the profession is being performed. With the study, as a result of the in-depth interviews conducted with 30 mediators who are active in the province of Istanbul (European and Anatolian sides) and registered with the registry of mediators maintained by the Department of Mediation, the fact that mediation is considered as a profession by the majority of the participants reveals the question of to what extent the mediator professional liability insurance, which is included in the practice of the model law i.e., the Austrian Federal Law on Mediation in Civil Disputes and presented as a prerequisite to perform the profession, is applicable and preferable for Türkiye; and the mediators' needs and approaches to this insurance in case of creation of such insurance are discussed and analyzed in the study.
868641
Keywords: Assurance; Geçmişe etkili sigorta; Liability insurance; Mandatory mediation; Mesleki sorumluluk sigortası; Mesuliyet sigortası; Médiateur; Private insurance; Private insurances; Professional liability insurance; Recroactive insurance; Responsabilité professionnelle; Sorumluluk sigortası; Zorunlu arabuluculuk; Özel sigortacılık; Özel sigortalar

Anonim şirkette imtiyazlı pay sahipleri özel kurulu - Yilmaz, Hümeyra (İstanbul Üniversitesi, 2024)
Bu doktora tezi, 6102 sayılı Türk Ticaret Kanunu'nun 454. maddesinde düzenlenen imtiyazlı pay sahipleri özel kurulunu konu almaktadır. Çalışmanın ilk bölümünde imtiyaza ilişkin genel bilgiler verildikten sonra ikinci bölümünde imtiyazlı pay sahipleri özel kurulunun yapısı, yetkisi, hukuki niteliği üzerinde durulmuştur. Çalışmanın üçüncü ve dördüncü bölümlerinde, imtiyazlı pay sahipleri özel kurulunun toplanma şartları ile toplantı süreci kapsamlı bir şekilde ele alınmıştır. Çalışmanın son bölümünde ise imtiyazlı pay sahipleri özel kurul kararlarının hukuki niteliği, etkisi ve hükümsüzlüğü irdelenmiştir. Çalışmanın hazırlanmasında, Türk hukukundaki ilgili mevzuat hükümleri başta olmak üzere karşılaştırmalı hukuktaki dikkate değer yasal düzenlemeler, öğretideki görüşler ve yargı kararlarından faydalanılmıştır. Anahtar kelimeler: Anonim şirketler, imtiyaz, TTK m. 454, imtiyazlı pay, imtiyazlı pay sahipleri özel kurulu. This doctoral thesis deals with the special committee of privileged shareholders regulated under Article 454 of the Turkish Commercial Code No. 6102. After giving general information about privilege in the first part of the study, the structure, authority, and legal nature of the special committee of privileged shareholders are mentioned in the second part. In the third and fourth parts of the study, the conditions for the meeting and the meeting process of the special committee of privileged shareholders are extensively discussed. In the last part of the study, the legal effect, nature, and invalidity of the special committee decisions of privileged shareholders are examined. In the preparation of the study, notable legal regulations in comparative law, doctrines and judicial decisions, especially related legislation in Turkish law have been benefited from. Key Words: Joint Stock Companies, privilege, the article 454 of the Turkish Commercial Code No. 6102, privileged share, the special committee of privileged shareholders.
Tez n°867760
Keywords: Anonim şirketler; Joint stock company; Special meeting; Turkish commercial law; Türk ticaret hukuku; Özel kurul

Le recouvrement contentieux des créances cambiaires - Yoli, Bi Manh (Revue d’étude et de recherche sur le droit et l’administration dans les pays d’Afrique, 2024)
Le recouvrement contentieux des créances cambiaires s’avère pénible en raison des conditions négatives préalables imposées par le droit cambiaire et l’inadaptation du droit commun des procédures simplifiées de recouvrement et des voies d’exécution. A cet égard, un aménagement consistant à introduire et à systématiser le référé-provision doublé d’une extension des effets des moyens de contraintes juridiques à tous les signataires du titre y compris le trésor public et le fonds de garantie semble nécessaire. En effet, l’acceptation par le porteur des effets de commerce comme moyen de paiement est justifiée par la purge des imperfections du titre. Le juge au rôle crucial dans l’application de la loi, doit assouplir les conditions d’obtention des moyens de contrainte et de mise en œuvre des voies d’exécution afin de réduire l’injustice. The contentious recovery of cambial claims proves to be burdensome due to the preliminary negative conditions imposed by cambial law and the inadequacy of the common law on simplified recovery procedures and enforcement measures. In this context, an adjustment involving the introduction and systematization of provisional referrals, combined with extending the effects of legal enforcement measures to all signatories of the instrument—including the public treasury and the guarantee fund seems necessary. Indeed, accepting commercial instruments as a means of payment is justified by their ability to purge the title’s imperfections. The judge has a crucial role when applying the law, must relax the conditions for obtaining mains of constraint and implementation of enforcement routes in order to reduce injustice.
Keywords: Cambiaire; Cambial; Contentieux; Contentious; Recouvrement de créances; Recovery of Debts

Measuring the Effects of Post-Convention Activities at the HCCH - Zhang, Ke (McGill University, 2024)
https://escholarship.mcgill.ca/concern/theses/cn69m944k
Keywords: HCCH; Hague Conference on Private International Law

الحماية الجزائية للعالمة التجارية بين التشريع الجزائري و التشريع المغربي - دراسة مقارنة - صافو, سارة (Université d'Oran 2 Mohamed Ben Ahmed, 2024)
الملخص تهدف هذه الدراسة بتحميل ومقارنة الحماية الجزائية من الجرائم الماسة بالعالمة التجارية في الجزائر والمغرب، في هذا الصدد تهدف الدراسة إلى معرفة األهمية االقتصادية التي تكتسيها العالمة التجارية محل الحماية و أثر الجرائم الواقعة عميها عمى االقتصاد الوطني لمبمدين، خاصة في ظل اتجاه الجزائر والمغرب نحو تبني اقتصاد مبني عمى المعرفة القائم عمى اإلبداع واالبتكار. في البداية، وبعد التطرق لألحكام المنظمة لمعالمة التجارية من خالل توضيح مدى توافق التشريعين، تعني الد ارسة بتحميل ومقارنة طبيعة القانونية لمعالمة التجارية من ضبط مفهومها إلى اكتساب الحق فيها، عن طريق توضيح أهميتها كمؤشر لقياس االقتصاد الوطني. تنتقل الد ارسة لتبين تدخل المشرعين الج ازئري والمغربي بوضع آليات حمائية قبمية وبعدية لردع الج ارئم الواقعة عمى العالمة التجارية، تتفحص الدراسة هنا، دور اإلجراءات التحفظية ودعوى التقميد كآلية لحماية القانونية لمعالمة التجارية بهدف حماية االقتصاد الوطني. وانطالقا من القسمين السابقين لمدراسة، تحاول هذه األخيرة توضيح بعض التوجهات االقتصادية التي انتهجتها كل من الجزائر والمغرب من اقتصاد تقميدي إلى اقتصاد مبني عمى المعرفة، وأن اإلشكال المطروح في مثل هكذا ظروف جديدة يكمن في مدى ارتباط حماية العالمة التجارية بحماية االقتصاد الوطني، تبين الدراسة في هذا الشأن أن اختالف حماية التشريع الج ازئري لمعالمة التجارية عن التشريع المغربي يكمن في اختالف اقتصاد دولتين. نخمص إلى القول أن السياسة الردعية التي أقرها التشريعين الج ازئري والمغربي ال تتوافق مع طبيعة هذه الج ارئم الماسة باالقتصاد الوطني، حيث يجب تعديل العقوبات وتكييفها مع األوضاع االقتصادية الجديدة من خالل تشديدها. Abstract: The aim of this study is to analyse and compare the penal protection against crimes against the brand in Algeria and Morocco in this regard. The study aims to learn about the legal nature of the protected brand and the impact of these crimes on the national economy of the two countries, especially in view of Algeria's and Morocco's trend towards a knowledge-based economy based on creativity and innovation. Initially, after addressing the provisions governing the trademark by clarifying the compatibility of the two legislations, the study means analysing and comparing the legal nature of the trademark in question from the control of its concept to the acquisition of the right to it, by clarifying its importance as an indicator of measurement of the national economy. The study goes on to show the intervention of Algerian and Moroccan legislators by establishing tribal and remote protectionist mechanisms to deter crimes against the trademark. The study examines here the role of provisional measures and the case for tradition as a mechanism for protecting the legal protection of the trademark in order to protect the national economy. The study goes on to show the intervention of Algerian and Moroccan legislators by establishing tribal and remote protectionist mechanisms to deter crimes against the trademark. The study examines here the role of provisional measures and the case for tradition as a mechanism for protecting the legal protection of the trademark in order to protect the national economy. Based on the previous two sections of the study, the latter attempts to clarify some of the economic trends adopted by Algeria and Morocco, from an economy based on quarters to an economy based on knowledge, and that the problem presented in such new circumstances lies in the extent to which protecting the trademark is linked to protecting the national economy. The study shows In this regard, the difference in Algerian trademark protection from Moroccan legislation lies in the difference in the economies of the two countries.We conclude by saying that the deterrent policy adopted by Algerian and Moroccan legislation is incompatible with the nature of these crimes, which affect the national economy. The penalties must be adjusted and adapted to the new economic conditions by tightening them. Résumé : Cette étude a pour objet le problème de la protection pénale de la marque commerciale en Algérie et au Maroc. Elle vise à faire connaitre l’importance économique de la marque protégée et l’impact économique des crimes dans les deux pays compte tenu de la tendance de ces deux pays à adopter une économie de créativité et d’innovation. L’étude consiste en la comparaison et en l’analyse juridique de la marque de l’adaptation de son concept à l’acquisition du droit à celle –ci après clarification de son importance en tant qu’indicateur de mesure de l’économie nationale. L’étude montre ensuite l’impact des législation algériennes et marocaines qui établissent des mécanismes visant à la protection à distance afin de dissuader tout crime contre la marque. Le rôle des mesures provisoires et aussi examine dans cette étude ainsi que l’action en contrefaçon en tant que moyen de protection juridique de la marque. Afin que protéger l’économies nationale. En outre, cette étude essaye d’illustrer certaines des tendances économiques algériennes d’une économie basée sur la rente vers une économie basée sur le savoir (créativité et innovation). Dans ces nouvel es circonstances, la protection des marques et liée à la protection de l’économie nationale. A cet égard, la protection de la marque commerciale en Algérie diffère de celle du Maroc du fait de la différence des économies des deux états algériens et marocains. Nous concluons que la politique de dissuasion adoptée par les législations algérienne et marocaine est incompatible avec la nature de ces crimes, qui affectent l’économie nationale. Les sanctions doivent être ajustées et adaptées aux nouvelles conditions économiques en les resserrant.
Keywords: Action pénale; Contrefaçon; Criminal case; Droit algérien; Droit marocain; Enregistrement; Fake; Marque commerciale; Mesures conservatoires; Procedures conservatory; Protection pénale; Registry; Trademark

الأعوان التجاريون لعملية النقل البحري - قزدعلي, أسماء (Université d'Oran 2 Mohamed Ben Ahmed, 2024)
الملخص : نظم القانون البحري الجزائري مهام و مسؤوليات كل من وكيل السفينة ووكيل الحمولة في المواد من 609 إلى 630 أما السمسار البحري فمن المادة 631 إلى المادة 639 ، فتعتبر هذه الأنشطة وليدة خوصصة النشاطات البحرية التي كانت محتكرة من قبل الدولة سابقا بالإضافة إلى ما أصبحت عليه السفن التجارية و تكاليفها الباهضة . كان ربان السفينة هو من يتولى القيام بهذه الأنشطة ذلك لحساب المجهز أو المرسل إليه ، فاقتضى الأمر إعفاءه منها ذلك نظرا لبقاء السفينة في الميناء مدة طويلة والبحث عن شخص طبيعي أو معنوي في كل ميناء يقوم لحساب المجهز أو المرسل إليه بتسليم البضائع وحراستها و المحافظة عليها و تحصيل الأجر عن ذلك . وعليه أصبح الأعوان التجاريون هم من يتولون القيام بهذه الأنشطة و المهام وذلك بناءا على عقد تنجر عنه جملة من الالتزامات و المسؤوليات على عاتق طرفاه . Le droit maritime algérien réglemente les fonctions et les responsabilités de consignataire du navire et de consignataire de cargaison dans les articles de 609 à 630. Le courtier naval de l’article 631 à l’article 639 considère ces activités comme la naissance de la privatisation des activités maritimes précédemment monopolisées par l’État en plus de ce que sont devenus les navires commerciaux et leurs coûts exorbitants. C’est le capitaine du navire qui a effectué ces activités au nom du transformateur ou du destinataire. Cela était rendu nécessaire par l’exemption, compte tenu du long séjour du navire au port et de la recherche d’une personne physique ou morale dans chaque port pour lequel le transformateur ou le destinataire livrait, gardait, entretenait et percevait les salaires. En conséquence, ce sont les agents commerciaux qui exercent ces activités et fonctions sur la base d’un contrat qui remplit un certain nombre d’obligations et de responsabilités des deux parties. Algerian maritime law regulates the duties and responsibilities of the ship’s agent and cargo agent in the section from 609 to 630. The naval broker from section 631 to section 639 considers these activities to be the birth of the privatization of maritime activities previously monopolized by the State in addition to what has become of commercial vessels and their exorbitant costs. The master of the vessel performed these activities on behalf of the processor or consignee. This was made necessary by the exemption, taking into account the vessel’s long stay in port and the search for a natural or legal person in each port for which the processor or consignee delivered, kept, maintained and collected wages. Consequently, it is the commercial agents who carry out these activities and functions on the basis of a contract which fulfils a number of obligations and responsibilities of both parties.
Keywords: Agency contract; Consignataire de cargaison; Consignataire de navire; Contrat de transport maritime; Contrat d’agence; Courtier maritime; Droit algérien; Droit maritime; Navire; Payload agent; Sea broker; Sea transport contract; Ship agent

الصفقات العمومية التي يبرمها أشخاص القانون الخاص في التشريع الجزائري مقارنا - كوثر, بن ملوكة (Université d'Oran 2 Mohamed Ben Ahmed, 2024)
الملخص يحظى مجال الصفقات العمومية بأهمية بالغة بالنسبة للاقتصاد الوطني، وتعود هذه الأهمية لاعتبار الصفقة العمومية الطريق القانوني الذي تستخدمه الدولة ومختلف المتعاملين من أجل انجاز المشاريع بجودة عالية بأقل التكاليف وآجال مدروسة، وكون تمويل الصفقات العمومية يعود للخزينة العامة للدولة وجب توفير الحماية القانونية لهذه العملية عن طريق إيجاد تنظيم قانوني خاص بها يحقق المصلحة العامة ويحترم الحرية الاقتصادية في ذات الوقت، وهو ما جسده المشرع الجزائري عمليا بإصدار المرسوم الرئاسي 15-247 الذي عرف عدة تعديلات سابقة ومواكبة لمتطلبات كل مرحلة، فالقول بالصفقة العمومية يحيل بالضرورة إلى أشخاص القانون العام أي الدولة والمؤسسات التابعة لها والقول بغير ذلك نوع من التضاد. لكن المشرع ألزم أشخاص القانون الخاص الخاضعين للتشريع التجاري بتطبيق أحكام التنظيم الصفقات العمومية في حالات محددة وهي التمويل الكلي أو الجزئي للصفقة من الخزينة العمومية (الدولة أو الجماعات الإقليمية) ما يخلق اشكال أي قانون يطبق في حالة النزاع وبالنتيجة أي هرم قضائي هو المختص في البت في منازعة أحد أطرافها أشخاص القانون الخاص ،وكذا حالات التمويل وتجسيدها عمليا، اضافة إلى دور الوسائل الودية المنصوص عليها في كل من تنظيم الصفقات العمومية أو قانون الإجراءات المدنية في حل المنازعات وتجسيد المشاريع واقعيا. Résumé Le domaine des marchés publics occupe une grande place dans l’économie nationale ; cela est dû au fait qu’un marché public est considéré comme la voie légale utilisée par l’État et les différents partenaires pour réaliser des projets au moindre coût et dans des délais raisonnés. Comme le financement des marchés publics relève du Trésor public, l’état est tenu d’assurer la protection juridique de ce processus en créant sa propre organisation juridique dans l’intérêt public tout en respectant la liberté économique, c’est ce que le législateur algérien a matérialisé, dans la pratique, par la promulgation du décret présidentiel n°15-274 qui a connu plusieurs modifications aux fins de de répondre aux exigences de chaque étape. Dire « Marché Public » renvoie nécessairement aux entités du droit commun, à savoir, l’état et ses institutions et affirmer les choses autrement serait une forme de contradiction. Toutefois, le législateur a engagé les entités du droit privé soumis à la législation commerciale dans l’application des dispositions de la réglementation des marchés publics dans un cas spécifique, à savoir, le financement total ou partiel du marché à partir du trésor public (États et/ou collectivités territoriales) ; de cela est issue une loi applicable en cas de conflit, avec pour conséquence, toute pyramide judiciaire compétente pour statuer sur un litige relevant en partie du droit privé, dans les cas de leur financement et matérialisation pratique, ainsi que lorsqu’il s’agit du rôle des moyens de règlement à l’amiable prévus aussi bien par la réglementation des marchés publics que par le Code de procédure civile dans la résolution des litiges et la réalisation concrète des projets. Abstract The field of public procurement occupies a major place in the national economy; this is due to the fact that a public procurement is considered to be the legal way used by the State and the various partners to carry out projects at the lowest cost and within reasonable deadlines. As the financing of public procurement is the responsibility of the Treasury, the State is required to ensure the legal protection of this process by creating its own legal organization in the public interest while respecting economic freedom, this is what the Algerian legislator materialized, in practice, by the promulgation of presidential decree No. 15-274 which has undergone several modifications in order to meet the requirements of each stage. To say "Public Procurement" necessarily refers to the entities of common law, namely, the state and its institutions and to affirm things otherwise would be a form of contradiction. However, the legislator has committed the private law entities subject to commercial law to apply the provisions of the public procurement regulation in a specific case, namely, the total or partial financing of the contract from the public treasury (States and/or territorial authorities); from this comes a law applicable in case of conflict, with the consequence, any judicial pyramid competent to rule on a dispute falling partly under private law, in cases of their financing and practical materialization, and when it concerns the role of the means of amicable settlement provided for by the regulation of public contracts as well as by the Code of Civil Procedure in the resolution of disputes and the concrete implementation of projects.
Keywords: Commercial and public company; Conflict of judicial compétences; Conflit des compétences judiciaires; Entreprise publique Industrielle; Entreprise publique commerciale; Financement par le trésor; Financing by treasury; Industrial public company; Marché; Market; Means of amicable settlement; Moyens de règlement à l’amiable